A comprehensive overview of evolutionary relationships and geographic distributions of cownose rays: more valid taxa needing protective measures - Yasmim Trindade C. Cunha; Renata Daldin Leite; Lucas Gabriel Pereira da Silva; Vanessa Paes Cruz; Jorge Luiz S. Nunes; Matheus Marcos Rotundo; Paola Palacios-Barreto; Píndaro Diaz-Jaimes; Ana P. Barbosa Martins; M. Aaron Macneil; Chris G. Mull; José Augusto Pires Bitencourt; et al. (Reviews in Fish Biology and Fisheries, 2026)
Rays of the family Rhinopteridae Jordan & Evermann, 1896 are highly migratory and widely distributed in warm tropical and temperate waters. Along the Brazilian coast, the presence of two species has been recorded: Rhinoptera bonasus Mitchill, 1815 and Rhinoptera brasiliensis Müller, 1836. These stingrays are commonly caught as bycatch in trawl fisheries, however, the two species lack distinctive external morphological features that allow for reliable differentiation—species identification is primarily based on the shape and arrangement of teeth in the buccal plates. This study aimed to investigate the evolutionary history of the genus Rhinoptera and to explore which evolutionary drivers, such as biogeographic events or behavioral traits, have influenced its diversification. To achieve this, we analyzed both mitochondrial and nuclear genetic markers, focusing on the species occurring along the Brazilian coast. Specimens of both species were collected across various locations in Brazil, and additional sequences from other Rhinoptera species were obtained from GenBank. Our results reveal the presence of multiple cryptic species within Rhinoptera , particularly within R. bonasus , and likely in Rhinoptera steindachneri Evermann & Jenkins, 1891 and Rhinoptera javanica Müller & Henle, 1841. Notably, R. bonasus does not occur in Brazilian waters nor in parts of the Caribbean where a distinct cryptic sister lineage was identified. Based on our findings, we propose the resurrection of Rhinoptera lalandii Müller & Henle, 1841 as the species representing the lineage found along the Brazilian coast and the Eastern Atlantic Ocean. We suggest that philopatric behavior may represent one of several factors potentially influencing diversification within Rhinopteridae, although this hypothesis requires direct behavioral and population level validation. These findings highlight the urgent need for a comprehensive taxonomic revision of the family, as well as a reassessment of current conservation strategies to better reflect the hidden diversity within this group of species. Graphical abstract

Nucleic acid based profile of body surface and gut bacteria among wall gecko: a potential hub for antibiotic resistance dissemination within household - Ubreye B. Owhe-Ureghe; Bright E. Igere; Landley A. Orutugu; Eucharia O. Brisibe; Chukwunonso M. Ukwamedua; Victory O. Ogbe; Emmanuel O. Jonathan; Rukevwe P. Ichipi (Molecular Biology Reports, 2026)

Objective-specific pollen count thresholds for robust and relevant assemblages in boreal and northern temperate forests of eastern Canada - Jonathan A. Lesven; Dorian M. Gaboriau; Pierre J.H. Richard; Adam A. Ali; Hugo Asselin; Marion Blache; Martin P. Girardin; Mathis Jean-Sépet; Noé Moroy; Yves Bergeron (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Invasive barred owls select old-forest structure: Functional habitat loss for spotted owls and a threat to old-forest fauna - Vitek Jirinec; Mourad W. Gabriel; J. Mark Higley; Raymond J. Davis; Jonathan E. Tenberge; Christina P. Varian; Daniel F. Hofstadter; M. Zachariah Peery; Julianna M.A. Jenkins; Alan B. Franklin; Greta M. Wengert (Biological Conservation, 2026)

Zircon geochronology of the Gordonbrook Serpentinite: A fragment of mantle wedge within the New England Orogen, eastern Australia - George G.F. Murray; Solomon Buckman; Allen P. Nutman; Wanchese M. Saktura; Jonathan C. Aitchison; Vickie C. Bennett; Zhen Yan; Changlei Fu (Lithos, 2026)

Corrigendum to “Revisiting the modifiable areal unit problem in the era of exposome-wide association studies: Assessing the performance of the CDC/ATSDR social vulnerability index at privacy-protecting spatial scales” [Environ. Res. (2026) 124912] - Jonathan V. Lewis; Nathaniel MacNell; Ian D. Buller; Gary Larson; David Fargo; Charles P. Schmitt; Lawrence S. Kirschner; David M. Reif; Farida S. Akhtari; Cristina M. Justice; John S. House; Kyle P. Messier; et al. (Environmental Research, 2026)

Corrigendum to “Revisiting the modifiable areal unit problem in the era of exposome-wide association studies: Assessing the performance of the CDC/ATSDR social vulnerability index at privacy-protecting spatial scales” [Environ. Res. (2026) 124912] - Jonathan V. Lewis; Nathaniel MacNell; Ian D. Buller; Gary Larson; David Fargo; Charles P. Schmitt; Lawrence S. Kirschner; David M. Reif; Farida S. Akhtari; Cristina M. Justice; John S. House; Kyle P. Messier; et al. (Environmental Research, 2026)

Revisiting the modifiable areal unit problem in the era of exposome-wide association studies: Assessing the performance of the CDC/ATSDR social vulnerability index at privacy-protecting spatial scales - Jonathan V. Lewis; Nathaniel MacNell; Ian D. Buller; Gary Larson; David C. Fargo; Charles P. Schmitt; Lawrence S. Kirschner; David M. Reif; Farida S. Akhtari; Cristina M. Justice; John S. House; Kyle P. Messier; et al. (Environmental Research, 2026)

Dune Russet: A French-Fry Potato Cultivar with High Specific Gravity under High-Temperature Growing Conditions and Excellent Processing Quality after Long-Term Cold Storage - M. Isabel Vales; Douglas C. Scheuring; Jeffrey W. Koym; Jeewan Pandey; Stephany E. Toinga-Villafuerte; Joshua R. Johnson; Caroline P. Gray; David G. Holm; Mohamad Chikh-Ali; Robert G. Wilson; Richard G. Novy; Jonathan L. Whitworth; et al. (American Journal of Potato Research, 2026)
Dune Russet (COTX08063-2Ru) is the first French fry russet potato cultivar released by the Texas A&M Potato Breeding Program. It derives from a cross made by the Colorado State University Potato Program between Premier Russet and A99073-1 and was subsequently selected and advanced by the Texas Program. Dune Russet has oblong potato tubers with light russet skin texture and white flesh. It is characterized by having excellent French fry quality and cold-induced sweetening resistance, producing light-colored fries directly from the field and even after several months (three to eight) in cold storage at 4.4 °C. Dune Russet is especially recommended for areas that experience high-temperature stress during the growing season, as it can retain high specific gravity near 1.090 and produce light French fries despite heat stress. Across multi-location trials, Dune Russet outperformed the reference cultivar, Russet Burbank, and other processing cultivars in French fry quality, while offering some field-based PVY tolerance and good agronomic performance, including competitive marketable yields and a high proportion of US No. 1 tubers.

Nutrient Enrichment Increases Grassland Biomass Sensitivity to Interannual Precipitation Variation - Ingrid J. Slette; Eric W. Seabloom; Carlos Alberto Arnillas; Jonathan D. Bakker; Dana Blumenthal; Jane A. Catford; Scott L. Collins; Nico Eisenhauer; Philip A. Fay; Magda Garbowski; Sylvia Haider; W. Stanley Harpole; et al. (Global Change Biology, 2026)
Primary production underpins much of ecosystem functioning and is often limited by nutrient and water availability. Ongoing global increases in nutrient inputs and interannual precipitation variability are thus likely to impact primary production, with unclear consequences for interannual variability in plant biomass. We used data from 35 grasslands in the Nutrient Network coordinated fertilization experiment to test if nutrient addition alters the response of plant biomass to year‐to‐year variation in growing season precipitation, and whether the effects of nutrient addition vary with factors such as site aridity or plant community composition. Nutrient addition increased biomass (by an average of 46% across sites), rain‐use efficiency (by 48%), and the sensitivity of biomass to interannual variation in precipitation (i.e., larger increase in biomass in wet years; by 13%), but did not change the strength of the interannual precipitation‐biomass correlation. Both sensitivity and correlation strength were higher in more arid sites, regardless of nutrient addition. These results suggest that grassland ecosystem functioning may become more variable from year to year as nutrient enrichment increases biomass sensitivity to precipitation and precipitation becomes more variable.

Uncovering correlates of decline and critical refuges for a threatened terrestrial mammal - Natalya M. Maitz; Michelle S. Ward; Jonathan R. Rhodes; Ben C. Scheele; Hugh P. Possingham; Diana O. Fisher (Conservation Biology, 2026)
Globally, the geographic ranges of numerous species are contracting. Identifying spatiotemporal patterns of threat impact can illuminate why species decline in some parts of their range but persist in others. We developed a correlative approach to identify species’ response thresholds and locate ecological refuge areas associated with persistence to inform conservation planning and management. We integrated changes in realized niche characteristics for a threatened Australian mammal, the brush‐tailed rock‐wallaby ( Petrogale penicillata ), with the distributions of threatening processes and environmental features to identify predictors of extirpation and persistence. We used occurrence records to construct historical (2004 or before) and contemporary (2005–2022) species distribution models. We then determined differences in niche characteristics between areas of extirpation and persistence. We applied generalized additive mixed models to determine species‐specific thresholds for extirpation, which we used to identify ecological refuges. Across the two periods, brush‐tailed rock‐wallaby habitat declined by 75%, resulting in realized niche shifts. Extirpations occurred where habitat distance to water increased, and red fox ( Vulpes vulpes ) densities and feral goat ( Capra hircus ) habitat suitability were relatively high. Relatively high topographic ruggedness and high minimum temperatures were associated with persistence. Species persistence was also positively correlated with increasing dingo ( Canis familiaris ) habitat suitability, and inappropriate fire regimes (e.g., more frequent fires than expected for a vegetation group), both of which have been suggested as threats to the species. Specific refuge locations were identified in southeastern Queensland and northern New South Wales. Our findings highlight the importance of quantitative species‐specific threat assessments to prevent misguided conclusions from cross‐taxa threat generalizations. As spatial data become increasingly accessible, our novel approach will provide practitioners with evidence on which to base fine‐scale investigations. Our approach can be applied to other species undergoing range contractions.

Vegetation Increases CH 4 Emissions and Methanotroph Diversity in Marine Sediments - Marion Dolivet‐Maréchal; Carlos Palacin‐Lizarbe; Henri M. P. Siljanen; Dhiraj Paul; Abigaïl Delort; Jonathan Gervaix; Charline Creuzé des Châtelliers; Sabine Schmidt; Mathis Cognat; David Sebag; Olivier Taugourdeau; Clara Schübert; et al. (Global Change Biology, 2026)
Seagrass meadows are key blue carbon (C) ecosystems, storing large amounts of organic C over centuries. Their climate benefits may be reduced by methane (CH 4 ) emissions, whose microbial and environmental descriptors in Zostera noltii meadows, dominant seagrass in North‐Western Europe, remain poorly understood. We studied CH 4 fluxes, CH 4 ‐producing and consuming microbial communities and sediment physicochemical parameters in Z. noltii meadows and adjacent bare sediments across seven sites in Arcachon Bay, France. In situ CH 4 fluxes were measured at low tide during daytime conditions, providing standardized estimates of peak emissions. Microbial communities were characterized using targeted metagenomics of three functional genes ( mcrA , mmoX , pmoA ) and quantitative PCR. CH 4 fluxes were higher in vegetated than bare sediments (24.4 ± 2.6 vs. 9.4 ± 0.7 μmol m −2 day −1 ). Mixed linear models and random forest analyses identified C accumulation rate and CO 2 flux as the strongest positive descriptors of CH 4 fluxes. Vegetated sediments hosted more diverse methanotrophs, while methanogens showed no habitat differences. Four genera ( mcrA–Methanolobus , mmoX–Methylocella , pmoA–Methylococcus , Methyloglobulus ) emerged as abundant, seagrass‐associated, correlated with CH 4 fluxes, and highlighted by models. Functional diversity, especially pmoA richness, was a stronger microbial descriptor of CH 4 fluxes than gene abundance or a specific genus. Findings indicate Z. noltii meadows enhance C burial and CH 4 emission, with methanotroph diversity potentially mitigating CH 4 emissions. Our results provide the first integrated assessment of CH 4 fluxes and their descriptors in Z. noltii meadows, based on limited temporal coverage capturing the daytime peak emission conditions, highlighting the intertwined nature of C burial and CH 4 emissions and the need to account for both in blue C climate assessments.

Continent-wide stock structure and connectivity of silver trevally (Pseudocaranx georgianus) based on population genomics and otolith shape and chemistry - Zoriana H.T. Lam; John Stewart; Jonathan Sandoval-Castillo; Patrick Reis-Santos; Rhiannon A. Van Eck; Bronwyn M. Gillanders; Peter Ritchie; Maren Wellenreuther; Charlie Huveneers; David V. Fairclough; Ashley M. Fowler; Julian Hughes; et al. (Fisheries Research, 2026)

Explaining state investment in drinking water infrastructure for disadvantaged communities, 1997-2016 - Xi Chen; Jonathan M. Fisk; John C. Morris; Ryan P. Scott (Utilities Policy, 2026)

Serum PFAS concentrations and neuromorphometry in adolescents: The HOME Study - Jasmine Haraburda; Jonathan Dudley; Kimberly Yolton; Yingying Xu; Joseph M. Braun; Aimin Chen; Bruce P. Lanphear; Kim M. Cecil (Environmental Research, 2026)

The impact of rain events on the supply and movement of fine sediment in engineered intertidal systems - Heidi M. Burgess; Jonathan Dale; Martin P. Smith (Continental Shelf Research, 2026)

Mind the Gap: Human and AI Uncertainties in Cardiac MRI Segmentation - Qiao Lin; Xin Chen; Chao Chen; Nikesh Jathanna; Peter P. Swoboda; Shahnaz Jamil-Copley; Jonathan M. Garibaldi (Cardiovascular Engineering and Technology, 2026)

What Have We Learned From Empirical Applications of Modern Coexistence Theory? - Peter B. Adler; Matteo Detto; Stephen P. Ellner; Theo L. Gibbs; Zachary J. Gold; Samuel J. Leonard; Jacob I. Levine; Annie E. Schiffer; Chuliang Song; Michael Stemkovski; Megan L. Vahsen; Jonathan M. Levine (Ecology Letters, 2026)
Since the early 2000's, Modern Coexistence Theory (MCT) has guided empirical investigations of coexistence. We reviewed empirical applications of MCT to answer two questions: (1) What have we learned about the strength of temporal, spatial and variation‐independent mechanisms of coexistence in nature? (2) How have studies of niche and fitness differences advanced our understanding of coexistence? With respect to the first question, we now have evidence that the temporal storage effect and variation‐independent mechanisms help stabilize coexistence in many systems. We have not learned more due to the low number of tests of these mechanisms (24 out of 84 MCT studies), the narrow focus on mechanisms involving temporal variation and grassland communities, and lack of rigorous model validation. With respect to our second question, studies of niche and fitness differences (61 of 84 studies) have answered fundamental questions about the role of phylogenetic relatedness, plant–soil feedbacks, and functional traits in coexistence. We recommend that future empirical MCT studies (1) match hypotheses to MCT quantities, (2) address gaps in empirical studies, (3) avoid known biases in estimating competition coefficients, and (4) validate models with independent data.

Why controlling for habitat amount is critical for resolving the fragmentation debate - Lenore Fahrig; Carmen Galán‐Acedo; Brandon P. M. Edwards; Andrew K. Habrich; Amanda E. Martin; Cécile H. Albert; Victor Arroyo‐Rodríguez; Allison D. Binley; Jonathan R. Cole; Jessica K. Lockhart; Scott E. Nielsen; Federico Riva; et al. (Conservation Biology, 2026)

Preserving the gut microbiome: hydrogel-forming microneedle delivery of tetracycline reduces gut microbiome disruption compared to oral administration - Stephen A. Kelly; Li Zhao; Jonathan Nzakizwanayo; Aoife M. Rodgers; Thomas P. Thompson; Andrew J. Lee; Helen O. McCarthy; John W. McGrath; Rebecca J. Ingram; Brian V. Jones; Brendan F. Gilmore; Ryan F. Donnelly (Drug Delivery and Translational Research, 2026)
Antibiotics cause significant gut microbiome dysbiosis, particularly when administered orally. This contributes to antimicrobial resistance (AMR) and is associated with myriad health conditions. Novel drug delivery strategies that minimize gut exposure while maintaining therapeutic efficacy are urgently needed. This study aimed to evaluate whether a novel transdermal system could reduce gut microbiome disruption compared to oral delivery. Sprague-Dawley rats received a single tetracycline dose via oral gavage, IV injection, or hydrogel-forming microneedle patch. Faecal samples were collected longitudinally and analysed using 16 S rRNA gene sequencing. Oral tetracycline caused the greatest disruption to gut microbiota. Compared to the timepoint immediately prior to treatment (Day 5a), peak dysbiosis was observed at Day 7. The Firmicutes: Bacteroidetes ratio was significantly reduced following oral and IV tetracycline therapy, but not following microneedle administration. The most significant reductions in alpha and beta diversity at Day 7 were observed in the oral group. Differential abundance analysis showed oral treatment resulted in the highest number of depleted and enriched taxa. The microbiome-sparing effect of microneedle delivery was consistent across all analytical measures, offering a promising strategy to preserve host microbiome health. This minimally invasive approach represents a clinically viable alternative to oral and IV antibiotic administration.

A sea-to-soil solution for the green tides threatening shellfish aquaculture: conceptual model and lessons learned from a pilot project - Sarah M. Collier; Emily Buckner; Nicole J. Capizzi; Meg Chadsey; Douglas P. Collins; Jonathan P. Davis; Erick Dowell; Alan Ismach; Brittany G. Johnson; Sergey Rabotyagov; Rob Smith; Katie R. Webb; et al. (Journal of Environmental Management, 2026)

From kelp forests to turf reefs: Patterns, drivers, and impacts to functional diversity - Shane P. Farrell; Dara S. Yiu; Stuart K. Ryan; Rene D. Francolini; Courtney E. Stuart; Jonathan S. Lefcheck; Yasmina M. Shah Esmaeili; Douglas B. Rasher (Ecology, 2026)
Kelp forests are declining in many regions due to ocean warming, predator loss, and other anthropogenic stressors. In areas of rapid ocean warming, including the southern Gulf of Maine, these ecosystems have transitioned to a novel state dominated by low‐lying mats of turf algae. However, the pace, drivers, and ecological consequences of this transition remain unclear. Here, we used field surveys from 32 sites over 5 years (2018–2023) to reveal a continuation of kelp forest collapse and northward expansion of turf algae across Maine's coast. Next, we united data on benthic cover with key environmental variables in a structural equation model to show that turf algae were directly enhanced by higher ocean temperatures and decreased wave disturbance and indirectly enhanced by a warming‐induced loss of kelp cover. Lastly, we revealed the shift from kelp to turf yielded a seaweed assemblage dominated by traits associated with rapid growth, high surface area‐to‐volume ratios, and markedly reduced canopy height, indicating declines in habitat provisioning and carbon storage with kelp forest loss. Our findings highlight the accelerating impacts of climate change on temperate reef ecosystems and the vital services they provide. Further, we provide insights into a new state shift that is now occurring globally and underscore the need for urgent actions to mitigate further loss of foundational kelp forests.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Early Imaging Biomarkers of Cartilage Strain After ACL Reconstruction Predict Patient Pain and Altered Knee Loading - Emily Y. Miller; Timothy Lowe; Hongtian Zhu; Woowon Lee; Pablo F. Argote; Danielle Dresdner; James Kelly; Rachel M. Frank; Eric McCarty; Jonathan Bravman; Daniel Stokes; Nancy C. Emery; et al. (Annals of Biomedical Engineering, 2026)
Purpose To investigate temporal evolution of cartilage strain and relaxometry following ACL reconstruction, and examine associations between MRI metrics, pain, and knee loading patterns during gait as potential early markers of cartilage degeneration. Methods Twenty-five participants (15 female, 10 male; mean age 25.6 years) undergoing ACL reconstruction completed MRI assessments at 6 and 12 month post-surgery, including displacement-encoding MRI (intratissue strain) and quantitative relaxometry (T2, T2*, T1ρ). Pain was evaluated using patient-reported outcome scores. Gait analysis quantified knee adduction moment, knee extension moment, and knee flexion moment at 12 months in a subset of patients. Correlations between MRI metrics in cartilage contact regions, patient-reported outcomes, and knee loading were evaluated. Results Between 6 and 12 month post-reconstruction, increased tibial compressive and transverse strains correlated with worsening pain, while increased tibial shear strain associated with reduced pain and improved outcomes. Participants demonstrating greater symptom improvement exhibited higher knee adduction moments, which associated with favorable compositional changes including decreased femoral T1ρ and decreased tibial hydrostatic strain. Higher knee extension moments associated with increased tibial compressive and hydrostatic strain. Conclusion Cartilage strain and T1ρ changes associate with pain and altered loading patterns, suggesting potential as early post-traumatic osteoarthritis markers. The observed links between knee loading patterns and cartilage structural changes highlight beneficial adaptation of the reconstructed knee to mechanical loading, and potential avenues for early therapeutic (gait-modifiable) intervention. Advanced MRI may enable early identification of at-risk patients following ACL reconstruction.

Comparative efficacy of electrokinetic and static leaching for selective metal recovery and nutrient release from porphyry Cu tailings - Yujie Yan; Gawen R.T. Jenkin; Andrew P. Abbott; Alexandria Tanciongco; Carlo A. Arcilla; Cris Reven L. Gibaga; Daniel J. Smith; Djoan Kate Tungpalan; Jonathan E. Chambers; John Henry C. Gervasio; James Symons; Justine Perry T. Domingo; et al. (Chemical Engineering Journal, 2026)

Temporal evolution of polycyclic aromatic hydrocarbons in sediments of the Hooghly river, West Bengal, India - M. Toscanesi; M. Arienzo; L. Ferrara; P. Mondal; M. P. Jonathan; S. K. Sarkar; C. Donadio; M. Trifuoggi (International Journal of Environmental Science and Technology, 2026)
The study evaluated the effect of monsoons on the levels of polycyclic aromatic hydrocarbons in the Hooghly River estuary sediments over 2018–2021. It was observed a cyclical enrichment of organic material, carbonate deposits, and clay over the post-monsoon and impoverishment over the monsoon because of the heavy rains and flood events. The mean total level of polycyclic aromatic hydrocarbons was 1682 ng/g with a wide range of variability depending on the season, 125–6518 ng/g, higher than previous assays and lower than a contemporary survey. Also, there was a marked predominance of the polycyclic aromatic hydrocarbon heavy pool, ~ 83%, with fluoranthene and pyrene making more than 40% of the total hydrocarbons loads and with a large variability of the composition with the monsoon. Concerning the numerical sediment quality guidelines, the mean individual compound levels, and ∑PAHs, do not surpass effect range low, effect range median, and apparent effects threshold limits and keep fairly below thresholds with no evidence of detrimental biological consequences. Temporal trends of polycyclic aromatic hydrocarbons split over two periods after the 2019 monsoon, with a sudden drop in hydrocarbon levels from two times for naphthalene, acenaphthylene, pyrene, benzo(a)anthracene, chrysene, to 6–7 times for phenanthrene, benzo(b)fluoranthene, benzo(a)pyrene, and indeno[1,2,3-cd]pyrene, with an overall decrease of ∑PAHs of threefold from 2948 to 959 ng/g. Monsoon seems to play as a sort of natural attenuation effect, slowing down river decline.

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Gestational PBDE concentrations and functional connectivity in adolescents: The HOME Study - Jonathan Dudley; Kimberly Yolton; Alex D. Edmondson; Yingying Xu; Aimin Chen; Jeffrey R. Strawn; Joseph M. Braun; Andreas Sjodin; Bruce P. Lanphear; Kim M. Cecil (International Journal of Hygiene and Environmental Health, 2026)

Severe fire has impacted populations of the California spotted owl more than fuels management or drought-related tree mortality - Elizabeth Ming-Yue Ng; Connor M. Wood; H. Anu Kramer; Jason M. Winiarski; Kate A. McGinn; Sheila A. Whitmore; Jonathan P. Eiseman; Kevin G. Kelly; Sarah C. Sawyer; Craig Thompson; M. Zachariah Peery (Forest Ecology and Management, 2026)

Cicada necrobiome mediates greenhouse and trace gas pulses following periodic mass emergence - Megan L. Purchase; Richard P. Phillips; Jonathan D. Raff; Amy I. Phelps; Elizabeth Huenupi; Ryan M. Mushinski (Applied Soil Ecology, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Rethinking land-use Strategies: A multi-objective analysis of combined sparing and sharing approaches applied across great britain - Imane El Fartassi; Ryan T. Sharp; Victoria A. Bell; Andrew P. Whitmore; Helen Metcalfe; Nathan Missault; John Redhead; David M. Cooper; Jonathan Storkey; Helen Davies; Theo Jackson; Kevin Coleman; et al. (Journal of Environmental Management, 2026)

Fine-scale patterns and drivers of ploidy state in lentic and lotic macrophyte assemblages across the world - Tatiana Lobato-de Magalhães; Kevin Murphy; Thomas A. Davidson; Jorge García-Girón; Andrey Efremov; Victor Chepinoga; Eugenio Molina-Navarro; Celeste Franceschini; Roger P. Mormul; Hui Fu; Rossano Bolpagni; Juri Nascimbene; et al. (Aquatic Botany, 2026)

Modeling archaeological excavation-induced soil erosion in cultural heritage landscapes: A QGeoWEPP-based assessment at the Resuloğlu Mound, Türkiye - Kemal Koçaklı; Chris S. Renschler; Dennis C. Flanagan; Ryan P. McGehee; Jonathan M. Harbor; Bülent Arıkan; Orkan Özcan (Geoderma Regional, 2025)

Corrigendum to “Subchronic inhalation exposure to ultrafine particulate matter alters the intestinal microbiome in various mouse models” [Environ. Res. 248 (2024) 118242] - Candace Chang; Rajat Gupta; Farzaneh Sedighian; Allen Louie; David M. Gonzalez; Collin Le; Jae Min Cho; Seul-Ki Park; Jocelyn Castellanos; To-Wei Ting; Tien S. Dong; Nerea Arias-Jayo; et al. (Environmental Research, 2025)

Deep-sea ecosystems of the North Atlantic Ocean: discovery, status, function and future challenges - A. Louise Allcock; Diva J. Amon; Amelia E.H. Bridges; Ana Colaço; Elva Escobar-Briones; Ana Hilário; Kerry L. Howell; Nélia C. Mestre; Frank E. Muller-Karger; Imants G. Priede; Paul V.R. Snelgrove; Kathleen Sullivan Sealey; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Correction to: Hydrogeochemical Evaluation of an Urban Aquifer Under Stress: Rare Earth Elements Fractionation and Human Health Implications - K. M. Ochoa-Guerrero; P. F. Rodriguez-Espinosa; E. Martinez-Tavera; V. Balaram; M. P. Jonathan (Environmental Management, 2025)

Hydrogeochemical Evaluation of an Urban Aquifer Under Stress: Rare Earth Elements Fractionation and Human Health Implications - K. M. Ochoa-Guerrero; P. F. Rodriguez-Espinosa; E. Martinez-Tavera; V. Balaram; M. P. Jonathan (Environmental Management, 2025)

Habitat Differences in Resource Density and Distribution Affect Ecology and Life History of a Landscape‐Modifying Fish - Aneesh P. H. Bose; Boyd Dunster; Jonathan Henshaw; Lukas Koch; Jacqueline Grimm; Kristina M. Sefc; Alex Jordan (Molecular Ecology, 2025)
Resource heterogeneity is a widespread phenomenon, as resources are rarely spaced evenly across a landscape. Variation in resource density and distribution can have a myriad of behavioural, ecological, and evolutionary consequences for populations, yet clarifying these effects is still challenging. We combine both novel and previously published data on genetic parentage, relatedness, life history, and predation to present a comprehensive field study of a shell bed in Lake Tanganyika. Here, a wild population of the cichlid fish Neolamprologus multifasciatus is naturally subdivided into habitat regions that differ immensely in shelter density and distribution, as well as in the capacity for the fish to physically rearrange their shelters into clusters (i.e., engage in niche construction). Shelters were evenly, densely, and continuously spaced in one habitat, while they were highly clustered in the other habitat. We expected the environmental potential for polygyny to be greater in the clustered habitat relative to the continuous habitat. Predation regimes and life history traits differed, with N. multifasciatus in the evenly distributed habitat experiencing higher predation threats, earlier maturation, and slower growth than those in the clustered habitat. Metrics of selection, however, were surprisingly consistent between the two habitats, as were patterns of dispersal. Overall, our research leverages the natural subdivision of a wild population into distinct habitats to investigate the ecological and evolutionary implications of resource heterogeneity and habitat modification.

Neuromuscular control of a five-finger pinch task is influenced by training history - Dylan J. Carter; James R. Forsyth; Joshua P. M. Mattock; Jonathan Shemmell (Experimental Brain Research, 2025)
Hand control for dexterous and strength-based tasks involves several levels of the neuromuscular system which interact to produce force. We investigated hand force, motor unit (MU) control, and intermuscular coherence in specialist-trained groups to identify how training may affect neuromuscular force control and motor neuron activity. Equal groups of ten strength-trained (rock climbers) and dexterity-trained (musicians) individuals participated. Measures of forearm muscle structure were recorded and used to normalize maximal five-finger pinch force. Several submaximal trapezoidal pinch contractions were performed while force and electromyography (EMG) were recorded, and force steadiness was calculated. Motor unit firing rates were calculated from spike trains identified by surface EMG decomposition. Intermuscular coherence was calculated between two muscles controlling the hand (the abductor pollicis brevis and flexor digitorum superificialis), providing an estimate of the common synaptic inputs to these simultaneously activated muscles. Strength-trained participants had a higher force capacity (even when normalized to muscle size) and were steadier at controlling forces. The dexterity-trained group had faster MU discharge rates in the abductor pollicis brevis muscle at moderate force levels. Measures of synaptic inputs to the motor neuron pools were inconsistent. However, the largest peaks in the beta-band were at the lowest measured force level for the dexterity-trained group, while at the highest force intensity for the strength-trained group. These findings may indicate that the neuromuscular control of hand force differs between groups with different training histories.

Biofilm Responses to Experimental Nutrient Enrichment of Forest Streams: Light and Nutrients Interact to Increase Biomass, and Phosphorus Alters Stoichiometry - Phillip M. Bumpers; Jonathan P. Benstead; Vladislav Gulis; John S. Kominoski; John C. Maerz; David W. P. Manning; Seth J. Wenger; Amy D. Rosemond (Ecosystems, 2025)
Nutrient enrichment of aquatic ecosystems typically results in increased algal biomass, but the response magnitude is predicted to be attenuated in light-limited ecosystems. We tested the effects of experimental nutrient enrichment in small, highly shaded forest streams and compared responses of biofilm biomass and biofilm stoichiometry, which may be less sensitive to light. After one year of pre-treatment data collection, we enriched five streams continuously for 2 years with different ratios of nitrogen (N) and phosphorus (P), which allowed us to test the relative effect of N and P on two measures of biomass—chlorophyll a (Chl a ) and ash-free dry mass (AFDM)—and on biofilm stoichiometry (C:N, C:P, and N:P) monthly. Biomass increased in response to light and both nutrients; annual average Chl a increased 9.28 × and AFDM increased 1.13 × Biofilm stoichiometry was driven largely by streamwater P concentration, with greatest effects of experimental enrichments on C:P (0.58 ×) and N:P (0.79 ×). Biofilm C:P and N:P increased across the streamwater N:P gradient. Light had only weak effects on biofilm C:P and N:P ratios, suggesting biofilm stoichiometry could function as a useful indicator of nutrient pollution when light limitation might otherwise dampen changes in biomass. The lowest C:N and C:P ratios were associated with increased Chl a :AFDM ratios, indicating increased autotrophic contributions were associated with greater N and P content. Even in low-light environments, we detected relatively large responses of algae-containing biofilms to N and P enrichment, consistent with previously reported effects of experimental nutrient addition, including primary and secondary consumer growth and production.

Thermal treatment of hexafluoropropylene oxide dimer acid (HFPO-DA) using a pilot-scale research combustor - Nathan H. Weber; Gabrielle V. West; William R. Roberson; John C. Mackie; James M. Mattila; Preston Burnette; Matthew Allen; William Preston; William P. Linak; Jonathan D. Krug (Journal of Hazardous Materials, 2025)

Rainbow trout rapidly recover from exposure to niclosamide: A piscicide and molluscicide used to control sea lamprey and snail populations - R. Adrian Ionescu; Dejana Mitrovic; Oana Birceanu; Allison E. McDonald; Jonathan M. Wilson; Mark R. Servos; Michael P. Wilkie (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Acidity impacts on microbial diversity and litter decomposition for organic soils - Catharine M. Pschenyckyj; Chris D. Evans; Liz J. Shaw; Robert I. Griffiths; Michael C. Bell; Jonathan P. Ritson; Joanna M. Clark (Plant and Soil, 2025)

Reducing UVR Exposure in Pregnant Women and Infants: A Pilot Study - William J. Tanguy; Kenneth P. Tercyak; Yizhe Xu; Jonathan Chipman; Nathan Shen; Caroline Joung; Hannah L. Brady; Marcelo M. Sleiman; Douglas Grossman; Lauren H. Theilen; Yelena P. Wu (Journal of Cancer Education, 2025)

Soil health and ecological resilience of no-till, organic, and mixed-crop livestock systems in eastern Washington State - Alexandra.G. Davis; Lynne Carpenter-Boggs; Katherine L. Smith; Jonathan M. Wachter; Garett Heineck; David R. Huggins; John P. Reganold (Agriculture, Ecosystems & Environment, 2025)

Reimagining species on the move across space and time - Alexa L. Fredston; Morgan W. Tingley; Montague H.C. Neate-Clegg; Luke J. Evans; Laura H. Antão; Natalie C. Ban; I-Ching Chen; Yi-Wen Chen; Lise Comte; David P. Edwards; Birgitta Evengard; Belen Fadrique; et al. (Trends in Ecology & Evolution, 2025)

Organochlorine pesticide use and mosaic loss of chromosome Y in a study of male farmers - Lauren M. Hurwitz; Vicky C. Chang; Laura E. Beane Freeman; Mitchell J. Machiela; Weiyin Zhou; Gabriella Andreotti; Christine G. Parks; Dale P. Sandler; Nathaniel Rothman; Sonja I. Berndt; Jonathan N. Hofmann; Stella Koutros (Environmental Research, 2025)

Range‐Wide Genomic Analysis Reveals Regional and Meta‐Population Dynamics of Decline and Recovery in the Grey Seal - Morgan L. McCarthy; Kristina M. Cammen; Sandra M. Granquist; Rune Dietz; Jonas Teilmann; Charlotte Bie Thøstesen; Simon Kjeldgaard; Mia Valtonen; Mervi Kunnasranta; Bjørn Munro Jenssen; Markus P. Ahola; Britt‐Marie Bäcklin; et al. (Molecular Ecology, 2025)
Wildlife populations globally have experienced widespread historical declines due to anthropogenic and environmental impacts, yet for some species, contemporary management and conservation programmes have enabled recent recovery. The impacts of decline and recovery on genomic diversity and, vice versa, the genetic factors that contribute to conservation success or failure are rich areas for inquiry, with implications for shaping how we manage species into the future. To comprehensively characterise these processes in natural systems requires range‐wide sampling and international collaboration, particularly for species with wide dispersal capabilities, broad geographic distributions, and complex regional metapopulation dynamics. Here, we present the first range‐ and genome‐wide population genomic analysis of grey seals based on 3812 nuclear SNPs genotyped in 188 samples from 17 localities. Our analyses support the existence of three main grey seal populations centred in the NW Atlantic, NE Atlantic and Baltic Sea, and point to the existence of previously unrecognised substructure within the NE Atlantic. We detected remarkably low levels of genetic diversity in the NW Atlantic population, and demographic analyses revealed a turbulent history of NE Atlantic and Baltic Sea grey seals, with bottlenecks in the Middle Ages and the 20th century due to hunting and habitat alterations. We found some localities deviated from isolation by distance patterns, likely reflecting wide‐scale metapopulation dynamics associated with recolonisation and recovery in regions where they were historically extirpated. We identify at least six grey seal genetic populations and reveal marked genetic effects of past declines and recent recovery across the species' range.

Resource quantity and quality co‐limit consumer production in forest streams - Lee M. Demi; Phillip M. Bumpers; Wyatt F. Cross; Susan L. Eggert; John S. Kominoski; David W. P. Manning; Amy D. Rosemond; J. Bruce Wallace; Seth J. Wenger; Jonathan P. Benstead (Ecology, 2025)
Ecological theory predicts that consumers should be co‐limited by resource quantity and quality, given widespread consumer‐resource nutritional imbalances. We used 25 estimates of annual community secondary production (ACSP) of stream macroinvertebrates to assess the relative roles of basal resource quantity (leaf litter standing stock [LLSS]) and quality (% nitrogen and % phosphorus of leaf litter) in modulating patterns of production in forest streams. We also tested the effects of hypothesized indirect drivers (stream discharge and inorganic nutrient concentrations) on basal resource quality and quantity and secondary production. In the top model for ACSP, LLSS, and %P together explained 59% of its variation, providing strong evidence of co‐limitation by both resource quantity and quality. Mean annual stream discharge and stream water P concentration explained 75% and 43% of variation in LLSS and %P, respectively. Together, stream discharge and stream water P concentration explained 77% of the variation in ACSP, demonstrating a critical link between hypothesized indirect and direct (basal resources) drivers and ACSP. Our results are the first to demonstrate co‐limitation of ACSP and highlight several mechanisms by which drivers of anthropogenic global change, such as altered precipitation (stream discharge) and eutrophication, influence the productivity of animal communities in stream ecosystems.

Impacts of hypoxia and planktivory on crustacean and rotifer diel vertical and horizontal migration behaviors - Anna G. Schmidt; Isabel M. Anderson; Rosalie Bruel; Rosaura J. Chapina; Jonathan P. Doubek; Sarah Fiorini; Sadye K. Goldfarb; Gérard Lacroix; Heather L. Wander; Savannah Zigic; Jason D. Stockwell (Hydrobiologia, 2025)

Differential survival of Ilyanassa obsoleta to water temperature and association with the non-native red alga Gracilaria vermiculophylla - Timothy S. Lee; Amy E. Fowler; Jessica R. Largen; Jonathan P. Russo; Zackary J. Schlegel; Dawson K. Wright; April M. H. Blakeslee (Hydrobiologia, 2025)
Along the U.S. east coast, the widespread non-native red alga Gracilaria vermiculophylla provides habitat for an array of macroinvertebrates, including the eastern mudsnail Ilyanassa obsoleta . Though I. obsoleta tolerates a wide temperature range, increases in summer water temperatures may enhance mortality; furthermore, the presence of non-native algae in rising seawater temperatures could exacerbate harmful conditions. We tested how the presence or absence of G. vermiculophylla influenced snail mortality across a range of summer temperatures over a 3-week period. We found that I. obsoleta survived the longest in the lowest temperature (27 °C), followed by the medium (32 °C), and lastly the highest (36 °C) where all snails died within 2 days. Mortality was also higher and faster for snails in the presence versus absence of G. vermiculophylla . We suspected dissolved oxygen became very low at the higher temperatures with G. vermiculophylla ; thus we conducted a laboratory-based dissolved oxygen experiment. We found that G. vermiculophylla degraded and oxygen declined faster at the highest temperature treatment, thereby creating anoxic conditions. Altogether, our results demonstrate that G. vermiculophylla could enhance anoxic conditions at high summer temperatures, potentially leading to enhanced faunal mortality.

Spatial ecology and population dynamics of brown trout Salmo trutta L. in reservoirs and headwater tributaries - Jamie R. Dodd; Richard A. A. Noble; Andy D. Nunn; Holly M. Owen; Paolo Moccetti; Jonathan P. Harvey; Liam Wallace; Ben Gillespie; Domino A. Joyce; Jonathan D. Bolland (Journal of Fish Biology, 2025)
This investigation compared the spatial ecology and population dynamics of brown trout Salmo trutta L. between reservoirs with (impact; Langsett Reservoir) and without (control; Grimwith Reservoir) barriers to fish movements into headwater tributaries, and the effectiveness of a fish pass intended to remediate connectivity. Passive integrated transponder (PIT) telemetry revealed that fish that emigrated from Langsett and Grimwith tributaries were 1–3 and 0–2 years old, respectively, and predominantly did so in spring and autumn‐early winter in both systems. Weirs at Langsett Reservoir appeared to thwart emigration rate (26%) relative to Grimwith Reservoir (85%). Acoustic telemetry (two‐dimensional positions) in the impacted reservoir revealed that the largest home range was in October–December (95% monthly activity space S.D. up to 26.9 ± 6.69 ha in November), activity was influenced by both month and time of day, and fish occupied shallow water depths (relative to reservoir depth), especially at night. Brown trout tagged in Grimwith and Langsett Reservoirs (42.9% and 64.1%, respectively) and fish tagged in the tributaries that emigrated (37.2% and 27.7%, respectively) were detected immigrating into tributaries throughout the year. At both reservoirs, peak immigration for ≥3‐year‐old trout occurred primarily in autumn‐early winter. Overall passage efficiency went from 3% prior to remediation to 14% after and there was no significant increase in fish densities following the construction of the fish pass. Fish were attracted towards and entered the fish pass under a wide range of river levels, but only succeeded in passing upstream during low levels, which are uncommon druing the main migration period. Overall, this investigation significantly furthers our understanding of brown trout spatial ecology and population dynamics in reservoirs and headwater tributaries.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Role of low‐impact‐factor journals in conservation implementation - Jonathan J. Choi; Leo C. Gaskins; Joseph P. Morton; Julia A. Bingham; Ashley M. Blawas; Christine Hayes; Carmen Hoyt; Patrick N. Halpin; Brian Silliman (Conservation Biology, 2025)
Academic review, promotion, and tenure processes place a premium on frequent publication in high‐impact factor (IF) journals. However, conservation often relies on species‐specific information that is unlikely to have the broad appeal needed for high‐IF journals. Instead, this information is often distributed in low‐IF, taxa‐ and region‐specific journals. This suggests a potential mismatch between the incentives for academic researchers and the scientific needs of conservation implementation. To explore this mismatch, we looked at federal implementation of the United States Endangered Species Act (ESA), which requires the use of the “best available science” to list a species as endangered or threatened and thus receive powerful legal protections. In assessing the relationship between academic sources of this “best available science” and ESA implementation, we looked at the 13,292 sources (e.g., academic journals, books, reports, regulations, personal communications, etc.) cited by the second Obama administration (2012–2016) across all ESA listings. We compared the IFs of all 785 journals that published peer‐reviewed papers cited in these listings against their citation frequency in ESA listings to determine whether a journal's IF varied in proportion with its contribution to federal conservation. Most of the peer‐reviewed academic articles referenced in ESA listings came from low‐IF or no‐IF journals that tended to focus on specific taxa or regions. Although we support continued attention to cutting‐edge, multidisciplinary science for its ability to chart new pathways and paradigms, our findings stress the need to value and fund the taxa‐ and region‐specific science that underpins actionable conservation laws.

Nutrient limitation and seasonality associated with phytoplankton communities and cyanotoxin production in a large, hypereutrophic lake - Gabriella M. Lawson; Jakob L. Young; Zachary T. Aanderud; Erin F. Jones; Samuel Bratsman; Jonathan Daniels; Madeleine P. Malmfeldt; Michelle A. Baker; Benjamin W. Abbott; Scott Daly; Hans W. Paerl; Greg Carling; et al. (Harmful Algae, 2025)

Multi-scale forest heterogeneity promotes occupancy of dusky-footed woodrats in the Sierra Nevada - Corbin C. Kuntze; Jonathan N. Pauli; John J. Keane; Kevin N. Roberts; Brian P. Dotters; H. Anu Kramer; M. Zachariah Peery (Forest Ecology and Management, 2025)

Vertebrates in trade that pose high invasion risk to the United States - Wesley M. Daniel; Helen R. Sofaer; Catherine S. Jarnevich; Richard A. Erickson; Brett A. DeGregorio; Peder S. Engelstad; Jonathan Freedman; Susan Canavan; E.M. Dean; Michael J. Adams; Charmayne L. Anderson; Mindy Barnett; et al. (Biological Conservation, 2025)

LandFrag : A Dataset to Investigate the Effects of Forest Loss and Fragmentation on Biodiversity - Thiago Gonçalves‐Souza; Maurício Humberto Vancine; Nathan J. Sanders; Nick M. Haddad; Lucas Cortinhas; Anne Lene T. O. Aase; Willian Moura de Aguiar; Marcelo Adrian Aizen; Víctor Arroyo‐Rodríguez; Arturo Baz; Maíra Benchimol; Enrico Bernard; et al. (Global Ecology and Biogeography, 2025)
Motivation The accelerated and widespread conversion of once continuous ecosystems into fragmented landscapes has driven ecological research to understand the response of biodiversity to local (fragment size) and landscape (forest cover and fragmentation) changes. This information has important theoretical and applied implications, but is still far from complete. We compiled the most comprehensive and updated database to investigate how these local and landscape changes determine species composition, abundance and trait diversity of multiple taxonomic groups in forest fragments across the globe. Main Types of Variables Contained We gathered data for 1472 forest fragments, providing information on the abundance and composition of 9154 species belonging to vertebrates, invertebrates, and plants. For 2703 of these species, we obtained more than 20 functional traits. We provided the spatial location and size of each fragment and metrics of landscape composition and configuration. Spatial Location and Grain The dataset includes 1472 forest fragments sampled in 121 studies from all continents except Antarctica. Most datasets (77%) are from tropical regions, 17% are from temperate regions, and 6% are from subtropical regions. Species abundance and composition were collected at the plot or fragment scale, whereas the landscape metrics were extracted with buffer size ranging from a radius of 200–2000 m. Time Period and Grain Data on the abundance of species and community composition were collected between 1994 and 2022, and the landscape metrics were extracted from the same year that a given study collected the abundance and composition data. Major Taxa and Level of Measurement The studied organisms included invertebrates (Arachnida, Insecta and Gastropoda; 41% of the datasets), vertebrates (Amphibia, Squamata, Aves and Mammalia; 44%), and vascular plants (19%), and the lowest level of identification was species or morphospecies. Software Format The dataset and code can be downloaded on Zenodo or GitHub.

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Scaling up ocean conservation through recognition of key biodiversity areas in the Southern Ocean from multispecies tracking data - Sarah L. Becker; Charlotte Boyd; Jonathan M. Handley; Ben Raymond; Ryan Reisinger; Yan Ropert‐Coudert; Nora Apelgren; Tammy E. Davies; Mary‐Anne Lea; Mercedes Santos; Philip N. Trathan; Anton P. Van de Putte; et al. (Conservation Biology, 2025)
Biodiversity is critical for maintaining ecosystem function but is threatened by increasing anthropogenic pressures. In the Southern Ocean, a highly biologically productive region containing many endemic species, proactive management is urgently needed to mitigate increasing pressures from fishing, climate change, and tourism. Site‐based conservation is one important tool for managing the negative impacts of human activities on ecosystems. The Key Biodiversity Area (KBA) Standard is a standardized framework used to define sites vital for the persistence of global biodiversity based on criteria and quantitative thresholds. We used tracking data from 14 species of Antarctic and subantarctic seabirds and pinnipeds from the publicly available Retrospective Analysis of Antarctic Tracking Data (RAATD) data set to define KBAs for a diverse suite of marine predators. We used track2kba, an R package that supports identification of KBAs from telemetry data through identification of highly used habitat areas and estimates of local abundance within sites. We compared abundance estimates at each site with thresholds for KBA criteria A1, B1, and D1 (related to globally threatened species, individual geographically restricted species, and demographic aggregations, respectively). We identified 30 potential KBAs for 13 species distributed throughout the Southern Ocean that were vital for each individual species, population, and life‐history stage for which they were determined. These areas were identified as highly used by these populations based on observational data and complement the ongoing habitat modeling and bioregionalization work that has been used to prioritize conservation areas in this region. Although further work is needed to identify potential KBAs based on additional current and future data sets, we highlight the benefits of utilizing KBAs as part of a holistic approach to marine conservation, given their significant value as a global conservation tool.

Do the biological characteristics of trout ( Salmo trutta ) smolts influence their spring migration timing and maiden marine sojourn duration? - Jonathan P. Gillson; Robert E. Blackwell; Stephen D. Gregory; Jessica E. Marsh; Tea Bašić; Sophie A. M. Elliott; R. Andrew King; David L. Maxwell; William D. Riley; Jamie R. Stevens; Alan M. Walker; Rasmus B. Lauridsen (Journal of Fish Biology, 2025)
Anadromous salmonids migrate seaward to exploit feeding and growth opportunities in marine habitats, yet how smolt biological characteristics influence their marine migratory behavior remains poorly understood. This study used 9 years of trout ( Salmo trutta ) population monitoring data from 15,595 tagged age‐0+ parr, 1033 smolts detected migrating downstream in spring, and 99 adults detected returning from their first marine migration to the River Frome (Dorset, UK) to investigate the influence of smolt biological characteristics on their migration timing and maiden marine sojourn duration. Age‐specific differences in the influence of smolt length on migration timing were found, with longer 1‐year‐old smolts emigrating later than their shorter counterparts within the same age class, but the opposite association existed for 2‐year‐old smolts. A bespoke integrated statistical model quantified the effects of smolt emigration day of year, age, sex, and length on the probability of first‐time migrants returning to the river after one or more sea winters. Younger, later migrating smolts had a longer marine sojourn duration than their older, earlier migrating counterparts, and females remained at sea for longer periods than males. Although the statistical model was designed to maximize the use of information available in the data, it revealed only weak effects of smolt biological characteristics on the maiden marine sojourn duration. A complementary simulation study suggested that detecting more spring migrating smolts and analyzing longer time series of trout population monitoring data would increase the ability to detect statistically significant effects. Therefore, a strategic review of the trout population monitoring program, including more long‐term biological data collection, is recommended. The modelling work presented here can provide guidance on the size of the required dataset and how to maximize the power of imperfect data.

Long-term nighttime aircraft noise exposure and risk of hypertension in a prospective cohort of female nurses - Junenette L. Peters; Stephanie T. Grady; Francine Laden; Elizabeth Nelson; Matthew Bozigar; Jaime E. Hart; JoAnn E. Manson; Tianyi Huang; Susan Redline; Joel D. Kaufman; John P. Forman; Kathryn M. Rexrode; et al. (International Journal of Hygiene and Environmental Health, 2025)

After the n10: late oVEMP peaks in patients with unilateral vestibular loss and healthy volunteers - Alyssa C. Dyball; Xiao Ping Wu; Belinda Y. C Kwok; Chao Wang; Benjamin Nham; Jacob M. Pogson; Jonathan H. K. Kong; Rachael L. Taylor; Konrad P. Weber; Miriam S. Welgampola; Sally M. Rosengren (Experimental Brain Research, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Our planet and our future - M. P. Jonathan; Ana Judith Marmolejo-Rodríguez; Eugenia López López; Kalina Bermúdez Torres (Environmental Science and Pollution Research, 2024)

A global systematic review of the cultural ecosystem services provided by wetlands - Kevin A. Wood; Lucy L. Jupe; Francisca C. Aguiar; Alexandra M. Collins; Scott J. Davidson; Will Freeman; Liam Kirkpatrick; Tatiana Lobato-de Magalhães; Emma McKinley; Ana Nuno; Jordi F. Pagès; Antonella Petruzzella; et al. (Ecosystem Services, 2024)

Half a century of citizen science tag-recapture data reveals stock delineation and cross-jurisdictional connectivity of an iconic pelagic fish - Belinda K. Goddard; Tristan A. Guillemin; Hayden T. Schilling; Julian M. Hughes; Stephanie Brodie; Corey P. Green; Robert Harcourt; Charlie Huveneers; Daniel Ierodiaconou; Iain M. Suthers; Matthew D. Taylor; Sean R. Tracey; et al. (Reviews in Fish Biology and Fisheries, 2024)
Tag-recapture programs to monitor the movements of fish populations are among some of the longest-running citizen-science datasets to date. Here, using half a century of yellowtail kingfish ( Seriola lalandi, Carangidae) tag-recapture data collected through citizen-science projects, we report novel insights into population connectivity in Australia and New Zealand (NZ). Despite the importance of kingfish in commercial and recreational fisheries, substantial knowledge gaps about their stock structure and connectivity between jurisdictions hinder current management efforts. Between 1974 and 2022, 63,432 releases and 4636 recaptures (7.3%) of tagged kingfish were collected in Australia and NZ. Most tagged individuals (51.4%) were recaptured within 10 km of their original release location up to 14 years post-release (mean: 225 days), indicating some degree of site fidelity. However, 656 (14.2%) kingfish were recaptured over 100 km from their release location, with one fish travelling at least 2834 km in 702 days. Seasonal variability was evident for releases and recaptures, with more releases occurring in summer and autumn in most jurisdictions. Network analysis of recaptures revealed no connectivity between tagged kingfish from western and eastern Australia, supporting genetic delineation. By contrast, extensive connectivity exists across eastern Australia and NZ, with 87 kingfish moving between five Australian state jurisdictions, 316 individuals travelling across 15 bioregions and six kingfish moving between Australia and NZ. Our findings provide important new insights into the structure and connectivity of the eastern Australia kingfish stock and suggest increased collaboration between state and international fisheries jurisdictions may support improved stock assessment and management.

A Latitudinal Cline in the Taxonomic Structure of Eelgrass Epifaunal Communities is Associated With Plant Genetic Diversity - Collin P. Gross; J. Emmett Duffy; Kevin A. Hovel; Pamela L. Reynolds; Christoffer Boström; Katharyn E. Boyer; Mathieu Cusson; Johan Eklöf; Aschwin H. Engelen; Britas Klemens Eriksson; F. Joel Fodrie; John N. Griffin; et al. (Global Ecology and Biogeography, 2024)
Aim Biogenic structural complexity increases mobile animal richness and abundance at local, regional and global scales, yet animal taxa vary in their response to complexity. When these taxa also vary functionally, habitat structures favouring certain taxa may have consequences for ecosystem function. We characterised global patterns of epifaunal invertebrates in eelgrass ( Zostera marina ) beds that varied in structural and genetic composition. Location North America, Europe and Asia. Time Period 2014. Major Taxa Studied Peracarid crustaceans and gastropod molluscs. Methods We sampled epifaunal invertebrate communities in 49 eelgrass beds across 37° latitude in two ocean basins concurrently with measurements of eelgrass genetic diversity, structural complexity and other abiotic and biotic environmental variables. We examined how species richness, abundance and community composition varied with latitude and environmental predictors using a random forest approach. We also examined how functional trait composition varied along with community structure. Results Total species richness decreased with latitude, but this was accompanied by a taxonomic shift in dominance from peracarid crustaceans to gastropods, which exhibited different sets of functional traits. Greater eelgrass genetic diversity was strongly correlated with both richness and abundance of peracarids, but less so for gastropods. Main Conclusions Our results add to a growing body of literature that suggests genetic variation in plant traits influences their associated faunal assemblages via habitat structure. Because peracarids and gastropods exhibited distinct functional traits, our results suggest a tentative indirect link between broad‐scale variation in plant genetic diversity and ecosystem function.

The BirdLife Seabird Tracking Database: 20 years of collaboration for marine conservation - Ana P.B. Carneiro; Maria P. Dias; Bethany L. Clark; Elizabeth J. Pearmain; Jonathan Handley; Amy R. Hodgson; John P. Croxall; Richard A. Phillips; Steffen Oppel; Joanne M. Morten; Ben Lascelles; Cleo Cunningham; et al. (Biological Conservation, 2024)

Regional earthquake-induced landslide assessments for use in seismic risk analyses of distributed gas infrastructure systems - Olaide Ojomo; Ellen M. Rathje; Pengfei Wang; Greg Lavrendiatis; Paolo Zimmaro; Domniki Asimaki; Jonathan P. Stewart (Engineering Geology, 2024)

Mutagenic atmospheres generated from the photooxidation of NOx with selected VOCs and a complex mixture: Apportionment of aromatic mutagenicity for reacted gasoline vapor - Jonathan D. Krug; Theran P. Riedel; Michael Lewandowski; William A. Lonneman; John M. Turlington; Jose Zavala; Sarah H. Warren; Tadeusz E. Kleindienst; David M. DeMarini (Atmospheric Environment, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Long‐Term Alpine Plant Responses to Global Change Drivers Depend on Functional Traits - Jonathan J. Henn; Kurt E. Anderson; Laurel M. Brigham; Clifton P. Bueno de Mesquita; Courtney G. Collins; Sarah C. Elmendorf; Matthew D. Green; Jared D. Huxley; Nicole E. Rafferty; Annika Rose‐Person; Marko J. Spasojevic (Ecology Letters, 2024)
Forecasting plant responses under global change is a critical but challenging endeavour. Despite seemingly idiosyncratic responses of species to global change, greater generalisation of ‘winners’ and ‘losers’ may emerge from considering how species functional traits influence responses and how these responses scale to the community level. Here, we synthesised six long‐term global change experiments combined with locally measured functional traits. We quantified the change in abundance and probability of establishment through time for 70 alpine plant species and then assessed if leaf and stature traits were predictive of species and community responses across nitrogen addition, snow addition and warming treatments. Overall, we found that plants with more resource‐acquisitive trait strategies increased in abundance but each global change factor was related to different functional strategies. Nitrogen addition favoured species with lower leaf nitrogen, snow addition favoured species with cheaply constructed leaves and warming showed few consistent trends. Community‐weighted mean changes in trait values in response to nitrogen addition, snow addition and warming were often different from species‐specific trait effects on abundance and establishment, reflecting in part the responses and traits of dominant species. Together, these results highlight that the effects of traits can differ by scale and response of interest.

Temperature dependence of leaf breakdown in streams differs between organismal groups and leaf species - Carolyn S. Cummins; Amy D. Rosemond; Nathan J. Tomczyk; Seth J. Wenger; Phillip M. Bumpers; Vladislav Gulis; Ashley M. Helton; Jonathan P. Benstead (Ecology, 2024)
Increased temperatures are altering rates of organic matter (OM) breakdown in stream ecosystems with implications for carbon (C) cycling in the face of global change. The metabolic theory of ecology (MTE) provides a framework for predicting temperature effects on OM breakdown, but differences in the temperature dependence of breakdown driven by different organismal groups (i.e., microorganisms vs. invertebrate detritivores) and litter species remain unresolved. Over two years, we conducted 12 60‐day leaf litterbag incubations in 20 headwater streams in the southern Appalachian Mountains (USA). We compared temperature dependence (as activation energy, E a ) between microbial and detritivore‐mediated breakdown, and between a highly recalcitrant ( Rhododendron maximum ) and a relatively labile ( Acer rubrum ) leaf species. Detritivore‐mediated breakdown had a higher E a than microbial breakdown for both leaf species ( Rhododendron : 1.48 > 0.56 eV; Acer : 0.97 > 0.29 eV), and Rhododendron breakdown had a higher E a than Acer breakdown for both organismal groups. Similarly, the E a of total (coarse‐mesh) Rhododendron breakdown was higher than the E a of total Acer breakdown (0.89 > 0.52 eV). These effects for total breakdown were large, implying that the number of days to 95% mass loss would decline by 40% for Rhododendron and 26% for Acer between 12°C (our mean temperature value) and 16°C (+4°C, reflecting projected increases in global surface temperature due to climate change). Despite patterns in E a , overall breakdown rates were higher for microbes than detritivores, and for Acer than Rhododendron over most of our temperature gradient. Additionally, the E a for a subset of the microbial breakdown data declined from 0.40 to 0.22 eV when fungal biomass was included as a model predictor, highlighting the key role of fungi in determining the temperature dependence of litter breakdown. Our results imply that, as streams warm, routing of leaf litter C to detritivore‐mediated fates will increase faster than predicted by previous studies and MTE, especially for labile litter. As temperatures rise, earlier depletion of autumn‐shed, labile leaf litter combined with rapid breakdown rates of recalcitrant litter could exacerbate seasonal resource limitation and alter carbon storage and transport dynamics in temperate headwater stream networks.

Consequences of Local Conspecific Density Effects for Plant Diversity and Community Dynamics - Joseph A. LaManna; Florian Hartig; Jonathan A. Myers; Robert P. Freckleton; Matteo Detto; Akshay Surendra; Cole J. Doolittle; Bénédicte Bachelot; Robert Bagchi; Liza S. Comita; David M. DeFilippis; Nohemi Huanca‐Nunez; et al. (Ecology Letters, 2024)
Conspecific density dependence (CDD) in plant populations is widespread, most likely caused by local‐scale biotic interactions, and has potentially important implications for biodiversity, community composition, and ecosystem processes. However, progress in this important area of ecology has been hindered by differing viewpoints on CDD across subfields in ecology, lack of synthesis across CDD‐related frameworks, and misunderstandings about how empirical measurements of local CDD fit within the context of broader ecological theories on community assembly and diversity maintenance. Here, we propose a conceptual synthesis of local‐scale CDD and its causes, including species‐specific antagonistic and mutualistic interactions. First, we compare and clarify different uses of CDD and related concepts across subfields within ecology. We suggest the use of local stabilizing/destabilizing CDD to refer to the scenario where local conspecific density effects are more negative/positive than heterospecific effects. Second, we discuss different mechanisms for local stabilizing and destabilizing CDD, how those mechanisms are interrelated, and how they cut across several fields of study within ecology. Third, we place local stabilizing/destabilizing CDD within the context of broader ecological theories and discuss implications and challenges related to scaling up the effects of local CDD on populations, communities, and metacommunities. The ultimate goal of this synthesis is to provide a conceptual roadmap for researchers studying local CDD and its implications for population and community dynamics.

Sustainable mining in tropical, biodiverse landscapes: Environmental challenges and opportunities in the archipelagic Philippines - Justine Perry T. Domingo; Gawen R.T. Jenkin; Laura Quick; Richard D. Williams; Karen A. Hudson-Edwards; Cecilia Tortajada; Patrick Byrne; Tom J. Coulthard; Jenielyn T. Padrones; Rich Crane; Cris Reven L. Gibaga; Grigorios Vasilopoulos; et al. (Journal of Cleaner Production, 2024)

Twenty‐five emerging questions when detecting, understanding, and predicting future fish distributions in a changing climate - Molly M. Kressler; Georgina L. Hunt; Anna K. Stroh; John K. Pinnegar; Jonathan Mcdowell; Joseph W. Watson; Marcelo P. Gomes; Michał E. Skóra; Sam Fenton; Richard D. M. Nash; Rui Vieira; Martha Patricia Rincón‐Díaz (Journal of Fish Biology, 2024)
The 2023 Annual Symposium of the Fisheries Society of the British Isles hosted opportunities for researchers, scientists, and policy makers to reflect on the state of art of predicting fish distributions and consider the implications to the marine and aquatic environments of a changing climate. The outcome of one special interest group at the Symposium was a collection of questions, organized under five themes, which begin to capture the state of the field and identify priorities for research and management over the coming years. The five themes were Physiology, Mechanisms, Detect and Measure, Manage, and Wider Ecosystems. The questions, 25 of them, addressed concepts which remain poorly understood, are data deficient, and/or are likely to be impacted in measurable or profound ways by climate change. Moving from the first to the last theme, the questions expanded in the scope of their considerations, from specific processes within the individual to ecosystem‐wide impacts, but no one question is bigger than any other: each is important in detecting, understanding, and predicting fish distributions, and each will be impacted by an aspect of climate change. In this way, our questions, particularly those concerning unknown mechanisms and data deficiencies, aimed to offer a guide to other researchers, managers, and policy makers in the prioritization of future work as a changing climate is expected to have complex and disperse impacts on fish populations and distributions that will require a coordinated effort to address.

Advancing Understanding of Chemical Exposures and Maternal-child Health Through the U.S. Environmental Influences on Child Health Outcomes (ECHO) Program: A Scoping Review - Emily S. Barrett; Jennifer L. Ames; Stephanie M. Eick; Alicia K. Peterson; Zorimar Rivera-Núñez; Anne P. Starling; Jessie P. Buckley; Barbara O‟Brien; Lisa Peterson; Patrick Parsons; Kannan Kurunthacalam; Manish Arora; et al. (Current Environmental Health Reports, 2024)
Purpose of Review Environmental chemical exposures may disrupt child development, with long-lasting health impacts. To date, U.S. studies of early environmental exposures have been limited in size and diversity, hindering power and generalizability. With harmonized data from over 60,000 participants representing 69 pregnancy cohorts, the National Institutes of Health’s Environmental influences on Child Health Outcomes (ECHO) Program is the largest study of U.S. children’s health. Here, we: (1) review ECHO-wide studies of chemical exposures and maternal-child health; and (2) outline opportunities for future research using ECHO data. Recent Findings As of early 2024, in addition to over 200 single-cohort (or award) papers on chemical exposures supported by ECHO, ten collaborative multi-cohort papers have been made possible by ECHO data harmonization and new data collection. Multi-cohort papers have examined prenatal exposure to per- and polyfluoroalkyl substances (PFAS), phthalates, phenols and parabens, organophosphate esters (OPEs), metals, melamine and aromatic amines, and emerging contaminants. They have primarily focused on describing patterns of maternal exposure or examining associations with maternal and infant outcomes; fewer studies have examined later child outcomes (e.g., autism) although follow up of enrolled ECHO children continues. The NICHD’s Data and Specimen Hub (DASH) database houses extensive ECHO data including over 470,000 chemical assay results and complementary data on priority outcome areas (pre, peri-, and postnatal, airway, obesity, neurodevelopment, and positive health), making it a rich resource for future analyses. Summary ECHO’s extensive data repository, including biomarkers of chemical exposures, can be used to advance our understanding of environmental influences on children’s health. Although few published studies have capitalized on these unique harmonized data to date, many analyses are underway with data now widely available.

Photogrammetry scans for neuroanatomy education - a new multi-camera system: technical note - André S. B. Oliveira; Luciano C. P. C. Leonel; Megan M. J. Bauman; Alessandro De Bonis; Edward R. LaHood; Stephen Graepel; Michael J. Link; Carlos D. Pinheiro-Neto; Nirusha Lachman; Jonathan M. Morris; Maria Peris-Celda (Neuroinformatics, 2024)

Catalytic production of light Olefins: Perspective and prospective - Naif S. Almuqati; Afrah M. Aldawsari; Khalid N. Alharbi; Sergio González-Cortés; Mohammed F. Alotibi; Fawaz Alzaidi; Jonathan R. Dilworth; Peter P. Edwards (Fuel, 2024)

The murine metastatic microenvironment of experimental brain metastases of breast cancer differs by host age in vivo: a proteomic study - Allison L. Hunt; Imran Khan; Alex M. L. Wu; Sasha C. Makohon-Moore; Brian L. Hood; Kelly A. Conrads; Tamara Abulez; Jonathan Ogata; Dave Mitchell; Glenn Gist; Julie Oliver; Debbie Wei; et al. (Clinical & Experimental Metastasis, 2024)

Environmental warming increases the importance of high‐turnover energy channels in stream food webs - James R. Junker; Wyatt F. Cross; James M. Hood; Jonathan P. Benstead; Alexander D. Huryn; Daniel Nelson; Jón S. Ólafsson; Gísli M. Gíslason (Ecology, 2024)
Warming temperatures are altering communities and trophic networks across Earth's ecosystems. While the overall influence of warming on food webs is often context‐dependent, increasing temperatures are predicted to change communities in two fundamental ways: (1) by reducing average body size and (2) by increasing individual metabolic rates. These warming‐induced changes have the potential to influence the distribution of food web fluxes, food web stability, and the relative importance of deterministic and stochastic ecological processes shaping community assembly. Here, we quantified patterns and the relative distribution of organic matter fluxes through stream food webs spanning a broad natural temperature gradient (5–27°C). We then related these patterns to species and community trait distributions of mean body size and population biomass turnover ( P : B ) within and across streams. We predicted that (1) communities in warmer streams would exhibit smaller body size and higher P:B and (2) organic matter fluxes within warmer communities would increasingly skew toward smaller, higher P:B populations. Across the temperature gradient, warmer communities were characterized by smaller body size (~9% per °C) and higher P:B (~7% faster turnover per °C) populations on average. Additionally, organic matter fluxes within warmer streams were increasingly skewed toward higher P:B populations, demonstrating that warming can restructure organic matter fluxes in both an absolute and relative sense. With warming, the relative distribution of organic matter fluxes was decreasingly likely to arise through the random sorting of species, suggesting stronger selection for traits driving high turnover with increasing temperature. Our study suggests that a warming world will favor energy fluxes through “smaller and faster” populations, and that these changes may be more predictable than previously thought.

Reproducible responses of geochemical and microbial successional patterns in the subsurface to carbon source amendment - Jonathan P. Michael; Andrew D. Putt; Yunfeng Yang; Benjamin G. Adams; Kathryn R. McBride; Yupeng Fan; Kenneth A. Lowe; Daliang Ning; Sindhu Jagadamma; Ji Won Moon; Dawn M. Klingeman; Ping Zhang; et al. (Water Research, 2024)

New Oldowan locality Sare-Abururu (ca. 1.7 Ma) provides evidence of diverse hominin behaviors on the Homa Peninsula, Kenya - Emma M. Finestone; Thomas W. Plummer; Thomas H. Vincent; Scott A. Blumenthal; Peter W. Ditchfield; Laura C. Bishop; James S. Oliver; Andy I.R. Herries; Christopher Vere Palfery; Timothy P. Lane; Elizabeth McGuire; Jonathan S. Reeves; et al. (Journal of Human Evolution, 2024)

Subchronic inhalation exposure to ultrafine particulate matter alters the intestinal microbiome in various mouse models - Candace Chang; Rajat Gupta; Farzaneh Sedighian; Allen Louie; David M. Gonzalez; Collin Le; Jae Min Cho; Seul-Ki Park; Jocelyn Castellanos; To-Wei Ting; Tien S. Dong; Nerea Arias-Jayo; et al. (Environmental Research, 2024)

Multiple biotic interactions establish phytoplankton community structure across environmental gradients - Stephanie Dutkiewicz; Christopher L. Follett; Michael J. Follows; Fernanda Henderikx‐Freitas; Francois Ribalet; Mary R. Gradoville; Sacha N. Coesel; Hanna Farnelid; Zoe V. Finkel; Andrew J. Irwin; Oliver Jahn; David M. Karl; et al. (Limnology and Oceanography, 2024)
The combination of taxa and size classes of phytoplankton that coexist at any location affects the structure of the marine food web and the magnitude of carbon fluxes to the deep ocean. But what controls the patterns of this community structure across environmental gradients remains unclear. Here, we focus on the North East Pacific Transition Zone, a ~ 10° region of latitude straddling warm, nutrient‐poor subtropical and cold, nutrient‐rich subpolar gyres. Data from three cruises to the region revealed intricate patterns of phytoplankton community structure: poleward increases in the number of cell size classes; increasing biomass of picoeukaryotes and diatoms; decreases in diazotrophs and Prochlorococcus ; and both increases and decreases in Synechococcus . These patterns can only be partially explained by existing theories. Using data, theory, and numerical simulations, we show that the patterns of plankton distributions across the transition zone are the result of gradients in nutrient supply rates, which control a range of complex biotic interactions. We examine how interactions such as size‐specific grazing, multiple trophic strategies, shared grazing between several phytoplankton size classes and heterotrophic bacteria, and competition for multiple resources can individually explain aspects of the observed community structure. However, it is the combination of all these interactions together that is needed to explain the bulk compositional patterns in phytoplankton across the North East Pacific Transition Zone. The synthesis of multiple mechanisms is essential for us to begin to understand the shaping of community structure over large environmental gradients.

An empirical DNA-based identification of morphologically similar snappers (Lutjanus campechanus, Lutjanus purpureus) using a versatile bioinformatics workflow for the discovery and analysis of informative single-nucleotide polymorphisms - Robert A. Literman; Mayara P. V. Matos; Sara M. Handy; Jonathan R. Deeds (Frontiers in Marine Science, 2024)
The commercially important species Lutjanus campechanus (Northern/Gulf red snapper) and Lutjanus purpureus (Southern/Caribbean red snapper) are the protagonists of a decade’s long taxonomic debate over their species delimitation, due in part to partial habitat overlap, extensive morphological similarity, and the lack of resolution when applying canonically reliable DNA barcoding approaches. In this study, we leveraged publicly available RAD-Seq data for L. campechanus and L. purpureus to identify species-informative single‐nucleotide polymorphisms (SNPs) at the genome scale that were successful in distinguishing the Northern and Southern red snappers, while also detecting individuals exhibiting introgression. This 4-step empirical approach demonstrates the value of applying novel bioinformatics pipelines to existing genome-scale data to maximize the distillation of informative subsets. Our results facilitate economically relevant species identification in addition to confirming or challenging species identifications for specimens with data in public databases. These findings and their applications will benefit future sustainability strategies and broader research questions surrounding these overfished and evolutionarily entangled snapper species.

A model for community-driven development of best practices: the Ocean Observatories Initiative Biogeochemical Sensor Data Best Practices and User Guide - Hilary I. Palevsky; Sophie Clayton; Heather Benway; Mairead Maheigan; Dariia Atamanchuk; Roman Battisti; Jennifer Batryn; Annie Bourbonnais; Ellen M. Briggs; Filipa Carvalho; Alison P. Chase; Rachel Eveleth; et al. (Frontiers in Marine Science, 2024)
The field of oceanography is transitioning from data-poor to data-rich, thanks in part to increased deployment of in-situ platforms and sensors, such as those that instrument the US-funded Ocean Observatories Initiative (OOI). However, generating science-ready data products from these sensors, particularly those making biogeochemical measurements, often requires extensive end-user calibration and validation procedures, which can present a significant barrier. Openly available community-developed and -vetted Best Practices contribute to overcoming such barriers, but collaboratively developing user-friendly Best Practices can be challenging. Here we describe the process undertaken by the NSF-funded OOI Biogeochemical Sensor Data Working Group to develop Best Practices for creating science-ready biogeochemical data products from OOI data, culminating in the publication of the GOOS-endorsed OOI Biogeochemical Sensor Data Best Practices and User Guide. For Best Practices related to ocean observatories, engaging observatory staff is crucial, but having a “user-defined” process ensures the final product addresses user needs. Our process prioritized bringing together a diverse team and creating an inclusive environment where all participants could effectively contribute. Incorporating the perspectives of a wide range of experts and prospective end users through an iterative review process that included “Beta Testers’’ enabled us to produce a final product that combines technical information with a user-friendly structure that illustrates data analysis pipelines via flowcharts and worked examples accompanied by pseudo-code. Our process and its impact on improving the accessibility and utility of the end product provides a roadmap for other groups undertaking similar community-driven activities to develop and disseminate new Ocean Best Practices.

The foraging ecology of green turtles (Chelonia mydas) in New Caledonia - Tyffen C. Read; Laurent Wantiez; Florent Keller; Jonathan M. Werry; Jason P. van de Merwe; Justin J. Meager; Olivier Chateau; Richard Farman; Colin J. Limpus (Marine Biology, 2024)
Green sea turtles ( Chelonia mydas ) face many threats from anthropogenic activity and are listed as Endangered on the International Union for the Conservation of Nature (IUCN) Red List of Threatened Species. They spend the majority of their lives in coastal foraging areas, and show strong fidelity to narrow foraging ranges. Understanding the foraging ecology of green turtles is therefore important for their management and conservation. Using stable isotopes analysis ( n = 200) and identification of stomach contents ( n = 21), this study investigated the foraging ecology of four distinct green turtle foraging aggregations (Goro, Isle of Pines, Ouen Island and Uo/Mato Islands) within the Grand Lagon Sud. This World Heritage Area located in New Caledonia supports regionally important nesting and foraging green turtle populations. The δ 13 C and δ 15 N values of skin samples ranged from − 19.3 to − 7.3‰ and 2.8–15.9‰, respectively. Metrics of isotopic niche and regression analyses were used to assess the degree of omnivory, trophic diversity and potential ontogenetic diet shifts in the different aggregations of foraging green turtles in this location. Each of the four sites and four age-classes had distinct isotopic niches, with evidence of omnivory and ontogenetic shifts, particular in new recruits and juveniles, and at Goro and Uo/Mato Islands. This was generally supported by the stomach contents analyses of a small number of green turtles opportunistically sampled from traditional ceremonies. This study provides important information on the foraging ecology of green turtles in New Caledonia, supporting management outcomes in this region. This collaboration with the tribes of the Grand Lagon Sud is also the first step towards the integrated management of the resource.

Endovascular treatment of patients with stroke caused by anterior cerebral artery occlusions - Erik M. Vos; Manon Kappelhof; Sanne J. den Hartog; Jonathan M. Coutinho; Bart J. Emmer; Bob Roozenbeek; Wim H. van Zwam; Robert J. van Oostenbrugge; H. Bart van der Worp; Maarten Uyttenboogaart; Adriaan C. G. M. van Es; Charles B. L. M. Majoie; et al. (Acta Neurologica Belgica, 2024)
Background Occlusion of the anterior cerebral artery (ACA) is uncommon but may lead to significant disability. The benefit of endovascular treatment (EVT) for ACA occlusions remains uncertain. Methods We included patients treated with EVT and compared patients with ACA occlusions with patients who had internal carotid artery (ICA) or proximal (M1/M2) middle cerebral artery (MCA) occlusions from the MR CLEAN Registry. Primary outcome was the modified Rankin Scale score (mRS). Secondary outcomes were functional independence (mRS 0–2), National Institutes of Health Stroke Scale (NIHSS) score, delta-NIHSS (baseline minus NIHSS score at 24–48 h), and successful recanalization (expanded thrombolysis in cerebral infarction (eTICI) score 2b-3). Safety outcomes were symptomatic intracranial hemorrhage (sICH), periprocedural complications, and mortality. Results Of 5193 patients, 11 (0.2%) had primary ACA occlusions. Median NIHSS at baseline was lower in patients with ACA versus ICA/MCA occlusions (11, IQR 9–14; versus 15, IQR 11–19). Functional outcome did not differ from patients with ICA/MCA occlusions. Functional independence was 4/11 (36%) in patients with ACA versus 1949/4815 (41%) in ICA/MCA occlusions; median delta-NIHSS was − 1 (IQR − 7 to 2) and − 4 (IQR − 9 to 0), respectively. Successful recanalization was 4/9 (44%), versus 3083/4787 (64%) in ICA/MCA occlusions. Mortality was 3/11 (27%) versus 1263/4815 (26%). One patient with ACA occlusion had sICH; no other complications occurred. Conclusion In this cohort ACA occlusions were uncommon. Functional outcome did not differ between patients with ACA occlusions and ICA/MCA occlusions. Prospective research is needed to determine feasibility, safety, and outcomes of EVT for ACA occlusions.

Comparisons of aerosol generation across different musical instruments and loudness - Jianghan Tian; Henry E. Symons; Natalie A. Watson; Justice Archer; Lauren P. McCarthy; Joshua Harrison; Malcolm Kittle; William J. Browne; Brian Saccente-Kennedy; Ruth Epstein; Christopher M. Orton; James D. Calder; et al. (Journal of Aerosol Science, 2024)

Incentivizing household action: Exploring the behavioral wedge in the 2021 Infrastructure Investment and Jobs Act and the 2022 Inflation Reduction Act - Mariah D. Caballero; Michael P. Vandenbergh; Jonathan M. Gilligan; Elodie O. Currier (Energy Policy, 2024)

A new conceptual model of global ocean heat uptake - Jonathan M. Gregory; Jonah Bloch-Johnson; Matthew P. Couldrey; Eleftheria Exarchou; Stephen M. Griffies; Till Kuhlbrodt; Emily Newsom; Oleg A. Saenko; Tatsuo Suzuki; Quran Wu; Shogo Urakawa; Laure Zanna (Climate Dynamics, 2024)
We formulate a new conceptual model, named “ MT 2”, to describe global ocean heat uptake, as simulated by atmosphere–ocean general circulation models (AOGCMs) forced by increasing atmospheric CO $$_{2}$$ 2 , as a function of global-mean surface temperature change T and the strength of the Atlantic meridional overturning circulation (AMOC, M ). MT 2 has two routes whereby heat reaches the deep ocean. On the basis of circumstantial evidence, we hypothetically identify these routes as low- and high-latitude. In low latitudes, which dominate the global-mean energy balance, heat uptake is temperature-driven and described by the two-layer model, with global-mean T as the temperature change of the upper layer. In high latitudes, a proportion p (about 14%) of the forcing is taken up along isopycnals, mostly in the Southern Ocean, nearly like a passive tracer, and unrelated to T . Because the proportion p depends linearly on the AMOC strength in the unperturbed climate, we hypothesise that high-latitude heat uptake and the AMOC are both affected by some characteristic of the unperturbed global ocean state, possibly related to stratification. MT 2 can explain several relationships among AOGCM projections, some found in this work, others previously reported: $$\bullet $$ ∙ Ocean heat uptake efficiency correlates strongly with the AMOC. $$\bullet $$ ∙ Global ocean heat uptake is not correlated with the AMOC. $$\bullet $$ ∙ Transient climate response (TCR) is anticorrelated with the AMOC. $$\bullet $$ ∙ T projected for the late twenty-first century under high-forcing scenarios correlates more strongly with the effective climate sensitivity than with the TCR.

Geothermal Play Fairway Analysis, Part 2: GIS methodology - Jacob DeAngelo; John W. Shervais; Jonathan M. Glen; Dennis Nielson; Sabodh Garg; Patrick F. Dobson; Erika Gasperikova; Eric Sonnenthal; Lee M. Liberty; Drew L. Siler; James P. Evans (Geothermics, 2024)

Geothermal play fairway analysis, part 1: Example from the Snake River Plain, Idaho - John W. Shervais; Jacob DeAngelo; Jonathan M. Glen; Dennis L. Nielson; Sabodh Garg; Patrick Dobson; Erika Gasperikova; Eric Sonnenthal; Lee M. Liberty; Dennis L. Newell; Drew Siler; James P. Evans (Geothermics, 2024)

Population genomic structure of a widespread, urban‐dwelling mammal: The eastern grey squirrel ( Sciurus carolinensis ) - Nicole A. Fusco; Bradley J. Cosentino; James P. Gibbs; Maximilian L. Allen; Alexander J. Blumenfeld; George H. Boettner; Elizabeth J. Carlen; Merri Collins; Catherine Dennison; Devin DiGiacopo; André‐Philippe Drapeau Picard; Jonathan Edmonson; et al. (Molecular Ecology, 2024)
Urbanization is a persistent and widespread driver of global environmental change, potentially shaping evolutionary processes due to genetic drift and reduced gene flow in cities induced by habitat fragmentation and small population sizes. We tested this prediction for the eastern grey squirrel ( Sciurus carolinensis ), a common and conspicuous forest‐dwelling rodent, by obtaining 44K SNPs using reduced representation sequencing (ddRAD) for 403 individuals sampled across the species' native range in eastern North America. We observed moderate levels of genetic diversity, low levels of inbreeding, and only a modest signal of isolation‐by‐distance. Clustering and migration analyses show that estimated levels of migration and genetic connectivity were higher than expected across cities and forested areas, specifically within the eastern portion of the species' range dominated by urbanization, and genetic connectivity was less than expected within the western range where the landscape is fragmented by agriculture. Landscape genetic methods revealed greater gene flow among individual squirrels in forested regions, which likely provide abundant food and shelter for squirrels. Although gene flow appears to be higher in areas with more tree cover, only slight discontinuities in gene flow suggest eastern grey squirrels have maintained connected populations across urban areas in all but the most heavily fragmented agricultural landscapes. Our results suggest urbanization shapes biological evolution in wildlife species depending strongly on the composition and habitability of the landscape matrix surrounding urban areas.

Understanding temporal variability across trophic levels and spatial scales in freshwater ecosystems - Tadeu Siqueira; Charles P. Hawkins; Julian D. Olden; Jonathan Tonkin; Lise Comte; Victor S. Saito; Thomas L. Anderson; Gedimar P. Barbosa; Núria Bonada; Claudia C. Bonecker; Miguel Cañedo‐Argüelles; Thibault Datry; et al. (Ecology, 2024)
A tenet of ecology is that temporal variability in ecological structure and processes tends to decrease with increasing spatial scales (from locales to regions) and levels of biological organization (from populations to communities). However, patterns in temporal variability across trophic levels and the mechanisms that produce them remain poorly understood. Here we analyzed the abundance time series of spatially structured communities (i.e., metacommunities) spanning basal resources to top predators from 355 freshwater sites across three continents. Specifically, we used a hierarchical partitioning method to disentangle the propagation of temporal variability in abundance across spatial scales and trophic levels. We then used structural equation modeling to determine if the strength and direction of relationships between temporal variability, synchrony, biodiversity, and environmental and spatial settings depended on trophic level and spatial scale. We found that temporal variability in abundance decreased from producers to tertiary consumers but did so mainly at the local scale. Species population synchrony within sites increased with trophic level, whereas synchrony among communities decreased. At the local scale, temporal variability in precipitation and species diversity were associated with population variability (linear partial coefficient, β = 0.23) and population synchrony (β = −0.39) similarly across trophic levels, respectively. At the regional scale, community synchrony was not related to climatic or spatial predictors, but the strength of relationships between metacommunity variability and community synchrony decreased systematically from top predators (β = 0.73) to secondary consumers (β = 0.54), to primary consumers (β = 0.30) to producers (β = 0). Our results suggest that mobile predators may often stabilize metacommunities by buffering variability that originates at the base of food webs. This finding illustrates that the trophic structure of metacommunities, which integrates variation in organismal body size and its correlates, should be considered when investigating ecological stability in natural systems. More broadly, our work advances the notion that temporal stability is an emergent property of ecosystems that may be threatened in complex ways by biodiversity loss and habitat fragmentation.

Evaluating changes in shear wave velocity due to blast-induced liquefaction - Jonathan F. Hubler; James P. Hanley; Andrew C. Stolte; Liam Wotherspoon; Kyle M. Rollins (Soil Dynamics and Earthquake Engineering, 2024)

Geographical movements, site fidelity and connectivity of killer whales within and outside herring grounds in Icelandic coastal waters - Tatiana M. J. Marchon; Marianne H. Rasmussen; Charla J. Basran; Megan Whittaker; Chiara G. Bertulli; Cathy Harlow; Rob Lott; Oliver Boisseau; Frédéric Gendron; Luisa Guo; Tess Hudson; Hörður Jónsson; et al. (Marine Biology, 2024)

What factors influence the rediscovery of lost tetrapod species? - Tim Lindken; Christopher V. Anderson; Daniel Ariano‐Sánchez; Goni Barki; Christina Biggs; Philip Bowles; Ramamoorthi Chaitanya; Drew T. Cronin; Sonja C. Jähnig; Jonathan M. Jeschke; Rosalind J. Kennerley; Thomas E. Lacher; et al. (Global Change Biology, 2024)
We created a database of lost and rediscovered tetrapod species, identified patterns in their distribution and factors influencing rediscovery. Tetrapod species are being lost at a faster rate than they are being rediscovered, due to slowing rates of rediscovery for amphibians, birds and mammals, and rapid rates of loss for reptiles. Finding lost species and preventing future losses should therefore be a conservation priority. By comparing the taxonomic and spatial distribution of lost and rediscovered tetrapod species, we have identified regions and taxa with many lost species in comparison to those that have been rediscovered—our results may help to prioritise search effort to find them. By identifying factors that influence rediscovery, we have improved our ability to broadly distinguish the types of species that are likely to be found from those that are not (because they are likely to be extinct). Some lost species, particularly those that are small and perceived to be uncharismatic, may have been neglected in terms of conservation effort, and other lost species may be hard to find due to their intrinsic characteristics and the characteristics of the environments they occupy (e.g. nocturnal species, fossorial species and species occupying habitats that are more difficult to survey such as wetlands). These lost species may genuinely await rediscovery. However, other lost species that possess characteristics associated with rediscovery (e.g. large species) and that are also associated with factors that negatively influence rediscovery (e.g. those occupying small islands) are more likely to be extinct. Our results may foster pragmatic search protocols that prioritise lost species likely to still exist.

Elevated CO 2 interacts with nutrient inputs to restructure plant communities in phosphorus‐limited grasslands - Christopher R. Taylor; Luke C. England; J. Ben Keane; Jessica A. C. Davies; Jonathan R. Leake; Iain P. Hartley; Simon M. Smart; Victoria Janes‐Bassett; Gareth K. Phoenix (Global Change Biology, 2024)
Globally pervasive increases in atmospheric CO 2 and nitrogen (N) deposition could have substantial effects on plant communities, either directly or mediated by their interactions with soil nutrient limitation. While the direct consequences of N enrichment on plant communities are well documented, potential interactions with rising CO 2 and globally widespread phosphorus (P) limitation remain poorly understood. We investigated the consequences of simultaneous elevated CO 2 (eCO 2 ) and N and P additions on grassland biodiversity, community and functional composition in P‐limited grasslands. We exposed soil‐turf monoliths from limestone and acidic grasslands that have received >25 years of N additions (3.5 and 14 g m −2 year −1 ) and 11 (limestone) or 25 (acidic) years of P additions (3.5 g m −2 year −1 ) to eCO 2 (600 ppm) for 3 years. Across both grasslands, eCO 2 , N and P additions significantly changed community composition. Limestone communities were more responsive to eCO 2 and saw significant functional shifts resulting from eCO 2 –nutrient interactions. Here, legume cover tripled in response to combined eCO 2 and P additions, and combined eCO 2 and N treatments shifted functional dominance from grasses to sedges. We suggest that eCO 2 may disproportionately benefit P acquisition by sedges by subsidising the carbon cost of locally intense root exudation at the expense of co‐occurring grasses. In contrast, the functional composition of the acidic grassland was insensitive to eCO 2 and its interactions with nutrient additions. Greater diversity of P‐acquisition strategies in the limestone grassland, combined with a more functionally even and diverse community, may contribute to the stronger responses compared to the acidic grassland. Our work suggests we may see large changes in the composition and biodiversity of P‐limited grasslands in response to eCO 2 and its interactions with nutrient loading, particularly where these contain a high diversity of P‐acquisition strategies or developmentally young soils with sufficient bioavailable mineral P.

Un‘covering’ blanket bonds: Assessing the adoption of blanket bonds across the states - Nurun Naher; Adam P. Mayer; Jonathan M. Fisk; John C. Morris (The Extractive Industries and Society, 2023)

Superiority of a Representative MRI Flow Waveform over Doppler Ultrasound for Aortic Wave Reflection Assessment in Children and Adolescents With/Without a History of Heart Disease - Jonathan P. Mynard; Remi Kowalski; Hilary A. Harrington; Avinash Kondiboyina; Joseph J. Smolich; Michael M. H. Cheung (Annals of Biomedical Engineering, 2023)
Wave separation analysis (WSA) reveals the impact of forward- and backward-running waves on the arterial pressure pulse, but the calculations require a flow waveform. This study investigated (1) the variability of the ascending aortic flow waveform in children and adolescents with/without a childhood heart disease history (CHD); (2) the accuracy of WSA obtained with a representative flow waveform (RepFlow), compared with the triangulation method and published ultrasound-derived adult representative flow; (3) the impact of limitations in Doppler ultrasound on WSA; and (4) generalizability of results to adults with a history of CHD. Phase contrast MRI was performed in youth without ( n = 45, Group 1, 10–19 years) and with CHD ( n = 79, Group 2, 7–18 years), and adults with CHD history ( n = 29, Group 3, 19–59 years). Segmented aortic cross-sectional area was used as a surrogate for the central pressure waveform in WSA. A subject-specific virtual Doppler ultrasound was performed on MRI data by extracting velocities from a sample volume. Time/amplitude-normalized ascending aortic flow waveforms were highly consistent amongst all groups. WSA with RepFlow therefore yielded errors

Refuge‐yeah or refuge‐nah? Predicting locations of forest resistance and recruitment in a fiery world - Kyle C. Rodman; Kimberley T. Davis; Sean A. Parks; Teresa B. Chapman; Jonathan D. Coop; Jose M. Iniguez; John P. Roccaforte; Andrew J. Sánchez Meador; Judith D. Springer; Camille S. Stevens‐Rumann; Michael T. Stoddard; Amy E. M. Waltz; et al. (Global Change Biology, 2023)
Climate warming, land use change, and altered fire regimes are driving ecological transformations that can have critical effects on Earth's biota. Fire refugia—locations that are burned less frequently or severely than their surroundings—may act as sites of relative stability during this period of rapid change by being resistant to fire and supporting post‐fire recovery in adjacent areas. Because of their value to forest ecosystem persistence, there is an urgent need to anticipate where refugia are most likely to be found and where they align with environmental conditions that support post‐fire tree recruitment. Using biophysical predictors and patterns of burn severity from 1180 recent fire events, we mapped the locations of potential fire refugia across upland conifer forests in the southwestern United States (US) (99,428 km 2 of forest area), a region that is highly vulnerable to fire‐driven transformation. We found that low pre‐fire forest cover, flat slopes or topographic concavities, moderate weather conditions, spring‐season burning, and areas affected by low‐ to moderate‐severity fire within the previous 15 years were most commonly associated with refugia. Based on current (i.e., 2021) conditions, we predicted that 67.6% and 18.1% of conifer forests in our study area would contain refugia under moderate and extreme fire weather, respectively. However, potential refugia were 36.4% (moderate weather) and 31.2% (extreme weather) more common across forests that experienced recent fires, supporting the increased use of prescribed and resource objective fires during moderate weather conditions to promote fire‐resistant landscapes. When overlaid with models of tree recruitment, 23.2% (moderate weather) and 6.4% (extreme weather) of forests were classified as refugia with a high potential to support post‐fire recruitment in the surrounding landscape. These locations may be disproportionately valuable for ecosystem sustainability, providing habitat for fire‐sensitive species and maintaining forest persistence in an increasingly fire‐prone world.

Moana Project: lessons learned from a national scale transdisciplinary research project - Joao M. A. C. Souza; Malene Felsing; Julie Jakoboski; Jonathan P. A. Gardner; Maui Hudson (Frontiers in Marine Science, 2023)

Correction: Rotational Head Kinematics in Football Impacts: An Injury Risk Function for Concussion - Steven Rowson; Stefan M. Duma; Jonathan G. Beckwith; Jeffrey J. Chu; Richard M. Greenwald; Joseph J. Crisco; P. Gunnar Brolinson; Ann-Christine Duhaime; Thomas W. Mcallister; Arthur C. Maerlender (Annals of Biomedical Engineering, 2023)

Occurrence and sources of microplastics on Arctic beaches: Svalbard - Tesni Lloyd-Jones; Jonathan J. Dick; Timothy P. Lane; Eoghan M. Cunningham; Konstadinos Kiriakoulakis (Marine Pollution Bulletin, 2023)

Restoration ecology through the lens of coexistence theory - Lauren M. Hallett; Lina Aoyama; György Barabás; Benjamin Gilbert; Loralee Larios; Nancy Shackelford; Chhaya M. Werner; Oscar Godoy; Emma R. Ladouceur; Jacob E. Lucero; Christopher P. Weiss-Lehman; Jonathan M. Chase; et al. (Trends in Ecology & Evolution, 2023)

Joint associations between established genetic susceptibility loci, pesticide exposures, and risk of prostate cancer - Lauren M. Hurwitz; Laura E. Beane Freeman; Gabriella Andreotti; Jonathan N. Hofmann; Christine G. Parks; Dale P. Sandler; Jay H. Lubin; Jia Liu; Kristine Jones; Sonja I. Berndt; Stella Koutros (Environmental Research, 2023)

Assessment of Changes of Complex Shoreline from Medium-Resolution Satellite Imagery - Nikolay P. Nezlin; Julie D. Herman; Jonathan Hodge; Stephen Sagar; Robbi Bishop-Taylor; Guangming Zheng; Paul M. DiGiacomo (Estuaries and Coasts, 2023)

Root phenotypes for improved nitrogen capture - Jonathan P. Lynch; Tania Galindo-Castañeda; Hannah M. Schneider; Jagdeep Singh Sidhu; Harini Rangarajan; Larry M. York (Plant and Soil, 2023)
Background Suboptimal nitrogen availability is a primary constraint for crop production in low-input agroecosystems, while nitrogen fertilization is a primary contributor to the energy, economic, and environmental costs of crop production in high-input agroecosystems. In this article we consider avenues to develop crops with improved nitrogen capture and reduced requirement for nitrogen fertilizer. Scope Intraspecific variation for an array of root phenotypes has been associated with improved nitrogen capture in cereal crops, including architectural phenotypes that colocalize root foraging with nitrogen availability in the soil; anatomical phenotypes that reduce the metabolic costs of soil exploration, improve penetration of hard soil, and exploit the rhizosphere; subcellular phenotypes that reduce the nitrogen requirement of plant tissue; molecular phenotypes exhibiting optimized nitrate uptake kinetics; and rhizosphere phenotypes that optimize associations with the rhizosphere microbiome. For each of these topics we provide examples of root phenotypes which merit attention as potential selection targets for crop improvement. Several cross-cutting issues are addressed including the importance of soil hydrology and impedance, phenotypic plasticity, integrated phenotypes, in silico modeling, and breeding strategies using high throughput phenotyping for co-optimization of multiple phenes. Conclusions Substantial phenotypic variation exists in crop germplasm for an array of root phenotypes that improve nitrogen capture. Although this topic merits greater research attention than it currently receives, we have adequate understanding and tools to develop crops with improved nitrogen capture. Root phenotypes are underutilized yet attractive breeding targets for the development of the nitrogen efficient crops urgently needed in global agriculture.

Mapping material use and embodied carbon in UK construction - Michał P. Drewniok; José Manuel Cruz Azevedo; Cyrille F. Dunant; Julian M. Allwood; Jonathan M. Cullen; Tim Ibell; Will Hawkins (Resources, Conservation and Recycling, 2023)

Red rock crab (Cancer productus) movement is not influenced by electromagnetic fields produced by a submarine power transmission cable - Jonathan P. Williams; Erin M. Jaco; Zoe Scholz; Chelsea M. Williams; Daniel J. Pondella; Michael K. Rasser; Donna M. Schroeder (Continental Shelf Research, 2023)

A comparison of techniques for verifying the accuracy of precision decomposition-derived relationships between motor unit firing rates and recruitment thresholds from surface EMG signals - Jonathan P. Beausejour; Paul Bohlen; Kylie K. Harmon; Ryan M. Girts; Jason I. Pagan; Debbie L. Hahs-Vaughn; Trent J. Herda; Matt S. Stock (Experimental Brain Research, 2023)

Parallel evaluation of alternative skin barrier models and excised human skin for dermal absorption studies in vitro - Alec T. Salminen; Kelly J. Davis; Robert P. Felton; Nathania Nischal; Linda S. VonTungeln; Frederick A. Beland; Kristy Derr; Paul C. Brown; Marc Ferrer; Linda M. Katz; Nicole C. Kleinstreuer; Jonathan Leshin; et al. (Toxicology in Vitro, 2023)

AgAnimalGenomes: browsers for viewing and manually annotating farm animal genomes - Deborah A. Triant; Amy T. Walsh; Gabrielle A. Hartley; Bruna Petry; Morgan R. Stegemiller; Benjamin M. Nelson; Makenna M. McKendrick; Emily P. Fuller; Noelle E. Cockett; James E. Koltes; Stephanie D. McKay; Jonathan A. Green; et al. (Mammalian Genome, 2023)
Current genome sequencing technologies have made it possible to generate highly contiguous genome assemblies for non-model animal species. Despite advances in genome assembly methods, there is still room for improvement in the delineation of specific gene features in the genomes. Here we present genome visualization and annotation tools to support seven livestock species (bovine, chicken, goat, horse, pig, sheep, and water buffalo), available in a new resource called AgAnimalGenomes. In addition to supporting the manual refinement of gene models, these browsers provide visualization tracks for hundreds of RNAseq experiments, as well as data generated by the Functional Annotation of Animal Genomes (FAANG) Consortium. For species with predicted gene sets from both Ensembl and RefSeq, the browsers provide special tracks showing the thousands of protein-coding genes that disagree across the two gene sources, serving as a valuable resource to alert researchers to gene model issues that may affect data interpretation. We describe the data and search methods available in the new genome browsers and how to use the provided tools to edit and create new gene models.

Residual impacts of a wildland urban interface fire on urban particulate matter and dust: a study from the Marshall Fire - Jonathan M. Silberstein; Liora E. Mael; Caroline R. Frischmon; Emma S. Rieves; Evan R. Coffey; Trupti Das; William Dresser; Avery C. Hatch; Jyotishree Nath; Helena O. Pliszka; Colleen E. Reid; Marina E. Vance; et al. (Air Quality, Atmosphere & Health, 2023)
The impacts of wildfires along the wildland urban interface (WUI) on atmospheric particulate concentrations and composition are an understudied source of air pollution exposure. To assess the residual impacts of the 2021 Marshall Fire (Colorado), a wildfire that predominantly burned homes and other human-made materials, on homes within the fire perimeter that escaped the fire, we performed a combination of fine particulate matter (PM 2.5 ) filter sampling and chemical analysis, indoor dust collection and chemical analysis, community scale PurpleAir PM 2.5 analysis, and indoor particle number concentration measurements. Following the fire, the chemical speciation of dust collected in smoke-affected homes in the burned zone showed elevated concentrations of the biomass burning marker levoglucosan (median levo = 4147 ng g −1 ), EPA priority toxic polycyclic aromatic hydrocarbons (median Σ 16 PAH = 1859.3 ng g −1 ), and metals (median Σ 20 Metals = 34.6 mg g −1 ) when compared to samples collected in homes outside of the burn zone 6 months after the fire. As indoor dust particles are often resuspended and can become airborne, the enhanced concentration of hazardous metals and organics within dust samples may pose a threat to human health. Indoor airborne particulate organic carbon (median = 1.91 μg m −3 ), particulate elemental carbon (median = .02 μg m −3 ), and quantified semi-volatile organic species in PM 2.5 were found in concentrations comparable to ambient air in urban areas across the USA. Particle number and size distribution analysis at a heavily instrumented supersite home located immediately next to the burned area showed indoor particulates in low concentrations (below 10 μg m −3 ) across various sizes of PM (12 nm–20 μm), but were elevated by resuspension from human activity, including cleaning. Graphical Abstract

Diversity–stability relationships across organism groups and ecosystem types become decoupled across spatial scales - Nathan I. Wisnoski; Riley Andrade; Max C. N. Castorani; Christopher P. Catano; Aldo Compagnoni; Thomas Lamy; Nina K. Lany; Luca Marazzi; Sydne Record; Annie C. Smith; Christopher M. Swan; Jonathan D. Tonkin; et al. (Ecology, 2023)
The relationship between biodiversity and stability, or its inverse, temporal variability, is multidimensional and complex. Temporal variability in aggregate properties, like total biomass or abundance, is typically lower in communities with higher species diversity (i.e., the diversity–stability relationship [DSR]). At broader spatial extents, regional‐scale aggregate variability is also lower with higher regional diversity (in plant systems) and with lower spatial synchrony. However, focusing exclusively on aggregate properties of communities may overlook potentially destabilizing compositional shifts. It is not yet clear how diversity is related to different components of variability across spatial scales, nor whether regional DSRs emerge across a broad range of organisms and ecosystem types. To test these questions, we compiled a large collection of long‐term metacommunity data spanning a wide range of taxonomic groups (e.g., birds, fish, plants, invertebrates) and ecosystem types (e.g., deserts, forests, oceans). We applied a newly developed quantitative framework for jointly analyzing aggregate and compositional variability across scales. We quantified DSRs for composition and aggregate variability in local communities and metacommunities. At the local scale, more diverse communities were less variable, but this effect was stronger for aggregate than compositional properties. We found no stabilizing effect of γ‐diversity on metacommunity variability, but β‐diversity played a strong role in reducing compositional spatial synchrony, which reduced regional variability. Spatial synchrony differed among taxa, suggesting differences in stabilization by spatial processes. However, metacommunity variability was more strongly driven by local variability than by spatial synchrony. Across a broader range of taxa, our results suggest that high γ‐diversity does not consistently stabilize aggregate properties at regional scales without sufficient spatial β‐diversity to reduce spatial synchrony.

Nitrogen and Phosphorus Uptake Stoichiometry Tracks Supply Ratio During 2-year Whole-Ecosystem Nutrient Additions - Nathan J. Tomczyk; Amy D. Rosemond; John S. Kominoski; David W. P. Manning; Jonathan P. Benstead; Vladislav Gulis; Steven A. Thomas; Erin R. Hotchkiss; Ashley M. Helton (Ecosystems, 2023)

Radio- and stable carbon isotope analysis reveals minimal assimilation of petrogenic carbon into an oligotrophic freshwater food web after experimental spills of diluted bitumen - Stephanie D. Graves; Johanna J. Mason; Jose Luis Rodriguez-Gil; Jonathan Y. Séguin; Jules M. Blais; Mark L. Hanson; Bruce P. Hollebone; Vince P. Palace; Ian Clark; Leah Cundall; Daniel Layton-Matthews; Matthew I. Leybourne; et al. (Chemosphere, 2023)

Beyond ecology: ecosystem restoration as a process for social-ecological transformation - Anazélia M. Tedesco; Sofía López-Cubillos; Robin Chazdon; Jonathan R. Rhodes; Carla L. Archibald; Katharina-Victoria Pérez-Hämmerle; Pedro H.S. Brancalion; Kerrie A. Wilson; Mariana Oliveira; Diego F. Correa; Liz Ota; Tiffany H. Morrison; et al. (Trends in Ecology & Evolution, 2023)

Evolutionary genomics of oceanic island radiations - José Cerca; Darko D. Cotoras; Vanessa C. Bieker; Rishi De-Kayne; Pablo Vargas; Mario Fernández-Mazuecos; Julia López-Delgado; Oliver White; Martin Stervander; Anthony J. Geneva; Juan Ernesto Guevara Andino; Joana Isabel Meier; et al. (Trends in Ecology & Evolution, 2023)

Improving data collection in pregnancy safety studies: Towards standardization of data elements in pregnancy reports from public and private partners (ConcePTION) - Guillaume Favre; Jonathan L. Richardson; Alan Moore; Yvonne Geissbühler; Valentine Jehl; Alison Oliver; Svetlana Shechtman; Orna Diav-Citrin; Maya Berlin; Tal De-Haan; Anil Mor; Meritxell Sabidó; et al. (Neurotoxicology and Teratology, 2023)

A prospective nested case-control study of serum concentrations of per- and polyfluoroalkyl substances and aggressive prostate cancer risk - Jongeun Rhee; Kathryn H. Barry; Wen-Yi Huang; Joshua N. Sampson; Jonathan N. Hofmann; Debra T. Silverman; Antonia M. Calafat; Julianne Cook Botelho; Kayoko Kato; Mark P. Purdue; Sonja I. Berndt (Environmental Research, 2023)

SARS-CoV-2 3CL-protease inhibitors derived from ML300: investigation of P1 and replacements of the 1,2,3-benzotriazole - Alice Hooper; Jonathan D. Macdonald; Brenna Reilly; Joshua Maw; Aidan P. Wirrick; Sang Hoon Han; A. Abigail Lindsey; Emma G. Rico; Todd Romigh; Christopher M. Goins; Nancy S. Wang; Shaun R. Stauffer (Medicinal Chemistry Research, 2023)

Rapidly Changing Range Limits in a Warming World: Critical Data Limitations and Knowledge Gaps for Advancing Understanding of Mangrove Range Dynamics in the Southeastern USA - Rémi Bardou; Michael J. Osland; Steven Scyphers; Christine Shepard; Karen E. Aerni; Jahson B. Alemu I; Robert Crimian; Richard H. Day; Nicholas M. Enwright; Laura C. Feher; Sarah L. Gibbs; Kiera O’Donnell; et al. (Estuaries and Coasts, 2023)
Climate change is altering species’ range limits and transforming ecosystems. For example, warming temperatures are leading to the range expansion of tropical, cold-sensitive species at the expense of their cold-tolerant counterparts. In some temperate and subtropical coastal wetlands, warming winters are enabling mangrove forest encroachment into salt marsh, which is a major regime shift that has significant ecological and societal ramifications. Here, we synthesized existing data and expert knowledge to assess the distribution of mangroves near rapidly changing range limits in the southeastern USA. We used expert elicitation to identify data limitations and highlight knowledge gaps for advancing understanding of past, current, and future range dynamics. Mangroves near poleward range limits are often shorter, wider, and more shrublike compared to their tropical counterparts that grow as tall forests in freeze-free, resource-rich environments. The northern range limits of mangroves in the southeastern USA are particularly dynamic and climate sensitive due to abundance of suitable coastal wetland habitat and the exposure of mangroves to winter temperature extremes that are much colder than comparable range limits on other continents. Thus, there is need for methodological refinements and improved spatiotemporal data regarding changes in mangrove structure and abundance near northern range limits in the southeastern USA. Advancing understanding of rapidly changing range limits is critical for foundation plant species such as mangroves, as it provides a basis for anticipating and preparing for the cascading effects of climate-induced species redistribution on ecosystems and the human communities that depend on their ecosystem services.

Experimental nutrient enrichment of forest streams reduces ecosystem nitrogen and phosphorus storage - Phillip M. Bumpers; Amy D. Rosemond; David W. P. Manning; John S. Kominoski; Jonathan P. Benstead; Lee M. Demi (Limnology and Oceanography, 2023)
Streams store nutrients in standing stocks of organic matter (OM) and associated biologically sequestered elements. Unlike standing stocks of autotrophs, detritus is depleted by nutrient enrichment, potentially reducing areal storage of detritus‐associated nutrients. To test effects of nutrient‐loading on storage of nitrogen (N) and phosphorus (P) by autotrophic and detrital‐pool compartments, we quantified the effects of 2 yr of continuous experimental N and P additions on fine benthic organic matter (FBOM), leaves, wood, and biofilms in five forest streams. Our design tested the relative strength of N vs. P on OM nutrient content, areal OM storage, and areal nutrient storage in OM types. Enrichment increased nutrient content of all OM types; %P increased more than %N in leaves, wood, and biofilms, but not FBOM. Biofilm %P and %N increased more than in all detrital types. Areal FBOM and leaf storage declined with nutrient enrichment. Biofilm standing stocks were generally higher with enrichment but were not related to the streamwater N and P gradients. Despite increased OM nutrient content, total areal nutrient storage in leaves and wood decreased due to reduced OM storage. Although annual nutrient storage was stabilized by FBOM, seasonal variation in nutrient storage increased with enrichment. Leaf‐associated nutrient storage was reduced in most seasons, whereas FBOM and biofilm nutrient storage increased in winter and spring, respectively, relative to pretreatment. Overall, the combined responses of all OM types to enrichment resulted in reduced storage and altered seasonal availability of carbon and nutrients, which has implications for consumers and downstream processes.

Concentrations of penicillin and gentamicin following intrauterine administration of two compounded formulations - Theresa M Beachler; Mark G Papich; Larry W Wulf; Debosmita Kundu; Jonathan P Mochel; Katie E Withowski; Christopher S Bailey (Journal of Equine Veterinary Science, 2023)

Policy responses to COVID-19 in Sri Lanka and the consideration of Indigenous Peoples - Eranga K. Galappaththi; Chrishma D. Perera; Indunil P. Dharmasiri; James D. Ford; Sarath S. Kodithuwakku; Victoria Chicmana-Zapata; Carol Zavaleta-Cortijo; Kerrie Pickering; Bianca van Bavel; Keith Hyams; Ingrid Arotoma-Rojas; Francis Awaafo Akugre; et al. (Environmental Science & Policy, 2023)

Harnessing biodiversity data to inform policy: Rapid regional audits should underpin Local Nature Recovery Strategies - Liam P. Crowther; James J. Gilroy; Robert W. Hawkes; Will J. Peach; Daniel Salliss; Jonathan R. Webb; Paul M. Dolman (Biological Conservation, 2023)

Insights into the metamorphic history and origin of flake graphite mineralization at the Graphite Creek graphite deposit, Seward Peninsula, Alaska, USA - George N. D. Case; Susan M. Karl; Sean P. Regan; Craig A. Johnson; Eric T. Ellison; Jonathan Saul Caine; Christopher S. Holm-Denoma; Laura S. Pianowski; Jeffrey H. Marsh (Mineralium Deposita, 2023)
Graphite Creek is an unusual flake graphite deposit located on the Seward Peninsula, Alaska, USA. We present field observations, uranium-lead (U–Pb) monazite and titanite geochronology, carbon (C) and sulfur (S) stable isotope geochemistry, and graphite Raman spectroscopy data from this deposit that support a new model of flake graphite ore genesis in high-grade metamorphic environments. The Graphite Creek deposit is within the second sillimanite metamorphic zone of the Kigluaik Mountains gneiss dome. Flake graphite, hosted in sillimanite-gneiss and quartz-biotite paragneiss, occurs as disseminations and in sets of very high grade (up to 50 wt.% graphite), semi-massive to massive graphite lenses 0.2 to 1 m wide containing quartz, sillimanite, inclusions of garnet porphyroblasts, K-feldspar, and tourmaline. Restitic garnet, sillimanite, graphite, and biotite accumulations indicate a high degree of anatexis and melt loss. Strong yttrium depletion in monazite, high europium ratios (Eu/Eu*), and excursions of high strontium and thorium concentrations are consistent with biotite dehydration melting. Monazite and titanite U–Pb ages record peak metamorphism from ~ 97 to 92 million years ago (Ma) and a retrograde event at ~ 85 Ma. Raman spectroscopy confirms the presence of carbonaceous material and highly ordered, crystalline graphite. Graphite δ 13 C VPDB values of − 30 to − 12‰ and pyrrhotite δ 34 S VCDT values of − 14 to 10‰ are consistent with derivation from organic carbon and sulfur in sedimentary rocks, respectively. These data collectively suggest that formation of massive graphite lenses occurred approximately synchronously with high-temperature metamorphism and anatexis of a highly carbonaceous pelitic protolith. Melt extraction and fluid release associated with anatexis were likely crucial for concentrating graphite. High-temperature, graphitic migmatite sequences within high-strain shear zones may be favorable for the occurrence of high-grade flake graphite deposits.

Seasonal variation in cuckoldry rates in the socially monogamous cichlid fish Variabilichromis moorii - Holger Zimmermann; Aneesh P. H. Bose; Helgit Eisner; Jonathan M. Henshaw; Angelika Ziegelbecker; Florian Richter; Sandra Bračun; Cyprian Katongo; Karoline Fritzsche; Kristina M. Sefc (Hydrobiologia, 2023)
Mating patterns in animal populations can respond to environmental conditions and consequently vary across time. To examine this variation in nature, studies must include temporal replicates from the same population. Here, we report temporal variation in genetic parentage in the socially monogamous cichlid Variabilichromis moorii from Lake Tanganyika, using samples of broods and their brood-tending parents that were collected across five field trips from the same study population. The sampled broods were either spawned during the dry season (three field trips) or during the rainy season (two trips). In all seasons, we detected substantial rates of extra-pair paternity, which were ascribed to cuckoldry by bachelor males. Paternity shares of brood-tending males were consistently higher, and the numbers of sires per brood were consistently lower, in broods that were spawned in the dry seasons compared to broods from the rainy seasons. In contrast, the strength of size-assortative pairing in our V. moorii population did not vary temporally. Seasonal fluctuations in environmental conditions, such as water turbidity, are proposed as a mechanism behind variable cuckolder pressure. Our data demonstrate the utility of long-term monitoring to improve our understanding of animal mating patterns.

Four-decade (1977–2017) landscape tale of tourist reservoir hotspot El Piñol-Guatapé, Colombia - P. Godwyn-Paulson; M. P. Jonathan; Abraham Londoño Pineda; Oscar Vélez Rojas; G. Muthusankar; Harry Gutiérrez-Mosquera; C. Lakshumanan (Environmental Monitoring and Assessment, 2023)

Novel species discrimination method elucidates colony growth form variation between the New Zealand soft corals Kotatea aurantiaca and Kotatea lobata - Gustav M. Kessel; Philip Alderslade; Jaret P. Bilewitch; Kareen E. Schnabel; Jonathan P. A. Gardner (Marine Biodiversity, 2023)
In New Zealand, Kotatea aurantiaca and Kotatea lobata are two common, endemic, co-occurring, and morphologically similar soft coral species that currently cannot be distinguished without microscopic examination of sclerites and of which little is known regarding any aspect of their ecology or biology. The aim of the present study is to ascertain if, and in what ways, their colony growth forms differ, and to test the taxonomic value of macroscopic morphological character measurements using statistical discrimination analyses. A binary logistic regression model is developed whereby macroscopic characters of colony morphology can be used to assign specimens to either species with ~ 90% accuracy. Species assignment accuracy is greatest when ratios formed from morphological measurements are used rather than direct measurements. Here, these ratios are used for the first time to account for the appearance-altering habit among soft corals of hydrostatically expanding and contracting their coelenteron with seawater. Relationships between colony morphology and depth are also examined, and it is suggested that phenotypic plasticity detected in K. lobata , causing it to resemble K. aurantiaca more closely at greater depths, may contribute to their morphological overlap. It is anticipated that this discrimination technique will facilitate future research on the ecology and biology of these species and will be replicated on other sets of morphologically similar soft corals for which species discrimination has been problematic.

Nitrate: The Dr. Jekyll and Mr. Hyde of human health? - Catherine P. Bondonno; Liezhou Zhong; Nicola P. Bondonno; Marc Sim; Lauren C. Blekkenhorst; Alex Liu; Anjana Rajendra; Pratik Pokharel; Dorit W. Erichsen; Oliver Neubauer; Kevin D. Croft; Jonathan M. Hodgson (Trends in Food Science & Technology, 2023)

Contribution of soil bacteria to the atmosphere across biomes - Stephen D.J. Archer; Kevin C. Lee; Tancredi Caruso; Antonio Alcami; Jonathan G. Araya; S. Craig Cary; Don A. Cowan; Claudia Etchebehere; Batdelger Gantsetseg; Benito Gomez-Silva; Sean Hartery; Ian D. Hogg; et al. (Science of The Total Environment, 2023)

Corrigendum to “Quantifying annual spatial consistency in chick-rearing seabirds to inform important site identification” [Biol. Conserv. 281 (2023) 109994] - Martin Beal; Paulo Catry; Richard A. Phillips; Steffen Oppel; John P.Y. Arnould; Maria I. Bogdanova; Mark Bolton; Ana P.B. Carneiro; Corey Clatterbuck; Melinda Conners; Francis Daunt; Karine Delord; et al. (Biological Conservation, 2023)

Quantifying annual spatial consistency in chick-rearing seabirds to inform important site identification - Martin Beal; Paulo Catry; Richard A. Phillips; Steffen Oppel; John P.Y. Arnould; Maria I. Bogdanova; Mark Bolton; Ana P.B. Carneiro; Corey Clatterbuck; Melinda Conners; Francis Daunt; Karine Delord; et al. (Biological Conservation, 2023)

Greenhouse-gas forced changes in the Atlantic meridional overturning circulation and related worldwide sea-level change - Matthew P. Couldrey; Jonathan M. Gregory; Xiao Dong; Oluwayemi Garuba; Helmuth Haak; Aixue Hu; William J. Hurlin; Jiangbo Jin; Johann Jungclaus; Armin Köhl; Hailong Liu; Sayantani Ojha; et al. (Climate Dynamics, 2023)
The effect of anthropogenic climate change in the ocean is challenging to project because atmosphere-ocean general circulation models (AOGCMs) respond differently to forcing. This study focuses on changes in the Atlantic Meridional Overturning Circulation (AMOC), ocean heat content ( $$Δ$$ Δ OHC), and the spatial pattern of ocean dynamic sea level ( $$Δ ζ$$ Δ ζ ). We analyse experiments following the FAFMIP protocol, in which AOGCMs are forced at the ocean surface with standardised heat, freshwater and momentum flux perturbations, typical of those produced by doubling $$\hbox {CO}_{{2}}$$ CO 2 . Using two new heat-flux-forced experiments, we find that the AMOC weakening is mainly caused by and linearly related to the North Atlantic heat flux perturbation, and further weakened by a positive coupled heat flux feedback. The quantitative relationships are model-dependent, but few models show significant AMOC change due to freshwater or momentum forcing, or to heat flux forcing outside the North Atlantic. AMOC decline causes warming at the South Atlantic-Southern Ocean interface. It does not strongly affect the global-mean vertical distribution of $$Δ$$ Δ OHC, which is dominated by the Southern Ocean. AMOC decline strongly affects $$Δ ζ$$ Δ ζ in the North Atlantic, with smaller effects in the Southern Ocean and North Pacific. The ensemble-mean $$Δ ζ$$ Δ ζ and $$Δ$$ Δ OHC patterns are mostly attributable to the heat added by the flux perturbation, with smaller effects from ocean heat and salinity redistribution. The ensemble spread, on the other hand, is largely due to redistribution, with pronounced disagreement among the AOGCMs.

Ultraconserved elements-based phylogenomic systematics of the snake superfamily Elapoidea, with the description of a new Afro-Asian family - Sunandan Das; Eli Greenbaum; Shai Meiri; Aaron M. Bauer; Frank T. Burbrink; Christopher J. Raxworthy; Jeffrey L. Weinell; Rafe M. Brown; Jonathan Brecko; Olivier S.G. Pauwels; Nirhy Rabibisoa; Achille P. Raselimanana; et al. (Molecular Phylogenetics and Evolution, 2023)

Long-term aircraft noise exposure and risk of hypertension in postmenopausal women - Daniel D. Nguyen; Eric A. Whitsel; Gregory A. Wellenius; Jonathan I. Levy; Jessica H. Leibler; Stephanie T. Grady; James D. Stewart; Matthew P. Fox; Jason M. Collins; Melissa N. Eliot; Andrew Malwitz; JoAnn E. Manson; et al. (Environmental Research, 2023)

Intake of trace contaminants by corals in Abrolhos reef bank (western South Atlantic) during two decades of coastal impacts - Heitor Evangelista; Raquel L.M. de Paula; Newton Magalhães; Jefferson S. de Gois; Aderval S. Luna; Renata C. Cagnin; Valéria S. Quaresma; Flávia F. Bezerra; Jonathan P. Dia; Roberto V. Santos; André Pullen; Stefano Crivellari; et al. (Continental Shelf Research, 2023)

Differential cardiopulmonary effects of isoprene-versus toluene-generated photochemically-Aged smog in rats - Samantha J. Snow; Jonathan D. Krug; John M. Turlington; Judy E. Richards; Mette C. Schladweiler; Allen D. Ledbetter; Todd Krantz; Charly King; M. Ian Gilmour; Stephen H. Gavett; Urmila P. Kodavanti; Aimen K. Farraj; et al. (Atmospheric Environment, 2023)

Pollution Assessment with Respect to Five Heavy Metals in Urban Soils of the Greater Chennai Region, Southeast Coast of India - Kannan G.; Priyadarsi D. Roy; Sajimol Sundar; Tune Usha; Muthusankar Gowrappan; Pradeep Kishore V.; Ramki Periyasamy; Jonathan M. P.; Lakshumanan Chokkalingam (Water, Air, & Soil Pollution, 2023)

Reconstructing the dynamics of managed populations to estimate the impact of citizen surveillance - Daniel Spring; Thao P. Le; Samuel Adam Bloom; Jonathan M. Keith; Tom Kompas (Ecological Modelling, 2023)

Tsunami waves across the Pacific ring nations from January 15, 2022, underwater volcanic explosion at “The Hunga-Tonga-Hunga-Ha’apai” isles - M. P. Jonathan; P. Godwyn-Paulson; P. F. Rodríguez-Espinosa; P. D. Roy (Natural Hazards, 2023)

Does deterministic coexistence theory matter in a finite world? - Sebastian J. Schreiber; Jonathan M. Levine; Oscar Godoy; Nathan J. B. Kraft; Simon P. Hart (Ecology, 2023)
Contemporary studies of species coexistence are underpinned by deterministic models that assume that competing species have continuous (i.e., noninteger) densities, live in infinitely large landscapes, and coexist over infinite time horizons. By contrast, in nature, species are composed of discrete individuals subject to demographic stochasticity and occur in habitats of finite size where extinctions occur in finite time. One consequence of these discrepancies is that metrics of species’ coexistence derived from deterministic theory may be unreliable predictors of the duration of species coexistence in nature. These coexistence metrics include invasion growth rates and niche and fitness differences, which are now commonly applied in theoretical and empirical studies of species coexistence. In this study, we tested the efficacy of deterministic coexistence metrics on the duration of species coexistence in a finite world. We introduce new theoretical and computational methods to estimate coexistence times in stochastic counterparts of classic deterministic models of competition. Importantly, we parameterized this model using experimental field data for 90 pairwise combinations of 18 species of annual plants, allowing us to derive biologically informed estimates of coexistence times for a natural system. Strikingly, we found that for species expected to deterministically coexist, community sizes containing only 10 individuals had predicted coexistence times of more than 1000 years. We also found that invasion growth rates explained 60% of the variation in intrinsic coexistence times, reinforcing their general usefulness in studies of coexistence. However, only by integrating information on both invasion growth rates and species' equilibrium population sizes could most (>99%) of the variation in species coexistence times be explained. This integration was achieved with demographically uncoupled single‐species models solely determined by the invasion growth rates and equilibrium population sizes. Moreover, because of a complex relationship between niche overlap/fitness differences and equilibrium population sizes, increasing niche overlap and increasing fitness differences did not always result in decreasing coexistence times, as deterministic theory would predict. Nevertheless, our results tend to support the informed use of deterministic theory for understanding the duration of species’ coexistence while highlighting the need to incorporate information on species' equilibrium population sizes in addition to invasion growth rates.

Abiotic factors that affect the distribution of aquatic macrophytes in shallow north temperate Minnesota lakes: a spatial modeling approach - Samuel A. Schmid; Ryan M. Wersal; Jonathan P. Fleming (Aquatic Ecology, 2022)

Linking changes in species composition and biomass in a globally distributed grassland experiment - Emma Ladouceur; Shane A. Blowes; Jonathan M. Chase; Adam T. Clark; Magda Garbowski; Juan Alberti; Carlos Alberto Arnillas; Jonathan D. Bakker; Isabel C. Barrio; Siddharth Bharath; Elizabeth T. Borer; Lars A. Brudvig; et al. (Ecology Letters, 2022)
Global change drivers, such as anthropogenic nutrient inputs, are increasing globally. Nutrient deposition simultaneously alters plant biodiversity, species composition and ecosystem processes like aboveground biomass production. These changes are underpinned by species extinction, colonisation and shifting relative abundance. Here, we use the Price equation to quantify and link the contributions of species that are lost, gained or that persist to change in aboveground biomass in 59 experimental grassland sites. Under ambient (control) conditions, compositional and biomass turnover was high, and losses (i.e. local extinctions) were balanced by gains (i.e. colonisation). Under fertilisation, the decline in species richness resulted from increased species loss and decreases in species gained. Biomass increase under fertilisation resulted mostly from species that persist and to a lesser extent from species gained. Drivers of ecological change can interact relatively independently with diversity, composition and ecosystem processes and functions such as aboveground biomass due to the individual contributions of species lost, gained or persisting.

Reconstruction of short-term storm surge-driven increases in shallow coastal lake salinity using ostracod shell chemistry - Lucy R. Roberts; Jonathan A. Holmes; David J. Horne; Melanie J. Leng; Carl D. Sayer; Rhys G. O. Timms; Katy Flowers; Simon P. M. Blockley; Andrea Kelly (Natural Hazards, 2022)

Time Delta Head Impact Frequency: An Analysis on Head Impact Exposure in the Lead Up to a Concussion: Findings from the NCAA-DOD Care Consortium - Jack Seifert; Alok S. Shah; Jaroslaw Harezlak; Steven Rowson; Jason P. Mihalik; Larry Riggen; Stefan Duma; Alison Brooks; Kenneth L. Cameron; Christopher C. Giza; Joshua Goldman; Kevin M. Guskiewicz; et al. (Annals of Biomedical Engineering, 2022)
Sport-related concussions can result from a single high magnitude impact that generates concussive symptoms, repeated subconcussive head impacts aggregating to generate concussive symptoms, or a combined effect from the two mechanisms. The array of symptoms produced by these mechanisms may be clinically interpreted as a sport-related concussion. It was hypothesized that head impact exposure resulting in concussion is influenced by severity, total number, and frequency of subconcussive head impacts. The influence of total number and magnitude of impacts was previously explored, but frequency was investigated to a lesser degree. In this analysis, head impact frequency was investigated over a new metric called ‘time delta’, the time difference from the first recorded head impact of the day until the concussive impact. Four exposure metrics were analyzed over the time delta to determine whether frequency of head impact exposure was greater for athletes on their concussion date relative to other dates of contact participation. Those metrics included head impact frequency, head impact accrual rate, risk weighted exposure (RWE), and RWE accrual rate. Athletes experienced an elevated median number of impacts, RWE, and RWE accrual rate over the time delta on their concussion date compared to non-injury sessions. This finding suggests elevated frequency of head impact exposure on the concussion date compared to other dates that may precipitate the onset of concussion.

Helmet Technology, Head Impact Exposure, and Cortical Thinning Following a Season of High School Football - Jonathan A. Dudley; Alexis B. Slutsky-Ganesh; Jed A. Diekfuss; Jason M. Avedesian; Weihong Yuan; Christopher A. DiCesare; Brynne Williams; William P. Meehan; Destin Hill; Matthew B. Panzer; John D. DesJardins; Gregory D. Myer (Annals of Biomedical Engineering, 2022)

Head Impact Exposure in Youth and Collegiate American Football - Grace B. Choi; Eric P. Smith; Stefan M. Duma; Steven Rowson; Eamon Campolettano; Mireille E. Kelley; Derek A. Jones; Joel D. Stitzel; Jillian E. Urban; Amaris Genemaras; Jonathan G. Beckwith; Richard M. Greenwald; et al. (Annals of Biomedical Engineering, 2022)

Ecophysiological and genomic analyses of a representative isolate of highly abundant Bacillus cereus strains in contaminated subsurface sediments - Jennifer L. Goff; Elizabeth G. Szink; Michael P. Thorgersen; Andrew D. Putt; Yupeng Fan; Lauren M. Lui; Torben N. Nielsen; Kristopher A. Hunt; Jonathan P. Michael; Yajiao Wang; Daliang Ning; Ying Fu; et al. (Environmental Microbiology, 2022)
Bacillus cereus strain CPT56D‐587‐MTF (CPTF) was isolated from the highly contaminated Oak Ridge Reservation (ORR) subsurface. This site is contaminated with high levels of nitric acid and multiple heavy metals. Amplicon sequencing of the 16S rRNA genes (V4 region) in sediment from this area revealed an amplicon sequence variant (ASV) with 100% identity to the CPTF 16S rRNA sequence. Notably, this CPTF‐matching ASV had the highest relative abundance in this community survey, with a median relative abundance of 3.77% and comprised 20%–40% of reads in some samples. Pangenomic analysis revealed that strain CPTF has expanded genomic content compared to other B. cereus species—largely due to plasmid acquisition and expansion of transposable elements. This suggests that these features are important for rapid adaptation to native environmental stressors. We connected genotype to phenotype in the context of the unique geochemistry of the site. These analyses revealed that certain genes (e.g. nitrate reductase, heavy metal efflux pumps) that allow this strain to successfully occupy the geochemically heterogenous microniches of its native site are characteristic of the B. cereus species while others such as acid tolerance are mobile genetic element associated and are generally unique to strain CPTF.

Spatiotemporal responses of rice root architecture and anatomy to drought - Jenna E. Fonta; Jitender Giri; Phanchita Vejchasarn; Jonathan P. Lynch; Kathleen M. Brown (Plant and Soil, 2022)
Aims Growth reductions and yield losses from drought could be mitigated by developing rice genotypes with more efficient root systems. We examined spatiotemporal responses to drought in order to determine whether roots developing in upper vs. deeper soil layers respond differently to drought stress. Methods Root anatomical and architectural phenotypes of two rice genotypes, Azucena (drought tolerant) and IR64 (drought susceptible), were measured weekly in well-watered and vegetative-stage drought stress treatments in solid medium with stratified moisture availability. Basal and apical segments were collected from older, deeper nodal roots and apical segments from younger, shallow roots for assessment of anatomy and lateral rooting phenotypes. The relationship between root anatomy and root respiration rates was tested in solution culture and solid medium. Results Compared to IR64, Azucena had deeper root systems and larger diameter roots in both treatments but reduced its living tissue area in response to drought, while IR64 roots exhibited less plasticity in root diameter. Root respiration rates were positively correlated with root diameter and living tissue area, providing evidence that root anatomy affects the metabolic cost of tissues. In response to drought, Azucena showed reduced theoretical axial hydraulic conductance in shallow roots and at the base of deep roots but slightly greater conductance at the tip of deep roots, while IR64 displayed low plasticity in metaxylem phenotypes. Conclusion We propose that the plasticity of root phenotypes in Azucena contributes to its drought tolerance by reducing the metabolic cost of soil exploration and improving the efficiency of water transport.

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

How to prioritize species recovery after a megafire - Michelle Ward; Josie Carwardine; James E. M. Watson; Anna Pintor; Stephanie Stuart; Hugh P. Possingham; Jonathan R. Rhodes; Alexander R. Carey; Nancy Auerbach; April Reside; Chuan Ji Yong; Ayesha I. T. Tulloch (Conservation Biology, 2022)
Due to climate change, megafires are increasingly common and have sudden, extensive impacts on many species over vast areas, leaving decision makers uncertain about how best to prioritize recovery. We devised a decision‐support framework to prioritize conservation actions to improve species outcomes immediately after a megafire. Complementary locations are selected to extend recovery actions across all fire‐affected species’ habitats. We applied our method to areas burned in the 2019−2020 Australian megafires and assessed its conservation advantages by comparing our results with outcomes of a site‐richness approach (i.e., identifying areas that cost‐effectively recover the most species in any one location). We found that 290 threatened species were likely severely affected and will require immediate conservation action to prevent population declines and possible extirpation. We identified 179 subregions, mostly in southeastern Australia, that are key locations to extend actions that benefit multiple species. Cost savings were over AU$300 million to reduce 95% of threats across all species. Our complementarity‐based prioritization also spread postfire management actions across a wider proportion of the study area compared with the site‐richness method (43% vs. 37% of the landscape managed, respectively) and put more of each species’ range under management (average 90% vs. 79% of every species’ habitat managed). In addition to wildfire response, our framework can be used to prioritize conservation actions that will best mitigate threats affecting species following other extreme environmental events (e.g., floods and drought).

Rebirth of a reef: As-built description and rapid returns from the Palos Verdes Reef Restoration Project - Jonathan P. Williams; Chelsea M. Williams; Daniel J. Pondella; Zoe M. Scholz (Frontiers in Marine Science, 2022)
Palos Verdes Reef (PVR) is an artificial reef designed to restore rocky-reef associated marine species by directly restoring rocky-reef habitat that has been impacted by scour, sedimentation, and burial in the shallow subtidal portion of the Palos Verdes Peninsula in Los Angeles County, California, USA. The restoration reef provides high-quality habitat that is contiguous with the natural reef and allows for rapid succession. This project is a unique endeavor as restoring lost habitat in situ and has not been attempted in a temperate rocky reef and kelp forest community. While the primary design criteria for PVR is fish production in an area where already-limited hard substrate had been lost, it is also designed to be resilient to ongoing sedimentation and turbidity challenges on the peninsula. Following over a decade of design, planning, outreach, site surveying, and permitting, PVR was built in 2020 as 18 discrete modules using 52,729 tons of quarry rock placed approximately 8–80 m from existing, unburied rocky-reef habitat. There was no significant accumulation or scouring of sediment due to the placement of the reef and temperature data shows that internal tides regularly inundate the reef with cool, nutrient rich water. Rocky-reef associated taxa rapidly recruited to the restoration site, with visible changes occurring within just a few months post-construction. PVR modules showed rapid, significantly positive responses in fish density, fish biomass, kelp density, and biotic benthic cover less than 18 months after reef placement with a general pattern of succession in giant kelp growth from nearshore to offshore resulting in an established, thick canopy, in the nearshore, shallow modules. The newly available, high-quality habitat was quickly colonized and already shows late successional patterns with respect to fish and benthic communities. This restoration reef will produce large amounts of biomass over the long-term, though future surveys of multiple restored, adjacent, and reference sites will determine if high biomass at PVR is a result of new secondary production or attraction from nearby reefs.

A review of marine stressors impacting Atlantic salmon Salmo salar, with an assessment of the major threats to English stocks - Jonathan P. Gillson; Tea Bašić; Phil I. Davison; William D. Riley; Lawrence Talks; Alan M. Walker; Ian C. Russell (Reviews in Fish Biology and Fisheries, 2022)
Atlantic salmon Salmo salar is a socio-economically important anadromous fish species that has suffered synchronous population declines around the North Atlantic over the last five decades. Reduced marine survival has been implicated as a key driver of the declines, yet the relative importance of different stressors causing mortality at sea is not well understood. This review presents a synopsis of the principal stressors impacting Atlantic salmon in estuarine and marine environments. It also applies a semi-quantitative 2-D classification system to assess the relative effects of these stressors on English salmon stocks and their likely development over the next decade. Climate change and predation were identified as the biggest threats at present and over the next decade. Poor water quality and bycatch were classified as relatively high impact stressors, but with a lower likelihood of becoming more prevalent in the future due to available mitigation measures. Other, less influential, stressors included tidal barrages, artificial light at night, impingement in power-station cooling waters and thermal discharges, pile-driving noise pollution, invasive non-native species, electromagnetic fields, salmon mariculture, and tidal lagoons. Salmon fisheries exploitation was not regarded as an important stressor currently because effective exploitation rate controls have been implemented to substantially reduce fishing pressure. Future research priorities include addressing knowledge gaps on expanding stressor impacts from climate change, predation, renewable energy developments, and artificial light at night. Local management actions directed towards improving freshwater and estuarine habitats to maximise ecosystem resilience to stressors and minimise their cumulative impacts are recommended.

Ecosystems for future generations - M. P. Jonathan; Kalina Bermúdez Torres; Ana Judith Marmolejo-Rodríguez; Eugenia López López (Environmental Science and Pollution Research, 2022)

How to stay together? Habitat use by three sympatric sharks in the western coast of Baja California Sur, Mexico - Laura María Pantoja-Echevarría; Elena Tamburin; Fernando R. Elorriaga-Verplancken; Ana Judith Marmolejo-Rodríguez; Felipe Galván-Magaña; Arturo Tripp-Valdez; Ariagna Lara; M. P. Jonathan; S. B. Sujitha; Antonio Delgado-Huertas; Laura Arreola-Mendoza (Environmental Science and Pollution Research, 2022)

Improving sightings-derived residency estimation for whale shark aggregations: A novel metric applied to a global data set - Gonzalo Araujo; Ariana Agustines; Steffen S. Bach; Jesse E. M. Cochran; Emilio de la Parra-Galván; Rafael de la Parra-Venegas; Stella Diamant; Alistair Dove; Steve Fox; Rachel T. Graham; Sofia M. Green; Jonathan R. Green; et al. (Frontiers in Marine Science, 2022)
The world’s largest extant fish, the whale shark Rhincodon typus , is one of the most-studied species of sharks globally. The discovery of predictable aggregation sites where these animals gather seasonally or are sighted year-round – most of which are coastal and juvenile-dominated – has allowed for a rapid expansion of research on this species. The most common method for studying whale sharks at these sites is photographic identification (photo-ID). This technique allows for long-term individual-based data to be collected which can, in turn, be used to evaluate population structure, build population models, identify long-distance movements, and assess philopatry and other population dynamics. Lagged identification rate (LIR) models have fewer underlying assumptions than more traditional capture mark recapture approaches, making them more broadly applicable to marine taxa, especially far-ranging megafauna species like whale sharks. However, the increased flexibility comes at a cost. Parameter estimations based on LIR can be difficult to interpret and may not be comparable between areas with different sampling regimes. Using a unique data-set from the Philippines with ~8 years of nearly continuous survey effort, we were able to derive a metric for converting LIR residency estimates into more intuitive days-per-year units. We applied this metric to 25 different sites allowing for the first quantitatively-meaningful comparison of sightings-derived residence among the world’s whale shark aggregations. We validated these results against the only three published acoustic residence metrics (falling within the ranges established by these earlier works in all cases). The results were then used to understand residency behaviours exhibited by the sharks at each site. The adjusted residency metric is an improvement to LIR-based population modelling, already one of the most widely used tools for describing whale shark aggregations. The standardised methods presented here can serve as a valuable tool for assessing residency patterns of whale sharks, which is crucial for tailored conservation action, and can cautiously be tested in other taxa.

Fast and ballistic contractions involve greater neuromuscular power production in older adults during resistance exercise - Emmet J. Mc Dermott; Thomas G. Balshaw; Katherine Brooke-Wavell; Thomas M. Maden-Wilkinson; Jonathan P. Folland (European Journal of Applied Physiology, 2022)
Purpose Neuromuscular power is critical for healthy ageing. Conventional older adult resistance training (RT) guidelines typically recommend lifting slowly (2-s; CONV), whereas fast/explosive contractions performed either non-ballistically (FAST-NB) or ballistically (FAST-B, attempting to throw the load) may involve greater acute power production, and could ultimately provide a greater chronic power adaptation stimulus. To compare the neuromechanics (power, force, velocity, and muscle activation) of different types of concentric isoinertial RT contractions in older adults. Methods Twelve active older adult males completed three sessions, each randomly assigned to one type of concentric contraction (CONV or FAST-NB or FAST-B). Each session involved lifting a range of loads (20–80%1RM) using an instrumented isoinertial leg press dynamometer that measured power, force, and velocity. Muscle activation was assessed with surface electromyography (sEMG). Results Peak and mean power were markedly different, according to the concentric contraction explosive intent FAST-B > FAST-NB > CONV, with FAST-B producing substantially more power (+ 49 to 1172%, P ≤ 0.023), force (+ 10 to 136%, P < 0.05) and velocity (+ 55 to 483%, P ≤ 0.025) than CONV and FAST-NB contractions. Knee and hip extensor sEMG were typically higher during FAST-B than CON (all P < 0.02) and FAST-NB (≤ 50%1RM, P ≤ 0.001). Conclusions FAST-B contractions produced markedly greater power, force, velocity and muscle activation across a range of loads than both CONV or FAST-NB and could provide a more potent RT stimulus for the chronic development of older adult power.

Use of multiple endpoints to assess the impact of captivity on gut flora diversity in Long Island Sound Fundulus heteroclitus - Joseph P. Battaglia; Christian M. Kearney; Kirsten Guerette; Jordan Corbishley; Emily Sanchez; Brennah Kent; Hanna Storie; Emma Sharp; Shane Martin; Matthew Saberito; Jonathan D. Blake; Richard S. Feinn; et al. (Environmental Biology of Fishes, 2022)

Factors associated with changes in exercise behaviors during the COVID-19 pandemic - Caroline Himbert; Cassandra A. Hathaway; Bailee Daniels; Karen Salas; Anjelica Ashworth; Biljana Gigic; Tengda Lin; Richard Viskochil; Anne C. Kirchhoff; Douglas Grossman; Jennifer Ose; Jonathan Tward; et al. (Cancer Causes & Control, 2022)

Distance decay 2.0 – A global synthesis of taxonomic and functional turnover in ecological communities - Caio Graco‐Roza; Sonja Aarnio; Nerea Abrego; Alicia T. R. Acosta; Janne Alahuhta; Jan Altman; Claudia Angiolini; Jukka Aroviita; Fabio Attorre; Lars Baastrup‐Spohr; José J. Barrera‐Alba; Jonathan Belmaker; et al. (Global Ecology and Biogeography, 2022)
Aim Understanding the variation in community composition and species abundances (i.e., β‐diversity) is at the heart of community ecology. A common approach to examine β‐diversity is to evaluate directional variation in community composition by measuring the decay in the similarity among pairs of communities along spatial or environmental distance. We provide the first global synthesis of taxonomic and functional distance decay along spatial and environmental distance by analysing 148 datasets comprising different types of organisms and environments. Location Global. Time period 1990 to present. Major taxa studied From diatoms to mammals. Method We measured the strength of the decay using ranked Mantel tests (Mantel r ) and the rate of distance decay as the slope of an exponential fit using generalized linear models. We used null models to test whether functional similarity decays faster or slower than expected given the taxonomic decay along the spatial and environmental distance. We also unveiled the factors driving the rate of decay across the datasets, including latitude, spatial extent, realm and organismal features. Results Taxonomic distance decay was stronger than functional distance decay along both spatial and environmental distance. Functional distance decay was random given the taxonomic distance decay. The rate of taxonomic and functional spatial distance decay was fastest in the datasets from mid‐latitudes. Overall, datasets covering larger spatial extents showed a lower rate of decay along spatial distance but a higher rate of decay along environmental distance. Marine ecosystems had the slowest rate of decay along environmental distances. Main conclusions In general, taxonomic distance decay is a useful tool for biogeographical research because it reflects dispersal‐related factors in addition to species responses to climatic and environmental variables. Moreover, functional distance decay might be a cost‐effective option for investigating community changes in heterogeneous environments.

Correction to: Root anatomy and soil resource capture - Jonathan P. Lynch; Christopher F. Strock; Hannah M. Schneider; Jagdeep Singh Sidhu; Ishan Ajmera; Tania Galindo-Castaneda; Stephanie P. Klein; Meredith T. Hanlon (Plant and Soil, 2022)

FDA Approaches in Monitoring Drug Quality, Forces Impacting the Drug Quality, and Recent Alternative Strategies to Assess Quality in the US Drug Supply - Philip J. Almeter; James T. Isaacs; Aaron N. Hunter; Bradley S. Henderson; Thomas Platt; Billie J. Mitchell; David Do; Alyssa B. Brainard; Joshua E. Brown; Rachael M. Stone; Bao-Han Nguyen; Matthew F. Warren; et al. (Journal of Pharmaceutical Innovation, 2022)

Diversification and community assembly of the world’s largest tropical island - Jonathan D. Kennedy; Petter Z. Marki; Andrew H. Reeve; Mozes P. K. Blom; Dewi M. Prawiradilaga; Tri Haryoko; Bonny Koane; Pepijn Kamminga; Martin Irestedt; Knud A. Jønsson (Global Ecology and Biogeography, 2022)
Aim The species diversity and endemism of tropical biotas are major contributors to global biodiversity, but the factors underlying the formation of these systems remain poorly understood. Location The world's largest tropical island, New Guinea. Time period Miocene to present. Major taxa studied Passerine birds. Methods We first generated a species‐level phylogeny of all native breeding passerine birds to analyse spatial and elevational patterns of species richness, species age and phylogenetic diversity. Second, we used an existing dataset on bill morphology to analyse spatial and elevational patterns of functional diversity. Results The youngest New Guinean species are principally distributed in the lowlands and outlying mountain ranges, with the lowlands also maintaining the majority of non‐endemic species. In contrast, many species occurring in the central mountain range are phylogenetically distinct, range‐restricted, endemic lineages. Centres of accumulation for the oldest species are in montane forest, with these taxa having evolved unique bill forms in comparison to the remaining New Guinean species. For the morphological generalists, attaining a highland distribution does not necessarily represent the end to dispersal and diversification, because a number of new species have formed in the outlying mountain ranges, following recent colonization from the central range. Main conclusions We conclude that a general model of tropical montane diversification is that lineages commonly colonize the lowlands, shifting their ranges upslope through time to become range‐restricted montane forest endemics, attaining novel functional adaptations to these environments.

The acute effects of cannabidiol on emotional processing and anxiety: a neurocognitive imaging study - Michael A. P. Bloomfield; Yumeya Yamamori; Chandni Hindocha; Augustus P. M. Jones; Jocelyn L. L. Yim; Hannah R. Walker; Ben Statton; Matthew B. Wall; Rachel H. Lees; Oliver D. Howes; Valerie H. Curran; Jonathan P. Roiser; et al. (Psychopharmacology, 2022)
Rationale There is growing interest in the therapeutic potential of cannabidiol (CBD) across a range of psychiatric disorders. CBD has been found to reduce anxiety during experimentally induced stress in anxious individuals and healthy controls. However, the mechanisms underlying the putative anxiolytic effects of CBD are unknown. Objectives We sought to investigate the behavioural and neural effects of a single dose of CBD vs. placebo on a range of emotion-related measures to test cognitive-mechanistic models of its effects on anxiety. Methods We conducted a randomised, double-blind, placebo-controlled, crossover, acute oral challenge of 600 mg of CBD in 24 healthy participants on emotional processing, with neuroimaging (viewing emotional faces during functional magnetic resonance imaging) and cognitive (emotional appraisal) measures as well as subjective response to experimentally induced anxiety. Results CBD did not produce effects on brain responses to emotional faces and cognitive measures of emotional processing, or modulate experimentally induced anxiety, relative to placebo. Conclusions Given the rising popularity of CBD for its putative medical benefits, these findings question whether further research is warranted to investigate the clinical potential of CBD for the treatment of anxiety disorders.

Conventional versus drug-eluting embolic transarterial chemoembolization with doxorubicin: comparative drug delivery, pharmacokinetics, and treatment response in a rabbit VX2 tumor model - Ron C. Gaba; Ramzy C. Khabbaz; Ruth N. Muchiri; Joseph D. Morrison; Lobna Elkhadragy; William M. Totura; Jonathan P. Samuelson; Herbert E. Whiteley; Ryan L. Deaton; Peter L. Nguyen; Maria Sverdlov; Jeremy J. Johnson; et al. (Drug Delivery and Translational Research, 2022)

Assessing taxonomic and functional change in British breeding bird assemblages over time - Joseph P. Wayman; Jonathan P. Sadler; Thomas A. M. Pugh; Thomas E. Martin; Joseph A. Tobias; Thomas J. Matthews (Global Ecology and Biogeography, 2022)
Aim The aim was to identify the primary drivers of compositional change in breeding bird assemblages over a 40‐year period. Location Britain. Time period From 1970 to 2010. Major taxa studied Birds. Methods Using morphological trait measurements and a dataset of presence–absence data for British breeding birds surveyed in 10 km × 10 km hectads during two time periods, we calculated temporal taxonomic and functional beta diversity for each hectad alongside the change in species richness, mean nearest taxon distance (MNTD) and mean pairwise distance (MPD). We also estimated potential drivers of beta diversity, including climatic and land‐use and land‐cover (LULC) change variables, elevation and assemblage species richness in 1970 (1970 rich ). We used random forest regressions to test which variables best explained compositional change in the assemblages. We also assessed spatial taxonomic and functional change by analysing multiple‐site beta diversity and pairwise dissimilarities between time periods. Results Initial (1970) species richness was the most important predictor (highest importance score) across all models, with areas characterized by higher initial richness experiencing less assemblage change overall. The coordinates included to capture spatial autocorrelation in the data were also important predictors of change. Most climate and LULC variables had relatively low explanatory power; elevation and average temperature were the most influential. All metrics increased slightly with increasing elevation, except for species richness change and MPD, which decreased. Main conclusions The composition of British breeding bird assemblages changed substantially between 1970 and 2010. Spatial heterogeneity increased, both taxonomically and functionally. We show evidence that hectads with larger assemblages have been buffered from temporal diversity change and that those at higher elevations changed more in composition than those at lower elevations. Overall, coarse‐resolution climate and LULC explained only small to moderate amounts of variation, suggesting that stochastic assembly change or finer‐scale drivers might be drivers of temporal changes in assemblage composition.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

MASTREE+: Time‐series of plant reproductive effort from six continents - Andrew Hacket‐Pain; Jessie J. Foest; Ian S. Pearse; Jalene M. LaMontagne; Walter D. Koenig; Giorgio Vacchiano; Michał Bogdziewicz; Thomas Caignard; Paulina Celebias; Joep van Dormolen; Marcos Fernández‐Martínez; Jose V. Moris; et al. (Global Change Biology, 2022)
Significant gaps remain in understanding the response of plant reproduction to environmental change. This is partly because measuring reproduction in long‐lived plants requires direct observation over many years and such datasets have rarely been made publicly available. Here we introduce MASTREE+, a data set that collates reproductive time‐series data from across the globe and makes these data freely available to the community. MASTREE+ includes 73,828 georeferenced observations of annual reproduction (e.g. seed and fruit counts) in perennial plant populations worldwide. These observations consist of 5971 population‐level time‐series from 974 species in 66 countries. The mean and median time‐series length is 12.4 and 10 years respectively, and the data set includes 1122 series that extend over at least two decades (≥20 years of observations). For a subset of well‐studied species, MASTREE+ includes extensive replication of time‐series across geographical and climatic gradients. Here we describe the open‐access data set, available as a.csv file, and we introduce an associated web‐based app for data exploration. MASTREE+ will provide the basis for improved understanding of the response of long‐lived plant reproduction to environmental change. Additionally, MASTREE+ will enable investigation of the ecology and evolution of reproductive strategies in perennial plants, and the role of plant reproduction as a driver of ecosystem dynamics.

Restoring shallow lakes impaired by eutrophication: Approaches, outcomes, and challenges - Jonathan M. Abell; Deniz Özkundakci; David P. Hamilton; Paula Reeves (Critical Reviews in Environmental Science and Technology, 2022)

Nutrient identity modifies the destabilising effects of eutrophication in grasslands - Oliver Carroll; Evan Batzer; Siddharth Bharath; Elizabeth T. Borer; Sofía Campana; Ellen Esch; Yann Hautier; Timothy Ohlert; Eric W. Seabloom; Peter B. Adler; Jonathan D. Bakker; Lori Biederman; et al. (Ecology Letters, 2022)
Nutrient enrichment can simultaneously increase and destabilise plant biomass production, with co‐limitation by multiple nutrients potentially intensifying these effects. Here, we test how factorial additions of nitrogen (N), phosphorus (P) and potassium with essential nutrients (K+) affect the stability (mean/standard deviation) of aboveground biomass in 34 grasslands over 7 years. Destabilisation with fertilisation was prevalent but was driven by single nutrients, not synergistic nutrient interactions. On average, N‐based treatments increased mean biomass production by 21–51% but increased its standard deviation by 40–68% and so consistently reduced stability. Adding P increased interannual variability and reduced stability without altering mean biomass, while K+ had no general effects. Declines in stability were largest in the most nutrient‐limited grasslands, or where nutrients reduced species richness or intensified species synchrony. We show that nutrients can differentially impact the stability of biomass production, with N and P in particular disproportionately increasing its interannual variability.

Anthropogenic Mixing in Seasonally Stratified Shelf Seas by Offshore Wind Farm Infrastructure - Robert M. Dorrell; Charlie J. Lloyd; Ben J. Lincoln; Tom P. Rippeth; John R. Taylor; Colm-cille P. Caulfield; Jonathan Sharples; Jeff A. Polton; Brian D. Scannell; Deborah M. Greaves; Rob A. Hall; John H. Simpson (Frontiers in Marine Science, 2022)
The offshore wind energy sector has rapidly expanded over the past two decades, providing a renewable energy solution for coastal nations. Sector development has been led in Europe, but is growing globally. Most developments to date have been in well-mixed, i.e., unstratified, shallow-waters near to shore. Sector growth is, for the first time, pushing developments to deep water, into a brand new environment: seasonally stratified shelf seas. Seasonally stratified shelf seas, where water density varies with depth, have a disproportionately key role in primary production, marine ecosystem and biogeochemical cycling. Infrastructure will directly mix stratified shelf seas. The magnitude of this mixing, additional to natural background processes, has yet to be fully quantified. If large enough it may erode shelf sea stratification. Therefore, offshore wind growth may destabilize and fundamentally change shelf sea systems. However, enhanced mixing may also positively impact some marine ecosystems. This paper sets the scene for sector development into this new environment, reviews the potential physical and environmental benefits and impacts of large scale industrialization of seasonally stratified shelf seas and identifies areas where research is required to best utilize, manage, and mitigate environmental change.

Cleaner seas: reducing marine pollution - Kathryn A. Willis; Catarina Serra-Gonçalves; Kelsey Richardson; Qamar A. Schuyler; Halfdan Pedersen; Kelli Anderson; Jonathan S. Stark; Joanna Vince; Britta D. Hardesty; Chris Wilcox; Barbara F. Nowak; Jennifer L. Lavers; et al. (Reviews in Fish Biology and Fisheries, 2022)

Effects of continuous cycling training on motor unit firing rates, input excitation, and myosin heavy chain of the vastus lateralis in sedentary females - Michael A. Trevino; Hannah L. Dimmick; Mandy E. Parra; Adam J. Sterczala; Jonathan D. Miller; Jake A. Deckert; Philip M. Gallagher; Andrew C. Fry; Joseph P. Weir; Trent J. Herda (Experimental Brain Research, 2022)

Aortic haemodynamics: the effects of habitual endurance exercise, age and muscle sympathetic vasomotor outflow in healthy men - Denis J. Wakeham; Tony G. Dawkins; Rachel N. Lord; Jack S. Talbot; Freya M. Lodge; Bryony A. Curry; Lydia L. Simpson; Christopher J. A. Pugh; Robert E. Shave; Jonathan P. Moore (European Journal of Applied Physiology, 2022)
Purpose We determined the effect of habitual endurance exercise and age on aortic pulse wave velocity (aPWV), augmentation pressure (AP) and systolic blood pressure (aSBP), with statistical adjustments of aPWV and AP for heart rate and aortic mean arterial pressure, when appropriate. Furthermore, we assessed whether muscle sympathetic nerve activity (MSNA) correlates with AP in young and middle-aged men. Methods Aortic PWV, AP, aortic blood pressure (applanation tonometry; SphygmoCor) and MSNA (peroneal microneurography) were recorded in 46 normotensive men who were either young or middle-aged and endurance-trained runners or recreationally active nonrunners (10 nonrunners and 13 runners within each age-group). Between-group differences and relationships between variables were assessed via ANOVA/ANCOVA and Pearson product-moment correlation coefficients, respectively. Results Adjusted aPWV and adjusted AP were similar between runners and nonrunners in both age groups (all, P > 0.05), but higher with age (all, P < 0.001), with a greater effect size for the age-related difference in AP in runners (Hedges’ g , 3.6 vs 2.6). aSBP was lower in young ( P = 0.009; g = 2.6), but not middle-aged ( P = 0.341; g = 1.1), runners compared to nonrunners. MSNA burst frequency did not correlate with AP in either age group (young: r = 0.00, P = 0.994; middle-aged: r = − 0.11, P = 0.604). Conclusion There is an age-dependent effect of habitual exercise on aortic haemodynamics, with lower aSBP in young runners compared to nonrunners only. Statistical adjustment of aPWV and AP markedly influenced the outcomes of this study, highlighting the importance of performing these analyses. Further, peripheral sympathetic vasomotor outflow and AP were not correlated in young or middle-aged normotensive men.

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Cancer microenvironment and genomics: evolution in process - Stanley P. Leong; Isaac P. Witz; Orit Sagi-Assif; Sivan Izraely; Jonathan Sleeman; Brian Piening; Bernard A. Fox; Carlo B. Bifulco; Rachel Martini; Lisa Newman; Melissa Davis; Lauren M. Sanders; et al. (Clinical & Experimental Metastasis, 2022)

Cover Image - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)

A global agenda for advancing freshwater biodiversity research - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)
Global freshwater biodiversity is declining dramatically, and meeting the challenges of this crisis requires bold goals and the mobilisation of substantial resources. While the reasons are varied, investments in both research and conservation of freshwater biodiversity lag far behind those in the terrestrial and marine realms. Inspired by a global consultation, we identify 15 pressing priority needs, grouped into five research areas, in an effort to support informed stewardship of freshwater biodiversity. The proposed agenda aims to advance freshwater biodiversity research globally as a critical step in improving coordinated actions towards its sustainable management and conservation.

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Coastal winds and larval fish abundance indicate a recruitment mechanism for southeast Australian estuarine fisheries - Hayden T. Schilling; Charles Hinchliffe; Jonathan P. Gillson; Anthony G. Miskiewicz; Iain M. Suthers (Fisheries Oceanography, 2022)
Coastal winds transport water masses and larval fish onshore or offshore which may influence estuarine recruitment, yet our understanding of the mechanism underlying this relationship is limited. Here, we combine datasets from a historical database of larval fish off southeast Australia with a high‐resolution atmospheric reanalysis model to show that normalised abundance of coastally spawned larvae increased with weak to moderate upwelling favourable winds 14 days prior to sampling. The increase in abundance may reflect increased nutrient and plankton availability for larval fish. Normalised larval abundance decreased following strong upwelling favourable winds but increased after onshore (downwelling favourable) winds, due to wind‐driven transport. By combining a commercial estuarine fisheries catch‐rate dataset (4 species, 8 estuaries, 10 years) and the high‐resolution atmospheric reanalysis model, we show that negative effects of upwelling favourable winds during the spawning period can be detected in lagged estuarine commercial fisheries catch rates (lagged by 2–8 years depending on species' growth rates), potentially representing the same mechanism proposed for larval fish. Upwelling favourable winds in the southeast Australian region have increased since 1850 while onshore winds have decreased, which may have reduced larval recruitment to estuaries. Coastal winds are likely an important factor for estuarine recruitment in the southeast Australian region and future research on the estuarine recruitment of fish should incorporate coastal winds.

Correction to: Extracellular Microvesicles Released From Brain Endothelial Cells are Detected in Animal Models Of HIV‑1 Signifying Unresolved Inflammation - Servio H. Ramirez; Tetyana P. Buzhdygan; Jonathan F. Hale; Liang Cheng; Guangming Li; Bryson Hoover‑Hankerson; Roshanak Razmpour; Uma Sriram; Lishan Su; Raghava Potula; Allison M. Andrews (Journal of Neuroimmune Pharmacology, 2021)

Extracellular Microvesicles Released From Brain Endothelial Cells are Detected in Animal Models Of HIV-1 Signifying Unresolved Inflammation - Servio H. Ramirez; Tetyana P. Buzhdygan; Jonathan F. Hale; Liang Cheng; Guangming Li; Bryson Hoover-Hankerson; Roshanak Razmpour; Uma Sriram; Lishan Su; Raghava Potula; Allison M. Andrews (Journal of Neuroimmune Pharmacology, 2021)
Treatment of HIV-infected patients with antiretroviral therapy (ART) has effectively suppressed viral replication; however, the central nervous system is still a major target and reservoir of the virus leading to the possible development of HIV-associated neurocognitive disorders (HAND). Furthermore, a hallmark feature of HAND is the disruption of the blood–brain barrier that leads to loss of tight junction protein (TJP) complexes. Extracellular vesicles (EVs), released by every cell type in the body, occur in greater quantities in response to cellular activation or injury. We have found that inflammatory insults activate brain endothelial cells (EC) and induce the release of EVs containing TJPs such as Occludin. We thus hypothesized that HIV infection and unresolved neuroinflammation will result in the release of brain-EC derived EVs. Herein, our results show elevated levels of brain-EC EVs in a humanized mouse model of HIV infection. Furthermore, while ART reduced brain-EC EVs, it was unable to completely resolve increased vesicles detectable in the blood. In addition to inflammatory insults, HIV-1 viral proteins (Tat and gp120) increased the release of Occludin + vesicles from human brain microvasculature ECs. This increase in vesicle release could be prevented by knock-down of the small GTPase ARF6. ARF6 has been shown to regulate EV biogenesis in other cell types, and we provide further evidence for the involvement of ARF6 in brain EC derived EVs. Overall, this study offers insight into the process of brain vascular remodeling (via EVs) in the setting of neuroinflammation and thus provides possibilities for biomarker monitoring and targeting of ARF6. Graphical abstract

Simulating an invasion: unsealed water storage (rainwater tanks) and urban block design facilitate the spread of the dengue fever mosquito, Aedes aegypti, in Brisbane, Australia - Brendan J. Trewin; Hazel R. Parry; Daniel E. Pagendam; Gregor J. Devine; Myron P. Zalucki; Jonathan M. Darbro; Cassie C. Jansen; Nancy A. Schellhorn (Biological Invasions, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Correction to: Whole Body PMHS Response in Injurious Experimental Accelerative Loading Events - Jonathan D. Rupp; Lauren Zaseck; Carl S. Miller; Anne C. Bonifas; Matthew P. Reed; Don Sherman; John M. Cavanaugh; Kyle Ott; Constantine K. Demetropoulos (Annals of Biomedical Engineering, 2021)

Global exposure of population and land‐use to meteorological droughts under different warming levels and SSPs : A CORDEX ‐based study - Jonathan Spinoni; Paulo Barbosa; Edoardo Bucchignani; John Cassano; Tereza Cavazos; Alessandro Cescatti; Jens H. Christensen; Ole B. Christensen; Erika Coppola; Jason P. Evans; Giovanni Forzieri; Beate Geyer; et al. (International Journal of Climatology, 2021)
Global warming is likely to cause a progressive drought increase in some regions, but how population and natural resources will be affected is still underexplored. This study focuses on global population, forests, croplands and pastures exposure to meteorological drought hazard in the 21st century, expressed as frequency and severity of drought events. As input, we use a large ensemble of climate simulations from the Coordinated Regional Climate Downscaling Experiment (CORDEX), population projections from the NASA‐SEDAC dataset and land‐use projections from the Land‐Use Harmonization 2 project for 1981–2100. The exposure to drought hazard is presented for five Shared Socioeconomic Pathways (SSP1‐SSP5) at four Global Warming Levels (GWLs: 1.5°C to 4°C). Results show that considering only Standardized Precipitation Index (SPI; based on precipitation), the SSP3 at GWL4 projects the largest fraction of the global population (14%) to experience an increase in drought frequency and severity (versus 1981–2010), with this value increasing to 60% if temperature is considered (indirectly included in the Standardized Precipitation‐Evapotranspiration Index, SPEI). With SPEI, considering the highest GWL for each SSP, 8 (for SSP2, SSP4, SSP5) and 11 (SSP3) billion people, that is, more than 90%, will be affected by at least one unprecedented drought. For SSP5 at GWL4, approximately 2 × 10 6 km 2 of forests and croplands (respectively, 6% and 11%) and 1.5 × 10 6 km 2 of pastures (19%) will be exposed to increased drought frequency and severity according to SPI, but for SPEI this extent will rise to 17 × 10 6 km 2 of forests (49%), 6 × 10 6 km 2 of pastures (78%) and 12 × 10 6 km 2 of croplands (67%), being mid‐latitudes the most affected. The projected likely increase of drought frequency and severity significantly increases population and land‐use exposure to drought, even at low GWLs, thus extensive mitigation and adaptation efforts are needed to avoid the most severe impacts of climate change.

Animal Borne Ocean Sensors – AniBOS – An Essential Component of the Global Ocean Observing System - Clive R. McMahon; Fabien Roquet; Sophie Baudel; Mathieu Belbeoch; Sophie Bestley; Clint Blight; Lars Boehme; Fiona Carse; Daniel P. Costa; Michael A. Fedak; Christophe Guinet; Robert Harcourt; et al. (Frontiers in Marine Science, 2021)
Marine animals equipped with biological and physical electronic sensors have produced long-term data streams on key marine environmental variables, hydrography, animal behavior and ecology. These data are an essential component of the Global Ocean Observing System (GOOS). The Animal Borne Ocean Sensors (AniBOS) network aims to coordinate the long-term collection and delivery of marine data streams, providing a complementary capability to other GOOS networks that monitor Essential Ocean Variables (EOVs), essential climate variables (ECVs) and essential biodiversity variables (EBVs). AniBOS augments observations of temperature and salinity within the upper ocean, in areas that are under-sampled, providing information that is urgently needed for an improved understanding of climate and ocean variability and for forecasting. Additionally, measurements of chlorophyll fluorescence and dissolved oxygen concentrations are emerging. The observations AniBOS provides are used widely across the research, modeling and operational oceanographic communities. High latitude, shallow coastal shelves and tropical seas have historically been sampled poorly with traditional observing platforms for many reasons including sea ice presence, limited satellite coverage and logistical costs. Animal-borne sensors are helping to fill that gap by collecting and transmitting in near real time an average of 500 temperature-salinity-depth profiles per animal annually and, when instruments are recovered (∼30% of instruments deployed annually, n = 103 ± 34), up to 1,000 profiles per month in these regions. Increased observations from under-sampled regions greatly improve the accuracy and confidence in estimates of ocean state and improve studies of climate variability by delivering data that refine climate prediction estimates at regional and global scales. The GOOS Observations Coordination Group (OCG) reviews, advises on and coordinates activities across the global ocean observing networks to strengthen the effective implementation of the system. AniBOS was formally recognized in 2020 as a GOOS network. This improves our ability to observe the ocean’s structure and animals that live in them more comprehensively, concomitantly improving our understanding of global ocean and climate processes for societal benefit consistent with the UN Sustainability Goals 13 and 14: Climate and Life below Water. Working within the GOOS OCG framework ensures that AniBOS is an essential component of an integrated Global Ocean Observing System.

Predicting moisture content during maize nixtamalization using machine learning with NIR spectroscopy - Michael J. Burns; Jonathan S. Renk; David P. Eickholt; Amanda M. Gilbert; Travis J. Hattery; Mark Holmes; Nickolas Anderson; Amanda J. Waters; Sathya Kalambur; Sherry A. Flint-Garcia; Marna D. Yandeau-Nelson; George A. Annor; et al. (Theoretical and Applied Genetics, 2021)

Whole Body PMHS Response in Injurious Experimental Accelerative Loading Events - Jonathan D. Rupp; Lauren Zaseck; Carl S. Miller; Anne C. Bonifas; Matthew P. Reed; Don Sherman; John M. Cavanaugh; Kyle Ott; Constantine K. Demetropoulos (Annals of Biomedical Engineering, 2021)

Temporal rarity is a better predictor of local extinction risk than spatial rarity - Peter A. Wilfahrt; Ashley L. Asmus; Eric W. Seabloom; Jeremiah A. Henning; Peter Adler; Carlos A. Arnillas; Jonathan D. Bakker; Lori Biederman; Lars A. Brudvig; Marc Cadotte; Pedro Daleo; Anu Eskelinen; et al. (Ecology, 2021)
Spatial rarity is often used to predict extinction risk, but rarity can also occur temporally. Perhaps more relevant in the context of global change is whether a species is core to a community (persistent) or transient (intermittently present), with transient species often susceptible to human activities that reduce niche space. Using 5–12 yr of data on 1,447 plant species from 49 grasslands on five continents, we show that local abundance and species persistence under ambient conditions are both effective predictors of local extinction risk following experimental exclusion of grazers or addition of nutrients; persistence was a more powerful predictor than local abundance. While perturbations increased the risk of exclusion for low persistence and abundance species, transient but abundant species were also highly likely to be excluded from a perturbed plot relative to ambient conditions. Moreover, low persistence and low abundance species that were not excluded from perturbed plots tended to have a modest increase in abundance following perturbance. Last, even core species with high abundances had large decreases in persistence and increased losses in perturbed plots, threatening the long‐term stability of these grasslands. Our results demonstrate that expanding the concept of rarity to include temporal dynamics, in addition to local abundance, more effectively predicts extinction risk in response to environmental change than either rarity axis predicts alone.

Decomposing decomposition: isolating direct effects of temperature from other drivers of detrital processing - Oliver J. Wilmot; James M. Hood; Alexander D. Huryn; Jonathan P. Benstead (Ecology, 2021)
Understanding the observed temperature dependence of decomposition (i.e., its "apparent" activation energy) requires separation of direct effects of temperature on consumer metabolism (i.e., the "inherent" activation energy) from those driven by indirect seasonal patterns in phenology and biomass, and by longer‐term, climate‐driven shifts in acclimation, adaptation, and community assembly. Such parsing is important because studies that relate temperature to decomposition usually involve multi‐season data and/or spatial proxies for long‐term shifts, and so incorporate these indirect factors. The various effects of such factors can obscure the inherent temperature dependence of detrital processing. Separating the inherent temperature dependence of decomposition from other drivers is important for accurate prediction of the contribution of detritus‐sourced greenhouse gases to climate warming and requires novel approaches to data collection and analysis. Here, we present breakdown rates of red maple litter incubated in coarse‐ and fine‐mesh litterbags (the latter excluding macroinvertebrates) for serial approximately one‐month increments over one year in nine streams along a natural temperature gradient (mean annual: 12.8°–16.4°C) from north Georgia to central Alabama, USA. We analyzed these data using distance‐based redundancy analysis and generalized additive mixed models to parse the dependence of decomposition rates on temperature, seasonality, and shredding macroinvertebrate biomass. Microbial decomposition in fine‐mesh bags was significantly influenced by both temperature and seasonality. Accounting for seasonality corrected the temperature dependence of decomposition rate from 0.25 to 0.08 eV. Shredder assemblage structure in coarse‐mesh bags was related to temperature across both sites and seasons, shifting from “cold” stonefly‐dominated communities to “warm” communities dominated by snails or crayfish. Shredder biomass was not a significant predictor of either coarse‐mesh or macroinvertebrate‐mediated (i.e., coarse‐ minus fine‐mesh) breakdown rates, which were also jointly influenced by temperature and seasonality. Unlike fine‐mesh bags, however, temperature dependence of litter breakdown did not differ between models with and without seasonality for either coarse‐mesh (0.36 eV) or macroinvertebrate‐mediated (0.13 eV) rates. We conclude that indirect (non‐thermal) seasonal and site‐level effects play a variable and potentially strong role in shaping the apparent temperature dependence of detrital breakdown. Such effects should be incorporated into studies designed to estimate inherent temperature dependence of slow ecological processes.

Root anatomy and soil resource capture - Jonathan P. Lynch; Christopher F. Strock; Hannah M. Schneider; Jagdeep Singh Sidhu; Ishan Ajmera; Tania Galindo-Castañeda; Stephanie P. Klein; Meredith T. Hanlon (Plant and Soil, 2021)
Background Suboptimal water and nutrient availability are primary constraints in global agriculture. Root anatomy plays key roles in soil resource acquisition. In this article we summarize evidence that root anatomical phenotypes present opportunities for crop breeding. Scope Root anatomical phenotypes influence soil resource acquisition by regulating the metabolic cost of soil exploration, exploitation of the rhizosphere, the penetration of hard soil domains, the axial and radial transport of water, and interactions with soil biota including mycorrhizal fungi, pathogens, insects, and the rhizosphere microbiome. For each of these topics we provide examples of anatomical phenotypes which merit attention as selection targets for crop improvement. Several cross-cutting issues are addressed including the importance of phenotypic plasticity, integrated phenotypes, C sequestration, in silico modeling, and novel methods to phenotype root anatomy including image analysis tools. Conclusions An array of anatomical phenes have substantial importance for the acquisition of water and nutrients. Substantial phenotypic variation exists in crop germplasm. New tools and methods are making it easier to phenotype root anatomy, determine its genetic control, and understand its utility for plant fitness. Root anatomical phenotypes are underutilized yet attractive breeding targets for the development of the efficient, resilient crops urgently needed in global agriculture.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Flow is more Important than Temperature in Driving Patterns of Organic Matter Storage and Stoichiometry in Stream Ecosystems - James R. Junker; Wyatt F. Cross; Jonathan P. Benstead; Alexander D. Huryn; James M. Hood; Daniel Nelson; Gísli M. Gíslason; Jón S. Ólafsson (Ecosystems, 2021)

Volume reduction without neuronal loss in the primate pulvinar complex following striate cortex lesions - Jonathan M. Chan; Katrina H. Worthy; Marcello G. P. Rosa; David H. Reser; Nafiseh Atapour (Brain Structure and Function, 2021)

Alternative futures for global biological invasions - Núria Roura-Pascual; Brian Leung; Wolfgang Rabitsch; Lucas Rutting; Joost Vervoort; Sven Bacher; Stefan Dullinger; Karl-Heinz Erb; Jonathan M. Jeschke; Stelios Katsanevakis; Ingolf Kühn; Bernd Lenzner; et al. (Sustainability Science, 2021)
Scenario analysis has emerged as a key tool to analyze complex and uncertain future socio-ecological developments. However, currently existing global scenarios (narratives of how the world may develop) have neglected biological invasions, a major threat to biodiversity and the economy. Here, we use a novel participatory process to develop a diverse set of global biological invasion scenarios spanning a wide range of plausible global futures through to 2050. We adapted the widely used “two axes” scenario analysis approach to develop four families of four scenarios each, resulting in 16 scenarios that were later clustered into four contrasting sets of futures. Our analysis highlights that socioeconomic developments and technological innovation have the potential to shape biological invasions, in addition to well-known drivers, such as climate and human land use change and global trade. Our scenarios partially align with the shared socioeconomic pathways created by the climate change research community. Several factors that drive differences in biological invasions were underrepresented in the shared socioeconomic pathways; in particular, the implementation of biosecurity policies. We argue that including factors related to public environmental awareness and technological and trade development in global scenarios and models is essential to adequately consider biological invasions in global environmental assessments and thereby obtain a more integrative picture of future social–ecological developments.

Through the Boundaries: Environmental Factors Affecting Reef Benthic Cover in Marine Protected Areas in the Philippines - Fleurdeliz M. Panga; Jonathan A. Anticamara; Miledel Christine C. Quibilan; Michael P. Atrigenio; Porfirio M. Aliño (Frontiers in Marine Science, 2021)
Philippine coral reefs have been on the decline since the 1970s, and this degradation has posed a risk to biodiversity, food security, and livelihood in the country. In an effort to arrest this degradation, marine protected areas (MPAs) were established across the country. MPAs are known to improve fish biomass, but their effect on live coral cover and other benthos is not yet well documented and understood. In this study, 28 MPAs across the Philippines were surveyed comparing benthic cover and indices between protected reefs and adjacent unprotected reefs. No consistent differences were found between reefs inside and outside MPAs through all the benthic categories and reef health indices considered that are indicative of protection effects or recovery within MPAs. However, there were notable site-specific differences in benthic cover across the study MPAs-suggesting that factors other than protection play important roles in influencing benthic cover inside and outside of MPAs. Storm frequency and proximity to rivers, as a proxy for siltation, were the strongest negative correlates to live coral cover. Also, high coastal population, a proxy for pollution, and occurrence of blast and poison fishing positively correlated with high dead coral cover. The lack of significant difference in benthic cover between reefs inside and outside MPAs suggests that protection does not necessarily guarantee immediate improvement in benthic condition. Correlations between benthic condition and storm frequency, siltation, and pollution suggest that it is necessary to augment MPAs with other management strategies that will address the multiple stressors that are usually indiscriminate of MPA boundaries. Supplementing long-term and systematic monitoring of benthic cover and biodiversity inside and outside of MPAs with data on other important environmental and human impact variables will help improve understanding of benthic cover and biodiversity dynamics inside and outside of MPA boundaries.

EurOP2E – the European Open Platform for Prescribing Education, a consensus study among clinical pharmacology and therapeutics teachers - Michiel J. Bakkum; Milan C. Richir; Paraskevi Papaioannidou; Robert Likic; Emilio J. Sanz; Thierry Christiaens; João N. Costa; Romaldas Mačiulaitis; Lorena Dima; Jamie Coleman; Jelle Tichelaar; Michiel A. van Agtmael; et al. (European Journal of Clinical Pharmacology, 2021)
Purpose Sharing and developing digital educational resources and open educational resources has been proposed as a way to harmonize and improve clinical pharmacology and therapeutics (CPT) education in European medical schools. Previous research, however, has shown that there are barriers to the adoption and implementation of open educational resources. The aim of this study was to determine perceived opportunities and barriers to the use and creation of open educational resources among European CPT teachers and possible solutions for these barriers. Methods CPT teachers of British and EU medical schools completed an online survey. Opportunities and challenges were identified by thematic analyses and subsequently discussed in an international consensus meeting. Results Data from 99 CPT teachers from 95 medical schools were analysed. Thirty teachers (30.3%) shared or collaboratively produced digital educational resources. All teachers foresaw opportunities in the more active use of open educational resources, including improving the quality of their teaching. The challenges reported were language barriers, local differences, lack of time, technological issues, difficulties with quality management, and copyright restrictions. Practical solutions for these challenges were discussed and include a peer review system, clear indexing, and use of copyright licenses that permit adaptation of resources. Conclusion Key challenges to making greater use of CPT open educational resources are a limited applicability of such resources due to language and local differences and quality concerns. These challenges may be resolved by relatively simple measures, such as allowing adaptation and translation of resources and a peer review system.

Light and depth dependency of nitrogen fixation by the non‐photosynthetic, symbiotic cyanobacterium UCYN‐A - Mary R. Gradoville; Ana M. Cabello; Samuel T. Wilson; Kendra A. Turk‐Kubo; David M. Karl; Jonathan P. Zehr (Environmental Microbiology, 2021)
Summary The symbiotic cyanobacterium UCYN‐A is one of the most globally abundant marine dinitrogen (N 2 )‐fixers, but cultures have not been available and its biology and ecology are poorly understood. We used cultivation‐independent approaches to investigate how UCYN‐A single‐cell N 2 fixation rates (NFRs) and nifH gene expression vary as a function of depth and photoperiod. Twelve‐hour day/night incubations showed that UCYN‐A only fixed N 2 during the day. Experiments conducted using in situ arrays showed a light‐dependence of NFRs by the UCYN‐A symbiosis, with the highest rates in surface waters (5–45 m) and lower rates at depth (≥ 75 m). Analysis of NFRs versus in situ light intensity yielded a light saturation parameter ( I k ) for UCYN‐A of 44 μmol quanta m −2 s −1 . This is low compared with other marine diazotrophs, suggesting an ecological advantage for the UCYN‐A symbiosis under low‐light conditions. In contrast to cell‐specific NFRs, nifH gene‐specific expression levels did not vary with depth, indicating that light regulates N 2 fixation by UCYN‐A through processes other than transcription, likely including host–symbiont interactions. These results offer new insights into the physiology of the UCYN‐A symbiosis in the subtropical North Pacific Ocean and provide clues to the environmental drivers of its global distributions.

An exploratory study to investigate the association between age, physical activity, femoral trochlear cartilage thickness and biomarkers of tissue metabolism in adult males - Harry M. Roberts; Claire L. Griffith-McGeever; Julian A. Owen; Lewis Angell; Jonathan P. Moore; Jeanette M. Thom (European Journal of Applied Physiology, 2021)
Purpose To investigate the association between age, physical activity, femoral trochlear cartilage thickness and biomarkers of tissue metabolism in a cross-sectional sample of adult males. This study utilizes several emerging biomarkers that have been associated with early joint degenerative changes; serum COMP (cartilage oligomeric matrix protein), HA (hyaluronan) and lubricin. Methods Eighty-one males (age: mean (range): 43(18–70) years; body mass index: 25.2 (21.0–30.6) kg/m 2 ) volunteered. Resting serum COMP, HA and lubricin concentrations were determined via commercially available enzyme-linked immunosorbent assay (ELISA) and femoral trochlear cartilage thickness via supra-patellar ultrasound imaging. Physical activity levels were assessed using questionnaires. Statistical analyses were performed using correlation and regression analyses. Results Age was correlated with lateral trochlear cartilage thickness ( r = − 0.372; p < 0.01) and serum COMP ( r = 0.342; p < 0.01). 7-day physical activity was correlated with serum COMP ( r = 0.357, p < 0.01), and 12-month physical activity with both lateral trochlear cartilage thickness ( r = 0.340, p = 0.01) and serum HA ( r = 0.296, p < 0.05). Regression analyses revealed that age significantly accounted for the variability in lateral cartilage thickness and serum COMP, following the adjustment for potential cofounders. However, the association between age and lateral trochlear cartilage thickness was not moderated by physical activity levels (all p > 0.05). Conclusion This study indicates that older age may be associated with thinner lateral trochlear cartilage and higher cartilage turnover. Being physically active may also be positive for lateral trochlear cartilage thickness. However, overall, both age and physical activity level only account for a small amount of the variability in cartilage thickness and serum biomarkers.

Future carbon emissions from global mangrove forest loss - Maria F. Adame; Rod M. Connolly; Mischa P. Turschwell; Catherine E. Lovelock; Temilola Fatoyinbo; David Lagomasino; Liza A. Goldberg; Jordan Holdorf; Daniel A. Friess; Sigit D. Sasmito; Jonathan Sanderman; Michael Sievers; et al. (Global Change Biology, 2021)
Mangroves have among the highest carbon densities of any tropical forest. These ‘blue carbon’ ecosystems can store large amounts of carbon for long periods, and their protection reduces greenhouse gas emissions and supports climate change mitigation. Incorporating mangroves into Nationally Determined Contributions to the Paris Agreement and their valuation on carbon markets requires predicting how the management of different land‐uses can prevent future greenhouse gas emissions and increase CO 2 sequestration. We integrated comprehensive global datasets for carbon stocks, mangrove distribution, deforestation rates, and land‐use change drivers into a predictive model of mangrove carbon emissions. We project emissions and foregone soil carbon sequestration potential under ‘business as usual’ rates of mangrove loss. Emissions from mangrove loss could reach 2391 Tg CO 2 eq by the end of the century, or 3392 Tg CO 2 eq when considering foregone soil carbon sequestration. The highest emissions were predicted in southeast and south Asia (West Coral Triangle, Sunda Shelf, and the Bay of Bengal) due to conversion to aquaculture or agriculture, followed by the Caribbean (Tropical Northwest Atlantic) due to clearing and erosion, and the Andaman coast (West Myanmar) and north Brazil due to erosion. Together, these six regions accounted for 90% of the total potential CO 2 eq future emissions. Mangrove loss has been slowing, and global emissions could be more than halved if reduced loss rates remain in the future. Notably, the location of global emission hotspots was consistent with every dataset used to calculate deforestation rates or with alternative assumptions about carbon storage and emissions. Our results indicate the regions in need of policy actions to address emissions arising from mangrove loss and the drivers that could be managed to prevent them.

A global reconnaissance of particulates and metals/metalloids in untreated drinking water sources - Jonathan W. Peterson; Benjamin M. Fry; Daniel R. Wade; Ford J. Fishman; Jacob T. Stid; Jonas M. Peterson; Cleveland E. Tarp; Randall D. Wade; Sarah A. Brokus; Michael J. Pikaart; Brent P. Krueger; Aaron A. Best (Environmental Monitoring and Assessment, 2021)
Metal and metalloid contamination in drinking water sources is a global concern, particularly in developing countries. This study used hollow membrane water filters and metal-capturing polyurethane foams to sample 71 drinking water sources in 22 different countries. Field sampling was performed with sampling kits prepared in the lab at Hope College in Holland, MI, USA. Filters and foams were sent back to the lab after sampling, and subsequent analysis of flushates and rinsates allowed the estimation of suspended solids and metal and other analayte concentrations in source waters. Estimated particulate concentrations were 0–92 mg/L, and consisted of quartz, feldspar, and clay, with some samples containing metal oxides or sulfide phases. As and Cu were the only analytes which occurred above the World Health Organization (WHO) guidelines of 10 μg/L and 2000 μg/L, respectively, with As exceeding the guideline in 45% of the sources and Cu in 3%. Except for one value of ~ 285 μg/L, As concentrations were 45–200 μg/L (river), 65–179 μg/L (well), and 112–178 μg/L (tap). Other metals (Ce, Fe, Mg, Mn, Zn) with no WHO guideline were also detected, with Mn the most common. This study demonstrated that filters and foams can be used for reconnaissance characterization of untreated drinking water. However, estimated metal and other analyte concentrations could only be reported as minimum values due to potential incomplete retrieval of foam-bound analytes. A qualitative reporting methodology was used to report analytes as “present” if the concentration was below the WHO guideline, and “present-recommend retesting” if the concentration was quantifiable and above the WHO guideline.

Diurnal changes in perineuronal nets and parvalbumin neurons in the rat medial prefrontal cortex - John H. Harkness; Angela E. Gonzalez; Priyanka N. Bushana; Emily T. Jorgensen; Deborah M. Hegarty; Ariel A. Di Nardo; Alain Prochiantz; Jonathan P. Wisor; Sue A. Aicher; Travis E. Brown; Barbara A. Sorg (Brain Structure and Function, 2021)

The extent and variability of storm‐induced temperature changes in lakes measured with long‐term and high‐frequency data - Jonathan P. Doubek; Orlane Anneville; Gaël Dur; Aleksandra M. Lewandowska; Vijay P. Patil; James A. Rusak; Nico Salmaso; Christian Torsten Seltmann; Dietmar Straile; Pablo Urrutia‐Cordero; Patrick Venail; Rita Adrian; et al. (Limnology and Oceanography, 2021)
The intensity and frequency of storms are projected to increase in many regions of the world because of climate change. Storms can alter environmental conditions in many ecosystems. In lakes and reservoirs, storms can reduce epilimnetic temperatures from wind‐induced mixing with colder hypolimnetic waters, direct precipitation to the lake's surface, and watershed runoff. We analyzed 18 long‐term and high‐frequency lake datasets from 11 countries to assess the magnitude of wind‐ vs. rainstorm‐induced changes in epilimnetic temperature. We found small day‐to‐day epilimnetic temperature decreases in response to strong wind and heavy rain during stratified conditions. Day‐to‐day epilimnetic temperature decreased, on average, by 0.28°C during the strongest windstorms (storm mean daily wind speed among lakes: 6.7 ± 2.7 m s −1 , 1 SD) and by 0.15°C after the heaviest rainstorms (storm mean daily rainfall: 21.3 ± 9.0 mm). The largest decreases in epilimnetic temperature were observed ≥2 d after sustained strong wind or heavy rain (top 5 th percentile of wind and rain events for each lake) in shallow and medium‐depth lakes. The smallest decreases occurred in deep lakes. Epilimnetic temperature change from windstorms, but not rainstorms, was negatively correlated with maximum lake depth. However, even the largest storm‐induced mean epilimnetic temperature decreases were typically

The relationship between niche breadth and range size of beech ( Fagus ) species worldwide - Qiong Cai; Erik Welk; Chengjun Ji; Wenjing Fang; Francesco M. Sabatini; Jianxiao Zhu; Jiangling Zhu; Zhiyao Tang; Fabio Attorre; Juan A. Campos; Andraž Čarni; Milan Chytrý; et al. (Journal of Biogeography, 2021)
Aim This work explores whether the commonly observed positive range size–niche breadth relationship exists for Fagus , one of the most dominant and widespread broad‐leaved deciduous tree genera in temperate forests of the Northern Hemisphere. Additionally, we ask whether the 10 extant Fagus species’ niche breadths and climatic tolerances are under phylogenetic control. Location Northern Hemisphere temperate forests. Taxon Fagus L. Methods Combining the global vegetation database sPlot with Chinese vegetation data, we extracted 107,758 relevés containing Fagus species. We estimated biotic and climatic niche breadths per species using plot‐based co‐occurrence data and a resource‐based approach, respectively. We examined the relationships of these estimates with range size and tested for their phylogenetic signal, prior to which a Random Forest (RF) analysis was applied to test which climatic properties are most conserved across the Fagus species. Results Neither biotic niche breadth nor climatic niche breadth was correlated with range size, and the two niche breadths were incongruent as well. Notably, the widespread North American F. grandifolia had a distinctly smaller biotic niche breadth than the Chinese Fagus species ( F. engleriana , F. hayatae , F. longipetiolata and F. lucida ) with restricted distributions in isolated mountains. The RF analysis revealed that cold tolerance did not differ among the 10 species, and thus may represent an ancestral, fixed trait. In addition, neither biotic nor climatic niche breadths are under phylogenetic control. Main Conclusions We interpret the lack of a general positive range size–niche breadth relationship within the genus Fagus as a result of the widespread distribution, high among‐region variation in available niche space, landscape heterogeneity and Quaternary history. The results hold when estimating niche sizes either by fine‐scale co‐occurrence data or coarse‐scale climate data, suggesting a mechanistic link between factors operating across spatial scales. Besides, there was no evidence for diverging ecological specialization within the genus Fagus .

The Cerebellum and Implicit Sequencing: Evidence from Cerebellar Ataxia - Owen P. Morgan; Mitchell B. Slapik; Katherine G. Iannuzzelli; Stephen M. LaConte; Jonathan M. Lisinski; Peg C. Nopoulos; Ashley M. Cochran; Sharif I. Kronemer; Liana S. Rosenthal; Cherie L. Marvel (The Cerebellum, 2021)

A new method to estimate the lifetime of long‐life product categories - Cyrille F. Dunant; Trishla Shah; Michał P. Drewniok; Matteo Craglia; Jonathan M. Cullen (Journal of Industrial Ecology, 2021)
Increased recycling and reuse rates are a central part of the objectives laid out by the COP21. Nonetheless, the practical implementation of what has been called the circular economy, as well as its true potential, are not easily established. This is because the impact and implementation time scales of any intervention depend on knowing the lifetime of products, which is frequently unknown. This is particularly true in construction, responsible for 39% of worldwide emissions, 11% of which are embodied. Most material flow analysis (MFA) models will simply assume a range of plausible life expectancies when bottom‐up data are lacking. In this work, we propose a novel method of identification using the high quality but highly aggregated trade data available and use it to establish a “mortality curve” for buildings and other long‐lasting products. This identification method is intended to provide more reliable inputs to existing MFA models. It is widely applicable because of the general availability of the underlying data. Using it on United Kingdom trade data, we identify product classes at 1 year for packaging/home scrap, 1 to around 10 years for vehicles/equipment, and around 50 years for construction. The identification approach was then validated by using classical approaches using bottom‐up data for vehicles.

Miconia albicans and Curcuma longa herbal medicines positively modulate joint pain, function and inflammation in patients with osteoarthritis: a clinical study - Thiago P. O. Gomes; Jonathan I. N. Souza; Lucas C. Somerlate; Vanessa A. Mendonça; Nerilson M. Lima; Gabriela P. Carli; Sandra B. R. Castro; Teresinha de Jesus A. S. Andrade; João V. L. Dias; Marcone A. L. Oliveira; Caio C. S. Alves; Alessandra P. Carli (Inflammopharmacology, 2021)

Tundra wildfire triggers sustained lateral nutrient loss in Alaskan Arctic - Benjamin W. Abbott; Adrian V. Rocha; Arial Shogren; Jay P. Zarnetske; Frances Iannucci; William B. Bowden; Samuel P. Bratsman; Leika Patch; Rachel Watts; Randy Fulweber; Rebecca J. Frei; Amanda M. Huebner; et al. (Global Change Biology, 2021)
Climate change is creating widespread ecosystem disturbance across the permafrost zone, including a rapid increase in the extent and severity of tundra wildfire. The expansion of this previously rare disturbance has unknown consequences for lateral nutrient flux from terrestrial to aquatic environments. Lateral loss of nutrients could reduce carbon uptake and slow recovery of already nutrient‐limited tundra ecosystems. To investigate the effects of tundra wildfire on lateral nutrient export, we analyzed water chemistry in and around the 10‐year‐old Anaktuvuk River fire scar in northern Alaska. We collected water samples from 21 burned and 21 unburned watersheds during snowmelt, at peak growing season, and after plant senescence in 2017 and 2018. After a decade of ecosystem recovery, aboveground biomass had recovered in burned watersheds, but overall carbon and nitrogen remained ~20% lower, and the active layer remained ~10% deeper. Despite lower organic matter stocks, dissolved organic nutrients were substantially elevated in burned watersheds, with higher flow‐weighted concentrations of organic carbon (25% higher), organic nitrogen (59% higher), organic phosphorus (65% higher), and organic sulfur (47% higher). Geochemical proxies indicated greater interaction with mineral soils in watersheds with surface subsidence, but optical analysis and isotopes suggested that recent plant growth, not mineral soil, was the main source of organic nutrients in burned watersheds. Burned and unburned watersheds had similar δ 15 N‐NO 3 − , indicating that exported nitrogen was of preburn origin (i.e., not recently fixed). Lateral nitrogen flux from burned watersheds was 2‐ to 10‐fold higher than rates of background nitrogen fixation and atmospheric deposition estimated in this area. These findings indicate that wildfire in Arctic tundra can destabilize nitrogen, phosphorus, and sulfur previously stored in permafrost via plant uptake and leaching. This plant‐mediated nutrient loss could exacerbate terrestrial nutrient limitation after disturbance or serve as an important nutrient release mechanism during succession.

Nitrogen cycling microbiomes are structured by plant mycorrhizal associations with consequences for nitrogen oxide fluxes in forests - Ryan M. Mushinski; Zachary C. Payne; Jonathan D. Raff; Matthew E. Craig; Sally E. Pusede; Douglas B. Rusch; Jeffrey R. White; Richard P. Phillips (Global Change Biology, 2021)
Volatile nitrogen oxides (N 2 O, NO, NO 2 , HONO, …) can negatively impact climate, air quality, and human health. Using soils collected from temperate forests across the eastern United States, we show microbial communities involved in nitrogen (N) cycling are structured, in large part, by the composition of overstory trees, leading to predictable N‐cycling syndromes, with consequences for emissions of volatile nitrogen oxides to air. Trees associating with arbuscular mycorrhizal (AM) fungi promote soil microbial communities with higher N‐cycle potential and activity, relative to microbial communities in soils dominated by trees associating with ectomycorrhizal (ECM) fungi. Metagenomic analysis and gene expression studies reveal a 5 and 3.5 times greater estimated N‐cycle gene and transcript copy numbers, respectively, in AM relative to ECM soil. Furthermore, we observe a 60% linear decrease in volatile reactive nitrogen gas flux (NO y ≡ NO, NO 2 , HONO) as ECM tree abundance increases. Compared to oxic conditions, gas flux potential of N 2 O and NO increase significantly under anoxic conditions for AM soil (30‐ and 120‐fold increase), but not ECM soil—likely owing to small concentrations of available substrate ( ) in ECM soil. Linear mixed effects modeling shows that ECM tree abundance, microbial process rates, and geographic location are primarily responsible for variation in peak potential NO y flux. Given that nearly all tree species associate with either AM or ECM fungi, our results indicate that the consequences of tree species shifts associated with global change may have predictable consequences for soil N cycling.

An assessment of the MOD17A2 gross primary production product in the Caatinga biome, Brazil - Rosaria R. Ferreira; Pedro Mutti; Keila R. Mendes; Suany Campos; Thiago V. Marques; Cristiano P. Oliveira; Weber Gonçalves; Jonathan Mota; Gelson Difante; Stella A. Urbano; Leonardo Fernandes; Bergson G. Bezerra; et al. (International Journal of Remote Sensing, 2021)

Marine Important Bird and Biodiversity Areas for Penguins in Antarctica, Targets for Conservation Action - Jonathan Handley; Marie-Morgane Rouyer; Elizabeth J. Pearmain; Victoria Warwick-Evans; Katharina Teschke; Jefferson T. Hinke; Heather Lynch; Louise Emmerson; Colin Southwell; Gary Griffith; César A. Cárdenas; Aldina M. A. Franco; et al. (Frontiers in Marine Science, 2021)
Global targets for area-based conservation and management must move beyond threshold-based targets alone and must account for the quality of such areas. In the Southern Ocean around Antarctica, a region where key biodiversity faces unprecedented risks from climate change and where there is a growing demand to extract resources, a number of marine areas have been afforded enhanced conservation or management measures through two adopted marine protected areas (MPAs). However, evidence suggests that additional high quality areas could benefit from a proposed network of MPAs. Penguins offer a particular opportunity to identify high quality areas because these birds, as highly visible central-place foragers, are considered indicator species whose populations reflect the state of the surrounding marine environment. We compiled a comprehensive dataset of the location of penguin colonies and their associated abundance estimates in Antarctica. We then estimated the at-sea distribution of birds based on information derived from tracking data and through the application of a modified foraging radius approach with a density decay function to identify some of the most important marine areas for chick-rearing adult penguins throughout waters surrounding Antarctica following the Important Bird and Biodiversity Area (IBA) framework. Additionally, we assessed how marine IBAs overlapped with the currently adopted and proposed network of key management areas (primarily MPAs), and how the krill fishery likely overlapped with marine IBAs over the past five decades. We identified 63 marine IBAs throughout Antarctic waters and found that were the proposed MPAs to be adopted, the permanent conservation of high quality areas for penguin species would increase by between 49 and 100% depending on the species. Furthermore, our data show that, despite a generally contracting range of operation by the krill fishery in Antarctica over the past five decades, a consistently disproportionate amount of krill is being harvested within marine IBAs compared to the total area in which the fishery operates. Our results support the designation of the proposed MPA network and offer additional guidance as to where decision-makers should act before further perturbation occurs in the Antarctic marine ecosystem.

Epidemiology, Clinical Features, and Management of Texas Coral Snake (Micrurus tener) Envenomations Reported to the North American Snakebite Registry - Spencer Greene; Anne-Michelle Ruha; Sharan Campleman; Jeffrey Brent; Paul Wax; Kim Aldy; Peter Akpunonu; Vikhyat S. Bebarta; Gillian A. Beauchamp; Michael C. Beuhler; Mary Billington; William Boroughf; et al. (Journal of Medical Toxicology, 2021)

What causes the spread of model projections of ocean dynamic sea-level change in response to greenhouse gas forcing? - Matthew P. Couldrey; Jonathan M. Gregory; Fabio Boeira Dias; Peter Dobrohotoff; Catia M. Domingues; Oluwayemi Garuba; Stephen M. Griffies; Helmuth Haak; Aixue Hu; Masayoshi Ishii; Johann Jungclaus; Armin Köhl; et al. (Climate Dynamics, 2021)
Sea levels of different atmosphere–ocean general circulation models (AOGCMs) respond to climate change forcing in different ways, representing a crucial uncertainty in climate change research. We isolate the role of the ocean dynamics in setting the spatial pattern of dynamic sea-level ( ζ ) change by forcing several AOGCMs with prescribed identical heat, momentum (wind) and freshwater flux perturbations. This method produces a ζ projection spread comparable in magnitude to the spread that results from greenhouse gas forcing, indicating that the differences in ocean model formulation are the cause, rather than diversity in surface flux change. The heat flux change drives most of the global pattern of ζ change, while the momentum and water flux changes cause locally confined features. North Atlantic heat uptake causes large temperature and salinity driven density changes, altering local ocean transport and ζ . The spread between AOGCMs here is caused largely by differences in their regional transport adjustment, which redistributes heat that was already in the ocean prior to perturbation. The geographic details of the ζ change in the North Atlantic are diverse across models, but the underlying dynamic change is similar. In contrast, the heat absorbed by the Southern Ocean does not strongly alter the vertically coherent circulation. The Arctic ζ change is dissimilar across models, owing to differences in passive heat uptake and circulation change. Only the Arctic is strongly affected by nonlinear interactions between the three air-sea flux changes, and these are model specific.

Are we ready to track climate‐driven shifts in marine species across international boundaries? ‐ A global survey of scientific bottom trawl data - Aurore A. Maureaud; Romain Frelat; Laurène Pécuchet; Nancy Shackell; Bastien Mérigot; Malin L. Pinsky; Kofi Amador; Sean C. Anderson; Alexander Arkhipkin; Arnaud Auber; Iça Barri; Richard J. Bell; et al. (Global Change Biology, 2021)
Marine biota are redistributing at a rapid pace in response to climate change and shifting seascapes. While changes in fish populations and community structure threaten the sustainability of fisheries, our capacity to adapt by tracking and projecting marine species remains a challenge due to data discontinuities in biological observations, lack of data availability, and mismatch between data and real species distributions. To assess the extent of this challenge, we review the global status and accessibility of ongoing scientific bottom trawl surveys. In total, we gathered metadata for 283,925 samples from 95 surveys conducted regularly from 2001 to 2019. We identified that 59% of the metadata collected are not publicly available, highlighting that the availability of data is the most important challenge to assess species redistributions under global climate change. Given that the primary purpose of surveys is to provide independent data to inform stock assessment of commercially important populations, we further highlight that single surveys do not cover the full range of the main commercial demersal fish species. An average of 18 surveys is needed to cover at least 50% of species ranges, demonstrating the importance of combining multiple surveys to evaluate species range shifts. We assess the potential for combining surveys to track transboundary species redistributions and show that differences in sampling schemes and inconsistency in sampling can be overcome with spatio‐temporal modeling to follow species density redistributions. In light of our global assessment, we establish a framework for improving the management and conservation of transboundary and migrating marine demersal species. We provide directions to improve data availability and encourage countries to share survey data, to assess species vulnerabilities, and to support management adaptation in a time of climate‐driven ocean changes.

Responses of Intertidal Bacterial Biofilm Communities to Increasing pCO2 - Dorsaf Kerfahi; Ben P. Harvey; Sylvain Agostini; Koetsu Kon; Ruiping Huang; Jonathan M. Adams; Jason M. Hall-Spencer (Marine Biotechnology, 2020)

Predicting biodiversity richness in rapidly changing landscapes: climate, low human pressure or protection as salvation? - David W. Macdonald; Luca Chiaverini; Helen M. Bothwell; Żaneta Kaszta; Eric Ash; Gilmoore Bolongon; Özgün Emre Can; Ahimsa Campos-Arceiz; Phan Channa; Gopalasamy Reuben Clements; Andrew J. Hearn; Laurie Hedges; et al. (Biodiversity and Conservation, 2020)
Rates of biodiversity loss in Southeast Asia are among the highest in the world, and the Indo-Burma and South-Central China Biodiversity Hotspots rank among the world’s most threatened. Developing robust multi-species conservation models is critical for stemming biodiversity loss both here and globally. We used a large and geographically extensive remote-camera survey and multi-scale, multivariate optimization species distribution modelling to investigate the factors driving biodiversity across these two adjoining biodiversity hotspots. Four major findings emerged from the work. (i) We identified clear spatial patterns of species richness, with two main biodiverse centres in the Thai-Malay Peninsula and in the mountainous region of Southwest China. (ii) Carnivores in particular, and large ungulates to a lesser degree, were the strongest indicators of species richness. (iii) Climate had the largest effect on biodiversity, followed by protected status and human footprint. (iv) Gap analysis between the biodiversity model and the current system of protected areas revealed that the majority of areas supporting the highest predicted biodiversity are not protected. Our results highlighted several key locations that should be prioritized for expanding the protected area network to maximize conservation effectiveness. We demonstrated the importance of switching from single-species to multi-species approaches to highlight areas of high priority for biodiversity conservation. In addition, since these areas mostly occur over multiple countries, we also advocate for a paradigmatic focus on transboundary conservation planning.

Forget the audience: tadpoles release similar disturbance cues regardless of kinship or familiarity - Kevin R. Bairos-Novak; Adam L. Crane; Gabrielle H. Achtymichuk; Jonathan Hsin; Ita A. E. Rivera-Hernández; Olena M. Simko; Theresa E. Wrynn; Douglas P. Chivers; Maud C. O. Ferrari (Behavioral Ecology and Sociobiology, 2020)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Reference and current Trophic Level Index of New Zealand lakes: benchmarks to inform lake management and assessment - Jonathan M. Abell; Paul van Dam‐Bates; Deniz Özkundakci; David P. Hamilton (New Zealand Journal of Marine and Freshwater Research, 2020)
Knowledge of trophic status is fundamental to understanding the condition and function of lake ecosystems. We developed regression models to predict chlorophyll a concentrations (chl a ) in New Zealand lakes for reference and current states, based on an existing dataset of total nitrogen (TN) and total phosphorus (TP) concentrations for 1031 lakes. Models were then developed to predict Secchi depth based on chl a and a sediment resuspension term applicable to shallow lakes. Estimates of all four Trophic Level Index (TLI) variables (chl a , TN, TP and Secchi depth) were analysed to estimate reference and current state TLI for the nationally representative sample of 1031 lakes. There was a trend of eutrophication between reference and current states, with systematic differences among lake geomorphic types. Mean chl a increased 3.5‐fold (2.42 mg m −3 vs. 8.32 mg m −3 ) and mean Secchi depth decreased (indicating lower clarity) by approximately one‐third (9.62 m vs. 6.48 m) between reference and current states. On average, TLI increased by 0.67, with the TLI increase >1 in approximately one‐third (31%) of lakes. This study informs the status of lake ecosystems in NZ and provides benchmarks to guide management and assessment.

The problem of scale in predicting biological responses to climate - Luca Bütikofer; Karen Anderson; Daniel P. Bebber; Jonathan J. Bennie; Regan I. Early; Ilya M. D. Maclean (Global Change Biology, 2020)
Many analyses of biological responses to climate rely on gridded climate data derived from weather stations, which differ from the conditions experienced by organisms in at least two respects. First, the microclimate recorded by a weather station is often quite different to that near the ground surface, where many organisms live. Second, the temporal and spatial resolutions of gridded climate datasets derived from weather stations are often too coarse to capture the conditions experienced by organisms. Temporally and spatially coarse data have clear benefits in terms of reduced model size and complexity, but here we argue that coarse‐grained data introduce errors that, in biological studies, are too often ignored. However, in contrast to common perception, these errors are not necessarily caused directly by a spatial mismatch between the size of organisms and the scale at which climate data are collected. Rather, errors and biases are primarily due to (a) systematic discrepancies between the climate used in analysis and that experienced by organisms under study; and (b) the non‐linearity of most biological responses in combination with differences in climate variance between locations and time periods for which models are fitted and those for which projections are made. We discuss when exactly problems of scale can be expected to arise and highlight the potential to circumvent these by spatially and temporally down‐scaling climate. We also suggest ways in which adjustments to deal with issues of scale could be made without the need to run high‐resolution models over wide extents.

R esource supply governs the apparent temperature dependence of animal production in stream ecosystems - James R. Junker; Wyatt F. Cross; Jonathan P. Benstead; Alexander D. Huryn; James M. Hood; Daniel Nelson; Gísli M. Gíslason; Jón S. Ólafsson (Ecology Letters, 2020)
Rising global temperatures are changing how energy and materials move through ecosystems, with potential consequences for the role of animals in these processes. We tested a central prediction of the metabolic scaling framework—the temperature independence of animal community production—using a series of geothermally heated streams and a comprehensive empirical analysis. We show that the apparent temperature sensitivity of animal production was consistent with theory for individuals ( E p ind = 0.64 vs. 0.65 eV), but strongly amplified relative to theoretical expectations for communities, both among ( E p among = 0.67 vs. 0 eV) and within ( E p within = 1.52 vs. 0 eV) streams. After accounting for spatial and temporal variation in resources, we show that the apparent positive effect of temperature was driven by resource supply, providing strong empirical support for the temperature independence of invertebrate production and the necessary inclusion of resources in metabolic scaling efforts.

Functional re-organization of the gills of metamorphosing sea lamprey (Petromyzon marinus): preparation for a blood diet and the freshwater to seawater transition - Julia Sunga; Jonathan M. Wilson; Michael P. Wilkie (Journal of Comparative Physiology B, 2020)

Environmental DNA metabarcoding provides enhanced detection of the European eel Anguilla anguilla and fish community structure in pumped river catchments - Nathan P. Griffiths; Jonathan D. Bolland; Rosalind M. Wright; Leona A. Murphy; Robert K. Donnelly; Hayley V. Watson; Bernd Hänfling (Journal of Fish Biology, 2020)
The European eel Anguilla anguilla (eel hereafter) is critically endangered and has a catadromous life cycle, which means adult eels that live in pumped catchments must pass through pumps during their downstream spawning migration. Policy makers are currently lacking detailed site‐by‐site eel distribution information to estimate the overall impact of individual pumping stations on eel escapement, and as such lack the data to enable informed prioritisation of pumping station management and targeted mitigation. This study investigated whether environmental DNA (eDNA) metabarcoding can provide increased detection sensitivity for eel and fish community structure in highly regulated pumped catchments, when compared directly to current standard practice fish survey protocols (seine netting/electric fishing). Eels were detected in 14 of 17 sites (82.4%) using eDNA metabarcoding in contrast to 3 of 17 sites (17.6%) using traditional catch methods. In addition, when using eDNA monitoring, species richness was higher in 16 of 17 sites (94.1%), and site occupancy was greater than or equal to traditional methods for 23 of 26 of the fish species detected (88.5%). Although eDNA methods presented significantly higher average species richness and species site occupancy overall, eDNA and catch methods were positively correlated in terms of species richness and site occupancy. It was therefore found that eDNA metabarcoding was a high‐sensitivity method for detecting eels in pumped catchments while also increasing the detection of overall fish community structure compared to traditional catch methods. In addition, this study highlights how eDNA monitoring is especially suited to increase the detection of particular species, with traditional methods sufficient for others. This high sensitivity, coupled with the ability to sample multiple sites in a short time frame, suggests that eDNA metabarcoding workflows could be invaluable tools when prioritising pumping station management.

Persisting in a glaciated landscape: Pleistocene microrefugia evidenced by the tree wētā Hemideina maori in central South Island, New Zealand - Keith J. King; Debbie M. Lewis; Jonathan M. Waters; Graham P. Wallis (Journal of Biogeography, 2020)
Aim Repeated cycles of Pleistocene glaciation have influenced phylogeographic structure of taxa on New Zealand's South Island. Many taxa became restricted to refugia at either end of the island during glaciation, resulting in an area of low endemicity in central South Island. This area of low endemism is typified by the so‐called beech (or biotic) gap, where the absence of Nothofagus forest (and many other plant and invertebrate taxa) has been attributed to repeated glaciation. Some taxa, however, appear to have persisted in situ in localized refugia within the biotic gap. We test these alternative hypotheses in a large flightless alpine wētā (grasshopper). Location Southern Alps, South Island, New Zealand. Taxon Hemideina maori Pictet & Saussure, 1891 (Orthoptera: Anostostomatidae). Methods We used phylogeographic analysis of mitochondrial cytochrome c oxidase I ( cox1 ) and 25 nuclear DNA (nuDNA) markers to test for Pleistocene glacial microrefugia within the current montane South Island range of Hemideina maori . Results We identified eight deeply differentiated mtDNA lineages with limited sharing of haplotypes among populations. Genetic differentiation assessed using nuDNA revealed a similar pattern, with three groups broadly corresponding to the deepest mtDNA splits. The central South Island region exhibits substantial endemic mtDNA diversity and a distinctive nuclear lineage. Main conclusions These results indicate that H. maori likely persisted in microrefugia within the biotic gap during glaciation. These deep lineages are estimated to have started diverging prior to the initiation of glaciation, up to 3 Ma. These results add to a growing number of Southern Hemisphere examples of deep phylogeographic differentiation in glaciated alpine regions compared to Europe and North America, probably reflecting less intense glaciation. We suggest that other Southern Alps species showing northern and southern clades alone are more montane than alpine, and were reliant on warmer habitat to the north and south during glacial eras. Thus, there are species‐specific responses to climatic processes, influenced by distinctive habitat requirements and physiological traits.

A cross‐scale assessment of productivity–diversity relationships - Dylan Craven; Masha T. van der Sande; Carsten Meyer; Katharina Gerstner; Joanne M. Bennett; Darren P. Giling; Jes Hines; Helen R. P. Phillips; Felix May; Katherine H. Bannar‐Martin; Jonathan M. Chase; Petr Keil (Global Ecology and Biogeography, 2020)
Aim Biodiversity and ecosystem productivity vary across the globe, and considerable effort has been made to describe their relationships. Biodiversity and ecosystem functioning research has traditionally focused on how experimentally controlled species richness affects net primary productivity ( S → NPP) at small spatial grains. In contrast, the influence of productivity on richness (NPP → S ) has been explored at many grains in naturally assembled communities. Mismatches in spatial scale between approaches have fuelled debate about the strength and direction of biodiversity–productivity relationships. Here, we examine the direction and strength of the influence of productivity on diversity (NPP → S ) and the influence of diversity on productivity ( S → NPP) and how these vary across spatial grains. Location Contiguous USA. Time period 1999–2015. Major taxa studied Woody species (angiosperms and gymnosperms). Methods Using data from North American forests at grains from local (672 m 2 ) to coarse spatial units (median area = 35,677 km 2 ), we assess relationships between diversity and productivity using structural equation and random forest models, while accounting for variation in climate, environmental heterogeneity, management and forest age. Results We show that relationships between S and NPP strengthen with spatial grain. Within each grain, S → NPP and NPP → S have similar magnitudes, meaning that processes underlying S → NPP and NPP → S either operate simultaneously or that one of them is real and the other is an artefact. At all spatial grains, S was one of the weakest predictors of forest productivity, which was largely driven by biomass, temperature and forest management and age. Main conclusions We conclude that spatial grain mediates relationships between biodiversity and productivity in real‐world ecosystems and that results supporting predictions from each approach (NPP → S and S → NPP) serve as an impetus for future studies testing underlying mechanisms. Productivity–diversity relationships emerge at multiple spatial grains, which should widen the focus of national and global policy and research to larger spatial grains.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Association between APOE e4 and white matter hyperintensity volume, but not total brain volume or white matter integrity - Donald M. Lyall; Simon R. Cox; Laura M. Lyall; Carlos Celis-Morales; Breda Cullen; Daniel F. Mackay; Joey Ward; Rona J. Strawbridge; Andrew M. McIntosh; Naveed Sattar; Daniel J. Smith; Jonathan Cavanagh; et al. (Brain Imaging and Behavior, 2020)
Apolipoprotein ( APOE ) e4 genotype is an accepted risk factor for accelerated cognitive aging and dementia, though its neurostructural substrates are unclear. The deleterious effects of this genotype on brain structure may increase in magnitude into older age. This study aimed to investigate in UK Biobank the association between APOE e4 allele presence vs. absence and brain imaging variables that have been associated with worse cognitive abilities; and whether this association varies by cross-sectional age. We used brain magnetic resonance imaging (MRI) and genetic data from a general-population cohort: the UK Biobank ( N = 8395 after exclusions). We adjusted for the covariates of age in years, sex, Townsend social deprivation scores, smoking history and cardiometabolic diseases. There was a statistically significant association between APOE e4 genotype and increased (i.e. worse) white matter (WM) hyperintensity volumes (standardised beta = 0.088, 95% confidence intervals = 0.036 to 0.139, P = 0.001), a marker of poorer cerebrovascular health. There were no associations with left or right hippocampal, total grey matter (GM) or WM volumes, or WM tract integrity indexed by fractional anisotropy (FA) and mean diffusivity (MD). There were no statistically significant interactions with age. Future research in UK Biobank utilising intermediate phenotypes and longitudinal imaging hold significant promise for this area, particularly pertaining to APOE e4’s potential link with cerebrovascular contributions to cognitive aging.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Coastline variability of several Latin American cities alongside Pacific Ocean due to the unusual “Sea Swell” events of 2015 - P. Godwyn-Paulson; M. P. Jonathan; Francisco Reyes Hernandez; G. Muthusankar; C. Lakshumanan (Environmental Monitoring and Assessment, 2020)

Latitudinal constraints on the abundance and activity of the cyanobacterium UCYN‐A and other marine diazotrophs in the North Pacific - Mary R. Gradoville; Hanna Farnelid; Angelicque E. White; Kendra A. Turk‐Kubo; Brittany Stewart; François Ribalet; Sara Ferrón; Paulina Pinedo‐Gonzalez; E. Virginia Armbrust; David M. Karl; Seth John; Jonathan P. Zehr (Limnology and Oceanography, 2020)
The number of marine environments known to harbor dinitrogen (N 2 )‐fixing (diazotrophic) microorganisms is increasing, prompting a reassessment of the biogeography of marine diazotrophs and N 2 fixation rates (NFRs). Here, we investigate the diversity, abundance, and activity of diazotrophic microorganisms in the North Pacific Subtropical Gyre (NPSG), a diazotrophic habitat, and the North Pacific Transition Zone (NPTZ), a region characterized by strong physical, chemical, and biological gradients. Samples were collected on two springtime meridional cruises during 2016 and 2017, spanning from 23.5°N to 41.4°N along 158°W. We observed an abrupt decrease in diazotrophic abundances near the southern edge of the NPTZ, which coincided with a salinity front and with a ∼10‐fold increase in Synechococcus abundance, but without a concomitant change in phosphate or nitrate concentrations. In NPSG waters south of this diazotrophic boundary, nifH genes and NFRs were consistently detected and diazotrophic communities were dominated by UCYN‐A, an uncultivated, symbiotic cyanobacterium (2.8 × 10 3 to 1.0 × 10 6 nifH gene copies L −1 ). There was a significant positive relationship between quantitative polymerase chain reaction‐derived UCYN‐A nifH gene abundances and community NFRs in the NPSG, suggesting a large contribution of UCYN‐A to community NFRs. In the NPTZ waters to the north, NFRs were low or undetected and nifH genes were rare, with the few detected sequences represented by UCYN‐A and noncyanobacterial diazotrophs. The patterns we observed in UCYN‐A abundance in the context of local biogeochemistry suggest that the environmental controls of this organism may differ from those of cultivated marine cyanobacterial diazotrophs.

Global human influence maps reveal clear opportunities in conserving Earth’s remaining intact terrestrial ecosystems - Jason Riggio; Jonathan E. M. Baillie; Steven Brumby; Erle Ellis; Christina M. Kennedy; James R. Oakleaf; Alex Tait; Therese Tepe; David M. Theobald; Oscar Venter; James E. M. Watson; Andrew P. Jacobson (Global Change Biology, 2020)
Leading up to the Convention on Biological Diversity Conference of the Parties 15, there is momentum around setting bold conservation targets. Yet, it remains unclear how much of Earth's land area remains without significant human influence and where this land is located. We compare four recent global maps of human influences across Earth's land, Anthromes, Global Human Modification, Human Footprint and Low Impact Areas, to answer these questions. Despite using various methodologies and data, these different spatial assessments independently estimate similar percentages of the Earth's terrestrial surface as having very low (20%–34%) and low (48%–56%) human influence. Three out of four spatial assessments agree on 46% of the non‐permanent ice‐ or snow‐covered land as having low human influence. However, much of the very low and low influence portions of the planet are comprised of cold (e.g., boreal forests, montane grasslands and tundra) or arid (e.g., deserts) landscapes. Only four biomes (boreal forests, deserts, temperate coniferous forests and tundra) have a majority of datasets agreeing that at least half of their area has very low human influence. More concerning, all datasets. These findings suggest that about half of Earth's terrestrial surface has relatively low human influence and offers opportunities for proactive conservation actions to retain the last intact ecosystems on the planet. However, though the relative abundance of ecosystem areas with low human influence varies widely by biome, conserving these last intact areas should be a high priority before they are completely lost.

Storm impacts on phytoplankton community dynamics in lakes - Jason D. Stockwell; Jonathan P. Doubek; Rita Adrian; Orlane Anneville; Cayelan C. Carey; Laurence Carvalho; Lisette N. De Senerpont Domis; Gaël Dur; Marieke A. Frassl; Hans‐Peter Grossart; Bas W. Ibelings; Marc J. Lajeunesse; et al. (Global Change Biology, 2020)
In many regions across the globe, extreme weather events such as storms have increased in frequency, intensity, and duration due to climate change. Ecological theory predicts that such extreme events should have large impacts on ecosystem structure and function. High winds and precipitation associated with storms can affect lakes via short‐term runoff events from watersheds and physical mixing of the water column. In addition, lakes connected to rivers and streams will also experience flushing due to high flow rates. Although we have a well‐developed understanding of how wind and precipitation events can alter lake physical processes and some aspects of biogeochemical cycling, our mechanistic understanding of the emergent responses of phytoplankton communities is poor. Here we provide a comprehensive synthesis that identifies how storms interact with lake and watershed attributes and their antecedent conditions to generate changes in lake physical and chemical environments. Such changes can restructure phytoplankton communities and their dynamics, as well as result in altered ecological function (e.g., carbon, nutrient and energy cycling) in the short‐ and long‐term. We summarize the current understanding of storm‐induced phytoplankton dynamics, identify knowledge gaps with a systematic review of the literature, and suggest future research directions across a gradient of lake types and environmental conditions.

Evolutionary history and sex are significant drivers of crayfish demography in resource-limited cave ecosystems - Brock M. Huntsman; Michael P. Venarsky; Fitsum Abadi; Alexander D. Huryn; Bernard R. Kuhajda; Christian L. Cox; Jonathan P. Benstead (Evolutionary Ecology, 2020)

Thermal niche diversity and trophic redundancy drive neutral effects of warming on energy flux through a stream food web - Daniel Nelson; Jonathan P. Benstead; Alexander D. Huryn; Wyatt F. Cross; James M. Hood; Philip W. Johnson; James R. Junker; Gísli M. Gíslason; Jón S. Ólafsson (Ecology, 2020)
Climate warming is predicted to alter routing and flows of energy through food webs because of the critical and varied effects of temperature on physiological rates, community structure, and trophic dynamics. Few studies, however, have experimentally assessed the net effect of warming on energy flux and food web dynamics in natural intact communities. Here, we test how warming affects energy flux and the trophic basis of production in a natural invertebrate food web by experimentally heating a stream reach in southwest Iceland by ~4°C for 2 yr and comparing its response to an unheated reference stream. Previous results from this experiment showed that warming led to shifts in the structure of the invertebrate assemblage, with estimated increases in total metabolic demand but no change in annual secondary production. We hypothesized that elevated metabolic demand and invariant secondary production would combine to increase total consumption of organic matter in the food web, if diet composition did not change appreciably with warming. Dietary composition of primary consumers indeed varied little between streams and among years, with gut contents primarily consisting of diatoms (72.9%) and amorphous detritus (19.5%). Diatoms dominated the trophic basis of production of primary consumers in both study streams, contributing 79–86% to secondary production. Although warming increased the flux of filamentous algae within the food web, total resource consumption did not increase as predicted. The neutral net effect of warming on total energy flow through the food web was a result of taxon‐level variation in responses to warming, a neutral effect on total invertebrate production, and strong trophic redundancy within the invertebrate assemblage. Thus, food webs characterized by a high degree of trophic redundancy may be more resistant to the effects of climate warming than those with more diverse and specialized consumers.

Projecting terrestrial biodiversity intactness with GLOBIO 4 - Aafke M. Schipper; Jelle P. Hilbers; Johan R. Meijer; Laura H. Antão; Ana Benítez‐López; Melinda M. J. de Jonge; Luuk H. Leemans; Eddy Scheper; Rob Alkemade; Jonathan C. Doelman; Sido Mylius; Elke Stehfest; et al. (Global Change Biology, 2020)
Scenario‐based biodiversity modelling is a powerful approach to evaluate how possible future socio‐economic developments may affect biodiversity. Here, we evaluated the changes in terrestrial biodiversity intactness, expressed by the mean species abundance (MSA) metric, resulting from three of the shared socio‐economic pathways (SSPs) combined with different levels of climate change (according to representative concentration pathways [RCPs]): a future oriented towards sustainability (SSP1xRCP2.6), a future determined by a politically divided world (SSP3xRCP6.0) and a future with continued global dependency on fossil fuels (SSP5xRCP8.5). To this end, we first updated the GLOBIO model, which now runs at a spatial resolution of 10 arc‐seconds (~300 m), contains new modules for downscaling land use and for quantifying impacts of hunting in the tropics, and updated modules to quantify impacts of climate change, land use, habitat fragmentation and nitrogen pollution. We then used the updated model to project terrestrial biodiversity intactness from 2015 to 2050 as a function of land use and climate changes corresponding with the selected scenarios. We estimated a global area‐weighted mean MSA of 0.56 for 2015. Biodiversity intactness declined in all three scenarios, yet the decline was smaller in the sustainability scenario (−0.02) than the regional rivalry and fossil‐fuelled development scenarios (−0.06 and −0.05 respectively). We further found considerable variation in projected biodiversity change among different world regions, with large future losses particularly for sub‐Saharan Africa. In some scenario‐region combinations, we projected future biodiversity recovery due to reduced demands for agricultural land, yet this recovery was counteracted by increased impacts of other pressures (notably climate change and road disturbance). Effective measures to halt or reverse the decline of terrestrial biodiversity should not only reduce land demand (e.g. by increasing agricultural productivity and dietary changes) but also focus on reducing or mitigating the impacts of other pressures.

Development of a Concussion Risk Function for a Youth Population Using Head Linear and Rotational Acceleration - Eamon T. Campolettano; Ryan A. Gellner; Eric P. Smith; Srinidhi Bellamkonda; Casey T. Tierney; Joseph J. Crisco; Derek A. Jones; Mireille E. Kelley; Jillian E. Urban; Joel D. Stitzel; Amaris Genemaras; Jonathan G. Beckwith; et al. (Annals of Biomedical Engineering, 2020)
Physical differences between youth and adults, which include incomplete myelination, limited neck muscle development, and a higher head-body ratio in the youth population, likely contribute towards the increased susceptibility of youth to concussion. Previous research efforts have considered the biomechanics of concussion for adult populations, but these known age-related differences highlight the necessity of quantifying the risk of concussion for a youth population. This study adapted the previously developed Generalized Acceleration Model for Brian Injury Threshold (GAMBIT) that combines linear and rotational head acceleration to model the risk of concussion for a youth population with the Generalized Acceleration Model for Concussion in Youth (GAM-CY). Survival analysis was used in conjunction with head impact data collected during participation in youth football to model risk between individuals who sustained medically-diagnosed concussions ( n = 15). Receiver operator characteristic curves were generated for peak linear acceleration, peak rotational acceleration, and GAM-CY, all of which were observed to be better injury predictors than random guessing. GAM-CY was associated with an area under the curve of 0.89 (95% confidence interval: 0.82–0.95) when all head impacts experienced by the concussed players were considered. Concussion tolerance was observed to be lower for youth athletes, with average peak linear head acceleration of 62.4 ± 29.7 g compared to 102.5 ± 32.7 g for adults and average peak rotational head acceleration of 2609 ± 1591 rad/s 2 compared to 4412 ± 2326 rad/s 2 . These data provide further evidence of age-related differences in concussion tolerance and may be used for the development of youth-specific protective designs.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Frag SAD : A database of diversity and species abundance distributions from habitat fragments - Jonathan M. Chase; Mario Liebergesell; Alban Sagouis; Felix May; Shane A. Blowes; Åke Berg; Enrico Bernard; Berry J. Brosi; Marc W. Cadotte; Luis Cayuela; Adriano G. Chiarello; Jean‐Francois Cosson; et al. (Ecology, 2019)
Habitat destruction is the single greatest anthropogenic threat to biodiversity. Decades of research on this issue have led to the accumulation of hundreds of data sets comparing species assemblages in larger, intact, habitats to smaller, more fragmented, habitats. Despite this, little synthesis or consensus has been achieved, primarily because of non‐standardized sampling methodology and analyses of notoriously scale‐dependent response variables (i.e., species richness). To be able to compare and contrast the results of habitat fragmentation on species’ assemblages, it is necessary to have the underlying data on species abundances and sampling intensity, so that standardization can be achieved. To accomplish this, we systematically searched the literature for studies where abundances of species in assemblages (of any taxa) were sampled from many habitat patches that varied in size. From these, we extracted data from several studies, and contacted authors of studies where appropriate data were collected but not published, giving us 117 studies that compared species assemblages among habitat fragments that varied in area. Less than one‐half (41) of studies came from tropical forests of Central and South America, but there were many studies from temperate forests and grasslands from all continents except Antarctica. Fifty‐four of the studies were on invertebrates (mostly insects), but there were several studies on plants (15), birds (16), mammals (19), and reptiles and amphibians (13). We also collected qualitative information on the length of time since fragmentation. With data on total and relative abundances (and identities) of species, sampling effort, and affiliated meta‐data about the study sites, these data can be used to more definitively test hypotheses about the role of habitat fragmentation in altering patterns of biodiversity. There are no copyright restrictions. Please cite this data paper and the associated Dryad data set if the data are used in publications.

Genetically informed captive breeding of hybrids of an extinct species of Galapagos tortoise - Maud C. Quinzin; Jonathan Sandoval‐Castillo; Joshua M. Miller; Luciano B. Beheregaray; Michael A. Russello; Elizabeth A. Hunter; James P. Gibbs; Washington Tapia; Freddy Villalva; Adalgisa Caccone (Conservation Biology, 2019)
Hybridization poses a major challenge for species conservation because it threatens both genetic integrity and adaptive potential. Yet, hybridization can occasionally offer unprecedented opportunity for species recovery if the genome of an extinct taxon is present among living hybrids such that selective breeding could recapture it. We explored the design elements for establishing a captive‐breeding program for Galapagos tortoises ( Chelonoidis spp.) built around individuals with admixed ancestry involving an extinct species. The target individuals were hybrids between the extinct species from Floreana Island, C. niger , and an extant species, C. becki , which were recently found in the endemic range of C. becki , from Wolf Volcano on Isabela Island. We combined genotypic data from 35 tortoises with high ancestry from C. niger with forward‐in‐time simulations to explore captive breeding strategies that maximized overall genetic diversity and ancestry from C. niger while accommodating resource constraints, species biology, and the urgency to return tortoises to Floreana Island for facilitating ecosystem restoration. Overall genetic diversity was maximized when in the simulation tortoises were organized in relatively small breeding groups. Substantial amounts of the C. niger genome were captured despite limited resources available for selectively breeding tortoises in captivity. Genetic diversity was maximized when captive‐bred offspring were released to the wild rather than being used as additional breeders. Our results provide genetic‐based and practical guidance on the inclusion of hybrids with genomic representation from extinct taxa into species restoration programs and informs the ongoing debate on the value of hybrids in biodiversity conservation.

sFDvent: A global trait database for deep‐sea hydrothermal‐vent fauna - Abbie S. A. Chapman; Stace E. Beaulieu; Ana Colaço; Andrey V. Gebruk; Ana Hilario; Terue C. Kihara; Eva Ramirez‐Llodra; Jozée Sarrazin; Verena Tunnicliffe; Diva J. Amon; Maria C. Baker; Rachel E. Boschen‐Rose; et al. (Global Ecology and Biogeography, 2019)
Motivation Traits are increasingly being used to quantify global biodiversity patterns, with trait databases growing in size and number, across diverse taxa. Despite growing interest in a trait‐based approach to the biodiversity of the deep sea, where the impacts of human activities (including seabed mining) accelerate, there is no single repository for species traits for deep‐sea chemosynthesis‐based ecosystems, including hydrothermal vents. Using an international, collaborative approach, we have compiled the first global‐scale trait database for deep‐sea hydrothermal‐vent fauna – sFDvent ( s Div‐funded trait database for the F unctional D iversity of vent s). We formed a funded working group to select traits appropriate to: (a) capture the performance of vent species and their influence on ecosystem processes, and (b) compare trait‐based diversity in different ecosystems. Forty contributors, representing expertise across most known hydrothermal‐vent systems and taxa, scored species traits using online collaborative tools and shared workspaces. Here, we characterise the sFDvent database, describe our approach, and evaluate its scope. Finally, we compare the sFDvent database to similar databases from shallow‐marine and terrestrial ecosystems to highlight how the sFDvent database can inform cross‐ecosystem comparisons. We also make the sFDvent database publicly available online by assigning a persistent, unique DOI. Main types of variable contained Six hundred and forty‐six vent species names, associated location information (33 regions), and scores for 13 traits (in categories: community structure, generalist/specialist, geographic distribution, habitat use, life history, mobility, species associations, symbiont, and trophic structure). Contributor IDs, certainty scores, and references are also provided. Spatial location and grain Global coverage (grain size: ocean basin), spanning eight ocean basins, including vents on 12 mid‐ocean ridges and 6 back‐arc spreading centres. Time period and grain sFDvent includes information on deep‐sea vent species, and associated taxonomic updates, since they were first discovered in 1977. Time is not recorded. The database will be updated every 5 years. Major taxa and level of measurement Deep‐sea hydrothermal‐vent fauna with species‐level identification present or in progress. Software format .csv and MS Excel (.xlsx).

Shovelomics root traits assessed on the EURoot maize panel are highly heritable across environments but show low genotype-by-nitrogen interaction - Chantal A. Le Marié; Larry M. York; Alexandre Strigens; Marcos Malosetti; Karl-Heinz Camp; Silvia Giuliani; Jonathan P. Lynch; Andreas Hund (Euphytica, 2019)
The need for sustainable intensification of agriculture in the coming decades requires a reduction in nitrogen (N) fertilization. One opportunity to reduce N application rates without major losses in yield is breeding for nutrient efficient crops. A key parameter that influences nutrient uptake efficiency is the root system architecture (RSA). To explore the impact of N availability on RSA and to investigate the impact of the growth environment, a diverse set of 36 inbred dent maize lines crossed to the inbred flint line UH007 as a tester was evaluated for N-response over 2 years on three different sites. RSA was investigated by excavating and imaging of the root crowns followed by image analysis with REST software. Despite strong site and year effects, trait heritability was generally high. Root traits showing the greatest heritability (> 0.7) were the width of the root stock, indicative of the horizontal expansion, and the fill factor, a measure of the density of the root system. Heritabilities were in a similar range under high or low N application. Under N deficiency the root stock size decreased, the horizontal expansion decreased and the root stock became less dense. However, there was little differential response of the genotypes to low N availability. Thus, the assessed root traits were more constitutively expressed rather than showing genotype-specific plasticity to low N. In contrast, strong differences were observed for ‘stay green’ and silage yield, indicating that these highly heritable traits are good indicators for responsiveness to low N.

Comparison of Head Impact Exposure Between Concussed Football Athletes and Matched Controls: Evidence for a Possible Second Mechanism of Sport-Related Concussion - Brian D. Stemper; Alok S. Shah; Jaroslaw Harezlak; Steven Rowson; Jason P. Mihalik; Stefan M. Duma; Larry D. Riggen; Alison Brooks; Kenneth L. Cameron; Darren Campbell; John P. DiFiori; Christopher C. Giza; et al. (Annals of Biomedical Engineering, 2019)

Advancing Observation of Ocean Biogeochemistry, Biology, and Ecosystems With Cost-Effective in situ Sensing Technologies - Zhaohui Aleck Wang; Hassan Moustahfid; Amy V. Mueller; Anna P. M. Michel; Matthew Mowlem; Brian T. Glazer; T. Aran Mooney; William Michaels; Jonathan S. McQuillan; Julie C. Robidart; James Churchill; Marc Sourisseau; et al. (Frontiers in Marine Science, 2019)

Immune activity at the gut epithelium in the larval sea urchin - Katherine M. Buckley; Jonathan P. Rast (Cell and Tissue Research, 2019)

Proceedings of the fourth international molecular pathological epidemiology (MPE) meeting - Peter T. Campbell; Christine B. Ambrosone; Reiko Nishihara; Hugo J. W. L. Aerts; Melissa Bondy; Nilanjan Chatterjee; Montserrat Garcia-Closas; Marios Giannakis; Jeffrey A. Golden; Yujing J. Heng; N. Sertac Kip; Jill Koshiol; et al. (Cancer Causes & Control, 2019)

Taxonomy of the order Mononegavirales: update 2019 - Gaya K. Amarasinghe; María A. Ayllón; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Camila Chabi-Jesus; et al. (Archives of Virology, 2019)

The lasting biological signature of Pliocene tectonics: Reviewing the re‐routing of Australia's largest river drainage system - Jonathan M. Waters; Christopher P. Burridge; Dave Craw (Journal of Biogeography, 2019)
Aim Biological diversification can be substantially influenced by earth history. The links between biological and geological processes can be particularly tight for obligate freshwater biota. Here, we test for such links with respect to Pliocene shifts in drainage geometry of one of the Australia's largest river systems. Location Major rivers of south‐eastern Australia. Taxon Freshwater‐limited fishes and crayfish. Methods We synthesize recently published geological and freshwater phylogeographic data to elucidate the evolutionary history of south‐eastern Australia's major river drainages and their biotas. Results Recent data demonstrate how a major Pliocene drainage rearrangement event in the lower Murray‐Darling basin led to the evolution of a distinctive and “marooned” phylogeographic assemblage in the Glenelg and Wimmera drainages. Main conclusions Biological data from southern Australia illuminate the region's geological history, and vice versa. Our study highlights the persisting evolutionary effects of a major Pliocene drainage rearrangement. The lasting geological and biological preservation of such an ancient tectonic event is apparently facilitated by Australia's uniquely stable geological setting.

Trace elements in marine organisms of Magdalena Bay, Pacific Coast of Mexico: Bioaccumulation in a pristine environment - S. B. Sujitha; M. P. Jonathan; David Aurioles-Gamboa; Lorena Elizabeth Campos Villegas; Jimena Bohórquez-Herrera; Claudia J. Hernández-Camacho (Environmental Geochemistry and Health, 2019)

CAR T Cell Immunotherapy in Human and Veterinary Oncology: Changing the Odds Against Hematological Malignancies - Jonathan P. Mochel; Stephen C. Ekker; Chad M. Johannes; Albert E. Jergens; Karin Allenspach; Agnes Bourgois-Mochel; Michael Knouse; Sebastien Benzekry; Wesley Wierson; Amy K. LeBlanc; Saad S. Kenderian (The AAPS Journal, 2019)

Correction to: Widespread colonisation of Tanzanian catchments by introduced Oreochromis tilapia fishes: the legacy from decades of deliberate introduction - Asilatu Shechonge; Benjamin P. Ngatunga; Stephanie J. Bradbeer; Julia J. Day; Jennifer J. Freer; Antonia G. P. Ford; Jonathan Kihedu; Tabitha Richmond; Semvua Mzighani; Alan M. Smith; Emmanuel A. Sweke; Rashid Tamatamah; et al. (Hydrobiologia, 2019)

Widespread colonisation of Tanzanian catchments by introduced Oreochromis tilapia fishes: the legacy from decades of deliberate introduction - Asilatu Shechonge; Benjamin P. Ngatunga; Stephanie J. Bradbeer; Julia J. Day; Jennifer J. Freer; Antonia G. P. Ford; Jonathan Kihedu; Tabitha Richmond; Semvua Mzighani; Alan M. Smith; Emmanuel A. Sweke; Rashid Tamatamah; et al. (Hydrobiologia, 2019)

Cancer incidence in the Agricultural Health Study after 20 years of follow-up - Catherine C. Lerro; Stella Koutros; Gabriella Andreotti; Dale P. Sandler; Charles F. Lynch; Lydia M. Louis; Aaron Blair; Christine G. Parks; Srishti Shrestha; Jay H. Lubin; Paul S. Albert; Jonathan N. Hofmann; et al. (Cancer Causes & Control, 2019)

Taxonomy of the order Mononegavirales: second update 2018 - Piet Maes; Gaya K. Amarasinghe; María A. Ayllón; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Kartik Chandran; et al. (Archives of Virology, 2019)

UNVEILing connections between genotype, phenotype, and fitness in natural populations - Thomas C. Nelson; Matthew R. Jones; Jonathan P. Velotta; Abhilesh S. Dhawanjewar; Rena M. Schweizer (Molecular Ecology, 2019)
Understanding the links between genetic variation and fitness in natural populations is a central goal of evolutionary genetics. This monumental task spans the fields of classical and molecular genetics, population genetics, biochemistry, physiology, developmental biology, and ecology. Advances to our molecular and developmental toolkits are facilitating integrative approaches across these traditionally separate fields, providing a more complete picture of the genotype‐phenotype map in natural and non‐model systems. Here, we summarize research presented at the first annual symposium of the UNVEIL Network, an NSF‐funded collaboration between the University of Montana and the University of Nebraska, Lincoln, which took place from the 1st to the 3rd of June, 2018. We discuss how this body of work advances basic evolutionary science, what it implies for our ability to predict evolutionary change, and how it might inform novel conservation strategies.

Better Regional Ocean Observing Through Cross-National Cooperation: A Case Study From the Northeast Pacific - John A. Barth; Susan E. Allen; Edward P. Dever; Richard K. Dewey; Wiley Evans; Richard A. Feely; Jennifer L. Fisher; Jonathan P. Fram; Burke Hales; Debby Ianson; Jennifer Jackson; Kim Juniper; et al. (Frontiers in Marine Science, 2019)

Heavy metals in the volcanic and peri-urban terrain watershed of the River Yautepec, Mexico - Silvia Viridiana Vargas-Solano; Francisco Rodríguez-González; Martha Lucia Arenas-Ocampo; Rita Martínez-Velarde; S. B. Sujitha; M. P. Jonathan (Environmental Monitoring and Assessment, 2019)

Identifying pre-spawning aggregation sites for bonefish (Albula vulpes) in the Bahamas to inform habitat protection and species conservation - Aaron J. Adams; Jonathan M. Shenker; Zachary R. Jud; Justin P. Lewis; Eric Carey; Andy J. Danylchuk (Environmental Biology of Fishes, 2019)

Global climatology of planetary boundary layer top obtained from multi-satellite GPS RO observations - Ghouse Basha; P. Kishore; M. Venkat Ratnam; S. Ravindra Babu; Isabella Velicogna; Jonathan H. Jiang; Chi O. Ao (Climate Dynamics, 2019)

Lessons Learned From the United States Ocean Observatories Initiative - Leslie M. Smith; Kristen Yarincik; Liana Vaccari; Maxwell B. Kaplan; John A. Barth; Geoffrey S. Cram; Jonathan P. Fram; Michael Harrington; Orest E. Kawka; Deborah S. Kelley; Paul Matthias; Kristopher Newhall; et al. (Frontiers in Marine Science, 2019)

Time-trial performance is not impaired in either competitive athletes or untrained individuals following a prolonged cognitive task - Ida E. Clark; Richie P. Goulding; Fred J. DiMenna; Stephen J. Bailey; Martin I. Jones; Jonathan Fulford; Sinead T. J. McDonagh; Andrew M. Jones; Anni Vanhatalo (European Journal of Applied Physiology, 2019)

Unidirectional monosynaptic connections from auditory areas to the primary visual cortex in the marmoset monkey - Piotr Majka; Marcello G. P. Rosa; Shi Bai; Jonathan M. Chan; Bing-Xing Huo; Natalia Jermakow; Meng K. Lin; Yeonsook S. Takahashi; Ianina H. Wolkowicz; Katrina H. Worthy; Ramesh Rajan; David H. Reser; et al. (Brain Structure and Function, 2019)

UCYN‐A3, a newly characterized open ocean sublineage of the symbiotic N 2 ‐fixing cyanobacterium Candidatus Atelocyanobacterium thalassa - Francisco M. Cornejo‐Castillo; Maria del Carmen Muñoz‐Marín; Kendra A. Turk‐Kubo; Marta Royo‐Llonch; Hanna Farnelid; Silvia G. Acinas; Jonathan P. Zehr (Environmental Microbiology, 2019)
Summary The symbiotic unicellular cyanobacterium Candidatus Atelocyanobacterium thalassa (UCYN‐A) is one of the most abundant and widespread nitrogen (N 2 )‐fixing cyanobacteria in the ocean. Although it remains uncultivated, multiple sublineages have been detected based on partial nitrogenase ( nifH ) gene sequences, including the four most commonly detected sublineages UCYN‐A1, UCYN‐A2, UCYN‐A3 and UCYN‐A4. However, very little is known about UCYN‐A3 beyond the nifH sequences from nifH gene diversity surveys. In this study, single cell sorting, DNA sequencing, qPCR and CARD‐FISH assays revealed discrepancies involving the identification of sublineages, which led to new information on the diversity of the UCYN‐A symbiosis. 16S rRNA and nifH gene sequencing on single sorted cells allowed us to identify the 16S rRNA gene of the uncharacterized UCYN‐A3 sublineage. We designed new CARD‐FISH probes that allowed us to distinguish and observe UCYN‐A2 in a coastal location (SIO Pier; San Diego) and UCYN‐A3 in an open ocean location (Station ALOHA; Hawaii). Moreover, we reconstructed about 13% of the UCYN‐A3 genome from Tara Oceans metagenomic data. Finally, our findings unveil the UCYN‐A3 symbiosis in open ocean waters suggesting that the different UCYN‐A sublineages are distributed along different size fractions of the plankton defined by the cell‐size ranges of their prymnesiophyte hosts.

Future Research Directions on the “Elusive” White Shark - Charlie Huveneers; Kirin Apps; Edgar E. Becerril-García; Barry Bruce; Paul A. Butcher; Aaron B. Carlisle; Taylor K. Chapple; Heather M. Christiansen; Geremy Cliff; Tobey H. Curtis; Toby S. Daly-Engel; Heidi Dewar; et al. (Frontiers in Marine Science, 2018)

Leveraging Big Data Towards Functionally-Based, Catchment Scale Restoration Prioritization - John P. Lovette; Jonathan M. Duncan; Lindsey S. Smart; John P. Fay; Lydia P. Olander; Dean L. Urban; Nancy Daly; Jamie Blackwell; Anne B. Hoos; Ana María García; Lawrence E. Band (Environmental Management, 2018)

Demographic, clinical and lifestyle factors associated with high-intensity statin therapy in Australia: the AusDiab study - Karen Ho; Kris M. Jamsen; J. Simon Bell; Maarit Jaana Korhonen; Kevin P. Mc Namara; Dianna J. Magliano; Danny Liew; Taliesin E. Ryan-Atwood; Jonathan E. Shaw; Susan Luc; Jenni Ilomäki (European Journal of Clinical Pharmacology, 2018)

Brood‐tending males in a biparental fish suffer high paternity losses but rarely cuckold - Aneesh P. H. Bose; Holger Zimmermann; Jonathan M. Henshaw; Karoline Fritzsche; Kristina M. Sefc (Molecular Ecology, 2018)
Extra‐pair paternity within socially monogamous mating systems is well studied in birds and mammals but rather neglected in other animal taxa. In fishes, social monogamy has evolved several times but few studies have investigated the extent to which pair‐bonded male fish lose fertilizations to cuckolders and gain extra‐pair fertilizations themselves. We address this gap and present genetic paternity data collected from a wild population of Variabilichromis moorii , a socially monogamous African cichlid with biparental care of offspring. We show that brood‐tending, pair‐bonded males suffer exceptionally high paternity losses, siring only 63% of the offspring produced by their female partners on average. The number of cuckolders per brood ranged up to nine and yet, surprisingly, brood‐tending males in the population were rarely the culprits. Brood‐tending males sired very few extra‐pair offspring, despite breeding in close proximity to one another. While unpaired males were largely responsible for the cuckoldry, pair‐bonded males still enjoyed higher fertilization success than individual unpaired males. We discuss these results in the context of ecological and phenotypic constraints on cuckoldry and the fitness payoffs of alternative male tactics. Our study provides new insights into how pair‐bonded males handle the trade‐off between securing within‐pair and extra‐pair reproduction.

Inundation of a floodplain lake woodlands system: nutritional profiling and benefit to mature Eucalyptus largiflorens (Black Box) trees - Denise R. Fernando; Jonathan P. Lynch; Suzie M. Reichman; Gary J. Clark; Rebecca E. Miller; Tanya M. Doody (Wetlands Ecology and Management, 2018)

Rhenium and technetium complexes of thioamide derivatives of pyridylhydrazine that bind to amyloid-β plaques - Scott P. Fletcher; Asif Noor; James L. Hickey; Catriona A. McLean; Jonathan M. White; Paul S. Donnelly (JBIC Journal of Biological Inorganic Chemistry, 2018)

Characterisation of porcine epidemic diarrhea virus isolates during the 2014–2015 outbreak in the Philippines - Gemerlyn G. Garcia; Mark Arman D. Aquino; Michelle M. Balbin; Lawrence P. Belotindos; Jonathan G. Supnet; Claro N. Mingala (VirusDisease, 2018)

Flood resilience: consolidating knowledge between and within critical infrastructure sectors - Jonathan Pearson; G. Punzo; M. Mayfield; G. Brighty; A. Parsons; P. Collins; S. Jeavons; A. Tagg (Environment Systems and Decisions, 2018)

Efficient Computational Modeling of Human Ventricular Activation and Its Electrocardiographic Representation: A Sensitivity Study - Jonathan P. Cranford; Thomas J. O’Hara; Christopher T. Villongco; Omar M. Hafez; Robert C. Blake; Joseph Loscalzo; Jean-Luc Fattebert; David F. Richards; Xiaohua Zhang; James N. Glosli; Andrew D. McCulloch; David E. Krummen; et al. (Cardiovascular Engineering and Technology, 2018)

Cross-education does not accelerate the rehabilitation of neuromuscular functions after ACL reconstruction: a randomized controlled clinical trial - Tjerk Zult; Alli Gokeler; Jos J. A. M. van Raay; Reinoud W. Brouwer; Inge Zijdewind; Jonathan P. Farthing; Tibor Hortobágyi (European Journal of Applied Physiology, 2018)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Consensus guidelines for the use and interpretation of angiogenesis assays - Patrycja Nowak-Sliwinska; Kari Alitalo; Elizabeth Allen; Andrey Anisimov; Alfred C. Aplin; Robert Auerbach; Hellmut G. Augustin; David O. Bates; Judy R. van Beijnum; R. Hugh F. Bender; Gabriele Bergers; Andreas Bikfalvi; et al. (Angiogenesis, 2018)

A guano‐derived δ 13 C and δ 15 N record of climate since the Medieval Warm Period in north‐west Romania - Daniel M. Cleary; Bogdan P. Onac; Ioan Tanţău; Ferenc L. Forray; Jonathan G. Wynn; Monica Ionita; Tudor Tămaş (Journal of Quaternary Science, 2018)
A 285‐cm core of bat guano was recovered from Măgurici Cave in north‐west Romania and analyzed for δ 13 C, δ 15 N and pollen. Guano deposition occurred from AD 881 until 1240 and from AD 1651 to 2013, allowing for the interpretation of summer variations in precipitation and temperature during the Medieval Warm Period (MWP) and the Little Ice Age (LIA). A 2‰ increase in δ 13 C, 1.5‰ decrease in δ 15 N, and the presence of Ulmus , Quercus and Carpinus betulus indicate a warm and dry MWP occurred in the region. The lack of deposition during the beginning of the LIA suggests a possible climate‐induced change in prey availability resulting in bats vacating the cave. Variation of δ 13 C values between −25 and −23‰ at AD 1650 (LIA) indicates similar drier conditions as at the end of MWP. However, a 2‰ decrease in δ 13 C values that occurred between AD 1790 and 1900 suggests climate was trending towards wetter conditions at the end of the LIA. From AD 1938 to 2013, δ 13 C values appear to be more influenced by temperature, indicating that this parameter had a more significant effect on carbon discrimination than water availability.

Distance, elevation and environment as drivers of diversity and divergence in bumble bees across latitude and altitude - Jason M. Jackson; Meaghan L. Pimsler; Kennan Jeannet Oyen; Jonathan B. Koch‐Uhuad; James D. Herndon; James P. Strange; Michael E. Dillon; Jeffrey D. Lozier (Molecular Ecology, 2018)
Identifying drivers of dispersal limitation and genetic differentiation is a key goal in biogeography. We examine patterns of population connectivity and genetic diversity using restriction site‐associated DNA sequencing ( RAD seq) in two bumble bee species, Bombus vosnesenskii and Bombus bifarius, across latitude and altitude in mountain ranges from California, Oregon and Washington, U.S.A. Bombus vosnesenskii , which occurs across a broader elevational range at most latitudes, exhibits little population structure while B. bifarius , which occupies a relatively narrow higher elevation niche across most latitudes, exhibits much stronger population differentiation, although gene flow in both species is best explained by isolation with environmental niche resistance. A relationship between elevational habitat breadth and genetic diversity is also apparent, with B. vosnesenskii exhibiting relatively consistent levels of genetic diversity across its range, while B. bifarius has reduced genetic diversity at low latitudes, where it is restricted to high‐elevation habitat. The results of this study highlight the importance of the intersect between elevational range and habitat suitability in influencing population connectivity and suggest that future climate warming will have a fragmenting effect even on populations that are presently well connected, as they track their thermal niches upward in montane systems.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

The effect of aerobic walking and lower body resistance exercise on serum COMP and hyaluronan, in both males and females - Harry M. Roberts; Jonathan P. Moore; Jeanette M. Thom (European Journal of Applied Physiology, 2018)

Experimental Detritus Manipulations Unite Surface and Cave Stream Ecosystems Along a Common Energy Gradient - Michael P. Venarsky; Jonathan P. Benstead; Alexander D. Huryn; Brock M. Huntsman; Jennifer W. Edmonds; Robert H. Findlay; J. Bruce Wallace (Ecosystems, 2018)

Estimated Brain Tissue Response Following Impacts Associated With and Without Diagnosed Concussion - Jonathan G. Beckwith; Wei Zhao; Songbai Ji; Amaris G. Ajamil; Richard P. Bolander; Jeffrey J. Chu; Thomas W. McAllister; Joseph J. Crisco; Stefan M. Duma; Steven Rowson; Steven P. Broglio; Kevin M. Guskiewicz; et al. (Annals of Biomedical Engineering, 2018)

Biogeographic patterns of communities across diverse marine ecosystems in southern California - Jeremy T. Claisse; Carol A. Blanchette; Jenifer E. Dugan; Jonathan P. Williams; Jan Freiwald; Daniel J. Pondella; Nicholas K. Schooler; David M. Hubbard; Kathryn Davis; Laurel A. Zahn; Chelsea M. Williams; Jennifer E. Caselle (Marine Ecology, 2018)
Integrating results from monitoring efforts conducted across diverse marine ecosystems provides opportunities to reveal novel biogeographic patterns at larger spatial scales and among multiple taxonomic groups. We investigated large‐scale patterns of community similarity across major taxonomic groups (invertebrates, fishes or algae) from a range of marine ecosystems (rocky intertidal, sandy intertidal, kelp forest, shallow and deep soft‐bottom subtidal) in southern California. Because monitoring sites and methods varied among programs, site data were averaged over larger geographic regions to facilitate comparisons. For the majority of individual community types, locations that were geographically near or environmentally similar to one another tended to have more similar communities. However, our analysis found that this pattern of within community type similarity did not result in all pairs of these community types exhibiting high levels of cross‐community congruence. Rocky intertidal algae communities had high levels of congruence with the spatial patterns observed for almost all of the other (fish or invertebrate) community types. This was not surprising given algal distributions are known to be highly influenced by bottom‐up factors and they are important as food and habitat for marine fishes and invertebrates. However, relatively few pairwise comparisons of the spatial patterns between a fish community and an invertebrate community yielded significant correlations. These community types are generally comprised of assemblages of higher trophic level species, and additional ecological and anthropogenic factors may have altered their spatial patterns of community similarity. In most cases pairs of invertebrate community types and pairs of fish community types exhibited similar spatial patterns, although there were some notable exceptions. These findings have important implications for the design and interpretation of results of long‐term monitoring programs.

Combining abundance and performance data reveals how temperature regulates coastal occurrences and activity of a roaming apex predator - Nicholas L. Payne; Carl G. Meyer; James A. Smith; Jonathan D. R. Houghton; Adam Barnett; Bonnie J. Holmes; Itsumi Nakamura; Yannis P. Papastamatiou; Mark A. Royer; Daniel M. Coffey; James M. Anderson; Melanie R. Hutchinson; et al. (Global Change Biology, 2018)
The redistribution of species has emerged as one of the most pervasive impacts of anthropogenic climate warming, and presents many societal challenges. Understanding how temperature regulates species distributions is particularly important for mobile marine fauna such as sharks given their seemingly rapid responses to warming, and the socio‐political implications of human encounters with some dangerous species. The predictability of species distributions can potentially be improved by accounting for temperature's influence on performance, an elusive relationship for most large animals. We combined multi‐decadal catch data and bio‐logging to show that coastal abundance and swimming performance of tiger sharks Galeocerdo cuvier are both highest at ~22°C, suggesting thermal constraints on performance may regulate this species' distribution. Tiger sharks are responsible for a large proportion of shark bites on humans, and a focus of controversial control measures in several countries. The combination of distribution and performance data moves towards a mechanistic understanding of tiger shark's thermal niche, and delivers a simple yet powerful indicator for predicting the location and timing of their occurrences throughout coastlines. For example, tiger sharks are mostly caught at Australia's popular New South Wales beaches (i.e. near Sydney) in the warmest months, but our data suggest similar abundances will occur in winter and summer if annual sea surface temperatures increase by a further 1–2°C.

Erratum to: The Development of Translational Biomarkers as a Tool for Improving the Understanding, Diagnosis and Treatment of Chronic Neuropathic Pain - David A. Buckley; Elaine M. Jennings; Nikita N. Burke; Michelle Roche; Veronica McInerney; Jonathan D. Wren; David P. Finn; Patrick C. McHugh (Molecular Neurobiology, 2018)

The Development of Translational Biomarkers as a Tool for Improving the Understanding, Diagnosis and Treatment of Chronic Neuropathic Pain - David A. Buckley; Elaine M. Jennings; Nikita N. Burke; Michelle Roche; Veronica McInerney; Jonathan D. Wren; David P. Finn; Patrick C. McHugh (Molecular Neurobiology, 2018)

Increased resource use efficiency amplifies positive response of aquatic primary production to experimental warming - James M. Hood; Jonathan P. Benstead; Wyatt F. Cross; Alexander D. Huryn; Philip W. Johnson; Gísli M. Gíslason; James R. Junker; Daniel Nelson; Jón S. Ólafsson; Chau Tran (Global Change Biology, 2018)
Climate warming is affecting the structure and function of river ecosystems, including their role in transforming and transporting carbon (C), nitrogen (N), and phosphorus (P). Predicting how river ecosystems respond to warming has been hindered by a dearth of information about how otherwise well‐studied physiological responses to temperature scale from organismal to ecosystem levels. We conducted an ecosystem‐level temperature manipulation to quantify how coupling of stream ecosystem metabolism and nutrient uptake responded to a realistic warming scenario. A ~3.3°C increase in mean water temperature altered coupling of C, N, and P fluxes in ways inconsistent with single‐species laboratory experiments. Net primary production tripled during the year of experimental warming, while whole‐stream N and P uptake rates did not change, resulting in 289% and 281% increases in autotrophic dissolved inorganic N and P use efficiency ( UE ), respectively. Increased ecosystem production was a product of unexpectedly large increases in mass‐specific net primary production and autotroph biomass, supported by (i) combined increases in resource availability (via N mineralization and N 2 fixation) and (ii) elevated resource use efficiency, the latter associated with changes in community structure. These large changes in C and nutrient cycling could not have been predicted from the physiological effects of temperature alone. Our experiment provides clear ecosystem‐level evidence that warming can shift the balance between C and nutrient cycling in rivers, demonstrating that warming will alter the important role of in‐stream processes in C, N, and P transformations. Moreover, our results reveal a key role for nutrient supply and use efficiency in mediating responses of primary producers to climate warming.

Size, growth, and density data for shallow‐water sea urchins from Mexico to the Aleutian Islands, Alaska, 1956–2016 - Thomas A. Ebert; Louis M. Barr; James L. Bodkin; Dirk Burcham; Dominique Bureau; Henry S. Carson; Nancy L. Caruso; Jennifer E. Caselle; Jeremy T. Claisse; Sabrina Clemente; Kathryn Davis; Paul M. Detwiler; et al. (Ecology, 2018)
Size, growth, and density have been studied for North American Pacific coast sea urchins Strongylocentrotus purpuratus , S. droebachiensis, S. polyacanthus , Mesocentrotus (Strongylocentrotus) franciscanus , Lytechinus pictus , Centrostephanus coronatus , and Arbacia stellata by various workers at diverse sites and for varying lengths of time from 1956 to present. Numerous peer‐reviewed publications have used some of these data but some data have appeared only in graduate theses or the gray literature. There also are data that have never appeared outside original data sheets. Motivation for studies has included fisheries management and environmental monitoring of sewer and power plant outfalls as well as changes associated with disease epidemics. Studies also have focused on kelp restoration, community effects of sea otters, basic sea urchin biology, and monitoring. The data sets presented here are a historical record of size, density, and growth for a common group of marine invertebrates in intertidal and nearshore environments that can be used to test hypotheses concerning future changes associated with fisheries practices, shifts of predator distributions, climate and ecosystem changes, and ocean acidification along the Pacific Coast of North America and islands of the north Pacific. No copyright restrictions apply. Please credit this paper when using the data.

Functional implications of root cortical senescence for soil resource capture - Hannah M. Schneider; Jonathan P. Lynch (Plant and Soil, 2018)

Pollution evaluation of total and acid-leachable trace elements in surface sediments of Hooghly River Estuary and Sundarban Mangrove Wetland (India) - Priyanka Mondal; Amanda J. Reichelt-Brushett; M. P. Jonathan; S. B. Sujitha; Santosh Kumar Sarkar (Environmental Science and Pollution Research, 2018)

Litter P content drives consumer production in detritus‐based streams spanning an experimental N:P gradient - Lee M. Demi; Jonathan P. Benstead; Amy D. Rosemond; John C. Maerz (Ecology, 2018)
Ecological stoichiometry theory ( EST ) is a key framework for predicting how variation in N:P supply ratios influences biological processes, at molecular to ecosystem scales, by altering the availability of C, N, and P relative to organismal requirements. We tested EST predictions by fertilizing five forest streams at different dissolved molar N:P ratios (2, 8, 16, 32, 128) for two years and tracking responses of macroinvertebrate consumers to the resulting steep experimental gradient in basal resource stoichiometry (leaf litter %N, %P, and N:P). Nitrogen and P content of leaf litter, the dominant basal resource, increased in all five streams following enrichment, with steepest responses in litter %P and N:P ratio. Additionally, increases in primary consumer biomass and production occurred in all five streams following N and P enrichment (averages across all streams: biomass by 1.2×, production by 1.6×). Patterns of both biomass and production were best predicted by leaf litter N:P and %P and were unrelated to leaf litter %N. Primary consumer production increased most in streams where decreases in leaf litter N:P were largest. Macroinvertebrate predator biomass and production were also strongly positively related to litter %P, providing robust experimental evidence for the primacy of P limitation at multiple trophic levels in these ecosystems. However, production of predatory macroinvertebrates was not related directly to primary consumer production, suggesting the importance of additional controls for macroinvertebrates at upper trophic positions. Our results reveal potential drivers of animal production in detritus‐based ecosystems, including the relative importance of resource quality vs. quantity. Our study also sheds light on the more general impacts of variation in N:P supply ratio on nutrient‐poor ecosystems, providing strong empirical support for predictions that nutrient enrichment increases food web productivity whenever large elemental imbalances between basal resources and consumer demand are reduced.

Sensor manufacturer, temperature, and cyanobacteria morphology affect phycocyanin fluorescence measurements - Caroline M. Hodges; Susanna A. Wood; Jonathan Puddick; Christopher G. McBride; David P. Hamilton (Environmental Science and Pollution Research, 2018)

Re‐evaluation of MIS 3 glaciation using cosmogenic radionuclide and single grain luminescence ages, Kanas Valley, Chinese Altai - Natacha Gribenski; Krister N. Jansson; Frank Preusser; Jonathan M. Harbor; Arjen P. Stroeven; Mareike Trauerstein; Robin Blomdin; Jakob Heyman; Marc W. Caffee; Nathaniel A. Lifton; Wei Zhang (Journal of Quaternary Science, 2018)
Previous investigations observed a period of major glacial advances in Central Asia during marine oxygen isotope stage (MIS) 3 (57–29 ka), out of phase with global ice volume records. We have re‐examined the Kanas moraine complex in the Altai Mountains of Central Asia, where an MIS 3 glaciation had been previously inferred. New and consistent cosmogenic exposure and single‐grain luminescence ages indicate that the Kanas complex was formed during MIS 2 (29–12 ka), which brings its timing in line with the global ice volume record. We also identified a lateral moraine from a more extensive ice extent that dates to late MIS 5/MIS 4. To place our results in a wider contextual framework, we review the chronologies of another 26 proposed major MIS 3 glacial advances in Central Asia. For most of these sites, we find that the chronological data do not provide an unequivocal case for MIS 3 glaciation.

Kaiso is highly expressed in TNBC tissues of women of African ancestry compared to Caucasian women - Blessing I. Bassey-Archibong; Shawn M. Hercules; Lyndsay G. A. Rayner; Desiree H. A. Skeete; Suzanne P. Smith Connell; Ian Brain; Adetola Daramola; Adekunbiola A. F. Banjo; Jung S. Byun; Kevin Gardner; Jonathan Dushoff; Juliet M. Daniel (Cancer Causes & Control, 2017)

Ecological regime shift drives declining growth rates of sea turtles throughout the West Atlantic - Karen A. Bjorndal; Alan B. Bolten; Milani Chaloupka; Vincent S. Saba; Cláudio Bellini; Maria A. G. Marcovaldi; Armando J. B. Santos; Luis Felipe Wurdig Bortolon; Anne B. Meylan; Peter A. Meylan; Jennifer Gray; Robert Hardy; et al. (Global Change Biology, 2017)
Somatic growth is an integrated, individual‐based response to environmental conditions, especially in ectotherms. Growth dynamics of large, mobile animals are particularly useful as bio‐indicators of environmental change at regional scales. We assembled growth rate data from throughout the West Atlantic for green turtles, Chelonia mydas , which are long‐lived, highly migratory, primarily herbivorous mega‐consumers that may migrate over hundreds to thousands of kilometers. Our dataset, the largest ever compiled for sea turtles, has 9690 growth increments from 30 sites from Bermuda to Uruguay from 1973 to 2015. Using generalized additive mixed models, we evaluated covariates that could affect growth rates; body size, diet, and year have significant effects on growth. Growth increases in early years until 1999, then declines by 26% to 2015. The temporal (year) effect is of particular interest because two carnivorous species of sea turtles—hawksbills, Eretmochelys imbricata, and loggerheads, Caretta caretta —exhibited similar significant declines in growth rates starting in 1997 in the West Atlantic, based on previous studies. These synchronous declines in productivity among three sea turtle species across a trophic spectrum provide strong evidence that an ecological regime shift ( ERS ) in the Atlantic is driving growth dynamics. The ERS resulted from a synergy of the 1997/1998 El Niño Southern Oscillation ( ENSO )—the strongest on record—combined with an unprecedented warming rate over the last two to three decades. Further support is provided by the strong correlations between annualized mean growth rates of green turtles and both sea surface temperatures ( SST ) in the West Atlantic for years of declining growth rates ( r = −.94) and the Multivariate ENSO Index ( MEI ) for all years ( r = .74). Granger‐causality analysis also supports the latter finding. We discuss multiple stressors that could reinforce and prolong the effect of the ERS . This study demonstrates the importance of region‐wide collaborations.

Diversity and activity of nitrogen‐fixing communities across ocean basins - Mary R. Gradoville; Deniz Bombar; Byron C. Crump; Ricardo M. Letelier; Jonathan P. Zehr; Angelicque E. White (Limnology and Oceanography, 2017)
Recent observations of N 2 fixation rates (NFR) and the presence of nitrogenase ( nifH ) genes from heterotrophic N 2 ‐fixing (diazotrophic) prokaryotes in unusual habitats challenge the paradigm that pelagic marine N 2 fixation is constrained to cyanobacteria in warm, oligotrophic, surface waters. Here, we compare NFR and diazotrophic diversity (assessed via high‐throughput nifH sequencing) from a region known to be dominated by cyanobacterial diazotrophs (the North Pacific Subtropical Gyre, NPSG) to two regions dominated by heterotrophic diazotrophs: the Eastern South Pacific (ESP, from the Chilean upwelling system to the subtropical gyre) and the Pacific Northwest coastal upwelling system (PNW). We observed distinct biogeographical patterns among the three regions. Diazotrophic community structure differed strongly between the NPSG, dominated by cyanobacterium UCYN‐A, and the ESP, dominated by heterotrophic nifH group 1J/1K, yet surface NFR were similar in magnitude (up to 5.1 nmol N L −1 d −1 ). However, while diverse, predominantly heterotrophic nifH genes were recovered from the PNW and the mesopelagic of the NPSG, NFR were undetectable in both of these environments (although glucose amendments stimulated low rates in the deep NPSG). Our work suggests that while diazotrophs may be nearly omnipresent in marine waters, the activity of this functional group is regionally restricted. Further, we show that the detection limits of the 15 N 2 fixation assay suggest that many of the low NFR reported for the mesopelagic (often −1 d −1 in the literature) are not indicative of active diazotrophy, highlighting the challenges of assessing the ecosystem significance of heterotrophic diazotrophs.

Exposure to predators reduces collective foraging aggressiveness and eliminates its relationship with colony personality composition - Colin M. Wright; James L. L. Lichtenstein; Graham A. Montgomery; Lauren P. Luscuskie; Noa Pinter-Wollman; Jonathan N. Pruitt (Behavioral Ecology and Sociobiology, 2017)

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Symbiont strain is the main determinant of variation in Wolbachia ‐mediated protection against viruses across Drosophila species - Julien Martinez; Ignacio Tolosana; Suzan Ok; Sophie Smith; Kiana Snoeck; Jonathan P. Day; Francis M. Jiggins (Molecular Ecology, 2017)
Wolbachia is a common heritable bacterial symbiont in insects. Its evolutionary success lies in the diverse phenotypic effects it has on its hosts coupled to its propensity to move between host species over evolutionary timescales. In a survey of natural host–symbiont associations in a range of Drosophila species, we found that 10 of 16 Wolbachia strains protected their hosts against viral infection. By moving Wolbachia strains between host species, we found that the symbiont genome had a much greater influence on the level of antiviral protection than the host genome. The reason for this was that the level of protection depended on the density of the symbiont in host tissues, and Wolbachia rather than the host‐controlled density. The finding that virus resistance and symbiont density are largely under the control of symbiont genes in this system has important implications both for the evolution of these traits and for public health programmes using Wolbachia to prevent mosquitoes from transmitting disease.

Circulating levels of obesity-related markers and risk of renal cell carcinoma in the PLCO cancer screening trial - Linda M. Liao; Jonathan N. Hofmann; Eunyoung Cho; Michael N. Pollak; Wong-Ho Chow; Mark P. Purdue (Cancer Causes & Control, 2017)

Experimental whole‐stream warming alters community size structure - Daniel Nelson; Jonathan P. Benstead; Alexander D. Huryn; Wyatt F. Cross; James M. Hood; Philip W. Johnson; James R. Junker; Gísli M. Gíslason; Jón S. Ólafsson (Global Change Biology, 2017)
How ecological communities respond to predicted increases in temperature will determine the extent to which Earth's biodiversity and ecosystem functioning can be maintained into a warmer future. Warming is predicted to alter the structure of natural communities, but robust tests of such predictions require appropriate large‐scale manipulations of intact, natural habitat that is open to dispersal processes via exchange with regional species pools. Here, we report results of a two‐year whole‐stream warming experiment that shifted invertebrate assemblage structure via unanticipated mechanisms, while still conforming to community‐level metabolic theory. While warming by 3.8 °C decreased invertebrate abundance in the experimental stream by 60% relative to a reference stream, total invertebrate biomass was unchanged. Associated shifts in invertebrate assemblage structure were driven by the arrival of new taxa and a higher proportion of large, warm‐adapted species (i.e., snails and predatory dipterans) relative to small‐bodied, cold‐adapted taxa (e.g., chironomids and oligochaetes). Experimental warming consequently shifted assemblage size spectra in ways that were unexpected, but consistent with thermal optima of taxa in the regional species pool. Higher temperatures increased community‐level energy demand, which was presumably satisfied by higher primary production after warming. Our experiment demonstrates how warming reassembles communities within the constraints of energy supply via regional exchange of species that differ in thermal physiological traits. Similar responses will likely mediate impacts of anthropogenic warming on biodiversity and ecosystem function across all ecological communities.

Shifts in community size structure drive temperature invariance of secondary production in a stream‐warming experiment - Daniel Nelson; Jonathan P. Benstead; Alexander D. Huryn; Wyatt F. Cross; James M. Hood; Philip W. Johnson; James R. Junker; Gísli M. Gíslason; Jón S. Ólafsson (Ecology, 2017)
A central question at the interface of food‐web and climate change research is how secondary production, or the formation of heterotroph biomass over time, will respond to rising temperatures. The metabolic theory of ecology ( MTE ) hypothesizes the temperature‐invariance of secondary production, driven by matched and opposed forces that reduce biomass of heterotrophs while increasing their biomass turnover rate (production : biomass, or P : B ) with warming. To test this prediction at the whole community level, we used a geothermal heat exchanger to experimentally warm a stream in southwest Iceland by 3.8°C for two years. We quantified invertebrate community biomass, production, and P : B in the experimental stream and a reference stream for one year prior to warming and two years during warming. As predicted, warming had a neutral effect on community production, but this result was not driven by opposing effects on community biomass and P : B . Instead, warming had a positive effect on both the biomass and production of larger‐bodied, slower‐growing taxa (e.g., larval black flies, dipteran predators, snails) and a negative effect on small‐bodied taxa with relatively high growth rates (e.g., ostracods, larval chironomids). We attribute these divergent responses to differences in thermal preference between small‐ vs. large‐bodied taxa. Although metabolic demand vs. resource supply must ultimately constrain community production, our results highlight the potential for idiosyncratic community responses to warming, driven by variation in thermal preference and body size within regional species pools.

Taking the Circularity to the Next Level: A Special Issue on the Circular Economy - Nancy M. P. Bocken; Elsa A. Olivetti; Jonathan M. Cullen; José Potting; Reid Lifset (Journal of Industrial Ecology, 2017)

Role of DNA methylation in the dietary restriction mediated cellular memory - Archana Unnikrishnan; Jordan Jackson; Stephanie A. Matyi; Niran Hadad; Benjamin Wronowski; Constantin Georgescu; Karla P. Garrett; Jonathan D. Wren; Willard M. Freeman; Arlan Richardson (GeroScience, 2017)

Muscle size and strength: debunking the “completely separate phenomena” suggestion - Thomas G. Balshaw; Garry J. Massey; Thomas M. Maden-Wilkinson; Jonathan P. Folland (European Journal of Applied Physiology, 2017)

Quantifying the extent of niche areas in the global fleet of commercial ships: the potential for “super-hot spots” of biofouling - Cameron S. Moser; Timothy P. Wier; Matthew R. First; Jonathan F. Grant; Scott C. Riley; Stephanie H. Robbins-Wamsley; Mario N. Tamburri; Gregory M. Ruiz; A. Whitman Miller; Lisa A. Drake (Biological Invasions, 2017)

Functional responses can unify invasion ecology - Jaimie T. A. Dick; Mhairi E. Alexander; Anthony Ricciardi; Ciaran Laverty; Paul O. Downey; Meng Xu; Jonathan M. Jeschke; Wolf-Christian Saul; Matthew P. Hill; Ryan Wasserman; Daniel Barrios-O’Neill; Olaf L. F. Weyl; et al. (Biological Invasions, 2017)
We contend that invasion ecology requires a universal, measurable trait of species and their interactions with resources that predicts key elements of invasibility and ecological impact; here, we advocate that functional responses can help achieve this across taxonomic and trophic groups, among habitats and contexts, and can hence help unify disparate research interests in invasion ecology.

Fictional responses from Vonesh et al. - Jaimie T. A. Dick; Mhairi E. Alexander; Anthony Ricciardi; Ciaran Laverty; Paul O. Downey; Meng Xu; Jonathan M. Jeschke; Wolf-Christian Saul; Matthew P. Hill; Ryan Wasserman; Daniel Barrios-O’Neill; Olaf L. F. Weyl; et al. (Biological Invasions, 2017)

Cooperative Research to Evaluate an Incidental Catch Distribution Forecast - Sara M. Turner; Jonathan A. Hare; John P. Manderson; John J. Hoey; David E. Richardson; Christopher L. Sarro; Ryan Silva (Frontiers in Marine Science, 2017)

A roadmap for island biology: 50 fundamental questions after 50 years of The Theory of Island Biogeography - Jairo Patiño; Robert J. Whittaker; Paulo A.V. Borges; José María Fernández‐Palacios; Claudine Ah‐Peng; Miguel B. Araújo; Sergio P. Ávila; Pedro Cardoso; Josselin Cornuault; Erik J. de Boer; Lea de Nascimento; Artur Gil; et al. (Journal of Biogeography, 2017)
Aims The 50th anniversary of the publication of the seminal book, The Theory of Island Biogeography , by Robert H. MacArthur and Edward O. Wilson, is a timely moment to review and identify key research foci that could advance island biology. Here, we take a collaborative horizon‐scanning approach to identify 50 fundamental questions for the continued development of the field. Location Worldwide. Methods We adapted a well‐established methodology of horizon scanning to identify priority research questions in island biology, and initiated it during the Island Biology 2016 conference held in the Azores. A multidisciplinary working group prepared an initial pool of 187 questions. A series of online surveys was then used to refine a list of the 50 top priority questions. The final shortlist was restricted to questions with a broad conceptual scope, and which should be answerable through achievable research approaches. Results Questions were structured around four broad and partially overlapping island topics, including: (Macro)Ecology and Biogeography, (Macro)Evolution, Community Ecology, and Conservation and Management. These topics were then subdivided according to the following subject areas: global diversity patterns (five questions in total); island ontogeny and past climate change (4); island rules and syndromes (3); island biogeography theory (4); immigration–speciation–extinction dynamics (5); speciation and diversification (4); dispersal and colonization (3); community assembly (6); biotic interactions (2); global change (5); conservation and management policies (5); and invasive alien species (4). Main conclusions Collectively, this cross‐disciplinary set of topics covering the 50 fundamental questions has the potential to stimulate and guide future research in island biology. By covering fields ranging from biogeography, community ecology and evolution to global change, this horizon scan may help to foster the formation of interdisciplinary research networks, enhancing joint efforts to better understand the past, present and future of island biotas.

A global database of nitrogen and phosphorus excretion rates of aquatic animals - Michael J. Vanni; Peter B. McIntyre; Dennis Allen; Diane L. Arnott; Jonathan P. Benstead; David J. Berg; Åge Brabrand; Sébastien Brosse; Paul A. Bukaveckas; Adriano Caliman; Krista A. Capps; Luciana S. Carneiro; et al. (Ecology, 2017)
Animals can be important in modulating ecosystem‐level nutrient cycling, although their importance varies greatly among species and ecosystems. Nutrient cycling rates of individual animals represent valuable data for testing the predictions of important frameworks such as the Metabolic Theory of Ecology ( MTE ) and ecological stoichiometry ( ES ). They also represent an important set of functional traits that may reflect both environmental and phylogenetic influences. Over the past two decades, studies of animal‐mediated nutrient cycling have increased dramatically, especially in aquatic ecosystems. Here we present a global compilation of aquatic animal nutrient excretion rates. The dataset includes 10,534 observations from freshwater and marine animals of N and/or P excretion rates. These observations represent 491 species, including most aquatic phyla. Coverage varies greatly among phyla and other taxonomic levels. The dataset includes information on animal body size, ambient temperature, taxonomic affiliations, and animal body N:P. This data set was used to test predictions of MTE and ES , as described in Vanni and McIntyre (2016; Ecology DOI : 10.1002/ecy.1582 ).

Changes in agonist neural drive, hypertrophy and pre-training strength all contribute to the individual strength gains after resistance training - Thomas G. Balshaw; Garry J. Massey; Thomas M. Maden-Wilkinson; Antonio J. Morales-Artacho; Alexandra McKeown; Clare L. Appleby; Jonathan P. Folland (European Journal of Applied Physiology, 2017)

An insect-inspired model for visual binding I: learning objects and their characteristics - Brandon D. Northcutt; Jonathan P. Dyhr; Charles M. Higgins (Biological Cybernetics, 2017)

Flagship umbrella species needed for the conservation of overlooked aquatic biodiversity - Gregor Kalinkat; Juliano S. Cabral; William Darwall; G. Francesco Ficetola; Judith L. Fisher; Darren P. Giling; Marie‐Pierre Gosselin; Hans‐Peter Grossart; Sonja C. Jähnig; Jonathan M. Jeschke; Klaus Knopf; Stefano Larsen; et al. (Conservation Biology, 2017)

Association of AHSG with alopecia and mental retardation (APMR) syndrome - M. Reza Sailani; Fereshteh Jahanbani; Jafar Nasiri; Mahdiyeh Behnam; Mansoor Salehi; Maryam Sedghi; Majid Hoseinzadeh; Shinichi Takahashi; Amin Zia; Joshua Gruber; Janet Linnea Lynch; Daniel Lam; et al. (Human Genetics, 2017)

The impact of Southern Ocean residual upwelling on atmospheric CO2 on centennial and millennial timescales - Jonathan M. Lauderdale; Richard G. Williams; David R. Munday; David P. Marshall (Climate Dynamics, 2017)

Impact of nonnative feral pig removal on soil structure and nutrient availability in Hawaiian tropical montane wet forests - Michael S. Long; Creighton M. Litton; Christian P. Giardina; Jonathan Deenik; Rebecca J. Cole; Jed P. Sparks (Biological Invasions, 2017)

A global database of ant species abundances - Heloise Gibb; Rob R. Dunn; Nathan J. Sanders; Blair F. Grossman; Manoli Photakis; Silvia Abril; Donat Agosti; Alan N. Andersen; Elena Angulo; Inge Armbrecht; Xavier Arnan; Fabricio B. Baccaro; et al. (Ecology, 2017)
What forces structure ecological assemblages? A key limitation to general insights about assemblage structure is the availability of data that are collected at a small spatial grain (local assemblages) and a large spatial extent (global coverage). Here, we present published and unpublished data from 51 ,388 ant abundance and occurrence records of more than 2,693 species and 7,953 morphospecies from local assemblages collected at 4,212 locations around the world. Ants were selected because they are diverse and abundant globally, comprise a large fraction of animal biomass in most terrestrial communities, and are key contributors to a range of ecosystem functions. Data were collected between 1949 and 2014, and include, for each geo‐referenced sampling site, both the identity of the ants collected and details of sampling design, habitat type, and degree of disturbance. The aim of compiling this data set was to provide comprehensive species abundance data in order to test relationships between assemblage structure and environmental and biogeographic factors. Data were collected using a variety of standardized methods, such as pitfall and Winkler traps, and will be valuable for studies investigating large‐scale forces structuring local assemblages. Understanding such relationships is particularly critical under current rates of global change. We encourage authors holding additional data on systematically collected ant assemblages, especially those in dry and cold, and remote areas, to contact us and contribute their data to this growing data set.

Genome-wide association mapping and agronomic impact of cowpea root architecture - James D. Burridge; Hannah M. Schneider; Bao-Lam Huynh; Philip A. Roberts; Alexander Bucksch; Jonathan P. Lynch (Theoretical and Applied Genetics, 2017)

Seasonal fecundity is not related to geographic position across a species’ global range despite a central peak in abundance - Katharine J. Ruskin; Matthew A. Etterson; Thomas P. Hodgman; Alyssa C. Borowske; Jonathan B. Cohen; Chris S. Elphick; Christopher R. Field; Rebecca A. Kern; Erin King; Alison R. Kocek; Adrienne I. Kovach; Kathleen M. O’Brien; et al. (Oecologia, 2017)

Coastal erosion vs man-made protective structures: evaluating a two-decade history from southeastern India - G. Muthusankar; M. P. Jonathan; C. Lakshumanan; Priyadarsi D. Roy; K. Srinivasa-Raju (Natural Hazards, 2017)

Connectivity between the central nucleus of the amygdala and the bed nucleus of the stria terminalis in the non-human primate: neuronal tract tracing and developmental neuroimaging studies - Jonathan A. Oler; Do P. M. Tromp; Andrew S. Fox; Rothem Kovner; Richard J. Davidson; Andrew L. Alexander; Daniel R. McFarlin; Rasmus M. Birn; Benjamin E. Berg; Danielle M. deCampo; Ned H. Kalin; Julie L. Fudge (Brain Structure and Function, 2017)

Does wing size shape insect biogeography? Evidence from a diverse regional stonefly assemblage - Graham A. McCulloch; Graham P. Wallis; Jonathan M. Waters (Global Ecology and Biogeography, 2017)
Aim Dispersal ability has traditionally been seen as a key influence on species distributions, but recent biogeographical analyses have cast doubt on the strength of this association. Here we present biogeographical evidence from New Zealand's entire plecopteran fauna (100 species) to test for associations between flight ability and species range, and to determine the extent of wing reduction that is required to influence biogeographical patterns. Location The main islands of New Zealand, representing a land area of 270,000 km 2 . These islands host a diverse assemblage of endemic stoneflies, including a substantial number of wing‐reduced taxa. Methods We analyse biogeographical data, encompassing over 7000 species/locality records, across all 100 stonefly taxa recorded from New Zealand's mainland. Distributional data are analysed together with morphological data, in a phylogenetic framework, to test the hypothesis that wing length (dispersal ability) has a significant association with range size. Results Our analyses indicate a strong relationship between species wing length and area of occupancy, unconfounded by phylogenetic relationships. A significant positive correlation was also observed between geographical range and relative wing length in both sexes, with consistent patterns observed in distinct families. When the analysis was confined only to macropterous species the relationship between wing length and area of occupancy remained significant. Main conclusions This study shows that rapid switches in dispersal ability are linked to dramatic biogeographical contrasts. While complete wing loss is associated with major range reduction, it is also clear that even small reductions in wing size can significantly influence biogeographical patterns. Broadly, the analysis demonstrates that by focusing on a major regional assemblage of ecologically, and phylogenetically, similar taxa, it is possible to show that even subtle morphological shifts can be correlated with substantial biogeographical change.

Fine‐scale climate change: modelling spatial variation in biologically meaningful rates of warming - Ilya M. D. Maclean; Andrew J. Suggitt; Robert J. Wilson; James P. Duffy; Jonathan J. Bennie (Global Change Biology, 2017)
The existence of fine‐grain climate heterogeneity has prompted suggestions that species may be able to survive future climate change in pockets of suitable microclimate, termed ‘microrefugia’. However, evidence for microrefugia is hindered by lack of understanding of how rates of warming vary across a landscape. Here, we present a model that is applied to provide fine‐grained, multidecadal estimates of temperature change based on the underlying physical processes that influence microclimate. Weather station and remotely derived environmental data were used to construct physical variables that capture the effects of terrain, sea surface temperatures, altitude and surface albedo on local temperatures, which were then calibrated statistically to derive gridded estimates of temperature. We apply the model to the Lizard Peninsula, United Kingdom, to provide accurate (mean error = 1.21 °C; RMS error = 1.63 °C) hourly estimates of temperature at a resolution of 100 m for the period 1977–2014. We show that rates of warming vary across a landscape primarily due to long‐term trends in weather conditions. Total warming varied from 0.87 to 1.16 °C, with the slowest rates of warming evident on north‐east‐facing slopes. This variation contributed to substantial spatial heterogeneity in trends in bioclimatic variables: for example, the change in the length of the frost‐free season varied from +11 to −54 days and the increase in annual growing degree‐days from 51 to 267 °C days. Spatial variation in warming was caused primarily by a decrease in daytime cloud cover with a resulting increase in received solar radiation, and secondarily by a decrease in the strength of westerly winds, which has amplified the effects on temperature of solar radiation on west‐facing slopes. We emphasize the importance of multidecadal trends in weather conditions in determining spatial variation in rates of warming, suggesting that locations experiencing least warming may not remain consistent under future climate change.

Foliar bacteria and soil fertility mediate seedling performance: a new and cryptic dimension of niche differentiation - Eric A. Griffin; M. Brian Traw; Peter J. Morin; Jonathan N. Pruitt; S. Joseph Wright; Walter P. Carson (Ecology, 2016)
The phyllosphere (comprising the leaf surface and interior) is one of the world's largest microbial habitats and is host to an abundant and diverse array of bacteria. Nonetheless, the degree to which bacterial communities are benign, harmful, or beneficial to plants in situ is unknown. We tested the hypothesis that the net effect of reducing bacterial abundance and diversity would vary substantially among host species (from harmful to beneficial) and this would be strongly mediated by soil resource availability. To test this, we monitored tree seedling growth responses to commercial antibiotics among replicated resource supply treatments (N, P, K) in a tropical forest in Panama for 29 months. We applied either antibiotics or control water to replicated seedlings of five common tree species ( Alseis blackiana , Desmopsis panamensis , Heisteria concinna , Sorocea affinis , and Tetragastris panamensis ). These antibiotic treatments significantly reduced both the abundance and diversity of bacteria epiphytically as well as endophytically. Overall, the effect of antibiotics on performance was highly host specific. Applying antibiotics increased growth for three species by as much as 49% ( Alseis , Heisteria , and Tetragastris ), decreased growth for a fourth species by nearly 20% ( Sorocea ), and had no impact on a fifth species ( Desmopsis ). Perhaps more importantly, the degree to which foliar bacteria were harmful or not varied with soil resource supply. Specifically, applying antibiotics had no effect when potassium was added but increased growth rate by almost 40% in the absence of potassium. Alternatively, phosphorus enrichment caused the effect of bacteria to switch from being primarily beneficial to harmful or vice versa, but this depended entirely on the presence or absence of nitrogen enrichment (i.e., important and significant interactions). Our results are the first to demonstrate that the net effect of reducing the abundance and diversity of bacteria can have very strong positive and negative effects on seedling performance. Moreover, these effects were clearly mediated by soil resource availability. Though speculative, we suggest that foliar bacteria may interact with soil fertility to comprise an important, yet cryptic dimension of niche differentiation, which can have important implications for species coexistence.

The genetic architecture of resistance to virus infection in Drosophila - Rodrigo Cogni; Chuan Cao; Jonathan P. Day; Calum Bridson; Francis M. Jiggins (Molecular Ecology, 2016)
Variation in susceptibility to infection has a substantial genetic component in natural populations, and it has been argued that selection by pathogens may result in it having a simpler genetic architecture than many other quantitative traits. This is important as models of host–pathogen co‐evolution typically assume resistance is controlled by a small number of genes. Using the Drosophila melanogaster multiparent advanced intercross, we investigated the genetic architecture of resistance to two naturally occurring viruses, the sigma virus and DCV (Drosophila C virus). We found extensive genetic variation in resistance to both viruses. For DCV resistance, this variation is largely caused by two major‐effect loci. Sigma virus resistance involves more genes – we mapped five loci, and together these explained less than half the genetic variance. Nonetheless, several of these had a large effect on resistance. Models of co‐evolution typically assume strong epistatic interactions between polymorphisms controlling resistance, but we were only able to detect one locus that altered the effect of the main effect loci we had mapped. Most of the loci we mapped were probably at an intermediate frequency in natural populations. Overall, our results are consistent with major‐effect genes commonly affecting susceptibility to infectious diseases, with DCV resistance being a near‐Mendelian trait.

Comparative genomic, proteomic and exoproteomic analyses of three Pseudomonas strains reveals novel insights into the phosphorus scavenging capabilities of soil bacteria - Ian D. E. A. Lidbury; Andrew R. J. Murphy; David J. Scanlan; Gary D. Bending; Alexandra M. E. Jones; Jonathan D. Moore; Andrew Goodall; John P. Hammond; Elizabeth M. H. Wellington (Environmental Microbiology, 2016)
Summary Bacteria that inhabit the rhizosphere of agricultural crops can have a beneficial effect on crop growth. One such mechanism is the microbial‐driven solubilization and remineralization of complex forms of phosphorus (P). It is known that bacteria secrete various phosphatases in response to low P conditions. However, our understanding of their global proteomic response to P stress is limited. Here, exoproteomic analysis of Pseudomonas putida BIRD‐1 (BIRD‐1), Pseudomonas fluorescens SBW25 and Pseudomonas stutzeri DSM4166 was performed in unison with whole‐cell proteomic analysis of BIRD‐1 grown under phosphate (Pi) replete and Pi deplete conditions. Comparative exoproteomics revealed marked heterogeneity in the exoproteomes of each Pseudomonas strain in response to Pi depletion. In addition to well‐characterized members of the PHO regulon such as alkaline phosphatases, several proteins, previously not associated with the response to Pi depletion, were also identified. These included putative nucleases, phosphotriesterases, putative phosphonate transporters and outer membrane proteins. Moreover, in BIRD‐1, mutagenesis of the master regulator, phoBR , led us to confirm the addition of several novel PHO‐dependent proteins. Our data expands knowledge of the Pseudomonas PHO regulon, including species that are frequently used as bioinoculants, opening up the potential for more efficient and complete use of soil complexed P.

Dietary Nitrate, Nitric Oxide, and Cardiovascular Health - Catherine P. Bondonno; Kevin D. Croft; Jonathan M. Hodgson (Critical Reviews in Food Science and Nutrition, 2016)

Invasive blue mussels threaten regional scale genetic diversity in mainland and remote offshore locations: the need for baseline data and enhanced protection in the Southern Ocean - Jonathan P. A. Gardner; Małgorzata Zbawicka; Kristen M. Westfall; Roman Wenne (Global Change Biology, 2016)
Human‐mediated biological transfers of species have substantially modified many ecosystems with profound environmental and economic consequences. However, in many cases, invasion events are very hard to identify because of the absence of an appropriate baseline of information for receiving sites/regions. In this study, use of high‐resolution genetic markers (single nucleotide polymorphisms – SNP s) highlights the threat of introduced Northern Hemisphere blue mussels ( Mytilus galloprovincialis ) at a regional scale to Southern Hemisphere lineages of blue mussels via hybridization and introgression. Analysis of a multispecies SNP dataset reveals hotspots of invasive Northern Hemisphere blue mussels in some mainland New Zealand locations, as well as the existence of unique native lineages of blue mussels on remote oceanic islands in the Southern Ocean that are now threatened by invasive mussels. Samples collected from an oil rig that has moved between South Africa, Australia, and New Zealand were identified as invasive Northern Hemisphere mussels, revealing the relative ease with which such non‐native species may be moved from region to region. In combination, our results highlight the existence of unique lineages of mussels (and by extension, presumably of other taxa) on remote offshore islands in the Southern Ocean, the need for more baseline data to help identify bioinvasion events, the ongoing threat of hybridization and introgression posed by invasive species, and the need for greater protection of some of the world's last great remote areas.

Infection risk decreases with increasing mismatch in host and pathogen environmental tolerances - A. Justin Nowakowski; Steven M. Whitfield; Evan A. Eskew; Michelle E. Thompson; Jonathan P. Rose; Benjamin L. Caraballo; Jacob L. Kerby; Maureen A. Donnelly; Brian D. Todd (Ecology Letters, 2016)
The fungal pathogen Batrachochytrium dendrobatidis ( Bd ) has caused the greatest known wildlife pandemic, infecting over 500 amphibian species. It remains unclear why some host species decline from disease‐related mortality whereas others persist. We introduce a conceptual model that predicts that infection risk in ectotherms will decrease as the difference between host and pathogen environmental tolerances (i.e. tolerance mismatch) increases. We test this prediction using both local‐scale data from Costa Rica and global analyses of over 11 000 Bd infection assays. We find that infection prevalence decreases with increasing thermal tolerance mismatch and with increasing host tolerance of habitat modification. The relationship between environmental tolerance mismatches and Bd infection prevalence is generalisable across multiple amphibian families and spatial scales, and the magnitude of the tolerance mismatch effect depends on environmental context. These findings may help explain patterns of amphibian declines driven by a global wildlife pandemic.

The macroecology of infectious diseases: a new perspective on global‐scale drivers of pathogen distributions and impacts - Patrick R. Stephens; Sonia Altizer; Katherine F. Smith; A. Alonso Aguirre; James H. Brown; Sarah A. Budischak; James E. Byers; Tad A. Dallas; T. Jonathan Davies; John M. Drake; Vanessa O. Ezenwa; Maxwell J. Farrell; et al. (Ecology Letters, 2016)
Identifying drivers of infectious disease patterns and impacts at the broadest scales of organisation is one of the most crucial challenges for modern science, yet answers to many fundamental questions remain elusive. These include what factors commonly facilitate transmission of pathogens to novel host species, what drives variation in immune investment among host species, and more generally what drives global patterns of parasite diversity and distribution? Here we consider how the perspectives and tools of macroecology, a field that investigates patterns and processes at broad spatial, temporal and taxonomic scales, are expanding scientific understanding of global infectious disease ecology. In particular, emerging approaches are providing new insights about scaling properties across all living taxa, and new strategies for mapping pathogen biodiversity and infection risk. Ultimately, macroecology is establishing a framework to more accurately predict global patterns of infectious disease distribution and emergence.

The effect of vigorous running and cycling on serum COMP, lubricin, and femoral cartilage thickness: a pilot study - Harry M. Roberts; Jonathan P. Moore; Claire L. Griffith-McGeever; Matthew B. Fortes; Jeanette M. Thom (European Journal of Applied Physiology, 2016)

Taxonomy of the order Mononegavirales: update 2016 - Claudio L. Afonso; Gaya K. Amarasinghe; Krisztián Bányai; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Nicolás Bejerman; Kim R. Blasdell; François-Xavier Briand; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; et al. (Archives of Virology, 2016)

The biogeography and community structure of kelp forest macroinvertebrates - Laurel A. Zahn; Jeremy T. Claisse; Jonathan P. Williams; Chelsea M. Williams; Daniel J. Pondella (Marine Ecology, 2016)
Understanding species distributions and their community structure is increasingly important when taking an ecosystem‐based approach to conservation and management. However, knowledge of the distribution and community structure of species in mid‐range trophic levels ( e.g . macroinvertebrates) is lacking in most marine ecosystems. Our study aimed to examine the spatial distribution and community‐level biogeographic patterns of common kelp forest–rocky reef macroinvertebrates in Southern California and to evaluate the effects of environmental gradients on these communities. Quantitative SCUBA surveys were used to estimate macroinvertebrate densities at 92 sites from 2008–2012. Non‐metric multidimensional scaling was used to evaluate spatial patterns of macroinvertebrate communities among Regions. We found that kelp forest–rocky reef macroinvertebrate communities are distinct among different island and mainland regions, and their community patterns exhibited a strong relationship with an environmental gradient ( i.e . sea surface temperature) even after controlling for geographic distance between sites. High abundances of urchin species ( Strongylocentrotus purpuratus and Strongylocentrotus franciscanus ) were strong drivers of regional differences. Macroinvertebrate community patterns were driven by characteristic species that were typically more prevalent at warmer or colder sites. Our results provide the first quantitative analysis of macroinvertebrate community structure within the California kelp forest ecosystem. We also describe the distribution and abundance of 92 conspicuous kelp forest‐rocky reef macroinvertebrates among nine pre‐defined Regions. This study provides important preliminary information on these macroinvertebrate species that will be directly useful to inform management of invertebrate fisheries and spatial protection of marine resources.

How variation between individuals affects species coexistence - Simon P. Hart; Sebastian J. Schreiber; Jonathan M. Levine (Ecology Letters, 2016)
Although the effects of variation between individuals within species are traditionally ignored in studies of species coexistence, the magnitude of intraspecific variation in nature is forcing ecologists to reconsider. Compelling intuitive arguments suggest that individual variation may provide a previously unrecognised route to diversity maintenance by blurring species‐level competitive differences or substituting for species‐level niche differences. These arguments, which are motivating a large body of empirical work, have rarely been evaluated with quantitative theory. Here we incorporate intraspecific variation into a common model of competition and identify three pathways by which this variation affects coexistence: (1) changes in competitive dynamics because of nonlinear averaging, (2) changes in species’ mean interaction strengths because of variation in underlying traits (also via nonlinear averaging) and (3) effects on stochastic demography. As a consequence of the first two mechanisms, we find that intraspecific variation in competitive ability increases the dominance of superior competitors, and intraspecific niche variation reduces species‐level niche differentiation, both of which make coexistence more difficult. In addition, individual variation can exacerbate the effects of demographic stochasticity, and this further destabilises coexistence. Our work provides a theoretical foundation for emerging empirical interests in the effects of intraspecific variation on species diversity.

Physical Stability of Freeze-Dried Isomalt Diastereomer Mixtures - Anna-Kaisa Koskinen; Sara J. Fraser-Miller; Johan P. Bøtker; Ville P. Heljo; Jonathan E. Barnsley; Keith C. Gordon; Clare J. Strachan; Anne M. Juppo (Pharmaceutical Research, 2016)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Warming alters coupled carbon and nutrient cycles in experimental streams - Tanner J. Williamson; Wyatt F. Cross; Jonathan P. Benstead; Gísli M. Gíslason; James M. Hood; Alexander D. Huryn; Philip W. Johnson; Jill R. Welter (Global Change Biology, 2016)
Although much effort has been devoted to quantifying how warming alters carbon cycling across diverse ecosystems, less is known about how these changes are linked to the cycling of bioavailable nitrogen and phosphorus. In freshwater ecosystems, benthic biofilms (i.e. thin films of algae, bacteria, fungi, and detrital matter) act as biogeochemical hotspots by controlling important fluxes of energy and material. Understanding how biofilms respond to warming is thus critical for predicting responses of coupled elemental cycles in freshwater systems. We developed biofilm communities in experimental streamside channels along a gradient of mean water temperatures (7.5–23.6 °C), while closely maintaining natural diel and seasonal temperature variation with a common water and propagule source. Both structural (i.e. biomass, stoichiometry, assemblage structure) and functional (i.e. metabolism, N 2 ‐fixation, nutrient uptake) attributes of biofilms were measured on multiple dates to link changes in carbon flow explicitly to the dynamics of nitrogen and phosphorus. Temperature had strong positive effects on biofilm biomass (2.8‐ to 24‐fold variation) and net ecosystem productivity (44‐ to 317‐fold variation), despite extremely low concentrations of limiting dissolved nitrogen. Temperature had surprisingly minimal effects on biofilm stoichiometry: carbon:nitrogen (C:N) ratios were temperature‐invariant, while carbon:phosphorus (C:P) ratios declined slightly with increasing temperature. Biofilm communities were dominated by cyanobacteria at all temperatures (>91% of total biovolume) and N 2 ‐fixation rates increased up to 120‐fold between the coldest and warmest treatments. Although ammonium‐N uptake increased with temperature (2.8‐ to 6.8‐fold variation), the much higher N 2 ‐fixation rates supplied the majority of N to the ecosystem at higher temperatures. Our results demonstrate that temperature can alter how carbon is cycled and coupled to nitrogen and phosphorus. The uncoupling of C fixation from dissolved inorganic nitrogen supply produced large unexpected changes in biofilm development, elemental cycling, and likely downstream exports of nutrients and organic matter.

Establishment of a standard reference material (SRM) herbal DNA barcode library of Vitex negundo L. (lagundi) for quality control measures - Jay Edneil C. Olivar; Joanner Paulus Erik P. Alaba; Jose Francisco M. Atienza; Jerick Jeffrey S. Tan; Maximo T. Umali; Grecebio Jonathan D. Alejandro (Food Additives & Contaminants: Part A, 2016)

The impact of tropical forest logging and oil palm agriculture on the soil microbiome - Binu M. Tripathi; David P. Edwards; Lucas William Mendes; Mincheol Kim; Ke Dong; Hyoki Kim; Jonathan M. Adams (Molecular Ecology, 2016)
Selective logging and forest conversion to oil palm agriculture are rapidly altering tropical forests. However, functional responses of the soil microbiome to these land‐use changes are poorly understood. Using 16S rRNA gene and shotgun metagenomic sequencing, we compared composition and functional attributes of soil biota between unlogged, once‐logged and twice‐logged rainforest, and areas converted to oil palm plantations in Sabah, Borneo. Although there was no significant effect of logging history, we found a significant difference between the taxonomic and functional composition of both primary and logged forests and oil palm. Oil palm had greater abundances of genes associated with DNA , RNA , protein metabolism and other core metabolic functions, but conversely, lower abundance of genes associated with secondary metabolism and cell–cell interactions, indicating less importance of antagonism or mutualism in the more oligotrophic oil palm environment. Overall, these results show a striking difference in taxonomic composition and functional gene diversity of soil microorganisms between oil palm and forest, but no significant difference between primary forest and forest areas with differing logging history. This reinforces the view that logged forest retains most features and functions of the original soil community. However, networks based on strong correlations between taxonomy and functions showed that network complexity is unexpectedly increased due to both logging and oil palm agriculture, which suggests a pervasive effect of both land‐use changes on the interaction of soil microbes.

QTL mapping and breeding value estimation through pedigree-based analysis of fruit size and weight in four diverse peach breeding programs - Jonathan Fresnedo-Ramírez; Terrence J. Frett; Paul J. Sandefur; Alejandra Salgado-Rojas; John R. Clark; Ksenija Gasic; Cameron P. Peace; Natalie Anderson; Timothy P. Hartmann; David H. Byrne; Marco C. A. M. Bink; Eric van de Weg; et al. (Tree Genetics & Genomes, 2016)

Global impacts of the 1980s regime shift - Philip C. Reid; Renata E. Hari; Grégory Beaugrand; David M. Livingstone; Christoph Marty; Dietmar Straile; Jonathan Barichivich; Eric Goberville; Rita Adrian; Yasuyuki Aono; Ross Brown; James Foster; et al. (Global Change Biology, 2016)
Despite evidence from a number of Earth systems that abrupt temporal changes known as regime shifts are important, their nature, scale and mechanisms remain poorly documented and understood. Applying principal component analysis, change‐point analysis and a sequential t ‐test analysis of regime shifts to 72 time series, we confirm that the 1980s regime shift represented a major change in the Earth's biophysical systems from the upper atmosphere to the depths of the ocean and from the Arctic to the Antarctic, and occurred at slightly different times around the world. Using historical climate model simulations from the Coupled Model Intercomparison Project Phase 5 ( CMIP 5) and statistical modelling of historical temperatures, we then demonstrate that this event was triggered by rapid global warming from anthropogenic plus natural forcing, the latter associated with the recovery from the El Chichón volcanic eruption. The shift in temperature that occurred at this time is hypothesized as the main forcing for a cascade of abrupt environmental changes. Within the context of the last century or more, the 1980s event was unique in terms of its global scope and scale; our observed consequences imply that if unavoidable natural events such as major volcanic eruptions interact with anthropogenic warming unforeseen multiplier effects may occur.

Quantifying the total wetted surface area of the world fleet: a first step in determining the potential extent of ships’ biofouling - Cameron S. Moser; Timothy P. Wier; Jonathan F. Grant; Matthew R. First; Mario N. Tamburri; Gregory M. Ruiz; A. Whitman Miller; Lisa A. Drake (Biological Invasions, 2016)

The critical role of ants in the extensive dispersal of Acacia seeds revealed by genetic parentage assignment - Caitlin M. Pascov; Paul G. Nevill; Carole P. Elliott; Jonathan D. Majer; Janet M. Anthony; Siegfried L. Krauss (Oecologia, 2015)

Within‐river genetic connectivity patterns reflect contrasting geomorphology - Jonathan M. Waters; Dave Craw; Christopher P. Burridge; Martyn Kennedy; Tania M. King; Graham P. Wallis (Journal of Biogeography, 2015)
Aim To test the hypothesis that geomorphological features, shaped by underlying geology, can influence within‐river connectivity patterns in freshwater‐limited fishes. Location Rivers draining the eastern flanks of the Southern Alps in South Island, New Zealand. Methods We analyse up to 1624 bp of mt DNA from 499 ‘flathead’ Galaxias specimens from 145 localities across 14 different river systems. Variation among sampling sites within systems is characterized using ϕ statistics. Results Although similar levels of DNA sequence variation were detected in all rivers sampled, spatial partitioning of this variation was significantly greater within schist ( n = 5; mean ϕ ST = 0.696) than within greywacke ( n = 10; mean ϕ ST = 0.268) rivers. Main conclusions Population connectivity can be strongly influenced by underlying geology, leading to profound differences in the connectivity, phylogeography and diversity of riverine species.

Metal enrichment of soils following the April 2012–2013 eruptive activity of the Popocatépetl volcano, Puebla, Mexico - P. F. Rodriguez-Espinosa; M. P. Jonathan; S. S. Morales-García; Lorena Elizabeth Campos Villegas; E. Martínez-Tavera; N. P. Muñoz-Sevilla; Miguel Alvarado Cardona (Environmental Monitoring and Assessment, 2015)

Salamander growth rates increase along an experimental stream phosphorus gradient - Phillip M. Bumpers; John C. Maerz; Amy D. Rosemond; Jonathan P. Benstead (Ecology, 2015)
Nutrient‐driven perturbations to the resource base of food webs are predicted to attenuate with trophic distance, so it is unclear whether higher‐level consumers will generally respond to anthropogenic nutrient loading. Few studies have tested whether nutrient (specifically, nitrogen [N] and phosphorus [P]) enrichment of aquatic ecosystems propagates through multiple trophic levels to affect predators, or whether N vs. P is relatively more important in driving effects on food webs. We conducted two‐year whole‐stream N and P additions to five streams to generate gradients in N and P concentration and N:P ratio (target N:P = 2, 8, 16, 32, 128). Larval salamanders are vertebrate predators of primary and secondary macroinvertebrate consumers in many heterotrophic headwater streams in which the basal resources are detritus and associated microorganisms. We determined the effects of N and P on the growth rates of caged and free‐roaming larval Desmognathus quadramaculatus and the average body size of larval Eurycea wilderae . Growth rates and average body size increased by up to 40% and 60%, respectively, with P concentration and were negatively related to N:P ratio. These findings were consistent across both species of salamanders using different methodologies (cage vs. free‐roaming) and at different temporal scales (3 months vs. 2 yr). Nitrogen concentration was not significantly related to increased growth rate or body size of the salamander species tested. Our findings suggest that salamander growth responds to the relaxation of ecosystem‐level P limitation and that moderate P enrichment can have relatively large effects on vertebrate predators in detritus‐based food webs.

The ecological forecast horizon, and examples of its uses and determinants - Owen L. Petchey; Mikael Pontarp; Thomas M. Massie; Sonia Kéfi; Arpat Ozgul; Maja Weilenmann; Gian Marco Palamara; Florian Altermatt; Blake Matthews; Jonathan M. Levine; Dylan Z. Childs; Brian J. McGill; et al. (Ecology Letters, 2015)
Forecasts of ecological dynamics in changing environments are increasingly important, and are available for a plethora of variables, such as species abundance and distribution, community structure and ecosystem processes. There is, however, a general absence of knowledge about how far into the future, or other dimensions (space, temperature, phylogenetic distance), useful ecological forecasts can be made, and about how features of ecological systems relate to these distances. The ecological forecast horizon is the dimensional distance for which useful forecasts can be made. Five case studies illustrate the influence of various sources of uncertainty (e.g. parameter uncertainty, environmental variation, demographic stochasticity and evolution), level of ecological organisation (e.g. population or community), and organismal properties (e.g. body size or number of trophic links) on temporal, spatial and phylogenetic forecast horizons. Insights from these case studies demonstrate that the ecological forecast horizon is a flexible and powerful tool for researching and communicating ecological predictability. It also has potential for motivating and guiding agenda setting for ecological forecasting research and development.

Pharmacokinetic/Pharmacodynamic Modeling of Renin-Angiotensin Aldosterone Biomarkers Following Angiotensin-Converting Enzyme (ACE) Inhibition Therapy with Benazepril in Dogs - Jonathan P. Mochel; Martin Fink; Mathieu Peyrou; Antoine Soubret; Jérôme M. Giraudel; Meindert Danhof (Pharmaceutical Research, 2015)

Src Family Kinase Inhibitors Antagonize the Toxicity of Multiple Serotypes of Botulinum Neurotoxin in Human Embryonic Stem Cell-Derived Motor Neurons - Erkan Kiris; James C. Burnett; Jonathan E. Nuss; Laura M. Wanner; Brian D. Peyser; Hao T. Du; Glenn Y. Gomba; Krishna P. Kota; Rekha G. Panchal; Rick Gussio; Christopher D. Kane; Lino Tessarollo; et al. (Neurotoxicity Research, 2015)

Cristobalite in the 2011–2012 Cordón Caulle eruption (Chile) - C. Ian Schipper; Jonathan M. Castro; Hugh Tuffen; Fabian B. Wadsworth; Debra Chappell; Andres E. Pantoja; Mark P. Simpson; Eric C. Le Ru (Bulletin of Volcanology, 2015)

Investigation of Darwin’s naturalization hypothesis in invaded macrophyte communities - Jonathan P. Fleming; Eric D. Dibble; John D. Madsen; Ryan M. Wersal (Biological Invasions, 2015)

Microglia: dismantling and rebuilding circuits after acute neurological injury - Jenna M. Ziebell; P. David Adelson; Jonathan Lifshitz (Metabolic Brain Disease, 2015)

Cross-fostering by foreign conspecific queens and slave-making workers influences individual- and colony-level personality - Carl N. Keiser; Colin M. Wright; Nishant Singh; Joseph A. DeShane; Andreas P. Modlmeier; Jonathan N. Pruitt (Behavioral Ecology and Sociobiology, 2015)

Interactions between temperature and nutrients across levels of ecological organization - Wyatt F. Cross; James M. Hood; Jonathan P. Benstead; Alexander D. Huryn; Daniel Nelson (Global Change Biology, 2015)
Temperature and nutrient availability play key roles in controlling the pathways and rates at which energy and materials move through ecosystems. These factors have also changed dramatically on Earth over the past century as human activities have intensified. Although significant effort has been devoted to understanding the role of temperature and nutrients in isolation, less is known about how these two factors interact to influence ecological processes. Recent advances in ecological stoichiometry and metabolic ecology provide a useful framework for making progress in this area, but conceptual synthesis and review are needed to help catalyze additional research. Here, we examine known and potential interactions between temperature and nutrients from a variety of physiological, community, and ecosystem perspectives. We first review patterns at the level of the individual, focusing on four traits – growth, respiration, body size, and elemental content – that should theoretically govern how temperature and nutrients interact to influence higher levels of biological organization. We next explore the interactive effects of temperature and nutrients on populations, communities, and food webs by synthesizing information related to community size spectra, biomass distributions, and elemental composition. We use metabolic theory to make predictions about how population‐level secondary production should respond to interactions between temperature and resource supply, setting up qualitative predictions about the flows of energy and materials through metazoan food webs. Last, we examine how temperature–nutrient interactions influence processes at the whole‐ecosystem level, focusing on apparent vs. intrinsic activation energies of ecosystem processes, how to represent temperature–nutrient interactions in ecosystem models, and patterns with respect to nutrient uptake and organic matter decomposition. We conclude that a better understanding of interactions between temperature and nutrients will be critical for developing realistic predictions about ecological responses to multiple, simultaneous drivers of global change, including climate warming and elevated nutrient supply.

Does N 2 fixation amplify the temperature dependence of ecosystem metabolism? - Jill R. Welter; Jonathan P. Benstead; Wyatt F. Cross; James M. Hood; Alexander D. Huryn; Philip W. Johnson; Tanner J. Williamson (Ecology, 2015)
Variation in resource supply can cause variation in temperature dependences of metabolic processes (e.g., photosynthesis and respiration). Understanding such divergence is particularly important when using metabolic theory to predict ecosystem responses to climate warming. Few studies, however, have assessed the effect of temperature–resource interactions on metabolic processes, particularly in cases where the supply of limiting resources exhibits temperature dependence. We investigated the responses of biomass accrual, gross primary production (GPP), community respiration (CR), and N 2 fixation to warming during biofilm development in a streamside channel experiment. Areal rates of GPP, CR, biomass accrual, and N 2 fixation scaled positively with temperature, showing a 32‐ to 71‐fold range across the temperature gradient (~7°–24°C). Areal N 2 ‐fixation rates exhibited apparent activation energies (1.5–2.0 eV; 1 eV = ~1.6 × 10 −19 J) approximating the activation energy of the nitrogenase reaction. In contrast, mean apparent activation energies for areal rates of GPP (2.1–2.2 eV) and CR (1.6–1.9 eV) were 6.5‐ and 2.7‐fold higher than estimates based on metabolic theory predictions (i.e., 0.32 and 0.65 eV, respectively) and did not significantly differ from the apparent activation energy observed for N 2 fixation. Mass‐specific activation energies for N 2 fixation (1.4–1.6 eV), GPP (0.3–0.5 eV), and CR (no observed temperature relationship) were near or lower than theoretical predictions. We attribute the divergence of areal activation energies from those predicted by metabolic theory to increases in N 2 fixation with temperature, leading to amplified temperature dependences of biomass accrual and areal rates of GPP and R. Such interactions between temperature dependences must be incorporated into metabolic models to improve predictions of ecosystem responses to climate change.

Estimating continuous body size-based shifts in δ15N–δ13C space using multivariate hierarchical models - Jonathan C. P. Reum; Rachel A. Hovel; Correigh M. Greene (Marine Biology, 2015)

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Multiplication of microbes below 0.690 water activity: implications for terrestrial and extraterrestrial life - Andrew Stevenson; Jürgen Burkhardt; Charles S. Cockell; Jonathan A. Cray; Jan Dijksterhuis; Mark Fox‐Powell; Terence P. Kee; Gerhard Kminek; Terry J. McGenity; Kenneth N. Timmis; David J. Timson; Mary A. Voytek; et al. (Environmental Microbiology, 2015)
Summary Since a key requirement of known life forms is available water (water activity; a w ), recent searches for signatures of past life in terrestrial and extraterrestrial environments have targeted places known to have contained significant quantities of biologically available water. However, early life on E arth inhabited high‐salt environments, suggesting an ability to withstand low water‐activity. The lower limit of water activity that enables cell division appears to be ∼ 0.605 which, until now, was only known to be exhibited by a single eukaryote, the sugar‐tolerant, fungal xerophile X eromyces bisporus . The first forms of life on E arth were, though, prokaryotic. Recent evidence now indicates that some halophilic A rchaea and B acteria have water‐activity limits more or less equal to those of X . bisporus . We discuss water activity in relation to the limits of E arth's present‐day biosphere; the possibility of microbial multiplication by utilizing water from thin, aqueous films or non‐liquid sources; whether prokaryotes were the first organisms able to multiply close to the 0.605‐a w limit; and whether extraterrestrial aqueous milieux of ≥ 0.605 a w can resemble fertile microbial habitats found on Earth.

QTL mapping and phenotypic variation of root anatomical traits in maize (Zea mays L.) - Amy L. Burton; James Johnson; Jillian Foerster; Meredith T. Hanlon; Shawn M. Kaeppler; Jonathan P. Lynch; Kathleen M. Brown (Theoretical and Applied Genetics, 2015)

Plant diversity predicts beta but not alpha diversity of soil microbes across grasslands worldwide - Suzanne M. Prober; Jonathan W. Leff; Scott T. Bates; Elizabeth T. Borer; Jennifer Firn; W. Stanley Harpole; Eric M. Lind; Eric W. Seabloom; Peter B. Adler; Jonathan D. Bakker; Elsa E. Cleland; Nicole M. DeCrappeo; et al. (Ecology Letters, 2015)
Aboveground–belowground interactions exert critical controls on the composition and function of terrestrial ecosystems, yet the fundamental relationships between plant diversity and soil microbial diversity remain elusive. Theory predicts predominantly positive associations but tests within single sites have shown variable relationships, and associations between plant and microbial diversity across broad spatial scales remain largely unexplored. We compared the diversity of plant, bacterial, archaeal and fungal communities in one hundred and forty‐five 1 m 2 plots across 25 temperate grassland sites from four continents. Across sites, the plant alpha diversity patterns were poorly related to those observed for any soil microbial group. However, plant beta diversity (compositional dissimilarity between sites) was significantly correlated with the beta diversity of bacterial and fungal communities, even after controlling for environmental factors. Thus, across a global range of temperate grasslands, plant diversity can predict patterns in the composition of soil microbial communities, but not patterns in alpha diversity.

Tri-modal regulation of cardiac muscle relaxation; intracellular calcium decline, thin filament deactivation, and cross-bridge cycling kinetics - Brandon J. Biesiadecki; Jonathan P. Davis; Mark T. Ziolo; Paul M. L. Janssen (Biophysical Reviews, 2014)

Association genetics, geography and ecophysiology link stomatal patterning in P opulus trichocarpa with carbon gain and disease resistance trade‐offs - Athena D. McKown; Robert D. Guy; Linda Quamme; Jaroslav Klápště; Jonathan La Mantia; C. P. Constabel; Yousry A. El‐Kassaby; Richard C. Hamelin; Michael Zifkin; M. S. Azam (Molecular Ecology, 2014)
Stomata are essential for diffusive entry of gases to support photosynthesis, but may also expose internal leaf tissues to pathogens. To uncover trade‐offs in range‐wide adaptation relating to stomata, we investigated the underlying genetics of stomatal traits and linked variability in these traits with geoclimate, ecophysiology, condensed foliar tannins and pathogen susceptibility in black cottonwood ( P opulus trichocarpa ). Upper (adaxial) and lower (abaxial) leaf stomatal traits were measured from 454 accessions collected throughout much of the species range. We calculated broad‐sense heritability ( H 2 ) of stomatal traits and, using SNP data from a 34 K P opulus SNP array, performed a genome‐wide association studies ( GWAS ) to uncover genes underlying stomatal trait variation. H 2 values for stomatal traits were moderate (average H 2 = 0.33). GWAS identified genes associated primarily with adaxial stomata, including polarity genes ( PHABULOSA ), stomatal development genes ( BRASSINOSTEROID ‐ INSENSITIVE 2 ) and disease/wound‐response genes ( GLUTAMATE ‐ CYSTEINE LIGASE ). Stomatal traits correlated with latitude, gas exchange, condensed tannins and leaf rust ( M elampsora ) infection. Latitudinal trends of greater adaxial stomata numbers and guard cell pore size corresponded with higher stomatal conductance ( g s ) and photosynthesis ( A max ), faster shoot elongation, lower foliar tannins and greater M elampsora susceptibility. This suggests an evolutionary trade‐off related to differing selection pressures across the species range. In northern environments, more adaxial stomata and larger pore sizes reflect selection for rapid carbon gain and growth. By contrast, southern genotypes have fewer adaxial stomata, smaller pore sizes and higher levels of condensed tannins, possibly linked to greater pressure from natural leaf pathogens, which are less significant in northern ecosystems.

QTL mapping and phenotypic variation for root architectural traits in maize (Zea mays L.) - Amy L. Burton; James M. Johnson; Jillian M. Foerster; Candice N. Hirsch; C. R. Buell; Meredith T. Hanlon; Shawn M. Kaeppler; Kathleen M. Brown; Jonathan P. Lynch (Theoretical and Applied Genetics, 2014)

Quantitative food web analysis supports the energy-limitation hypothesis in cave stream ecosystems - Michael P. Venarsky; Brock M. Huntsman; Alexander D. Huryn; Jonathan P. Benstead; Bernard R. Kuhajda (Oecologia, 2014)

Climate change and geothermal ecosystems: natural laboratories, sentinel systems, and future refugia - Eoin J. O'Gorman; Jonathan P. Benstead; Wyatt F. Cross; Nikolai Friberg; James M. Hood; Philip W. Johnson; Bjarni D. Sigurdsson; Guy Woodward (Global Change Biology, 2014)
Understanding and predicting how global warming affects the structure and functioning of natural ecosystems is a key challenge of the 21st century. Isolated laboratory and field experiments testing global change hypotheses have been criticized for being too small‐scale and overly simplistic, whereas surveys are inferential and often confound temperature with other drivers. Research that utilizes natural thermal gradients offers a more promising approach and geothermal ecosystems in particular, which span a range of temperatures within a single biogeographic area, allow us to take the laboratory into nature rather than vice versa . By isolating temperature from other drivers, its ecological effects can be quantified without any loss of realism, and transient and equilibrial responses can be measured in the same system across scales that are not feasible using other empirical methods. Embedding manipulative experiments within geothermal gradients is an especially powerful approach, informing us to what extent small‐scale experiments can predict the future behaviour of real ecosystems. Geothermal areas also act as sentinel systems by tracking responses of ecological networks to warming and helping to maintain ecosystem functioning in a changing landscape by providing sources of organisms that are preadapted to different climatic conditions. Here, we highlight the emerging use of geothermal systems in climate change research, identify novel research avenues, and assess their roles for catalysing our understanding of ecological and evolutionary responses to global warming.

nifH pyrosequencing reveals the potential for location‐specific soil chemistry to influence N 2 ‐fixing community dynamics - Mónica M. Collavino; H. James Tripp; Ildiko E. Frank; María L. Vidoz; Priscila A. Calderoli; Mariano Donato; Jonathan P. Zehr; O. Mario Aguilar (Environmental Microbiology, 2014)
Summary A dataset of 87 020 nifH reads and 16 782 unique nifH protein sequences obtained over 2 years from four locations across a gradient of agricultural soil types in A rgentina were analysed to provide a detailed and comprehensive picture of the diversity, abundance and responses of the N 2 ‐fixing community in relation to differences in soil chemistry and agricultural practices. Phylogenetic analysis revealed an expected high proportion of A lphaproteobacteria , B etaproteobacteria and D eltaproteobacteria , mainly relatives to B radyrhizobium and M ethylosinus / M ethylocystis , but a surprising paucity of G ammaproteobacteria . Analysis of variance and stepwise regression modelling suggested location and treatment‐specific influences of soil type on diazotrophic community composition and organic carbon concentrations on nifH diversity. nifH gene abundance, determined by quantitative real‐time polymerase chain reaction, was higher in agricultural soils than in non‐agricultural soils, and was influenced by soil chemistry under intensive crop rotation but not under monoculture. At some locations, sustainable increased crop yields might be possible through the management of soil chemistry to improve the abundance and diversity of N 2 ‐fixing bacteria.

Seasonal changes in light availability modify the temperature dependence of ecosystem metabolism in an arctic stream - Alexander D. Huryn; Jonathan P. Benstead; Stephanie M. Parker (Ecology, 2014)
Light and temperature are key ecosystem drivers, but their synchronous annual cycles typically confound partitioning of their relative influence. Arctic spring‐streams, subject to extreme annual fluctuations in light but stable water temperatures, provide a rare contrast that allows the parsing of their independent effects. Over 30 months, we assessed the effects of light and temperature on ecosystem metabolism and nutrient uptake in Ivishak Spring, Alaska, USA. (latitude 69° N, water temperature range ∼4°–7°C) using open‐channel methods and short‐term NH 4 + ‐N, NO 3 − ‐N, and P additions, respectively. We predicted that rates of ecosystem respiration (ER) would mirror seasonal patterns of gross primary production (GPP), rather than temperature, due to relatively constant rates of metabolic demand year‐round, resulting in carbon limitation during winter (October–March) when photosynthesis effectively ceases. Because patterns of nutrient uptake and GPP are often coupled due to assimilatory demand, we also predicted that extreme annual cycles of light would result in equally extreme cycles of nutrient uptake, with demand being relaxed during winter. In accordance with our prediction, we found that ER scaled linearly with GPP. Peak summer rates of GPP (>4.0 g C·m −2 ·d −1 ) and ER (>5.0 g C·m −2 ·d −1 ) were surprisingly high, being comparable to those of productive streams at temperate latitudes. Winter rates (GPP ∼0.0, ER −2 ·d −1 ) were low, however, and Arrhenius plots showed clear deviations from theoretical temperature dependence of GPP and ER during winter when other factors assumed primacy. For GPP, this factor was undoubtedly light availability, but for ER, carbon limitation is implicated due to low GPP. Significant nutrient uptake occurred only for NH 4 + ‐N, indicating N limitation, and rates of uptake were also synchronous with cycles of light availability. Consequently, light, rather than temperature, was the major driver of annual patterns of ER and nutrient cycles in this arctic ecosystem. Synchronous light and temperature cycles are pervasive among ecosystems. The winter onset and severity of energy limitation we document highlights the importance of this synchrony and how the confounding of light and temperature obscures details of mechanisms by which these fundamental drivers affect ecosystem processes.

Coupling of dietary phosphorus and growth across diverse fish taxa: a meta‐analysis of experimental aquaculture studies - Jonathan P. Benstead; James M. Hood; Nathan V. Whelan; Michael R. Kendrick; Daniel Nelson; Amanda F. Hanninen; Lee M. Demi (Ecology, 2014)
Imbalances in phosphorus (P) intake relative to demand negatively affect animal growth, but their consequences are less understood for vertebrates, in which bone represents a significant and potentially flexible pool of P. Flexibility in body‐P content could buffer vertebrates from the effects of imbalances between P intake and demand, reducing the likelihood of a sharp stoichiometric “knife‐edge” in the relationship between growth rate and diet‐P level. We conducted a meta‐analysis of published aquaculture experiments that tested effects of diet %P on fish growth rate (49 studies, 28 species) and body‐P content (27 of the studies in the main data set, 20 species). Our meta‐analysis revealed significant P limitation of growth, as well as significant negative effects of excess P on growth rate. Diet‐P thresholds for these effects occurred at ecologically relevant levels (optimal diet‐P of 1.2% ± 0.45%, mean ± SD, under experimental conditions of high ration). Finally, the analysis also suggested a pattern of relatively shallow relationships between growth rate and diet‐P level, coupled with surprisingly flexible body‐P content in fishes. This result is consistent with fish using flexible body‐P content (presumably mediated through bone P) to buffer imbalances between P intake and demand. Together, our results provide evidence for a relatively “dull” stoichiometric “knife‐edge” in fishes, driven in part by flexible body‐P content.

A bioenergetic framework for the temperature dependence of trophic interactions - Benjamin Gilbert; Tyler D. Tunney; Kevin S. McCann; John P. DeLong; David A. Vasseur; Van Savage; Jonathan B. Shurin; Anthony I. Dell; Brandon T. Barton; Christopher D.G. Harley; Heather M. Kharouba; Pavel Kratina; et al. (Ecology Letters, 2014)
Changing temperature can substantially shift ecological communities by altering the strength and stability of trophic interactions. Because many ecological rates are constrained by temperature, new approaches are required to understand how simultaneous changes in multiple rates alter the relative performance of species and their trophic interactions. We develop an energetic approach to identify the relationship between biomass fluxes and standing biomass across trophic levels. Our approach links ecological rates and trophic dynamics to measure temperature‐dependent changes to the strength of trophic interactions and determine how these changes alter food web stability. It accomplishes this by using biomass as a common energetic currency and isolating three temperature‐dependent processes that are common to all consumer–resource interactions: biomass accumulation of the resource, resource consumption and consumer mortality. Using this framework, we clarify when and how temperature alters consumer to resource biomass ratios, equilibrium resilience, consumer variability, extinction risk and transient vs. equilibrium dynamics. Finally, we characterise key asymmetries in species responses to temperature that produce these distinct dynamic behaviours and identify when they are likely to emerge. Overall, our framework provides a mechanistic and more unified understanding of the temperature dependence of trophic dynamics in terms of ecological rates, biomass ratios and stability.

Trace metal in beach sediments of Velanganni Coast, South India: application of autoclave leach method - P. Krishnakumar; C. Lakshumanan; M. P. Jonathan; M. Sundararajan; M. Navarrete-Lopez (Arabian Journal of Geosciences, 2014)

The contribution of muscle hypertrophy to strength changes following resistance training - Robert M. Erskine; Gareth Fletcher; Jonathan P. Folland (European Journal of Applied Physiology, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Low genetic variation in cold tolerance linked to species distributions in butterflies - Jonathan M. P. Davis; Belinda van Heerwaarden; Carla M. Sgrò; Jennifer A. Donald; Darrell J. Kemp (Evolutionary Ecology, 2014)

Life on the edge: thermal optima for aerobic scope of equatorial reef fishes are close to current day temperatures - Jodie L. Rummer; Christine S. Couturier; Jonathan A. W. Stecyk; Naomi M. Gardiner; Jeff P. Kinch; Göran E. Nilsson; Philip L. Munday (Global Change Biology, 2014)
Equatorial populations of marine species are predicted to be most impacted by global warming because they could be adapted to a narrow range of temperatures in their local environment. We investigated the thermal range at which aerobic metabolic performance is optimum in equatorial populations of coral reef fish in northern Papua New Guinea. Four species of damselfishes and two species of cardinal fishes were held for 14 days at 29, 31, 33, and 34 °C, which incorporated their existing thermal range (29–31 °C) as well as projected increases in ocean surface temperatures of up to 3 °C by the end of this century. Resting and maximum oxygen consumption rates were measured for each species at each temperature and used to calculate the thermal reaction norm of aerobic scope. Our results indicate that one of the six species, Chromis atripectoralis , is already living above its thermal optimum of 29 °C. The other five species appeared to be living close to their thermal optima (ca. 31 °C). Aerobic scope was significantly reduced in all species, and approached zero for two species at 3 °C above current‐day temperatures. One species was unable to survive even short‐term exposure to 34 °C. Our results indicate that low‐latitude reef fish populations are living close to their thermal optima and may be more sensitive to ocean warming than higher‐latitude populations. Even relatively small temperature increases (2–3 °C) could result in population declines and potentially redistribution of equatorial species to higher latitudes if adaptation cannot keep pace.

Shoulder impingement revisited: evolution of diagnostic understanding in orthopedic surgery and physical therapy - Jonathan P. Braman; Kristin D. Zhao; Rebekah L. Lawrence; Alicia K. Harrison; Paula M. Ludewig (Medical & Biological Engineering & Computing, 2014)

A glossary for biometeorology - Simon N. Gosling; Erin K. Bryce; P. Grady Dixon; Katharina M. A. Gabriel; Elaine Y. Gosling; Jonathan M. Hanes; David M. Hondula; Liang Liang; Priscilla Ayleen Bustos Mac Lean; Stefan Muthers; Sheila Tavares Nascimento; Martina Petralli; et al. (International Journal of Biometeorology, 2014)

The significance of past interdrainage connectivity for studies of diversity, distribution and movement of freshwater‐limited taxa within a catchment - Cecilia Carrea; Leigh V. Anderson; Dave Craw; Jonathan M. Waters; Christopher P. Burridge (Journal of Biogeography, 2014)
Aim Historical connectivity between drainages may represent an underappreciated contributor to the biodiversity within a catchment. First, we tested whether an isolated population of freshwater‐limited galaxiids represents a contribution by past interdrainage connectivity to this system's biodiversity, rather than reflecting intracatchment dispersal or speciation. Second, we sought to distinguish between possible geomorphic processes that could have allowed any past connectivity. Location The Clutha and adjacent Southland region drainages on the South Island of New Zealand. Methods We estimated the phylogeographical relationships among 466 cytochrome b sequences from ‘roundhead’ Galaxias populations throughout the Southland region and the Clutha drainage, using three different methods. Subsequently, possible geomorphic mechanisms of interdrainage connectivity were examined concurrently with genetic population divergence time estimates obtained by coalescent analysis. Results All samples obtained in the lower Clutha system were genetically attributable to G. gollumoides and reflected at least a third, independent colonization event from Southland involving this species, rather than intradrainage dispersal or speciation by pre‐existing Clutha populations. Geomorphological inferences and divergence time estimates of less than 7 ka are consistent with headwater connections across low divides between the lower Clutha and the Catlins region of Southland, rather than anastomosing of main channels during low sea stands. Main conclusions The observation of at least three interdrainage connectivity events influencing the diversity and distribution of G. gollumoides lineages within the Clutha system highlights the potential significance of these processes as contributors to the magnitude and distribution of biodiversity within catchments.

Kinetics of the reaction between the hydroxyl radical and organic matter standards from the International Humic Substance Society - Garrett McKay; Jonathan L. Kleinman; Kimberly M. Johnston; Mei Mei Dong; Fernando L. Rosario-Ortiz; Stephen P. Mezyk (Journal of Soils and Sediments, 2014)

Abrupt deglaciation on the northeastern Tibetan Plateau: evidence from Lake Qinghai - Xiuju Liu; Steven M. Colman; Erik T. Brown; Andrew C. G. Henderson; Josef P. Werne; Jonathan A. Holmes (Journal of Paleolimnology, 2014)

Effects of probiotics supplementation on gastrointestinal permeability, inflammation and exercise performance in the heat - Cecilia M. Shing; Jonathan M. Peake; Chin Leong Lim; David Briskey; Neil P. Walsh; Matthew B. Fortes; Kiran D. K. Ahuja; Luis Vitetta (European Journal of Applied Physiology, 2014)

Characterization of As and trace metals embedded in PM10 particles in Puebla City, México - S. S. Morales-García; P. F. Rodríguez-Espinosa; M. P. Jonathan; M. Navarrete-López; M. A. Herrera-García; N. P. Muñoz-Sevilla (Environmental Monitoring and Assessment, 2014)

Parametric Comparisons of Intracranial Mechanical Responses from Three Validated Finite Element Models of the Human Head - Songbai Ji; Hamidreza Ghadyani; Richard P. Bolander; Jonathan G. Beckwith; James C. Ford; Thomas W. McAllister; Laura A. Flashman; Keith D. Paulsen; Karin Ernstrom; Sonia Jain; Rema Raman; Liying Zhang; et al. (Annals of Biomedical Engineering, 2014)

Riluzole Partially Rescues Age-Associated, but not LPS-Induced, Loss of Glutamate Transporters and Spatial Memory - Holly M. Brothers; Isabelle Bardou; Sarah C. Hopp; Roxanne M. Kaercher; Angela W. Corona; Ashley M. Fenn; Jonathan P. Godbout; Gary L. Wenk (Journal of Neuroimmune Pharmacology, 2013)

Predicting invasion in grassland ecosystems: is exotic dominance the real embarrassment of richness? - Eric W. Seabloom; Elizabeth T. Borer; Yvonne Buckley; Elsa E. Cleland; Kendi Davies; Jennifer Firn; W. Stanley Harpole; Yann Hautier; Eric Lind; Andrew MacDougall; John L. Orrock; Suzanne M. Prober; et al. (Global Change Biology, 2013)
Invasions have increased the size of regional species pools, but are typically assumed to reduce native diversity. However, global‐scale tests of this assumption have been elusive because of the focus on exotic species richness, rather than relative abundance. This is problematic because low invader richness can indicate invasion resistance by the native community or, alternatively, dominance by a single exotic species. Here, we used a globally replicated study to quantify relationships between exotic richness and abundance in grass‐dominated ecosystems in 13 countries on six continents, ranging from salt marshes to alpine tundra. We tested effects of human land use, native community diversity, herbivore pressure, and nutrient limitation on exotic plant dominance. Despite its widespread use, exotic richness was a poor proxy for exotic dominance at low exotic richness, because sites that contained few exotic species ranged from relatively pristine (low exotic richness and cover) to almost completely exotic‐dominated ones (low exotic richness but high exotic cover). Both exotic cover and richness were predicted by native plant diversity (native grass richness) and land use (distance to cultivation). Although climate was important for predicting both exotic cover and richness, climatic factors predicting cover (precipitation variability) differed from those predicting richness (maximum temperature and mean temperature in the wettest quarter). Herbivory and nutrient limitation did not predict exotic richness or cover. Exotic dominance was greatest in areas with low native grass richness at the site‐ or regional‐scale. Although this could reflect native grass displacement, a lack of biotic resistance is a more likely explanation, given that grasses comprise the most aggressive invaders. These findings underscore the need to move beyond richness as a surrogate for the extent of invasion, because this metric confounds monodominance with invasion resistance. Monitoring species' relative abundance will more rapidly advance our understanding of invasions.

Predicting species distributions for conservation decisions - Antoine Guisan; Reid Tingley; John B. Baumgartner; Ilona Naujokaitis‐Lewis; Patricia R. Sutcliffe; Ayesha I. T. Tulloch; Tracey J. Regan; Lluis Brotons; Eve McDonald‐Madden; Chrystal Mantyka‐Pringle; Tara G. Martin; Jonathan R. Rhodes; et al. (Ecology Letters, 2013)
Species distribution models (SDMs) are increasingly proposed to support conservation decision making. However, evidence of SDMs supporting solutions for on‐ground conservation problems is still scarce in the scientific literature. Here, we show that successful examples exist but are still largely hidden in the grey literature, and thus less accessible for analysis and learning. Furthermore, the decision framework within which SDMs are used is rarely made explicit. Using case studies from biological invasions, identification of critical habitats, reserve selection and translocation of endangered species, we propose that SDMs may be tailored to suit a range of decision‐making contexts when used within a structured and transparent decision‐making process. To construct appropriate SDMs to more effectively guide conservation actions, modellers need to better understand the decision process, and decision makers need to provide feedback to modellers regarding the actual use of SDMs to support conservation decisions. This could be facilitated by individuals or institutions playing the role of ‘translators’ between modellers and decision makers. We encourage species distribution modellers to get involved in real decision‐making processes that will benefit from their technical input; this strategy has the potential to better bridge theory and practice, and contribute to improve both scientific knowledge and conservation outcomes.

The reduced mycorrhizal colonisation (rmc) mutation of tomato disrupts five gene sequences including the CYCLOPS/IPD3 homologue - Nicholas J. Larkan; Dan R. Ruzicka; Tamara Edmonds-Tibbett; Jonathan M. H. Durkin; Louise E. Jackson; F. Andrew Smith; Daniel P. Schachtman; Sally E. Smith; Susan J. Barker (Mycorrhiza, 2013)

Speciation of selected heavy metals geochemistry in surface sediments from Tirumalairajan river estuary, east coast of India - S. Venkatramanan; T. Ramkumar; I. Anithamary; M. P. Jonathan (Environmental Monitoring and Assessment, 2013)

Interlineage Mytilus galloprovincialis Lmk. 1819 hybridization yields inconsistent genetic outcomes in the Southern hemisphere - Kristen M. Westfall; Jonathan P. A. Gardner (Biological Invasions, 2013)

Biotic and abiotic controls on body size during critical life history stages of a pelagic fish, Pacific herring ( Clupea pallasii ) - Jonathan C. P. Reum; Timothy E. Essington; Correigh M. Greene; Casimir A. Rice; Patrick Polte; Kurt L. Fresh (Fisheries Oceanography, 2013)
Variation in growth and body size during critical life history stages can have important implications for life history schedules and survivorship. For P acific herring ( Clupea pallasii ), there is still debate as to whether juvenile body size is governed by density‐dependent or ‐independent processes and few have evaluated whether the relative importance of either process shifts over the course of early ontogeny. We used a unique data set consisting of seasonal measurements of abundance, body size, and spatial distribution within a semi‐enclosed basin of P uget S ound ( W ashington S tate, U . S . A .) to measure the relative importance of temperature and cohort abundance on body size at distinct time periods, and evaluated whether density‐dependent habitat shifts might be responsible for density‐dependent growth. Over the 9 years of sampling (2001–2010) midsummer body size was positively related to temperatures experienced during the egg/yolk sac and larval stages and unrelated to cohort abundance. However, fall body size was negatively correlated with abundance and uncorrelated with both midsummer body size and temperature, indicating a shift from density‐independent to density‐dependent control over the course of the growing season. Thus, density‐dependent effects may supplant density‐independent effects exhibited early in herring life history. Our data on spatial distributions of herring and their zooplankton prey indicate that density‐dependent reductions in growth may be explained by density‐dependent habitat shifts that lead to reduce overlap of herring with zooplankton. Evidence of density‐dependent growth in marine fish populations is often attributed to exploitative competition, but our results suggest that these patterns may partly be mediated by density‐dependent distribution expansions in to prey‐poor habitat.

Spatial distribution and phenotypic variation in root cortical aerenchyma of maize (Zea mays L.) - Amy L. Burton; Jonathan P. Lynch; Kathleen M. Brown (Plant and Soil, 2013)

Protein ingestion does not impair exercise-induced AMPK signalling when in a glycogen-depleted state: implications for train-low compete-high - Conor Taylor; Jonathan D. Bartlett; Christian Soler van de Graaf; Jari Louhelainen; Vicki Coyne; Zafar Iqbal; Don P. M. MacLaren; Warren Gregson; Graeme L. Close; James P. Morton (European Journal of Applied Physiology, 2013)

Knee extensor strength differences in obese and healthy-weight 10-to 13-year-olds - Margarita D. Tsiros; Alison M. Coates; Peter R. C. Howe; Paul N. Grimshaw; Jeff Walkley; Anthony Shield; Richard Mallows; Andrew P. Hills; Masaharu Kagawa; Sarah Shultz; Jonathan D. Buckley (European Journal of Applied Physiology, 2013)

US EPA particulate matter research centers: summary of research results for 2005–2011 - Patrick N. Breysse; Ralph J. Delfino; Francesca Dominici; Alison C. P. Elder; Mark W. Frampton; John R. Froines; Alison S. Geyh; John J. Godleski; Diane R. Gold; Philip K. Hopke; Petros Koutrakis; Ning Li; et al. (Air Quality, Atmosphere & Health, 2013)

Mechanistic Basis for Type 2 Long QT Syndrome Caused by KCNH2 Mutations that Disrupt Conserved Arginine Residues in the Voltage Sensor - Christie M. McBride; Ashley M. Smith; Jennifer L. Smith; Allison R. Reloj; Ellyn J. Velasco; Jonathan Powell; Claude S. Elayi; Daniel C. Bartos; Don E. Burgess; Brian P. Delisle (The Journal of Membrane Biology, 2013)

Storage and eruption of near-liquidus rhyolite magma at Cordón Caulle, Chile - Jonathan M. Castro; C. Ian Schipper; Sebastian P. Mueller; A. S. Militzer; Alvaro Amigo; Carolina Silva Parejas; Dorrit Jacob (Bulletin of Volcanology, 2013)

Outcome Evaluation of the National Cancer Institute Career Development Awards Program - Julie L. Mason; Ming Lei; Jessica M. Faupel-Badger; Erika P. Ginsburg; Yvette R. Seger; Leo DiJoseph; Joshua D. Schnell; Jonathan S. Wiest (Journal of Cancer Education, 2013)

Cyclodextrin-Crosslinked Poly(Acrylic Acid): Adhesion and Controlled Release of Diflunisal and Fluconazole from Solid Dosage Forms - Marguerite J. Kutyła; Michael W. Boehm; Jason R. Stokes; P. Nicholas Shaw; Nigel M. Davies; Ross P. McGeary; Jonathan Tuke; Benjamin P. Ross (AAPS PharmSciTech, 2013)

Physiological effects of diet mixing on consumer fitness: a meta‐analysis - Jonathan S. Lefcheck; Matthew A. Whalen; Theresa M. Davenport; Joshua P. Stone; J. Emmett Duffy (Ecology, 2013)
The degree of dietary generalism among consumers has important consequences for population, community, and ecosystem processes, yet the effects on consumer fitness of mixing food types have not been examined comprehensively. We conducted a meta‐analysis of 161 peer‐reviewed studies reporting 493 experimental manipulations of prey diversity to test whether diet mixing enhances consumer fitness based on the intrinsic nutritional quality of foods and consumer physiology. Averaged across studies, mixed diets conferred significantly higher fitness than the average of single‐species diets, but not the best single prey species. More than half of individual experiments, however, showed maximal growth and reproduction on mixed diets, consistent with the predicted benefits of a balanced diet. Mixed diets including chemically defended prey were no better than the average prey type, opposing the prediction that a diverse diet dilutes toxins. Finally, mixed‐model analysis showed that the effect of diet mixing was stronger for herbivores than for higher trophic levels. The generally weak evidence for the nutritional benefits of diet mixing in these primarily laboratory experiments suggests that diet generalism is not strongly favored by the inherent physiological benefits of mixing food types, but is more likely driven by ecological and environmental influences on consumer foraging.

Classifying inundation limits in SE coast of India: application of GIS - G. Muthusankar; C. Lakshumanan; V. Pradeep-Kishore; S. Eswaramoorthi; M. P. Jonathan (Natural Hazards, 2013)

Genetic diversity in a reintroduced swift fox population - Indrani Sasmal; Jonathan A. Jenks; Lisette P. Waits; Michael G. Gonda; Greg M. Schroeder; Shubham Datta (Conservation Genetics, 2013)

Stochastic and deterministic drivers of spatial and temporal turnover in breeding bird communities - James C. Stegen; Amy L. Freestone; Thomas O. Crist; Marti J. Anderson; Jonathan M. Chase; Liza S. Comita; Howard V. Cornell; Kendi F. Davies; Susan P. Harrison; Allen H. Hurlbert; Brian D. Inouye; Nathan J. B. Kraft; et al. (Global Ecology and Biogeography, 2013)
Aim A long‐standing challenge in ecology is to identify the suite of factors that lead to turnover in species composition in both space and time. These factors might be stochastic (e.g. sampling and priority effects) or deterministic (e.g. competition and environmental filtering). While numerous studies have examined the relationship between turnover and individual drivers of interest (e.g. primary productivity, habitat heterogeneity, or regional – ‘gamma’ – diversity), few studies have disentangled the simultaneous influences of multiple stochastic and deterministic processes on both temporal and spatial turnover. If turnover is governed primarily by stochastic sampling processes, removing the sampling effects of gamma diversity should result in non‐significant relationships between turnover and environmental variables. Conversely, if deterministic processes govern turnover patterns, removing sampling effects will have little influence on turnover gradients. Here, we test these predictions. Location The United States. Methods Continental‐scale, multidecadal data were used to quantify spatial and temporal turnover in avian community composition within 295 survey routes. A series of regression and structural equation models were coupled with a null model to construct statistical models describing turnover patterns. Results Examining explanatory variables alone or in combination showed that spatial and temporal turnover increased together, decreased with primary productivity and increased with habitat heterogeneity. The relationships between turnover and all variables became weaker when sampling effects were removed, but relationships with primary productivity and habitat heterogeneity remained relatively strong. In addition, spatial turnover increased strongly with spatial gamma diversity after sampling effects were removed. Main conclusions Our results show that spatial and temporal turnover are related to each other through a stochastic sampling process, but that each type of turnover is further influenced by deterministic processes. The relative influence of deterministic processes appears, however, to decrease with primary productivity and increase with habitat heterogeneity across an east–west longitudinal gradient in North America.

The association between chronic renal failure and renal cell carcinoma may differ between black and white Americans - Jonathan N. Hofmann; Kendra Schwartz; Wong-Ho Chow; Julie J. Ruterbusch; Brian M. Shuch; Sara Karami; Nathaniel Rothman; Sholom Wacholder; Barry I. Graubard; Joanne S. Colt; Mark P. Purdue (Cancer Causes & Control, 2013)

Histidine ligand variants of a flavo-diiron protein: effects on structure and activities - Han Fang; Jonathan D. Caranto; Rosalinda Mendoza; Alexander B. Taylor; P. John Hart; Donald M. Kurtz (JBIC Journal of Biological Inorganic Chemistry, 2012)

Heterozygote FANCD2 mutations associated with childhood T Cell ALL and testicular seminoma - Stephanie Smetsers; Joanne Muter; Claire Bristow; Leena Patel; Kate Chandler; Denise Bonney; Robert F. Wynn; Anthony D. Whetton; Andrew M. Will; Davy Rockx; Hans Joenje; Gordon Strathdee; et al. (Familial Cancer, 2012)

ABO blood group and risk of epithelial ovarian cancer within the Ovarian Cancer Association Consortium - Elizabeth M. Poole; Margaret A. Gates; Brigit A. High; Stephen J. Chanock; Daniel W. Cramer; Julie M. Cunningham; Brooke L. Fridley; Simon A. Gayther; Ellen L. Goode; Edwin S. Iversen; Jolanta Lissowska; Rachel T. Palmieri Weber; et al. (Cancer Causes & Control, 2012)

The mammalian gene function resource: the international knockout mouse consortium - Allan Bradley; Konstantinos Anastassiadis; Abdelkader Ayadi; James F. Battey; Cindy Bell; Marie-Christine Birling; Joanna Bottomley; Steve D. Brown; Antje Bürger; Carol J. Bult; Wendy Bushell; Francis S. Collins; et al. (Mammalian Genome, 2012)

Influence of passive lower-body heating on muscle metabolic perturbation and high-intensity exercise tolerance in humans - Stephen J. Bailey; Daryl P. Wilkerson; Jonathan Fulford; Andrew M. Jones (European Journal of Applied Physiology, 2012)

Erratum to: Progression of cutaneous melanoma: implications for treatment - Stanley P. L. Leong; Martin C. Mihm; George F. Murphy; Dave S. B. Hoon; Mohammed Kashani-Sabet; Sanjiv S. Agarwala; Jonathan S. Zager; Axel Hauschild; Vernon K. Sondak; Valerie Guild; John M. Kirkwood (Clinical & Experimental Metastasis, 2012)

Progression of cutaneous melanoma: implications for treatment - Stanley P. L. Leong; Martin C. Mihm; George F. Murphy; Dave S. B. Hoon; Mohammed Kashani-Sabet; Sanjiv S. Agarwala; Jonathan S. Zager; Axel Hauschild; Vernon K. Sondak; Valerie Guild; John M. Kirkwood (Clinical & Experimental Metastasis, 2012)

RootScan: Software for high-throughput analysis of root anatomical traits - Amy L. Burton; Michael Williams; Jonathan P. Lynch; Kathleen M. Brown (Plant and Soil, 2012)

Cystic fibrosis transmembrane conductance regulator in the gills of the climbing perch, Anabas testudineus, is involved in both hypoosmotic regulation during seawater acclimation and active ammonia excretion during ammonia exposure - Yuen K. Ip; Jonathan M. Wilson; Ai M. Loong; Xiu L. Chen; Wai P. Wong; Inês L. S. Delgado; Siew H. Lam; Shit F. Chew (Journal of Comparative Physiology B, 2012)

Effect of nutritional interventions and resistance exercise on aging muscle mass and strength - Darren G. Candow; Scott C. Forbes; Jonathan P. Little; Stephen M. Cornish; Craig Pinkoski; Philip D. Chilibeck (Biogerontology, 2012)

Offshore depositional sequence of 2004 tsunami from Chennai, SE coast of India - M. P. Jonathan; S. Srinivasalu; N. Thangadurai; N. Rajeshwara-Rao; V. Ram-Mohan; T. Narmatha (Natural Hazards, 2012)

Influence of year and genetic factors on chilling injury susceptibility in peach (Prunus persica (L.) Batsch) - Pedro J. Martínez-García; Cameron P. Peace; Dan E. Parfitt; Ebenezer A. Ogundiwin; Jonathan Fresnedo-Ramírez; Abhaya M. Dandekar; Thomas M. Gradziel; Carlos H. Crisosto (Euphytica, 2012)

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Autoclave decomposition method for metals in soils and sediments - M. Navarrete-López; M. P. Jonathan; P. F. Rodríguez-Espinosa; J. A. Salgado-Galeana (Environmental Monitoring and Assessment, 2012)

Cognitive and Behavioral Consequences of Impaired Immunoregulation in Aging - Angela W. Corona; Ashley M. Fenn; Jonathan P. Godbout (Journal of Neuroimmune Pharmacology, 2012)

The Effects of Permafrost Thaw on Soil Hydrologic, Thermal, and Carbon Dynamics in an Alaskan Peatland - Jonathan A. O’Donnell; M. Torre Jorgenson; Jennifer W. Harden; A. David McGuire; Mikhail Z. Kanevskiy; Kimberly P. Wickland (Ecosystems, 2012)

A parametric sensitivity study of entropy production and kinetic energy dissipation using the FAMOUS AOGCM - Salvatore Pascale; Jonathan M. Gregory; Maarten H. P. Ambaum; Rémi Tailleux (Climate Dynamics, 2012)

Potential climatic transitions with profound impact on Europe - Anders Levermann; Jonathan L. Bamber; Sybren Drijfhout; Andrey Ganopolski; Winfried Haeberli; Neil R. P. Harris; Matthias Huss; Kirstin Krüger; Timothy M. Lenton; Ronald W. Lindsay; Dirk Notz; Peter Wadhams; et al. (Climatic Change, 2012)

Marine dispersal as a pre‐requisite for Gondwanan vicariance among elements of the galaxiid fish fauna - Christopher P. Burridge; Robert M. McDowall; Dave Craw; Mark V. H. Wilson; Jonathan M. Waters (Journal of Biogeography, 2012)
Aim The aim of this study was to determine the contributions of Gondwanan vicariance and marine dispersal to the contemporary distribution of galaxiid fishes. This group has been central in arguments concerning the roles of dispersal and vicariance in the Southern Hemisphere, as some taxa have marine life history stages through which transoceanic dispersal may have been facilitated, yet other galaxiids are entirely restricted to freshwaters. Location Southern Hemisphere land masses of Gondwanan derivation. Methods Biogeographic hypotheses of Gondwanan vicariance and marine dispersal were tested using four lines of evidence: (1) concordance of species–area phylogenetic relationships, (2) molecular estimates of lineage divergence times with a priori expectations based on plate tectonics, (3) reconstructions of ancestral dispersal capabilities, and (4) reconstructions of distribution inheritance scenarios (using the dispersal–extinction–cladogenesis model to infer historical ranges and dispersal and extinction events). Results Phylogenetic relationships were reconstructed from 4531 mitochondrial and nuclear nucleotide characters, and 181 morphological characters, across 53 of the 56 presently recognized species. Phylogenetic relationships were generally well resolved and supported among galaxiids using the combined dataset, and conflicting relationships between molecular and morphological datasets typically received low topological support from either or both datasets. Transoceanic disjunctions were exhibited at 16 nodes, but only three pre‐dated relevant continental fragmentation events; furthermore, ancestral distribution inheritance scenarios for two of these nodes reflected cladogenesis within, rather than between, Gondwanan land masses, and ancestral marine dispersal capability could not be rejected for all three. Instead, the four lines of evidence surveyed suggest that Gondwanan vicariance occurred twice, but in both instances was preceded by marine dispersal between land masses, and in at least one instance was initiated by the cessation of marine dispersal subsequent to continental fragmentation. Main conclusions Gondwanan vicariance appears to have been preceded by marine dispersal in the few instances where it may explain contemporary galaxiid distribution, such that these biogeographic mechanisms may sometimes have a synergistic relationship.

Rotational Head Kinematics in Football Impacts: An Injury Risk Function for Concussion - Steven Rowson; Stefan M. Duma; Jonathan G. Beckwith; Jeffrey J. Chu; Richard M. Greenwald; Joseph J. Crisco; P. Gunnar Brolinson; Ann-Christine Duhaime; Thomas W. McAllister; Arthur C. Maerlender (Annals of Biomedical Engineering, 2012)
Recent research has suggested a possible link between sports-related concussions and neurodegenerative processes, highlighting the importance of developing methods to accurately quantify head impact tolerance. The use of kinematic parameters of the head to predict brain injury has been suggested because they are indicative of the inertial response of the brain. The objective of this study is to characterize the rotational kinematics of the head associated with concussive impacts using a large head acceleration dataset collected from human subjects. The helmets of 335 football players were instrumented with accelerometer arrays that measured head acceleration following head impacts sustained during play, resulting in data for 300,977 sub-concussive and 57 concussive head impacts. The average sub-concussive impact had a rotational acceleration of 1230 rad/s 2 and a rotational velocity of 5.5 rad/s, while the average concussive impact had a rotational acceleration of 5022 rad/s 2 and a rotational velocity of 22.3 rad/s. An injury risk curve was developed and a nominal injury value of 6383 rad/s 2 associated with 28.3 rad/s represents 50% risk of concussion. These data provide an increased understanding of the biomechanics associated with concussion and they provide critical insight into injury mechanisms, human tolerance to mechanical stimuli, and injury prevention techniques.

Multiple Effects of Changes in Arctic Snow Cover - Terry V. Callaghan; Margareta Johansson; Ross D. Brown; Pavel Ya. Groisman; Niklas Labba; Vladimir Radionov; Raymond S. Bradley; Sylvie Blangy; Olga N. Bulygina; Torben R. Christensen; Jonathan E. Colman; Richard L. H. Essery; et al. (Ambio, 2011)

Phenotypic variability and modelling of root structure of wild Lupinus angustifolius genotypes - Ying Long Chen; Vanessa M. Dunbabin; Johannes A. Postma; Art J. Diggle; Jairo A. Palta; Jonathan P. Lynch; Kadambot H. M. Siddique; Zed Rengel (Plant and Soil, 2011)

Mercury concentrations in oligohaline wetland vegetation and associated soil biogeochemistry - Jonathan M. Willis; Robert P. Gambrell; Mark W. Hester (Environmental Monitoring and Assessment, 2011)

Field survey report on the 11th March 2011 tsunami in Pacific coast of Mexico - M. P. Jonathan; P. D. Roy; J. L. Sánchez-Zavala; S. Srinivasalu; M. C. Macías-Romo; C. Lakshumanan (Natural Hazards, 2011)

Connectivity, small islands and large distances: the Cellana strigilis limpet complex in the Southern Ocean - CÉLINE M. O. REISSER; ANN R. WOOD; JAMES J. BELL; JONATHAN P. A. GARDNER (Molecular Ecology, 2011)
The Southern Ocean contains some of the most isolated islands on Earth, and fundamental questions remain regarding their colonization and the connectivity of their coastal biotas. Here, we conduct a genetic investigation into the Cellana strigilis (limpet) complex that was originally classified based on morphological characters into six subspecies, five of which are endemic to the New Zealand (NZ) subantarctic and Chatham islands (44–52°S). Previous genetic analyses of C. strigilis from six of the seven island groups revealed two lineages with little or no within‐lineage variation. We analysed C. strigilis samples from all seven island groups using two mitochondrial (COI and 16S), one nuclear (ATPase β) and 58 loci from four randomly amplified polymorphic DNA markers (RAPDs) and confirmed the existence of two distinct lineages. The pronounced genetic structuring within each lineage and the presence of private haplotypes in individual islands are the result of little genetic connectivity and therefore very high self‐recruitment. This study supports the significance of the subantarctic islands as refugia during the last glacial maximum and adds to the knowledge of contemporary population connectivity among coastal populations of remote islands in large oceans and the distance barrier to gene flow that exists in the sea (despite its continuous medium) for most taxa.

The Why, What, and How of Global Biodiversity Indicators Beyond the 2010 Target - JULIA P. G. JONES; BEN COLLEN; GILES ATKINSON; PETER W. J. BAXTER; PHILIP BUBB; JANINE B. ILLIAN; TODD E. KATZNER; AIDAN KEANE; JONATHAN LOH; EVE MCDONALD‐MADDEN; EMILY NICHOLSON; HENRIQUE M. PEREIRA; et al. (Conservation Biology, 2011)
The 2010 biodiversity target agreed by signatories to the Convention on Biological Diversity directed the attention of conservation professionals toward the development of indicators with which to measure changes in biological diversity at the global scale. We considered why global biodiversity indicators are needed, what characteristics successful global indicators have, and how existing indicators perform. Because monitoring could absorb a large proportion of funds available for conservation, we believe indicators should be linked explicitly to monitoring objectives and decisions about which monitoring schemes deserve funding should be informed by predictions of the value of such schemes to decision making. We suggest that raising awareness among the public and policy makers, auditing management actions, and informing policy choices are the most important global monitoring objectives. Using four well‐developed indicators of biological diversity (extent of forests, coverage of protected areas, Living Planet Index, Red List Index) as examples, we analyzed the characteristics needed for indicators to meet these objectives. We recommend that conservation professionals improve on existing indicators by eliminating spatial biases in data availability, fill gaps in information about ecosystems other than forests, and improve understanding of the way indicators respond to policy changes. Monitoring is not an end in itself, and we believe it is vital that the ultimate objectives of global monitoring of biological diversity inform development of new indicators.

Shovelomics: high throughput phenotyping of maize (Zea mays L.) root architecture in the field - Samuel Trachsel; Shawn M. Kaeppler; Kathleen M. Brown; Jonathan P. Lynch (Plant and Soil, 2011)

Non-uniform interhemispheric temperature trends over the past 550 years - Richard P. Duncan; Pavla Fenwick; Jonathan G. Palmer; Matt S. McGlone; Chris S. M. Turney (Climate Dynamics, 2010)

Non-directional motion detectors can be used to mimic optic flow dependent behaviors - Jonathan P. Dyhr; Charles M. Higgins (Biological Cybernetics, 2010)

Abundance and distribution of major groups of diazotrophic cyanobacteria and their potential contribution to N 2 fixation in the tropical Atlantic Ocean - Nicole L. Goebel; Kendra A. Turk; Katherine M. Achilles; Ryan Paerl; Ian Hewson; Amanda E. Morrison; Joseph P. Montoya; Christopher A. Edwards; Jonathan P. Zehr (Environmental Microbiology, 2010)
Summary The abundances of six N 2 ‐fixing cyanobacterial phylotypes were profiled at 22 stations across the tropical Atlantic Ocean during June 2006, and used to model the contribution of the diazotrophs to N 2 fixation. Diazotroph abundances were measured by targeting the nifH gene of Trichodesmium , unicellular groups A, B, C (UCYN‐A, UCYN‐B and UCYN‐C), and diatom‐cyanobiont symbioses Hemiaulus–Richelia , Rhizosolenia–Richelia and Chaetoceros–Calothrix . West to east gradients in temperature, salinity and nutrients [NO 3 ‐ + NO 2 ‐ , PO 4 3− , Si(OH) 4 ] showed the influence of the Amazon River plume and its effect on the distributions of the diazotrophs. Trichodesmium accounted for more than 93% of all nifH genes detected, dominated the warmer waters of the western Atlantic, and was the only diazotroph detected at the equatorial upwelling station. UCYN‐A was the next most abundant (> 5% of all nifH genes) and dominated the cooler waters of the eastern Atlantic near the Cape Verde Islands. UCYN‐C was found at a single depth (200 m) of high salinity and low temperature and nutrients, whereas UCYN‐B cells were widespread but in very low abundance (6.1 × 10 1 ± 4.6 × 10 2 gene copies l −1 ). The diatom‐cyanobionts were observed primarily in the western Atlantic within or near the high Si(OH) 4 input of the Amazon River plume. Overall, highest diazotroph abundances were observed at the surface and declined with depth, except for some subsurface peaks in Trichodesmium , UCYN‐B and UCYN‐A. Modelled contributions of Trichodesmium , UCYN‐B and UCYN‐A to total N 2 fixation suggested that Trichodesmium had the largest input, except for the potential of UCYN‐A at the Cape Verde Islands.

Ostracoda as an aid in identifying 2004 tsunami sediments: a report from SE coast of India - S. M. Hussain; S. P. Mohan; M. P. Jonathan (Natural Hazards, 2010)

Nitrogen and Phosphorus Limitation of Phytoplankton Growth in New Zealand Lakes: Implications for Eutrophication Control - Jonathan M. Abell; Deniz Özkundakci; David P. Hamilton (Ecosystems, 2010)

Niche conservatism as an emerging principle in ecology and conservation biology - John J. Wiens; David D. Ackerly; Andrew P. Allen; Brian L. Anacker; Lauren B. Buckley; Howard V. Cornell; Ellen I. Damschen; T. Jonathan Davies; John‐Arvid Grytnes; Susan P. Harrison; Bradford A. Hawkins; Robert D. Holt; et al. (Ecology Letters, 2010)
The diversity of life is ultimately generated by evolution, and much attention has focused on the rapid evolution of ecological traits. Yet, the tendency for many ecological traits to instead remain similar over time [niche conservatism (NC)] has many consequences for the fundamental patterns and processes studied in ecology and conservation biology. Here, we describe the mounting evidence for the importance of NC to major topics in ecology (e.g. species richness, ecosystem function) and conservation (e.g. climate change, invasive species). We also review other areas where it may be important but has generally been overlooked, in both ecology (e.g. food webs, disease ecology, mutualistic interactions) and conservation (e.g. habitat modification). We summarize methods for testing for NC, and suggest that a commonly used and advocated method (involving a test for phylogenetic signal) is potentially problematic, and describe alternative approaches. We suggest that considering NC: (1) focuses attention on the within‐species processes that cause traits to be conserved over time, (2) emphasizes connections between questions and research areas that are not obviously related (e.g. invasives, global warming, tropical richness), and (3) suggests new areas for research (e.g. why are some clades largely nocturnal? why do related species share diseases?).

Host Specific Social Parasites (Psithyrus) Indicate Chemical Recognition System in Bumblebees - Stephen J. Martin; Jonathan M. Carruthers; Paul H. Williams; Falko P. Drijfhout (Journal of Chemical Ecology, 2010)

Biomechanical Properties of Recurrent Laryngeal Nerve in the Piglet - Megan J. Alexander; Julie M. Barkmeier-Kraemer; Jonathan P. Vande Geest (Annals of Biomedical Engineering, 2010)

Coexistence of perennial plants: an embarrassment of niches - Peter B. Adler; Stephen P. Ellner; Jonathan M. Levine (Ecology Letters, 2010)
Ecology Letters (2010) 13: 1019–1029 Abstract Despite decades of research documenting niche differences between species, we lack a quantitative understanding of their effect on coexistence in natural communities. We perturbed an empirical sagebrush steppe community model to remove the demographic effect of niche differences and quantify their impact on coexistence. With stabilizing mechanisms operating, all species showed positive growth rates when rare, generating stable coexistence. Fluctuation‐independent mechanisms contributed more than temporal variability to coexistence and operated more strongly on recruitment than growth or survival. As expected, removal of stabilizing niche differences led to extinction of all inferior competitors. However, complete exclusion required 300–400 years, indicating small fitness differences among species. Our results show an ‘excess’ of niche differences: stabilizing mechanisms were not only strong enough to maintain diversity but were much stronger than necessary given the small fitness differences. The diversity of this community cannot be understood without consideration of niche differences.

Diel cycling of DNA staining and nifH gene regulation in the unicellular cyanobacterium Crocosphaera watsonii strain WH 8501 (Cyanophyta) - Kory Pennebaker; Katherine R. M. Mackey; Rachelle M. Smith; Stanly B. Williams; Jonathan P. Zehr (Environmental Microbiology, 2010)
Summary Crocosphaera watsonii WH 8501 is a marine unicellular cyanobacterium that fixes nitrogen primarily during the dark phase of a light–dark (LD) cycle. Circadian clocks modulate gene transcription and cellular activity in many, if not all, cyanobacteria. A model for circadian control has been proposed in cyanobacteria, called the oscilloid model, which is based on topological changes of nucleoid DNA which in turn regulates gene transcription. In this study, the marine unicellular diazotrophic cyanobacteria C. watsonii WH 8501 and Cyanothece sp. ATCC 51142 were found to have daily fluctuations in DNA staining using Hoechst 33342 and SYBR I Green fluorescent dyes. Up to 20‐fold decreases in DNA fluorescence of Hoechst‐stained cells were observed during the dark phase when cultures were grown with a 12:12 LD cycle or under continuous light (LL). The variation in DNA staining was consistent with changes in DNA topology proposed in the oscilloid model. The abundance of nifH transcripts in C. watsonii WH 8501 was rhythmic under LD and LL cycles, consistent with a circadian rhythm. Cycles of DNA fluorescence and photosynthetic efficiency were disrupted when cultures were shifted into an early dark phase; however, nifH transcripts predictably increased in abundance following the premature transition from light to darkness. Thus, nifH gene expression in C. watsonii WH 8501 appears to be influenced by both circadian and environmental factors.

A study on pre- and post-tsunami shallow deposits off SE coast of India from the 2004 Indian Ocean tsunami: a geochemical approach - S. Srinivasalu; M. P. Jonathan; N. Thangadurai; V. Ram-Mohan (Natural Hazards, 2010)

Acid leachable trace metals in sediment cores from Sunderban Mangrove Wetland, India: an approach towards regular monitoring - M. P. Jonathan; S. K. Sarkar; P. D. Roy; Md. A. Alam; M. Chatterjee; B. D. Bhattacharya; A. Bhattacharya; K. K. Satpathy (Ecotoxicology, 2010)

Evaluation of Acid Leachable Trace Metals in Soils Around a Five Centuries Old Mining District in Hidalgo, Central Mexico - M. P. Jonathan; M. Jayaprakash; S. Srinivasalu; P. D. Roy; N. Thangadurai; S. Muthuraj; V. Stephen-Pitchaimani (Water, Air, & Soil Pollution, 2010)

Correlates of sexually transmitted infection histories in a cohort of American male health professionals - Siobhan Sutcliffe; Ichiro Kawachi; John F. Alderete; Charlotte A. Gaydos; Lisa P. Jacobson; Frank J. Jenkins; Raphael P. Viscidi; Jonathan M. Zenilman; Elizabeth A. Platz (Cancer Causes & Control, 2009)

Metagenomic potential of microbial assemblages in the surface waters of the central Pacific Ocean tracks variability in oceanic habitat - Ian Hewson; Ryan W. Paerl; H. James Tripp; Jonathan P. Zehr; David M. Karl (Limnology and Oceanography, 2009)
Oceanic habitats may select for different organisms, thereby tuning genomic capabilities to local environmental conditions. To understand the relationship between microbial assemblage composition, functional capability, and habitat, a random genome shotgun sequencing (metagenomic) survey was conducted with surface‐water microbial assemblages (0.2–5‐µm size fraction) collected at seven locations along a meridional transect from the northern edge of the South Pacific subtropical gyre to the southern edge of the North Pacific subtropical gyre (16°S–13.5°N). A total of 1.1 million unique sequence reads were obtained, of which ~45% could be annotated to metabolic category. Microbial assemblages in equatorial divergence and countercurrent habitats were distinct phylogenetically from those in gyre waters. Ecotypes of dominant Cyanobacteria ( Prochlorococcus and Synechococcus ) had distinct distributions congruent with their physiological characteristics in cultivation. The metagenomic distribution of genes among metabolic pathways was very similar at all stations despite phylogenetic differences, but was unrelated to physicochemical habitat, suggesting that dominant microorganisms have a core suite of genes necessary for life in the open ocean. Among metabolic genes that varied across the transect, several patterns were observed. For example, phosphate (PO 4 3‐ ) stress response genes were more common in gyre waters than at the equator. The variability in frequency of several metabolic pathways (e.g., chlorophyll biosynthesis, PO 4 3‐ metabolism, and transcription initiation bacterial sigma factors) was related to physicochemical conditions, most of which were related to taxonomic differences among habitats. Microbial communities in the central Pacific Ocean are phylogenetically distinct to the oceanic provinces which they inhabit.

Identifying Change-Points in Biological Sequences via Sequential Importance Sampling - George Yu. Sofronov; Gareth E. Evans; Jonathan M. Keith; Dirk P. Kroese (Environmental Modeling & Assessment, 2009)

Do insects lose flight before they lose their wings? Population genetic structure in subalpine stoneflies - GRAHAM A. McCULLOCH; GRAHAM P. WALLIS; JONATHAN M. WATERS (Molecular Ecology, 2009)
Wing reduction and flightlessness are common features of alpine and subalpine insects, and are typically interpreted as evolutionary adaptations to increase fecundity and promote local recruitment. Here, we assess the impact of wing reduction on dispersal in stoneflies (Plecoptera: Gripopterygidae: Zelandoperla ) in southern New Zealand. Specifically, we present comparative phylogeographic analyses (COI; H3) of strong‐flying Zelandoperla decorata (144 individuals, 63 localities) vs. the co‐distributed but weak‐flying Zelandoperla fenestrata species group (186 individuals, 81 localities). The latter group exhibits a variety of morphotypes, ranging from fully winged to completely wingless. Consistent with its capacity for strong flight‐mediated dispersal, Z . decorata exhibited no substantial phylogeographic differentiation across its broad South Island range. Conversely the weak‐flying fenestrata species group exhibited substantial genetic structure across both fine and broad geographic scales. Intriguingly, the variable degrees of wing development observed within the fenestrata species group had no apparent impact on levels of phylogeographic structure, which were high regardless of morphotype, suggesting that even fully winged specimens of this group do not fly. This finding implies that Zelandoperla flight loss occurs independently of wing loss, and might reflect underlying flight muscle reduction.

Nitrate removal in stream ecosystems measured by 15N addition experiments: Total uptake - Robert O. Hall; Jennifer L. Tank; Daniel J. Sobota; Patrick J. Mulholland; Jonathan M. O'Brien; Walter K. Dodds; Jackson R. Webster; H. Maurice Valett; Geoffrey C. Poole; Bruce J. Peterson; Judy L. Meyer; William H. McDowell; et al. (Limnology and Oceanography, 2009)
We measured uptake length of 15 NO 3 − in 72 streams in eight regions across the United States and Puerto Rico to develop quantitative predictive models on controls of NO 3 − uptake length. As part of the Lotic Intersite Nitrogen eXperiment II project, we chose nine streams in each region corresponding to natural (reference), suburban‐urban, and agricultural land uses. Study streams spanned a range of human land use to maximize variation in NO 3 − concentration, geomorphology, and metabolism. We tested a causal model predicting controls on NO 3 − uptake length using structural equation modeling. The model included concomitant measurements of ecosystem metabolism, hydraulic parameters, and nitrogen concentration. We compared this structural equation model to multiple regression models which included additional biotic, catchment, and riparian variables. The structural equation model explained 79% of the variation in log uptake length ( S Wtot ). Uptake length increased with specific discharge ( Q/w ) and increasing NO 3 − concentrations, showing a loss in removal efficiency in streams with high NO 3 − concentration. Uptake lengths shortened with increasing gross primary production, suggesting autotrophic assimilation dominated NO 3 − removal. The fraction of catchment area as agriculture and suburban‐urban land use weakly predicted NO 3 − uptake in bivariate regression, and did improve prediction in a set of multiple regression models. Adding land use to the structural equation model showed that land use indirectly affected NO 3 − uptake lengths via directly increasing both gross primary production and NO 3 − concentration. Gross primary production shortened S Wtot , while increasing NO 3 − lengthened S Wtot resulting in no net effect of land use on NO 3 − removal.

Nitrate removal in stream ecosystems measured by 15N addition experiments: Denitrification - Patrick J. Mulholland; Robert O. Hall; Daniel J. Sobota; Walter K. Dodds; Stuart E. G. Findlay; Nancy B. Grimm; Stephen K. Hamilton; William H. McDowell; Jonathan M. O'Brien; Jennifer L. Tank; Linda R. Ashkenas; Lee W. Cooper; et al. (Limnology and Oceanography, 2009)
We measured denitrification rates using a field 15 NO 3 − tracer‐addition approach in a large, cross‐site study of nitrate uptake in reference, agricultural, and suburban‐urban streams. We measured denitrification rates in 49 of 72 streams studied. Uptake length due to denitrification ( S Wden n) ranged from 89 m to 184 km (median of 9050 m) and there were no significant differences among regions or land‐use categories, likely because of the wide range of conditions within each region and land use. N 2 production rates far exceeded N 2 O production rates in all streams. The fraction of total NO 3 − removal from water due to denitrification ranged from 0.5% to 100% among streams (median of 16%), and was related to NH 4 + concentration and ecosystem respiration rate (ER). Multivariate approaches showed that the most important factors controlling S Wden were specific discharge (discharge / width) and NO 3 − concentration (positive effects), and ER and transient storage zones (negative effects). The relationship between areal denitrification rate ( U den ) and NO 3 − concentration indicated a partial saturation effect. A power function with an exponent of 0.5 described this relationship better than a Michaelis‐Menten equation. Although U den increased with increasing NO 3 − concentration, the efficiency of NO 3 − removal from water via denitrification declined, resulting in a smaller proportion of streamwater NO 3 − load removed over a given length of stream. Regional differences in stream denitrification rates were small relative to the proximate factors of NO 3 − concentration and ecosystem respiration rate, and land use was an important but indirect control on denitrification in streams, primarily via its effect on NO 3 − concentration.

Leaf-level water use efficiency determined by carbon isotope discrimination in rice seedlings: genetic variation associated with population structure and QTL mapping - Yunbi Xu; Dominique This; Roman C. Pausch; Wendy M. Vonhof; Jason R. Coburn; Jonathan P. Comstock; Susan R. McCouch (Theoretical and Applied Genetics, 2009)

Climatic drivers of hemispheric asymmetry in global patterns of ant species richness - Robert R. Dunn; Donat Agosti; Alan N. Andersen; Xavier Arnan; Carsten A. Bruhl; Xim Cerdá; Aaron M. Ellison; Brian L. Fisher; Matthew C. Fitzpatrick; Heloise Gibb; Nicholas J. Gotelli; Aaron D. Gove; et al. (Ecology Letters, 2009)
Although many taxa show a latitudinal gradient in richness, the relationship between latitude and species richness is often asymmetrical between the northern and southern hemispheres. Here we examine the latitudinal pattern of species richness across 1003 local ant assemblages. We find latitudinal asymmetry, with southern hemisphere sites being more diverse than northern hemisphere sites. Most of this asymmetry could be explained statistically by differences in contemporary climate. Local ant species richness was positively associated with temperature, but negatively (although weakly) associated with temperature range and precipitation. After contemporary climate was accounted for, a modest difference in diversity between hemispheres persisted, suggesting that factors other than contemporary climate contributed to the hemispherical asymmetry. The most parsimonious explanation for this remaining asymmetry is that greater climate change since the Eocene in the northern than in the southern hemisphere has led to more extinctions in the northern hemisphere with consequent effects on local ant species richness.

Drug metabolizing enzyme induction pathways in experimental non-alcoholic steatohepatitis - Craig D. Fisher; Jonathan P. Jackson; Andrew J. Lickteig; Lisa M. Augustine; Nathan J. Cherrington (Archives of Toxicology, 2008)

Simulated Two-dimensional Red Blood Cell Motion, Deformation, and Partitioning in Microvessel Bifurcations - Jared O. Barber; Jonathan P. Alberding; Juan M. Restrepo; Timothy W. Secomb (Annals of Biomedical Engineering, 2008)

Tumor histology helps to identify Lynch syndrome among colorectal cancer patients - Brindusa Truta; Yunn-Yi Chen; Amie M. Blanco; Guoren Deng; Peggy G. Conrad; Yong Ho Kim; Eun Taek Park; Sanjay Kakar; Young S. Kim; Fernando Velayos; Marvin H. Sleisenger; Jonathan P. Terdiman (Familial Cancer, 2008)

Adrenaline potentiates insulin-stimulated PKB activation in the rat fast-twitch epitrochlearis muscle without affecting IRS-1-associated PI 3-kinase activity - Jørgen Jensen; Line M. Grønning-Wang; Einar Jebens; Jonathan P. Whitehead; Robert Zorec; Peter R. Shepherd (Pflügers Archiv - European Journal of Physiology, 2008)

Dissociation of force decline from calcium decline by preload in isolated rabbit myocardium - Michelle M. Monasky; Kenneth D. Varian; Jonathan P. Davis; Paul M. L. Janssen (Pflügers Archiv - European Journal of Physiology, 2008)

Regional distributions of nitrogen‐fixing bacteria in the Pacific Ocean - Matthew J. Church; Karin M. Björkman; David M. Karl; Mak A. Saito; Jonathan P. Zehr (Limnology and Oceanography, 2008)
We evaluated the regional distributions of six nitrogen (N 2 )‐fixing bacteria in the North Pacific Ocean using quantitative polymerase chain reaction amplification of planktonic nifH genes. Samples were collected on four oceanographic research cruises between March 2002 and May 2005 that spanned a latitudinal range from 12°S and 54°N between 152°W and 170°W. Samples were collected throughout the upper ocean ( 2 ‐fixing bacteria within the various oceanic biomes. In general, nifH ‐containing bacteria were most abundant in the midregions of the NPSG (latitudes between ~14°N and 29°N), where unicellular cyanobacterial phylotypes dominated nifH gene abundances. The abundances of all nifH ‐containing groups declined within the northern and southern regions of NPSG. Although nifH ‐containing groups were detectable in the northern regions of the SPSG, throughout the equatorial waters, and within the NPTZ, gene copy abundances of most groups were lower in these regions than those found the in the NPSG. In the NPSG, surface water abundances of the various nifH phylotypes examined ranged from −1 to ~10 5 nifH copies LS −1 . Overall, the abundances of an uncultivated, presumed unicellular nifH sequence‐type (termed Group A) were the most abundant and widely distributed of the phylotypes examined. Our results indicate that the distributions of N 2 ‐fixing plankton were largely restricted to the subtropical regions of the North and South Pacific Oceans.

Acamprosate attenuates cocaine- and cue-induced reinstatement of cocaine-seeking behavior in rats - M. Scott Bowers; Billy T. Chen; Jonathan K. Chou; Megan P. H. Osborne; Justin T. Gass; Ronald E. See; Antonello Bonci; Patricia H. Janak; M. Foster Olive (Psychopharmacology, 2007)

Characterization of a SEPT9 interacting protein, SEPT14, a novel testis-specific septin - Esther A. Peterson; Linda M. Kalikin; Jonathan D. Steels; Mathew P. Estey; William S. Trimble; Elizabeth M. Petty (Mammalian Genome, 2007)

Spring‐neap modulation of internal tide mixing and vertical nitrate fluxes at a shelf edge in summer - Jonathan Sharples; Jacqueline F. Tweddle; J. A. Mattias Green; Matthew R. Palmer; Young-Nam Kim; Anna E. Hickman; Patrick M. Holligan; C. Mark Moore; Tom P. Rippeth; John H. Simpson; Vladimir Krivtsov (Limnology and Oceanography, 2007)
Measurements of the intra‐tidal and spring‐neap variation in the vertical flux of nitrate into the base of the sub‐surface chlorophyll maximum (SCM) were made at the shelf edge of the Celtic Sea, a region with strong internal mixing driven by an internal tide. The neap tide daily mean nitrate flux was 1.3 (0.9‐1.8, 95% confidence interval) mmol m ‐2 d ‐1 . The spring tide flux was initially estimated as 3.5 (2.3‐5.2, 95% confidence interval) mmol m ‐2 d ‐1 . The higher spring tide nitrate flux was the result of turbulent dissipation occurring within the base of the SCM as compared to deeper dissipation during neap tides and was dominated by short events associated with the passage of internal solitons. Taking into account the likely under‐sampling of these short mixing events raised the spring tide nitrate flux estimate to about 9 mmol m ‐2 d ‐1 . The neap tide nitrate flux was sufficient to support substantial new production and a considerable fraction of the observed rates of carbon fixation. Spring tide fluxes were potentially in excess of the capacity of the phytoplankton community to uptake nitrate. This potential excess nitrate flux during spring tides may be utilized to support new production during the lower mixing associated with the transition toward neap tide. The shelf edge is shown to be a region with a significantly different phytoplankton community as compared to the adjacent Celtic Sea and northeast Atlantic Ocean, highlighting the role of gradients in physical processes leading to gradients in ecosystem structure.

Nitrogenase gene expression in the Chesapeake Bay Estuary - Steven M. Short; Jonathan P. Zehr (Environmental Microbiology, 2007)
Summary Like many estuaries, the Chesapeake Bay has pronounced gradients in salinity and nutrients. Previous studies have shown that there is a high diversity of nitrogenase ( nifH ) genes in the estuary, and that there are specific distributions of individual nifH phylotypes. In contrast to previous work that revealed the remarkable diversity of nifH phylotypes in the Chesapeake estuary, in this study of nifH expression we only detected two phylotypes, and both were phylogenetically related to cyanobacterial nifH genes. One of the phylotypes was closely related to a nifH sequence from the filamentous, heterocystous cyanobacterium Anabaena cylindrica , and was found at the head of the estuary. The other phylotype was found in a sample collected near the mouth of the estuary and was closely related to nifH sequences from Group A unicellular cyanobacteria, which has previously been reported in oceanic waters only. These nifH phylotypes had distinct patterns of expression that were restricted to different regions of the Chesapeake Bay. This study provides the first evidence of nifH expression in the Chesapeake Bay, and suggests that diazotrophic unicellular cyanobacteria have a broader distribution and activity than previously recognized.

An empirical test of freshwater vicariance via river capture - CHRISTOPHER P. BURRIDGE; DAVE CRAW; JONATHAN M. WATERS (Molecular Ecology, 2007)
River capture is a geomorphological process through which stream sections are displaced from one catchment to another, and it may represent a dominant facilitator of interdrainage transfer and cladogenesis in freshwater‐limited taxa. However, few studies have been conducted in a manner to explicitly test the biological significance of river capture. Here we present a multispecies phylogeographical analysis to test whether the nonmigratory fish fauna of the Von River (South Island, New Zealand) is the product of a well‐documented, Late Quaternary capture of a section of the Oreti River (Southland drainage). Specifically, we predict that nonmigratory fishes of the Von River will exhibit closer genetic affinities with those of Southland, rather than those of the Clutha system, into which the Von River presently drains. Mitochondrial DNA phylogeography (control region and cytochrome b sequence data) and analysis of nuclear orthologues of mtDNA sequences indicate that ‘flathead’ Galaxias of the Von River ( n = 31, three sites) have greatest genetic affinities with those of Southland ( Galaxias ‘southern’ , n = 216, 38 sites), rather than with those of the Clutha River ( Galaxias sp. ‘ D ’, n = 73, 32 sites). Likewise, Von River ‘roundhead’ Galaxias ( n = 52, four sites) have greatest genetic affinities with those of Southland drainages ( Galaxias gollumoides , n = 223, 58 sites), rather than with those of the Clutha River ( Galaxias pullus , Galaxias anomalus , Galaxias gollumoides of the Nevis tributary; n = 68, 32 sites). These findings are consistent with our predictions that genetic affinities of the nonmigratory fish fauna in the Von River would reflect past, rather than present, drainage connections. Consequently, river capture is responsible for the nonmigratory fish fauna of the Von River. In a broader context, river capture has frequently influenced the distribution of genetic lineages among catchments in New Zealand freshwater‐limited fish, and its biogeographical significance may have been underestimated in other regions.

Evolution and the latitudinal diversity gradient: speciation, extinction and biogeography - Gary G. Mittelbach; Douglas W. Schemske; Howard V. Cornell; Andrew P. Allen; Jonathan M. Brown; Mark B. Bush; Susan P. Harrison; Allen H. Hurlbert; Nancy Knowlton; Harilaos A. Lessios; Christy M. McCain; Amy R. McCune; et al. (Ecology Letters, 2007)
A latitudinal gradient in biodiversity has existed since before the time of the dinosaurs, yet how and why this gradient arose remains unresolved. Here we review two major hypotheses for the origin of the latitudinal diversity gradient. The time and area hypothesis holds that tropical climates are older and historically larger, allowing more opportunity for diversification. This hypothesis is supported by observations that temperate taxa are often younger than, and nested within, tropical taxa, and that diversity is positively correlated with the age and area of geographical regions. The diversification rate hypothesis holds that tropical regions diversify faster due to higher rates of speciation (caused by increased opportunities for the evolution of reproductive isolation, or faster molecular evolution, or the increased importance of biotic interactions), or due to lower extinction rates. There is phylogenetic evidence for higher rates of diversification in tropical clades, and palaeontological data demonstrate higher rates of origination for tropical taxa, but mixed evidence for latitudinal differences in extinction rates. Studies of latitudinal variation in incipient speciation also suggest faster speciation in the tropics. Distinguishing the roles of history, speciation and extinction in the origin of the latitudinal gradient represents a major challenge to future research.

Experiments linking nitrogenase gene expression to nitrogen fixation in the North Pacific subtropical gyre - Jonathan P. Zehr; Joseph P. Montoya; Bethany D. Jenkins; Ian Hewson; Elizabeth Mondragon; Cindy M. Short; Matthew J. Church; Andrew Hansen; David M. Karl (Limnology and Oceanography, 2007)
We examined diazotroph activity in controlled experiments containing natural populations of nitrogen (N 2 )‐fixing microbes collected offshore from Kane'ohe Bay, Hawai'i, and from Station ALOHA (A Long‐term Oligotrophic Habitat Assessment) in the North Pacific subtropical gyre. Quantitative polymerase chain reaction and reverse transcription‐polymerase chain reaction approaches showed that the abundances of the major phylotypes did not change substantially during experimental incubations. Diel phasing of nifH gene expression in the experiments was similar to that documented for natural populations. Cell‐specific N 2 fixation rates, calculated as 15 N 2 incorporation rate divided by specific phylotype abundance (gene copy number), varied between the experiments, but generally agreed with the abundance and levels of nifH expression of each group of diazotrophs. Phosphorus additions had little effect on the abundance, gene expression, or N 2 fixation activity of diazotrophs across the course of the 36‐h experiments, indicating that other factors may limit the growth, gene expression, and activity of diazotrophs in the North Pacific subtropical gyre.

Naturally occurring resistance of bone marrow mononuclear and metastatic cancer cells to anticancer agents - Christina Richard; Jonathan Yau; John P. H. Th’ng; Wilhelmina C. M. Duivenvoorden (Clinical & Experimental Metastasis, 2006)

Application of a nifH oligonucleotide microarray for profiling diversity of N 2 ‐fixing microorganisms in marine microbial mats - Pia H. Moisander; Lily Shiue; Grieg F. Steward; Bethany D. Jenkins; Brad M. Bebout; Jonathan P. Zehr (Environmental Microbiology, 2006)
Summary Diazotrophic community structure in microbial mats from Guerrero Negro (GN), Baja California, Mexico, was studied using polymerase chain reaction amplification of the nifH gene and a newly developed nifH oligonucleotide microarray. Ninety‐six oligonucleotide probes designed for nifH sequences from cultivated isolates and the environment were printed on glass microarrays. Phylogenetic analysis showed that the probes represented all of the main nifH clusters. Specificity was tested by (i) evaluation of cross hybridization using individual targets, and (ii) comparison of the observed hybridization signals and those predicted from the sequences cloned from microbial mats. Signal intensity had a positive relationship with target concentration and the percentage identity between probe and target. Under moderate stringency and high target concentration, specificity of the probes varied from 77% to 100% with the individual targets tested. At the end of a 7‐month long nutrient manipulation experiment in GN microbial mats, no expression of nitrogen fixation under nitrogen loading was detected, although a diverse community of diazotrophs was detected. The diversity in diazotrophic population present was higher than in the population expressing the nifH gene, and there were taxa specific differences in response to nutrients. The nifH microarray is a powerful tool for diazotroph community analysis in the marine environment.

Detection of quantitative trait loci for seminal root traits in maize (Zea mays L.) seedlings grown under differential phosphorus levels - Jinming Zhu; Suzanne M. Mickelson; Shawn M. Kaeppler; Jonathan P. Lynch (Theoretical and Applied Genetics, 2006)

A protocol for high-throughput phenotyping, suitable for quantitative trait analysis in mice - Leah C. Solberg; William Valdar; Dominique Gauguier; Graciela Nunez; Amy Taylor; Stephanie Burnett; Carmen Arboledas-Hita; Polinka Hernandez-Pliego; Stuart Davidson; Peter Burns; Shoumo Bhattacharya; Tertius Hough; et al. (Mammalian Genome, 2006)

Human lung cell growth is not stimulated by lead ions after lead chromate-induced genotoxicity - Sandra S. Wise; Amie L. Holmes; Jonathan A. Moreland; Hong Xie; Sarah J. Sandwick; Megan M. Stackpole; Elena Fomchenko; Sonia Teufack; Alfred J. May; Spiros P. Katsfis; John Pierce Wise (Molecular and Cellular Biochemistry, 2005)

Maternal lineages and Alzheimer disease risk in the Old Order Amish - Joelle M. van der Walt; William K. Scott; Susan Slifer; P. C. Gaskell; Eden R. Martin; Kathleen Welsh-Bohmer; Marilyn Creason; Amy Crunk; Denise Fuzzell; Lynne McFarland; Charles C. Kroner; C. E. Jackson; et al. (Human Genetics, 2005)

Zero tolerance ecology: improving ecological inference by modelling the source of zero observations - Tara G. Martin; Brendan A. Wintle; Jonathan R. Rhodes; Petra M. Kuhnert; Scott A. Field; Samantha J. Low‐Choy; Andrew J. Tyre; Hugh P. Possingham (Ecology Letters, 2005)
A common feature of ecological data sets is their tendency to contain many zero values. Statistical inference based on such data are likely to be inefficient or wrong unless careful thought is given to how these zeros arose and how best to model them. In this paper, we propose a framework for understanding how zero‐inflated data sets originate and deciding how best to model them. We define and classify the different kinds of zeros that occur in ecological data and describe how they arise: either from ‘true zero’ or ‘false zero’ observations. After reviewing recent developments in modelling zero‐inflated data sets, we use practical examples to demonstrate how failing to account for the source of zero inflation can reduce our ability to detect relationships in ecological data and at worst lead to incorrect inference. The adoption of methods that explicitly model the sources of zero observations will sharpen insights and improve the robustness of ecological analyses.

U–Pb baddeleyite ages and Hf, Nd isotope chemistry constraining repeated mafic magmatism in the Fennoscandian Shield from 1.6 to 0.9 Ga - Ulf Söderlund; Clark E. Isachsen; Göran Bylund; Larry M. Heaman; P. Jonathan Patchett; Jeff D. Vervoort; Ulf B. Andersson (Contributions to Mineralogy and Petrology, 2005)

Mapping of QTLs for lateral root branching and length in maize (Zea mays L.) under differential phosphorus supply - Jinming Zhu; Shawn M. Kaeppler; Jonathan P. Lynch (Theoretical and Applied Genetics, 2005)

A comparison of the phenotype and genotype in adenomatous polyposis patients with and without a family history - Brindusa Truta; Brian A. Allen; Peggy G. Conrad; Vivian Weinberg; Glenn A. Miller; Rob Pomponio; Lara R. Lipton; Germano Guerra; Ian P. M. Tomlinson; Marvin H. Sleisenger; Young S. Kim; Jonathan P. Terdiman (Familial Cancer, 2005)

Eye movement-related responses of neurons in human subthalamic nucleus - Adrian P. Fawcett; Jonathan O. Dostrovsky; Andres M. Lozano; William D. Hutchison (Experimental Brain Research, 2005)

Mapping of QTL controlling root hair length in maize (Zea mays L.) under phosphorus deficiency - Jinming Zhu; Shawn M. Kaeppler; Jonathan P. Lynch (Plant and Soil, 2005)

Nitrogenase gene diversity and microbial community structure: a cross‐system comparison - Jonathan P. Zehr; Bethany D. Jenkins; Steven M. Short; Grieg F. Steward (Environmental Microbiology, 2003)
Summary Biological nitrogen fixation is an important source of fixed nitrogen for the biosphere. Microorganisms catalyse biological nitrogen fixation with the enzyme nitrogenase, which has been highly conserved through evolution. Cloning and sequencing of one of the nitrogenase structural genes, nifH , has provided a large, rapidly expanding database of sequences from diverse terrestrial and aquatic environments. Comparison of nifH phylogenies to ribosomal RNA phylogenies from cultivated microorganisms shows little conclusive evidence of lateral gene transfer. Sequence diversity far outstrips representation by cultivated representatives. The phylogeny of nitrogenase includes branches that represent phylotypic groupings based on ribosomal RNA phylogeny, but also includes paralogous clades including the alternative, non‐molybdenum, non‐vanadium containing nitrogenases. Only a few alternative or archaeal nitrogenase sequences have as yet been obtained from the environment. Extensive analysis of the distribution of nifH phylotypes among habitats indicates that there are characteristic patterns of nitrogen fixing microorganisms in termite guts, sediment and soil environments, estuaries and salt marshes, and oligotrophic oceans. The distribution of nitrogen‐fixing microorganisms, although not entirely dictated by the nitrogen availability in the environment, is non‐random and can be predicted on the basis of habitat characteristics. The ability to assay for gene expression and investigate genome arrangements provides the promise of new tools for interrogating natural populations of diazotrophs. The broad analysis of nitrogenase genes provides a basis for developing molecular assays and bioinformatics approaches for the study of nitrogen fixation in the environment.

Letters - J. Alan Clark; Jonathan M. Hoekstra; P. Dee Boersma; Peter Kareiva (Conservation Biology, 2003)

Global synthesis of leaf area index observations: implications for ecological and remote sensing studies - Gregory P. Asner; Jonathan M. O. Scurlock; Jeffrey A. Hicke (Global Ecology and Biogeography, 2003)
Aim We present the first global synthesis of plant canopy leaf area index (LAI) measurements from more than 1000 published estimates representing ∼400 unique field sites. LAI is a key variable for regional and global models of biosphere‐atmosphere exchanges of energy, carbon dioxide, water vapour, and other materials. Location The location is global, geographically distributed. Results Biomes with LAI values well represented in the literature included croplands, forests and plantations. Biomes not well represented were deserts, shrublands, tundra and wetlands. Nearly 40% of the records in the database were published in the past 10 years (1991–2000), with a further 20% collected between 1981 and 1990. Mean (± SD) LAI, distributed between 15 biome classes, ranged from 1.3 ± 0.9 for deserts to 8.7 ± 4.3 for tree plantations, with temperate evergreen forests (needleleaf and broadleaf) displaying the highest average LAI (5.1–6.7) among the natural terrestrial vegetation classes. Following a statistical outlier analysis, the global mean (± SD) LAI decreased from 5.2 (4.1) to 4.5 (2.5), with a maximum LAI of 18. Biomes with the highest LAI values were plantations > temperate evergreen forests > wetlands. Those with the lowest LAI values were deserts Main conclusions Applications of the LAI database span a wide range of ecological, biogeochemical, physical, and climate research areas. The data provide input to terrestrial ecosystem and land‐surface models, for evaluation of global remote sensing products, for comparisons to field studies, and other applications. Example uses of the database for global plant productivity, fractional energy absorption, and remote sensing studies are highlighted.

Improving U.S. Endangered Species Act Recovery Plans: Key Findings and Recommendations of the SCB Recovery Plan Project - J. Alan Clark; Jonathan M. Hoekstra; P. Dee Boersma; Peter Kareiva (Conservation Biology, 2002)
To promote more effective recovery planning for species listed under the U.S. Endangered Species Act ( ESA), the Society for Conservation Biology sponsored a systematic review of a large sample of ESA recovery plans. The review was conducted in collaboration with the U.S. Fish and Wildlife Service, the National Center for Ecological Analysis and Synthesis, and 19 universities. We describe the genesis of the project and the development of the resulting database of information on ESA recovery plans. The project's primary goals were to characterize the content and attributes of recovery plans; to identify important differences, patterns, and trends among plans; and to use these results to develop recommendations for the U.S. Fish and Wildlife Service for improving recovery plans. We review key findings from published analyses of the project database and offer prioritized recommendations for improving recovery‐plan development and implementation. First, the use of science in recovery‐plan development and implementation could be improved by making threats a primary focus of plans, specifying adequate monitoring tasks for species status and recovery tasks, and ensuring that species trend data are current, quantitative, and documented. Second, recovery‐plan structure and development could be enhanced by keeping authorship teams small yet diverse, making existing administrative designations more biologically relevant, improving and standardizing the revision process, and reevaluating the use of multispecies plans. Third, agency resources and personnel could be better utilized by developing new recovery plan guidelines, assigning personnel explicit responsibility for overseeing plan implementation, expanding personnel training, and tracking expenditures in recovery programs. And fourth, several generic failings in the field of conservation biology could be addressed by reducing taxonomic bias and by collecting and fully integrating key biological information into recovery plans. The recovery‐plan project offers a model of how professional societies, universities, and government agencies can work together beneficially to address key issues in conservation biology.

The interaction between predation and competition: a review and synthesis - Jonathan M. Chase; Peter A. Abrams; James P. Grover; Sebastian Diehl; Peter Chesson; Robert D. Holt; Shane A. Richards; Roger M. Nisbet; Ted J. Case (Ecology Letters, 2002)
This review discusses the interface between two of the most important types of interactions between species, interspecific competition and predation. Predation has been claimed to increase, decrease, or have little effect on, the strength, impact or importance of interspecific competition. There is confusion about both the meaning of these terms and the likelihood of, and conditions required for, each of these outcomes. In this article we distinguish among three measures of the influence of predation on competitive outcomes: short‐term per capita consumption or growth rates, long‐term changes in density, and the probability of competitive coexistence. We then outline various theoretical mechanisms that can lead to qualitatively distinct effects of predators. The qualitative effect of predators can depend both on the mechanism of competition and on the definition of competitive strength/impact. In assessing the empirical literature, we ask: (1) What definitions of competitive strength/impact have been assumed? (2) Does strong evidence exist to support one or more of the possible mechanisms that can produce a given outcome? (3) Do biases in the choice of organism or manipulation exist, and are they likely to have influenced the conclusions reached? We conclude by discussing several unanswered questions, and espouse a stronger interchange between empirical and theoretical approaches to this important question.

Topsoil foraging – an architectural adaptation of plants to low phosphorus availability - Jonathan P. Lynch; Kathleen M. Brown (Plant and Soil, 2001)

Zinc accumulation by Thlaspi caerulescens from soils with different Zn availability: a pot study - Steven N. Whiting; Jonathan R. Leake; Stephen P. McGrath; Alan J. M. Baker (Plant and Soil, 2001)

Effect of phosphorus availability on basal root shallowness in common bean - Hong Liao; Gerardo Rubio; Xiaolong Yan; Aiqin Cao; Kathleen M. Brown; Jonathan P. Lynch (Plant and Soil, 2001)

Phytoplankton distribution and survival in the thermocline - Jonathan Sharples; Mark C. Moore; Tom P. Rippeth; Patrick M. Holligan; David J. Hydes; Neil R. Fisher; John H. Simpson (Limnology and Oceanography, 2001)
Observations of the vertical structure of density, concentrations of chlorophyll a and nitrate, and turbulent dissipation rates were made over a period of 25 h in a well‐stratified shelf region in the Western English Channel, between neap and spring tides. Maximum turbulent dissipation at the base of the thermocline occurred almost 5 h after maximum tidal currents. This turbulence aids phytoplankton growth by supplying bottom‐layer nutrients into the subsurface chlorophyll maximum but reduces phytoplankton concentrations in the thermocline by mixing cells from the base of the subsurface maximum into the bottom mixed layer. The turbulent dissipation observations were used to estimate an average nitrate flux into the thermocline of 2.0 (0.8‐3.2, 95% confidence interval) mmol m −2 d −1 , which is estimated to have been capable of supporting new phytoplankton growth at a rate of 160 (64–256) mg C m −2 d −1 . Turbulent entrainment of carbon from the base of the subsurface biomass maximum into the bottom mixed layer was observed to be 290 (120–480) mg C m −2 d −1 . This apparent excess export from the chlorophyll maximum is suggested to be a feature of the spring‐neap cycle, with export dominating as the tidal turbulence increases toward spring tides and erodes the base of the thermocline. The observed rate of carbon export into the bottom mixed layer could account for as much as 25% of the gross annual primary production in stratifying shelf seas. Such turbulent losses, combined with grazing losses and low light levels, suggest that phytoplankton need to be highly adapted to environmental conditions within the thermocline in order to survive.

Analysis of metal incorporation during overexpression of Clostridium pasteurianum rubredoxin by electrospray FTICR mass spectrometry - Kristina P. Taylor; Bryan A. Parks; Donald M. Kurtz; Jonathan I. Amster (JBIC Journal of Biological Inorganic Chemistry, 2001)

Genetic diversity in New Zealand Galaxias vulgaris sensu lato (Teleostei: Osmeriformes: Galaxiidae): a test of a biogeographic hypothesis - Graham P. Wallis; Karen F. Judge; Julie Bland; Jonathan M. Waters; Tim M. Berra (Journal of Biogeography, 2001)
Aim To test whether a geologically recent region with low endemism shows low genetic diversity in a freshwater fish species complex, in contrast to an adjacent area with high diversity. The low endemism is generally postulated to be the combined effect of Pleistocene glaciations and the unstable nature of the recent gravel outwash from young mountains to the west. This rock aggradation has formed a plain, crossed by several braided rivers. The faunas of these rivers have the potential to interchange through flooding or course changes. Location Southern and central South Island, New Zealand (NZ). We define the boundary of these two biogeographical regions as the Waitaki River, the most southerly braided river. To the north lies the Canterbury Plain, formed from coalesced alluvial fans; to the south is the Otago peneplain and associated mountain ranges. Methods Previous work has revealed considerable genetic structuring in the stream‐resident fish Galaxias vulgaris Stokell sensu lato , including a species complex in the southern region of South Island, NZ. Using isozyme electrophoresis, we have now examined genetic variation among a total of 58 samples of non‐migratory river galaxias from 24 river systems in South Island: 16 in the central region and eight to the south. Results Whereas samples from the central region do exhibit significant genetic structuring (Wright’s F ST =0.331), they are more genetically homogeneous (mean Nei’s D = 0.032) than populations to the south of the Waitaki River ( F ST =0.826, mean D =0.374). Main conclusions The results concur with our expectations of differences between the central and southern regions. We suggest that the divergence in the south reflects geological stability, whereas relatively shallow divergences within the central region reflects the more recent formation of the Canterbury Plain and its unstable braided rivers. The genetic structuring of this group has been promoted by the absence of the marine juvenile phase that is found in five other members of the genus native to NZ. This diversity of the southern region mirrors its diverse flora and invertebrate fauna, and has conservation implications that parallel those resulting from our improved knowledge of the NZ herpetofauna through the application of genetic analysis.

Biogeography of a southern hemisphere freshwater fish: how important is marine dispersal? - Jonathan M. Waters; Lucette H. Dijkstra; Graham P. Wallis (Molecular Ecology, 2000)
Galaxias maculatus is one of the world’s most widely distributed freshwater fish. This species has a marine‐tolerant juvenile phase, and a geographical range extending through much of the southern hemisphere. We conducted phylogeographic analyses of 163 control region haplotypes of G. maculatus , including samples from New Zealand (five locations), Tasmania (one location) and Chile (one location). A lack of genetic structure among New Zealand samples suggests that marine dispersal facilitates considerable gene flow on an intra‐continental scale. The discovery of a Tasmanian‐like haplotype in one of 144 New Zealand samples indicates that inter‐continental marine dispersal occurs but is insufficient to prevent mitochondrial DNA differentiation among continents. The sister relationship of Tasmanian and New Zealand clades implies that marine dispersal is an important biogeographical mechanism for this species. However, a vicariant role in the divergence of eastern and western Pacific G. maculatus cannot be rejected.

Across the Southern Alps by river capture? Freshwater fish phylogeography in South Island, New Zealand - Jonathan M. Waters; Graham P. Wallis (Molecular Ecology, 2000)
We used DNA analysis of galaxiid fish to test a hypothesis of localized headwater capture in South Island, New Zealand. The restricted western, but widespread eastern, distributions of three nonmigratory freshwater fish species suggest that part of the east‐flowing Waiau River has been captured by the west‐flowing Buller River. However, mitochondrial control region (Kimura 2‐parameter distance = 4.1–5.4%) and microsatellite flanking sequences do not support a relationship between Waiau ( N = 4 fish sequences) and western populations ( N = 8) of Galaxias vulgaris . Instead, the point of capture is probably to the north‐east, perhaps the Nelson lakes region. Phylogenetic analysis indicates that western populations, along with populations in the north‐east ( N = 18), represent a previously unidentified monophyletic Evolutionarily Significant Unit, possibly a cryptic species. We suggest a general caveat for zoogeographic conclusions based on distributional data alone.

Behavior and mutagenesis screens: the importance of baseline analysis of inbred strains - Lisa M. Tarantino; Thomas J. Gould; Jonathan P. Druhan; Maja Bucan (Mammalian Genome, 2000)

Characterization of microsatellite loci from a New Zealand freshwater fish ( Galaxias vulgaris ) and their potential for analysis of hybridization in Galaxiidae - Jonathan M. Waters; Yuzine B. Esa; Graham P. Wallis (Molecular Ecology, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Enhanced expression of a cold-induced gene coding for a glycine- rich protein in regenerative somaclonal variants of red clover (Trifolium pratense L.) - Marek Nelke; Jerzy Nowak; Jonathan M. Wright; Nancy L. McLean; Serge Laberge; Yves Castonguay; Louis-P. Vezina (Euphytica, 1999)

Bioequivalence of Topical Dermatological Dosage Forms-Methods of Evaluation of Bioequivalence - Vinod P. Shah; Gordon L. Flynn; Avraham Yacobi; Howard I. Maibach; Charles Bon; Nicholas M. Fleischer; Thomas J. Franz; Stanley A. Kaplan; Jeff Kawamoto; Lawrence J. Lesko; Jean-Paul Marty; Lynn K. Pershing; et al. (Pharmaceutical Research, 1998)

The "prismane" protein resolved: X-ray structure at 1.7 Å and multiple spectroscopy of two novel 4Fe clusters - Alexander F. Arendsen; Jonathan Hadden; Graeme Card; Alan S. McAlpine; Susan Bailey; Vjacheslav Zaitsev; Elizabeth H. M. Duke; P. F. Lindley; Monika Kröckel; Alfred X. Trautwein; Martinus C. Feiters; John M. Charnock; et al. (JBIC Journal of Biological Inorganic Chemistry, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Estimating respiration of roots in soil: Interactions with soil CO2, soil temperature and soil water content - Tjeerd J. Bouma; Kai L. Nielsen; David M. Eissenstat; Jonathan P. Lynch (Plant and Soil, 1997)